Quantifying methane and ammonia emissions from beef cattle finishing systems under sorghum and corn diets - Eduardo A. Santos; Nathan M. Sweet; Harleigh Johnson; Chinthaka Weerasekara; Nathan Malarich; Josefina Lacasa; Cosmin Blaga; Brett D. DePaola; Logan Thompson; Jaymelynn Farney; James Drouillard; Kevin C. Cossel; et al. (Agricultural and Forest Meteorology, 2026)

Legacy subsea plastics from the oil and gas industry: Environmental risks of decommissioning in situ - Freija Mendrik; Sarah C. Gall; Jiaxin Chen; Ami J. Northam; Anthony L. Andrady; Richard C. Thompson (Journal of Hazardous Materials, 2026)

Minimal contribution of bioerosion in the deterioration of biodegradable plastics in the marine environment: evidence from laboratory and field experiments - Winnie Courtene-Jones; Matthew Cole; Rachel L. Coppock; Allicia Fullarton; Holly D.L. Scott; Penelope K. Lindeque; Richard C. Thompson (Environmental Pollution, 2026)

GollumFit: An icecube open-source framework for binned-likelihood neutrino telescope analyses - R. Abbasi; M. Ackermann; J. Adams; S.K. Agarwalla; J.A. Aguilar; M. Ahlers; J.M. Alameddine; N.M. Amin; K. Andeen; C. Argüelles; Y. Ashida; S. Athanasiadou; et al. (Computer Physics Communications, 2026)

Spatial Mismatch Between Black Mangrove Avicennia germinans and Associated Herbivores Along the Range Edge Ecotone - Jamie E. Thompson; Steven C. Pennings; Anna R. Armitage (Estuaries and Coasts, 2026)
Globally, many plant communities are reorganizing in response to climate change, often at different rates than associated fauna. Asynchrony in range expansion between plants and fauna could alter biotic constraints on plant populations. Tropical mangroves are limited by folivory, but little is known about the importance of herbivory on mangroves near distributional range limits in subtropical regions. We hypothesized that herbivore abundance and herbivory intensity would vary along the extended range edge ecotone of Avicennia germinans (black mangrove) in the northern Gulf of Mexico, with higher pressure at southern sites where A. germinans stands were more extensive, and that leaf defensive characteristics would be enhanced in areas with more herbivory. We surveyed leaf damage, loss of yield, leaf defensive characteristics, and terrestrial arthropod abundance at four sites with varying levels of mangrove cover along the Texas (USA) coast. At southern sites with relatively high A. germinans cover, leaves had more than twice as much accumulated damage and up to 50% more loss of yield than at a northern site with low mangrove cover. The types of damage were more variable at southern than northern sites, suggesting higher consumer diversity. Herbivorous specialists on mangroves (e.g., mangrove buckeye Junonia spp.) were only detected at the southern sites with high mangrove cover. Leaf traits associated with decreased plant palatability (e.g., sclerophylly, phenolics) were variable among sites. Patterns at the four sites suggested asynchrony in mangrove and herbivore range expansion, where A. germinans distribution extended beyond the range of its associated consumers. Sampling a larger number of sites in future work could confirm this asynchrony and determine the importance of this spatial mismatch for the success of mangrove expansion.

Global sea surface salinity and temperature impacts on trace elements, crystallography, and organics in massive Porites coral skeletons from a museum collection - Gabriela A. Farfan; Alice C. Kojima; Diane M. Thompson; Andrea M. Quattrini (Coral Reefs, 2026)

Retraction notice to “Collapse of scallop Nodipecten nodosus production in the tropical Southeast Brazil as a possible consequence of global warming and water pollution” [Sci. Total Environ. 904 (2023) 166873] - Cristiane Thompson; Leonardo Bacha; Pedro Henrique C. Paz; Marcelo de Assis Passos Oliveira; Braulio Cherene Vaz Oliveira; Claudia Omachi; Caroline Chueke; Marcela de Lima Hilário; Michele Lima; Luciana Leomil; Thais Felix-Cordeiro; Thalya Lou Cordeiro da Cruz; et al. (Science of The Total Environment, 2026)

Mercury concentrations in cephalopods from the Pacific sector of the Southern Ocean in relation to their biology, habitat and trophic position - Marius Lespinas; José C. Xavier; Paco Bustamante; José P. Queirós; David R. Thompson; Pedro Coelho; Maria Eduarda Pereira; José Seco (Marine Environmental Research, 2026)

Application of quantitative and qualitative uncertainty assessment to inform risk management decision-making: a case study with diisononyl phthalate - Amanda N. Buerger; Chad M. Thompson; Melissa M. Heintz; Silvia Maberti; Christine M. Palermo; Laurie C. Haws (Food and Chemical Toxicology, 2026)

Ecological and genetic determinants of essential oil diversity in Mediterranean Thymus - José C. del Valle; Esther María Martín-Carretié; Francisco José García-Cárdenas; David Doblas; María Ángeles Ortiz; John Thompson; Perrine Gauthier; Bodil K. Ehlers; Diego Nieto-Lugilde; Regina Berjano (Biochemical Systematics and Ecology, 2026)

Heart rate and sub-blubber temperature in harbour seals (Phoca vitulina) measured during the moult and post-moult using implantable loggers - W. D. Paterson; L. L. Chaise; S. E. Moss; R. Milne; C. Gilbert; J. I. Currie; D. Thompson; D. J. McCafferty (Journal of Comparative Physiology B, 2026)
The moult represents an important seasonal change in the physiology of phocid seals. However, physiological measurements are challenging due to the impracticalities of instrumenting moulting animals. The aim of this study was (i) to assess the feasibility of a long-term deployment of fully implantable loggers to measure heart rate (HR) and sub-blubber temperature (T b ) in harbour seals ( Phoca vitulina ) and (ii) to compare HR and T b during moult and post-moult periods. Loggers were surgically implanted on an adult and sub-adult harbour seal in captivity. Animals healed quickly from surgery and loggers provided 65 days of continuous data before removal of the device. Results showed that in the adult when hauled out and in the water HR was lower during the moult compared with the post-moult. For the sub-adult, HR while in the water was also higher during the post-moult, however, when hauled out there was no difference in HR between the moult and post-moult periods. When hauled out, T b was greater for both animals during the moult compared with the post-moult. During haulout events, T b increased over time in both periods and T b in both animals was lower during post moult compared to the moult period. In the sub-adult, T b decreased with time in the water during the moult but showed little change during the post-moult period, whereas no temporal change was evident in the adult during either period. This study demonstrated that fully implantable loggers are a useful research tool allowing measurement of physiological parameters that are otherwise difficult to measure in pinnipeds. Physiological measurements suggested that the requirement to maintain higher skin temperature for hair growth during the moult was offset by lower metabolism to save energy in water, and on land in the case of adults. However, a decrease in body temperature with time in water in the sub-adult indicated that a smaller body size and less well-developed blubber layer is not as effective in reducing heat loss compared to adults. Future physio-logging on pinnipeds throughout their annual lifecycle may therefore benefit from similar techniques used to implant loggers.

Novel application of a PMSG assay for measurement of circulating LH levels in horses - Jaden R. Thompson; Sarah Barcalow; Ashley Stark; Kirsten E. Scoggin; Alan J. Conley; Shavahn C. Loux (Theriogenology, 2026)

Upper respiratory microbiome composition and associations with air pollution and infant respiratory health: a longitudinal study in Guatemala - Rina Das; Andrew Baldi; Sant-Rayn Pasricha; Lisa M. Thompson; Anaité Díaz-Artiga; Laura Maria Grajeda; John P. McCracken; Kelsey Jesser; Lance Waller; Matthew C. Freeman; Thomas Clasen; Sheela S. Sinharoy (International Journal of Hygiene and Environmental Health, 2026)

Memes as Structural Signals: A Chemical Model of Interpretive Compatibility - Eric Gladstone; David C. Thompson (Biosemiotics, 2026)

Analysis of second-generation epigenetic clocks reveals further associations between disproportionate biological ageing and hippocampal volume - Lidija Milicic; Michael Vacher; Vincent Doré; Pierrick Bourgeat; Rosita Shishegar; James D. Doecke; Paul Maruff; Christopher C. Rowe; Victor L. Villemagne; Michael Weiner; Paul Aisen; Ronald Petersen; et al. (GeroScience, 2026)

Will there ever be an in vitro assay that is predictive for human hepatotoxicity? - David C. Thompson (Archives of Toxicology, 2026)

The Sedimentary Geochemistry and Paleoenvironments Project Phase 2 data release: An open data resource for the study of Earth's environmental history - Úna C. Farrell; Hunter C. Olson; Maya O. Thompson; Michelle L. Abshire; Oyeleye O. Adeboye; Anne-Sofie C. Ahm; Lewis J. Alcott; Thomas J. Algeo; Ross P. Anderson; Arif H. Ansari; Lucas Pinto Heckert Bastos; Kohen W. Bauer; et al. (Chemical Geology, 2026)

Applying InVEST Model to Assess Selected Anthropogenic Stressors in Seagrass Habitats - Nikki Heherson A. Dagamac; Justine Lance P. Tolentino; Jenica Trysha S. M. Navarrete; Camille Angela C. Ngo; Gernelle M. Razon; Marvi Yñaki B. Villareal; James Philomeno C. Flores; Paul Cervin Evangelista-Rivera; Lillian Thompson; Katherine Iona Muller (Thalassas: An International Journal of Marine Sciences, 2026)

An Analysis of Dental Hygienists’ Practices and Perceptions Toward HPV Vaccination - Stacey B. Griner; Alexandra N. Farris; Nolan Kline; Malinee Neelamegam; Jane C. Cotter; Roi San Nhpang; Charlene Dickinson; Erika L. Thompson (Journal of Cancer Education, 2026)

Forecasting Ireland's retrofit trajectory: Overcoming policy gaps to meet climate action goals - E. Essien-Thompson; M. Mulville; G. Keane; C. Ahern (Energy Policy, 2026)

Development and validation of matrix-validated LC–MS/MS method for simultaneous quantification of 21 neonicotinoids and their metabolites in human urine - Wenjing Xi; Sarah Onysio; Mary C. Rhodes; Alexis J. Faudel; John C. Flunker; Mark K. Santillan; Donna A. Santillan; David M. Cwiertny; Darrin A. Thompson (Environmental Science and Pollution Research, 2026)
Neonicotinoids (NEOs) are the most widely used class of insecticides worldwide. Consequently, human exposure occurs through multiple pathways, including dietary intake and environmental contact. Previous analytical methods have primarily focused on parent compounds, often excluding key metabolites due to matrix effects and poor quantification in complex biological samples. This gap severely limits the ability to accurately assess total NEO exposure and internal dose, highlighting the urgent need for more comprehensive and reliable biomonitoring approaches. This study developed a comprehensive LC–MS/MS method to quantify 21 NEOs and metabolites in human urine, uniquely including key transformation products such as clothianidin-n-desmethyl, clothianidin-urea, imidacloprid-urea, imidacloprid-olefin, 5-hydroxy-imidacloprid, thiamethoxam-urea, and thiamethoxam-n-desmethyl, thereby enabling a more thorough assessment of human exposure to NEOs. The method was validated using both synthetic and pooled human urine, providing a critical assessment of matrix-dependent variations in detection limits, accuracy, and precision. Method performance demonstrated high sensitivity, specificity, accuracy, and precision, with limits of quantification (LOQ) from 0.017 to 0.46 ng/mL and limits of detection (LOD) from 0.0050 to 0.14 ng/mL. The method was applied to urine samples from 246 pregnant women and 47 farmers in eastern Iowa to assess exposure levels. Results indicated widespread NEO exposure with detection frequencies of 99% of pregnant women and 100% in farmers, with 18 different NEOs and metabolites detected across both populations. Metabolite monitoring revealed that imidacloprid metabolites (IMI-O, 5-OH-IMI) were stronger predictors of total neonicotinoid burden than parent compounds alone ( r s = 0.735 vs < 0.6 for parents), with some metabolites showing higher concentrations in pregnant women than farmers despite farmers having higher overall exposure. These findings demonstrate that parent-only biomonitoring substantially underestimates internal neonicotinoid exposure and fails to capture critical exposure pathways, particularly for vulnerable populations where metabolite patterns may differ significantly from occupational exposure profiles.

Scaling what works: a collaborative capacity-building program tailored to optimize resources and scale evidence-based interventions for cancer prevention and control - Mary Wangen; Jingle Xu; Amy Tran; Elizabeth A. Rohan; Prajakta Adsul; Cam Escoffery; Renée M. Ferrari; Nikki Hayes; Cari Herington; Katie Jones; Jaron Hoani King; Julie Kranick; et al. (Cancer Causes & Control, 2026)

Co-translational profiling in the cardiac endothelium in response to LPS-induced inflammation in female mice in vivo: a proof-of-concept approach - Chad M. Warren; Bhairavi Swaminathan; Paulina Langa; Stephanie R. Villa; Walter C. Thompson; Magdalena Chrzanowska; Jan K. Kitajewski; R. John Solaro; Beata M. Wolska; Paul H. Goldspink (Molecular and Cellular Biochemistry, 2026)
Producing functional proteins involves multiple steps during mRNA translation on the ribosomes. However, co-translational regulatory mechanisms remain poorly characterized in intact mammalian systems. As a proof-of-concept, we developed a multi-omics approach to investigate endothelial-specific, co-translational regulation by modifying the translating ribosome affinity purification (TRAP) in vivo. We simultaneously co-immunoprecipitated (IP) polysome-associated mRNAs and proteins from the hearts of hemagglutinin-tagged ribosomal protein L22 mice (RiboTag) crossed with inducible endothelial-specific Cdh5CreERT2 mice ( RiboTag EC ). To perturb endothelial function, female mice were injected with E. coli lipopolysaccharide (LPS) (6 mg/Kg, i.p., 12 h). Hearts were homogenized, with ~ 10% used for input RNA-Seq and proteomics controls, and the remainder for IP of ribosome-bound polyadenylated mRNA and proteins. Endothelial cell transcripts ( pecam1 , cdh5 ) were enriched > 5-fold, while markers characteristic of other cell types were significantly depleted (< 0.05 q-value). We aligned transcriptomic and proteomic datasets (> 1250 overlapping terms) to identify pathways associated with concordant and discordant co-translational regulation. LPS was identified as the upstream regulator of the co-translational dataset that was concordantly regulated. Upregulated mRNAs but not proteins related to glycolysis were discordantly regulated. These findings validate our proof-of-concept multi-omics approach as a predictive platform for identifying disease-relevant pathways regulated at the co-translational level in vivo.

Interpretable deep learning reveals spatiotemporal MRI features of brain aging that align with neurodegeneration - Nikhil N. Chaudhari; Owen M. Vega; Phoebe Imms; Jaron M. Kawamura; Nahian F. Chowdhury; Tamara Jafar; Andrei Irimia; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2026)
Cortical thinning and atrophy are hallmarks of brain aging that have been characterized using magnetic resonance imaging (MRI). Brain aging involves many neuroanatomic features whose effects on brain structure remain unexplored. To address this challenge, we trained interpretable deep neural networks (DNNs) to estimate brain age (BA) from T 1 -weighted ( T 1 w) MRI. By identifying MRI features unapparent to humans, DNNs can find aging-related structural alterations above and beyond cortical thickness and atrophy. Using a novel approach to DNN interpretability, we mapped brain aging progression in 25,539 cognitively normal UK Biobank adults aged 45–83 years. Cortical aging is found to involve anatomic features becoming prominent during the 50s within frontolateral, mesolimbic, cuneal, and occipitotemporal regions. From these foci, aging-related features propagate to adjacent areas at rates peaking in the 60s. Cortical thinning and atrophy do not trend closely with neurodegeneration, but important DNN-identifiable anatomic features have spatiotemporal dynamics that match those of amyloid or tau. Our results challenge the assumption that MRI cannot map anatomic features trending with neurodegeneration. Interpretable DNNs can empower MRI to quantify anatomic aging as a process of spatial feature expansion from focal regions into nearby structures in the sequence of neurodegenerative pathology. Traditional morphometrics explain only ∼1% of variance in DNN-identifiable features, which clarifies why the former are insensitive to anatomic changes involving neurodegeneration. Our results conceptualize brain aging in the context of spatial and temporal parallels between anatomic senescence and neuropathology. These findings may help to map cognitively normal adults’ neurodegenerative anatomy even without PET measurements. Graphical Abstract

Genetic algorithm optimization of nuclear criticality experiment for reduction of intermediate-energy 239Pu nuclear data uncertainties - Noah Kleedtke; Theresa Cutler; Denise Neudecker; Jesson Hutchinson; Peter Brain; Nicholas Thompson; Robert C. Little (Annals of Nuclear Energy, 2026)

SNAPSHOT USA 2024: Year 6 of the Coordinated National Camera Trap Survey of the United States - Brigit Rooney; Roland Kays; Michael V. Cove; Alex Jensen; Daniel J. Herrera; Camilla Price; Phuong‐Thao Nguyen‐Nu; Katrina Adamczyk; Peter D. Alexander; David Allen; Jesse M. Alston; Diego F. Alvarado‐Serrano; et al. (Global Ecology and Biogeography, 2026)
Motivation SNAPSHOT USA is an annual, multi‐contributor camera trap survey of mammals across the United States. The growing SNAPSHOT USA dataset is intended for tracking the spatial and temporal responses of mammal populations to changes in land use, land cover and climate. These data will be useful for exploring the drivers of spatial and temporal changes in relative abundance and distribution, as well as the impacts of species interactions on daily activity patterns. Main Types of Variables Contained SNAPSHOT USA 2024 contains 377,427 records of camera trap image sequence data and 3127 records of camera trap deployment metadata. Spatial Location and Grain Data were collected across the United States of America in 49 states, 12 ecoregions and many ecosystems. Time Period and Grain Data were collected between 1 August and 19 December in 2024. Major Taxa and Level of Measurement The dataset includes a wide range of taxa but is primarily focused on medium to large mammals. Software Format SNAPSHOT USA 2024 comprises two .csv files. The original data can be found within the SNAPSHOT USA 2024 project on the Wildlife Insights platform.

Cleaning products and classes associated with poor respiratory health - Xin Dai; Michael J. Abramson; Garun S. Hamilton; Bruce R. Thompson; Cecilie Svanes; Geza Benke; Sonia Kaushik; Shyamali C. Dharmage; Caroline J. Lodge (Environmental Science and Pollution Research, 2026)
Exposure to cleaning products may harm the lungs, mainly through inhalation of irritants and sensitising chemicals, which can induce airway inflammation and bronchial hyperresponsiveness. Given increased use of multiple cleaning products at work and home, understanding the impacts of their interplay, rather than individual exposures, is critical but has not been investigated to date. We aim to investigate the cross-sectional association between exposure to cleaning products at home and/or in the workplace and respiratory health. We conducted a cross-sectional analysis of 318 adults from the Melbourne arm of the European Community Respiratory Health Survey (ECRHS) III. Cleaning product exposure was assessed through questionnaires, categorising participant exposure into seven product groups. Latent class analysis was used to identify exposure classes. Adjusted multivariable regression modelled associations between cleaning product classes and respiratory outcomes. We identified four classes of exposure to cleaning products: “minimal users”, “light users”, “moderate users”, “heavy users”. The most exposed “heavy user group” characterised people using many different cleaning products on a weekly basis (especially bleach, sprays, polish, solvents, acids). This class was associated with increased risks of current asthma (OR, 3.24; 95% CI 1.19–8.77), and lower post-bronchodilator FEV 1 (z-score, −0.47) and FVC (−0.46) compared with “minimal users”. This work used a data-driven latent class approach to capture real-world cleaning product use patterns and relate them to respiratory health. We found that frequent use of multiple cleaning products was linked to more asthma and lower lung function, suggesting potential combined effects. These findings highlight the need for cleaning product standards and asthma care guidelines to mitigate risks associated with cleaning products.

Association of Milk Fat Intake on BMI Change and Nutrient Intake in WIC-Enrolled Toddlers - Rachel C. Grau; Lorrene D. Ritchie; Anisha Patel; Hannah R. Thompson (Journal of Nutrition Education and Behavior, 2026)

Insect polyploid adaptation for cell number and size varies in longstanding versus neopolyploid lines of the wasp Nasonia vitripennis - Saminathan Sivaprakasham Murugesan; Kelley Leung; Keita Yamaguchi; Emei Thompson; Leo W. Beukeboom; Eveline C. Verhulst (Journal of Insect Physiology, 2026)

Beyond size and shape: Physicochemical properties of microplastic test materials generated by cryomilling - Lucy Howarth-Forster; Robyn Barrett; Robert Clough; Lisbet Sørensen; Jack Allen; Chris Powell; Richard C. Thompson; Matthew Cole; Michael Wilde (Journal of Hazardous Materials, 2026)

Severe fire has impacted populations of the California spotted owl more than fuels management or drought-related tree mortality - Elizabeth Ming-Yue Ng; Connor M. Wood; H. Anu Kramer; Jason M. Winiarski; Kate A. McGinn; Sheila A. Whitmore; Jonathan P. Eiseman; Kevin G. Kelly; Sarah C. Sawyer; Craig Thompson; M. Zachariah Peery (Forest Ecology and Management, 2026)

Fuels management mitigates megafires to the benefit of old forest species - Kate McGinn; Gavin M. Jones; H. Anu Kramer; Sheila A. Whitmore; Jason M. Winiarski; Elizabeth Ming-Yue Ng; Connor M. Wood; Sarah C. Sawyer; Craig Thompson; M. Zachariah Peery (Forest Ecology and Management, 2026)

Next generation reference dwellings to inform national dwelling stock energy model for Ireland - C. Li; K. Raushan; E. Essien-Thompson; C. Ahern (Energy and Buildings, 2026)

Local and Landscape‐Level Environmental Conditions Drive Habitat Selection Across Terrestrial Mammal Species - Björn H. Franke; Aafke M. Schipper; Tal Avgar; Luca Börger; Nilanjan Chatterjee; Thomas Müller; Brian J. Smith; Briana Abrahms; Abdullahi H. Ali; Nina Attias; Hattie L. A. Bartlam‐Brooks; Floris M. van Beest; et al. (Global Ecology and Biogeography, 2026)
Aim Animal movements are a fundamental process affecting communities and ecosystems. Quantifying habitat selection across species and habitats is key for understanding how animals respond to environmental change. Currently, we lack comparative studies that examine how habitat selection varies across species traits and landscapes. We aim to quantify global patterns of habitat selection to help understand the fundamental drivers of movement behaviour. Location Global. Time Period Contemporary. Major Taxa Studied Terrestrial mammals. Methods We estimated selection coefficients for terrain ruggedness, vegetation productivity, human population density and distance to roads of individual terrestrial mammals through step‐selection analysis of 1344 GPS tracks across 48 species. We quantified intra‐ and interspecific variation and tested whether selection coefficients were associated with species traits and habitat availability. Results We observe an overall avoidance of roads and areas of high human population density as well as rugged terrain, with a large proportion of individuals selecting for areas of intermediate NDVI. However, we also found large intraspecific variation in habitat selection and show that this variation is predicted by local and landscape‐level environmental conditions rather than species traits. Individuals in more remote areas exhibited weaker functional responses to human presence than those in more disturbed areas. Avoidance of rugged terrain is also context‐dependent, with stronger avoidance when local ruggedness is high. The only exception to the observed intraspecific variability is consistent species‐level responses to road proximity. Main Conclusions Our findings contribute to the understanding of habitat selection by terrestrial mammals, showing that selection is largely shaped by environmental conditions and that animals exhibit high plasticity in their responses. Our results also provide further evidence for the significant impact of roads on animal movement. These insights can help us to understand the potential effects of environmental change on the behaviour of mammal species around the world.

Sex and APOE genotype specific brain regional vulnerability to Alzheimer's Disease - Qi Zeng; Minghui Wang; Erming Wang; Xianxiao Zhou; Peng Xu; Vahram Haroutunian; Dongming Cai; Bin Zhang; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2026)
Alzheimer’s disease (AD) disproportionately affects women and carriers of the apolipoprotein E ε4 allele (APOE4), yet little is known about how sex and APOE interact to influence white matter (WM) integrity during disease progression. We integrated diffusion MRI and matched blood transcriptomic data to investigate these interactions and their underlying biological mechanisms. WM microstructure was quantified using diffusion tensor imaging (DTI) and neurite orientation dispersion and density imaging (NODDI), and regional vulnerability was assessed with a composite vulnerability score (CVS) derived from associations between diffusion features and AD severity across clinical traits in each of the four sex-APOE groups (female or male, with or without APOE4). Brain parcellation with the Eve atlas revealed regions consistently affected across sex-APOE groups (e.g., parahippocampal and superior temporal gyri) and regions specific to individual groups (e.g., the cingulum in females with APOE4 and the middle frontal gyrus in males without APOE4). Gene co-expression network analysis of the matched blood expression data identified gene subnetworks linked to group-specific regional vulnerability, including a muscle tissue morphogenesis module regulated by NEURL1B and HIST1H2BN associated with middle frontal gyrus vulnerability. These findings demonstrate that sex and APOE genotype jointly shape region-specific WM vulnerability and its molecular signatures in AD. Understanding these interactions provides novel mechanistic insights and may inform precision approaches to drug development, biomarker discovery, and clinical trial design for AD.

Maternal ozone exposure and differential cardiometabolic outcomes in aging male and female offspring - Brendan Yoo; Janice A. Dye; Mehdi S. Hazari; Aimen K. Farraj; Erica J. Stewart; Leslie C. Thompson; Helen H. Nguyen; Samantha J. Snow; Michelle Fiamingo; Anna A. Fisher; Katherine L. O'Shaughnessy; Colette N. Miller (Toxicology and Applied Pharmacology, 2026)

First evidence of CP violation in beauty baryon to charmonium decays - R. Aaij; A.S.W. Abdelmotteleb; C. Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2026)

Evaluation of chronic toxicity and carcinogenicity of HFPO-DA in mice - Chad M. Thompson; Melissa M. Heintz; John M. Cullen; Laurie C. Haws (Regulatory Toxicology and Pharmacology, 2026)

The Sedimentary geochemistry and paleoenvironments project phase 2 data release: An open data resource for the study of Earth's environmental history - Úna C. Farrell; Hunter C. Olson; Maya O. Thompson; Michelle L. Abshire; Oyeleye O. Adeboye; Anne-Sofie C. Ahm; Lewis J. Alcott; Thomas J. Algeo; Ross P. Anderson; Arif H. Ansari; Lucas Pinto Heckert Bastos; Kohen W. Bauer; et al. (Chemical Geology, 2026)

Association between late-life air pollution exposure and medial temporal lobe atrophy in older women - Xinhui Wang; Lauren E. Salminen; Andrew J. Petkus; Ira Frahmand; Joshua Millstein; Daniel P. Beavers; Mark A. Espeland; Guray Erus; Meredith N. Braskie; Paul M. Thompson; Margaret Gatz; Helena C. Chui; et al. (NeuroToxicology, 2026)

Effect of water, sanitation, and hygiene on childhood growth in Ethiopia: a cluster-randomized trial - Tahvi Frank; Isabel J.B. Thompson; Solomon Aragie; Dionna M. Wittberg; Wondyifraw Tadesse; Adane Dagnew; Dagnachew Hailu; Jason S. Melo; Taye Zeru; Zerihun Tadesse; Benjamin F. Arnold; Matthew C. Freeman; et al. (International Journal of Hygiene and Environmental Health, 2026)

Assessing the degradation of polyester fibres from different textiles: A simulation based on laundry release - Vasiliki Soursou; Julián Campo; Yolanda Picó; Richard C. Thompson; Francesca De Falco (Environmental Pollution, 2026)

The transition from magmatic to hydrothermal crystallization conditions of a shallow-level granitic pluton - G. T. Thompson; C. J. Rufledt; J. B. Thomas (Contributions to Mineralogy and Petrology, 2026)
Many thermobarometric methods applied to granitic composition rocks that crystallized at < 5 kbar yield temperature estimates ~ 50 to 100 °C lower than the widely used haplogranite water-saturated solidus. To address thermobarometric discrepancies, we investigated a shallow-level granitic pluton that is not enriched in fluxing elements such as Li, B, P, or F. The Rito del Medio pluton (RDMP) near Questa, New Mexico contains numerous minerals and inclusions suitable for thermobarometric estimates, and it has abundant miarolitic cavities that represent the final crystallization stages. Occurrences of coexisting melt and fluid inclusions show that groundmass minerals crystallized from a water-saturated magma. After groundmass crystallization, the pluton transitioned to a fluid-dominated system manifested by the crystallization of freestanding minerals contained in the miarolitic cavities. The granite contains mica, feldspar, quartz, primary fluid inclusions in quartz, and accessory minerals including garnet with quartz inclusions. We used minerals and their inclusions in both paragenetic contexts to track changes in P, T, and mineral and fluid compositions that accompanied the magmatic-to-hydrothermal transition. Resultant univariant curves from thermobarometry for the groundmass minerals converge at ~ 1.9 to 2.1 kbar and ~ 590 to 625 °C indicating final magmatic crystallization. To address discrepancies between thermobarometric results and the haplogranite solidus, we performed crystallization experiments at 2 kbar, which show that RDMP compositions magmas complete crystallization at temperatures ~ 620–625 °C. Univariant curves for thermobarometric approaches applied to the RDMP miarolitic cavity minerals converge at ~ 1.5 to 2.1 kbar and ~ 500 to 525 °C defining the transition to hydrothermal crystallization conditions.

Increased benthic biodiversity and food web recovery after decommissioning of oil and gas infrastructure - Zelin Chen; Tom C. Cameron; Elena Couce; Clement Garcia; Natalie Hicks; Gareth E. Thomas; Murray S. A. Thompson; Corinne Whitby; Eoin J. O'Gorman (Limnology and Oceanography, 2026)
There is a global increase in the decommissioning of offshore oil and gas (O&G) infrastructure at the end of its operating lifetime. However, there is strikingly limited empirical evidence for the environmental and ecological impacts of decommissioning. Here, we employed a meta‐analytical approach on an industry benthic monitoring database to investigate the benthic biodiversity and food web properties of structures sampled in the short term ( 5 yr; scenario 3) after decommissioning. We found reduced species richness and simplified food webs in scenario 1, followed by the first signs of recovery in scenario 2, with a slightly higher proportion of intermediate species and density of food web connections. Food webs recovered further in scenario 3, with a much greater density of interactions, but also more links and longer food chains, while a reduction in generalism and connectance indicated an increased prevalence of specialist species. Our findings demonstrate disturbance risks associated with the decommissioning process in the short term, but a positive recovery trajectory over longer timescales. We highlight the importance of industry collecting more extensive and long‐term data at multiple time points and covering different decommissioning types, establishing a standardized data workflow for integrating with available monitoring efforts, and improving stakeholder participation and data accessibility to support an environmentally sound decommissioning process.

Meta-analysis of the spatial distribution and composition of plastic macro-debris in Indonesia - Max R. Kelly; Muhammad Reza Cordova; Susan Jobling; Richard C. Thompson (Regional Studies in Marine Science, 2025)

The benthic and epiphytic marine dinoflagellates of Aotearoa New Zealand and Rangitāhua Kermadec Islands, an updated checklist from 2018 to 2024 - Lesley L. Rhodes; Tomohiro Nishimura; J. Sam Murray; Sarah C. Finch; Lucy Thompson; Kirsty F. Smith (New Zealand Journal of Marine and Freshwater Research, 2025)
A checklist collating records of New Zealand’s benthic and epiphytic dinoflagellate species was published on‐line in 2018 [Rhodes L, Smith KF. 2019. A checklist of the benthic and epiphytic marine dinoflagellates of New Zealand, including Rangitāhua/Kermadec Islands. N Z J Mar Freshw Res. 53:258–277. doi: 10.1080/00288330.2018.1492425 ]. Over the last six years, seventeen species from nine genera (three newly reported genera) have been documented, including sand‐dwelling species. Isolation and identification of species using traditional microscopic techniques combined with analysis of DNA sequencing data has been supplemented by high‐throughput sequencing techniques (i.e. metabarcoding). Toxin data, based on liquid chromatography mass spectrometry (LC‐MS/MS), and toxicity of isolates are included where applicable. Forty‐two benthic and epiphytic dinoflagellate genera, including genera having benthic life stages, have now been recorded in Aotearoa New Zealand coastal waters including Rangitāhua Kermadec Islands (new record genera in bold): Adenoides , Alexandrium , Amphidinium , Archaeperidinium , Azadinium , Biecheleria , Blastodinium , Bysmatrum , Cachonina , Coolia , Crypthecodinium , Cryptoperidiniopsis , Dinophysis , Durinskia , Ensiculifera , Fukuyoa , Fragilidium , Gambierdiscus , Gonyaulax , Gymnodinium , Gyrodinium , Heterocapsa , Karenia , Karlodinium , Kryptoperidinium , Lepidodinium , Ostreopsis , Pelagodinium , Pentapharsodinium , Pfiesteria , Polarella , Prorocentrum , Protodinium , Protoperidinium , Pseudadenoides , Pseudopfiesteria , Scrippsiella , Symbiodinium , Thecadinium , Togula , Vulcanodinium and Woloszynskia.

Crown Exposure Regulates Aboveground Wood Productivity Responses to Soil Fertility in Lowland Tropical Forests - José A. Medina‐Vega; Álvaro Duque; Daniel Zuleta; Nicolás Castaño; Renato Valencia; Salomón Aguilar; David Mitre; Rolando Pérez; Shawn K. Y. Lum; David F. R. P. Burslem; Michael J. O'Brien; Glen Reynolds; et al. (Ecology Letters, 2025)
Understanding the drivers of aboveground wood productivity (AWP) in tropical forests is crucial for explaining ecosystem functioning and predicting their responses to environmental change. While climatic water availability is a well‐established driver, the role of soil nutrients and their interaction with other resources remains uncertain. We investigated how soil nutrients and light interactions shape AWP in lowland tropical forests using fine‐scale soil and tree (≥ 1 cm DBH) data from 15 large forest plots. Canopy‐exposed trees are nutrient‐limited, with AWP increasing more with phosphorus (P) than with potassium (K), indicating P's greater role in plant growth and productivity. Conversely, understory AWP declined in fertile areas, likely due to intensified size‐asymmetric competition. At the population level (mean across canopy layers), no relationship between soil nutrients and AWP emerged because contrasting responses among layers offset any overall association. Our results suggest that fine‐scale heterogeneity and canopy stratification drive nutrient effects on tropical forest productivity.

A Qualitative Exploration of Parent and School Staff Perceptions of Freshly Prepared Meals and Food Waste Implications in California Elementary Schools - Katharina C. Fiedler; Reka Vasicsek; Maya Ezekiel; Celeste Felix; Danielle L. Lee; Hannah Thompson; Wendi Gosliner; Stephanie Willits; Kristine Madsen; Lorrene D. Ritchie (Journal of Nutrition Education and Behavior, 2025)

Determining the accumulation potential of nanoplastics in crops: An investigation of 14C-labelled polystyrene nanoplastic into radishes - Nathaniel J. Clark; Astrid C. Fischer; Demelza Carne; George R. Littlejohn; Lee J. Durndell; Anne Plessis; Richard C. Thompson (Environmental Research, 2025)

Agricultural copper pesticide exposure and DNA methylation in Central Valley of California residents with and without Parkinson's disease - Yufan Gong; Yu Yu; Keren Zhang; Irish Pearl Cambronero Del Rosario; Myles Cockburn; Laura K. Thompson; Adrienne M. Keener; Jeff Bronstein; Beate R. Ritz; Kimberly C. Paul (Environmental Research, 2025)

Where there is smoke, there is fire: long- and mid-range biomass burning role on São Paulo's state air quality - Anderson Paulo Rudke; Leila Droprinchinski Martins; Jorge Alberto Martins; Maurício C. Mantoani; Maria de Fátima Andrade; Prashant Kumar; Ronaldo Adriano Alves; Rizzieri Pedruzzi; Tammy Thompson; Otavio Medeiros Sobrinho; Bruna Lima Véras Maia; Amanda Karine Chaves Ribeiro; et al. (Environmental Pollution, 2025)

Serum Biomarkers in Atlantic Salmon for Differential Diagnosis of Cardiomyopathy Syndrome and Pancreas Disease: Proteomic Identification of Serum Fibrinogen to Enhance Troponin Immunoassay as Optimal Diagnostic Approach - Francesca Riva; Lauren Elaine Black; Kim D. Thompson; Philippe Sourd; Andrei Bordeianu; Christopher C. Chadwick; Hooman Moghadam; Jorge Del‐Pozo; Janina Costa; Richard Burchmore; Nicola Brady; Lewis Moore; et al. (Journal of Fish Diseases, 2025)
Cardiac viral diseases are among the major causes of economic losses in Atlantic salmon ( Salmo salar L.) aquaculture. These include cardiomyopathy syndrome (CMS) caused by piscine myocarditis virus (PMCV) and pancreas disease (PD) caused by Atlantic salmonid alphavirus (SAV). The resulting cardiomyopathies impact fish stock in terms of mortality, quality, growth performance and economic loss. Diagnosis of these diseases is currently based on clinical signs, histopathology and RT‐qPCR. To identify putative biomarkers for use in the health assessment of Atlantic salmon, a quantitative proteomics investigation was undertaken with the aim of differentiating fish with CMS from healthy fish and fish with PD. Serum samples ( n = 9/group) were collected during health assessment from pens where clinical CMS or PD were present and compared to serum from healthy Atlantic salmon. There were 34 differentially abundant proteins (DAPs) in CMS compared to healthy, 66 comparing CMS to PD, and 81 comparing PD to healthy. In relation to healthy samples, most DAPs were shared between CMS and PD, with higher relative abundances observed in PD. An exception to this was serum fibrinogen, which was identified as a putative biomarker for CMS, whereas differentiation of Atlantic salmon with CMS from those with PD was enhanced by the calculation of the ratio of fibrinogen to skeletal troponin C.

Hindsight informs foresight: revisiting millennial forecasts of impacts and status of rocky shores in 2025 - Stephen J. Hawkins; Kathryn A. O'Shaughnessy; George M. Branch; Laura Airoldi; Simon Bray; Paul Brooks; Michael T. Burrows; Juan Carlos Castilla; Tasman P. Crowe; Thomas W. Davies; Louise B. Firth; Keith Hiscock; et al. (Marine Pollution Bulletin, 2025)

A comparison of the life history and distribution of vermilion rockfish (Sebastes miniatus) and its cryptic pair, sunset rockfish (S. crocotulus) along the Pacific Coast - John H. Harms; Anita Wray; John R. Hyde; Gary C. Longo; Jennifer A. Hempelmann; Anna E. Elz; R. Matthew Barnhart; James A. Benante; Aaron C. Chappell; Peter H. Frey; Colin L. Jones; Betty Kamikawa; et al. (Fisheries Research, 2025)

Wave impacts on vertical cliffs: Insights from laboratory experiments and field observations - Yaxiong Shen; Colin N. Whittaker; Catriona F. Thompson; Alison C. Raby; Adam P. Young; Mark E. Dickson (Coastal Engineering, 2025)

Fast-start performance and its dependence on temperature and salinity in sheepshead minnow (Cyprinodon variegatus) - David C. Collar; Kayla L. Stanley; Jessica S. Thompson (Environmental Biology of Fishes, 2025)
Estuarine fishes regularly experience fluctuations in water temperature and salinity, and many species exhibit broad tolerances that allow them to withstand extreme conditions without mortality. However, a full understanding of physiological capacities that permit occupancy of such changeable habitats also requires insight into how organismal performance responds to environmental variation. In this study, we evaluated fast-start escape performance of sheepshead minnow ( Cyprinodon variegatus ), a noted eurythermal and euryhaline estuary-resident, across temperatures near the warm extreme of its thermal range (24, 30, 36 °C) and salinities varying from low to hypersaline (2, 32, 52 ppt). Fast-start speeds were directly related to the temperature at which fish were tested, but they also exhibited dependence on acclimation conditions. Angular velocity of the initial C-bend was faster at higher test temperatures, but at any given temperature, rotation was fastest in fish held at lower temperatures and at intermediate or high salinities. While temperature and salinity effects were detectable, they were modest in magnitude. These results suggest that sheepshead minnow fast-start performance is relatively robust to environmental variability but can be influenced by fluctuating conditions within estuaries. Short-term increases in temperature brought on by daily tidal cycles may lead to elevated fast-start speeds, but long-term exposure to high temperatures (predicted to increase given climate change) or low salinities (resulting from rainwater inundation of marshes) may contribute to a reduction in fast-start performance and potentially increased vulnerability to predators.

Population Genetics and Invasion History of the European Starling Across Aotearoa New Zealand - Bryan Thompson; Kamolphat Atsawawaranunt; Melissa C. Nehmens; William S. Pearman; E. Owen Perkins; Pavel Pipek; Lee A. Rollins; Hui Zhen Tan; Annabel Whibley; Anna W. Santure; Katarina C. Stuart (Molecular Ecology, 2025)
The expansion of human settlements over the past few centuries is responsible for an unprecedented number of invasive species introductions globally. An important component of biological invasion management is understanding how introduction history and postintroduction processes have jointly shaped present‐day distributions and patterns of population structure, diversity and adaptation. One example of a successful invader is the European starling ( Sturnus vulgaris ), which was intentionally introduced to numerous countries in the 19th century, including Aotearoa New Zealand, where it has become firmly established. We used reduced representation sequencing to characterise the genetic population structure of the European starling in New Zealand, comparing it to that present in sampling locations in the native range and invasive Australian range. The population structure and genetic diversity patterns we found suggested restricted gene flow from the majority of New Zealand to the northmost sampling location (Auckland). We also profiled genetic bottlenecks and shared outlier genomic regions, which supported historical accounts of translocations between both Australian subpopulations and New Zealand, and provided evidence of which documented translocation events were more likely to have been successful. Using these results as well as historic demographic patterns, we demonstrate how genomic analysis complements even well‐documented invasion histories to better understand invasion processes, with direct implications for understanding contemporary gene flow and informing invasion management.

Surface-based morphometry reveals divergent aging trajectories in veterans with and without traumatic brain injury - Michelle C. Eliason; Amrutha Bindu Nagella; Cristian Cuadra; David S. Wack; Ghazala T. Saleem; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowki; Arthur W. Toga; et al. (GeroScience, 2025)

Materials Learning Algorithms (MALA): Scalable machine learning for electronic structure calculations in large-scale atomistic simulations - Attila Cangi; Lenz Fiedler; Bartosz Brzoza; Karan Shah; Timothy J. Callow; Daniel Kotik; Steve Schmerler; Matthew C. Barry; James M. Goff; Andrew Rohskopf; Dayton J. Vogel; Normand Modine; et al. (Computer Physics Communications, 2025)

The essential role of large research vessels in marine ecosystem observations and ocean sustainability - Erin V. Satterthwaite; John C. Field; Andrea J. Fassbender; Gerardo Aceves‐Medina; Steven J. Bograd; Elliott L. Hazen; Nastassia V. Patin; Zachary Gold; Katherine A. Barbeau; Danie Kinkade; Adam Shepherd; Rasmus Swalethorp; et al. (Limnology and Oceanography, 2025)
Our understanding of marine ecosystems and ability to manage them sustainably has come from multidisciplinary observations made repeatedly over long periods of time. These long‐term ecosystem observations depend on the capabilities of large research vessels, which play an essential role in the collection of global ocean observations. Research vessels serve as large, stable platforms for collecting high volume samples from the surface to the seafloor that provide uniquely valuable in situ marine ecosystem information. Additionally, they serve as mobile laboratories enabling the collection, preservation, processing, and analysis of unique samples and data, such as chemical, biogeochemical, and biological parameters. Given their capacity for, and repeated use in, collecting comprehensive marine ecosystem observations—across geology, physics, chemistry, and biology—large research vessels provide insight into long‐term regional ecosystem dynamics. They also act as platforms‐of‐opportunity for testing, refining, and comparing technologies, enabling innovation and the evolution of the observing system. High‐quality observations from large research vessels serve as the backbone for many other components of the global ocean observing system through their use in calibrating autonomous sensors and predictive modeling. Moreover, large research vessels function as mobile, experiential training and exploration platforms that facilitate discovery, education, and collaboration. An effective, modular marine ecosystem observing system will depend on large research vessels to sustain and augment existing observing programs and to deploy, service, and validate the growing array of autonomous platforms that contribute to it. Achieving this vision will likely require maintaining and upgrading ship‐based infrastructure and personnel, integrating emerging technologies, leveraging the unique capabilities of large research vessels in conjunction with other platforms, strengthening collaborative partnerships, and building social capital for marine ecosystem observations through training, knowledge sharing, and effective governance.

Phenotypic plasticity underlies seasonal and latitudinal variation in thermal tolerance in a native bee - Matt C. Elmer; Keyne Monro; Harley Thompson; Aidan Stuckey; Vanessa Kellermann (Ecology, 2025)
Climate change threatens biodiversity and ecosystem services around the globe. Despite the importance of native bees as pollinators, there is evidence of global declines, and we know very little about how climate shapes their distributions now and into the future. In the current study, we combined large‐scale seasonal field sampling and experimental acclimation to examine whether populations of an Australian bee, Exoneura robusta , vary in their capacity to adapt to different climates. Collecting female bees across a latitudinal cline and examining heat and cold tolerance, we found populations did not vary in their heat tolerance along a latitudinal gradient. In contrast, bees from higher latitudes tended to be more cold‐tolerant than bees from lower latitudes, but the relationship between cold tolerance and latitude differed between summer and spring (post‐winter). Such seasonal variation suggests that phenotypic plasticity plays a role in shaping cold tolerance, as bees are likely to belong to the same generation from summer to spring. To untangle the roles of plasticity and genetic variation in shaping variation in thermal tolerance across seasons, we acclimated adult females from three populations spanning the species' distributional range to either 21 or 26°C in glasshouses (approximating summer and spring/autumn temperatures experienced throughout their range). We then estimated heat and cold tolerance. Contrasting acclimation responses observed in the glasshouses to those observed in the field point to phenotypic plasticity in cold tolerance rather than genetic variation underpinning population variation. In contrast, heat tolerance varied little in the field and in our glasshouse experiments. These results suggest bees may have little capacity to increase their heat tolerance, which is high at ~47°C, via genetic or plastic responses as climate changes.

Assessing the Effectiveness of 3D-Printed Ceramic Structures for Coral Restoration: Growth, Survivorship, and Biodiversity Using Visual Surveys and eDNA - Vriko Yu; Alison D. Corley; Horace Lau; Philip D. Thompson; Zhongyue Wilson Wan; Jane C. Y. Wong; Zoe Kwan Ting Wong; Louise Wai Hung Li; Shelby E. McIlroy; David M. Baker (Journal of Marine Science and Engineering, 2025)
Coral reef degradation has spurred the development of artificial structures to mitigate losses in coral cover. These structures serve as substrates for coral transplantation, with the expectation that growing corals will attract reef-associated taxa—while the substrate’s ability to directly support biodiversity is often neglected. We evaluated a novel 3D-printed modular tile made of porous terra cotta, designed with complex surface structures to enhance micro- and cryptic biodiversity, through a restoration project in Hong Kong. Over four years, we monitored 378 outplanted coral fragments using diver assessments and photography, while biodiversity changes were assessed through visual surveys and eDNA metabarcoding. Coral survivorship was high, with 88% survival after four years. Visual surveys recorded seven times more fish and almost 60% more invertebrates at the restoration site compared to a nearby unrestored area. eDNA analyses revealed a 23.5% higher eukaryote ASV richness at the restoration site than the unrestored site and 13.3% greater richness relative to a natural reference coral community. This study highlights the tiles’ dual functionality: (1) supporting coral growth and (2) enhancing cryptic biodiversity, an aspect often neglected in traditional reef restoration efforts. Our findings underscore the potential of 3D-printed ceramic structures to improve both coral restoration outcomes and broader reef ecosystem recovery.

Group Psychosocial Interventions Following Acquired Brain Injury: A Systematic Review and Meta-analysis of Group Process and Outcomes - Hannah L. McGlashan; Kate Thompson; Michael Lam; Tegan Cruwys; Zoe C. Walter; Elizabeth Beadle; Catherine Haslam (Neuropsychology Review, 2025)
Acquired brain injury can result in disability with direct and indirect consequences for psychosocial functioning. Psychosocial interventions embedded within traditional neurorehabilitation may provide a valuable buffer. While there is evidence of benefits associated with group-based psychosocial interventions, there is no single recommended intervention, despite several different approaches having been trialled. This systematic review aimed to provide a critical appraisal of existing group psychosocial interventions in neurorehabilitation, meta-analyse their efficacy, and explore the contribution of group process to outcomes. Eligible studies were published in English-language peer-reviewed journals and recruited adults with acquired brain injury in receipt of group psychosocial interventions. Outcomes of interest were depression, anxiety, quality of life, emotional distress, community integration, and social support. A systematic search of CINAHL, PsycINFO, Medline, Web of Science and Embase from database inception until 08.07.2024 was conducted. Risk of bias was assessed using the Effective Public Health Practice Project Quality Assessment Tool for Quantitative Studies. Effect sizes were calculated using Hedges’ g and estimated using a three-level random effects model. Sixty-five studies were included in the systematic review, and 48 were included in the meta-analysis ( n = 2653). There was an overall small effect on psychosocial outcomes (Hedges’ g = 0.24, 95% CIs [0.16, 0.33]), though none of the included studies satisfactorily analysed group process despite 70% of these studies proclaiming their importance. Overall, there were mixed findings across intervention type and significant heterogeneity. Recommendations for future psychosocial group interventions in neurorehabilitation are provided.

Neighborhood environmental vulnerability factors strongly drove COVID-19 fatality and excess all-cause mortality in New York City, while long-term air pollutant associations were weak and varied - Alexander Azan; Sneha Kannoth; Cong Zhang; Mehr Shafiq; Earle C. Chambers; Perry E. Sheffield; Sandra S. Albrecht; Azure Thompson; Jennifer Woo Baidal; Min Qian; Stephanie Lovinsky-Desir; Jeanette A. Stingone (Science of The Total Environment, 2025)

Human health risk assessment of three smoke flavoring primary products - G. Brorby; A. Franzen; C. Thompson; D. Wikoff; C. Doepker (Food and Chemical Toxicology, 2025)

In-situ formation of glyphosate and AMPA in activated sludge from phosphonates used as antiscalants and bleach stabilizers in households and industry - L. Engelbart; S. Bieger; K. Thompson; L. Fischer; T. Bader; M. Kramer; S.B. Haderlein; A.M. Röhnelt; P.R. Martin; D. Buchner; R. Bloch; H. Rügner; et al. (Water Research, 2025)

Cross‐Continental Analysis Shows That Disturbance Effects on Reptile Body Condition Do Not Predict Abundance Responses - Kristina J. Macdonald; Don A. Driscoll; Michael D. Craig; Robert A. Davis; Steven J. Hromada; C. M. Gienger; Lee A. Fitzgerald; Daniel J. Leavitt; Danielle K. Walkup; Rickard Abom; Adrian F. Wayne; Gordon R. Friend; et al. (Global Change Biology, 2025)
Ecological disturbances are discrete events that alter or transform the physical, chemical, or biological characteristics of ecosystems. Disturbance can cause animal populations to decline and, according to the risk‐disturbance hypothesis and population collapse framework, these declines can be predicted by declines in animal body condition. However, no research has empirically examined the general relationship between body condition and abundance, nor their relationship in response to disturbance. We used a combined dataset representing 33 studies and > 42,000 observations of 75 species from Australia, New Zealand, Spain and the United States of America to test predictions relating to the relationship between reptile body condition and abundance. We first investigated the relationship at the site level and then used meta‐analytical models to test whether populations showed linked changes in abundance and body condition in response to disturbance. We further tested whether key environmental and species traits influenced this relationship and whether there was a time‐lagged effect of body condition responses on abundance. We found a positive relationship between mean reptile body condition and abundance at the site level. However, the relationship was largely lost when investigating population responses to disturbance. As such, our results provided no support for the risk‐disturbance hypothesis and limited support for the population collapse framework. Therefore, the impacts of disturbance on reptile body condition cannot be assumed to reflect or predict abundance responses. We provide a new conceptual framework that shows how disturbances can modify or uncouple the relationship between abundance and body condition by influencing underlying drivers, such as predation, competition and resource availability. Monitoring programs that infer population impacts based on changes in body condition should first confirm the relationship between these two variables in the relevant study system.

Continental Patterns of Phenotypic Variation Along Replicated Urban Gradients: A Mega‐Analysis - M. J. Thompson; J. G. A. Martin; C. Biard; J. Bleu; C. J. Branston; P. Capilla‐Lasheras; N. J. Dingemanse; D. M. Dominoni; M. Eens; T. Eeva; K. L. Evans; C. Isaksson; et al. (Ecology Letters, 2025)
Individual variation among and within natural populations can have eco‐evolutionary implications by, for example, affecting species interactions or evolutionary potential. Urban systems present a unique opportunity to evaluate how environmental change shapes variation since urban phenotypic differentiation is widely documented on contemporary timescales. We introduce and test three hypotheses to determine how urbanisation affects phenotypic variation at different population levels. Combining 21 long‐term datasets in a mega‐analysis approach, we synthesise how urbanisation impacts variation in tarsus length and lay date among and within subpopulations of great and blue tits ( Parus major , Cyanistes caeruleus ) at a continental scale. Our synthesis reveals that urbanisation is associated with increased phenotypic variation within subpopulations by 11% on average, and by as much as 25% across the species and traits examined. We also find some evidence (for tarsus length in great tits) that urbanisation increases differentiation between subpopulations. We did not, however, find that urbanisation increases differences between subpopulations in their within‐subpopulation variation. Our synthesis provides novel insights into how urban contexts impact individual diversity at different spatial scales and we highlight future directions that could establish the genetic and environmental effects that underlie these continental patterns of urban phenotypic variation.

Applying U–Th disequilibrium for dating siliceous sinters - L. Sankovitch; C. Munoz-Saez; A.M. Hudson; L. Godfrey; J.M. Thompson (Journal of Volcanology and Geothermal Research, 2025)

Hypotheses for the water and metal fluxes to the rippled Amapari Marker Band, Gale Crater, Mars - E.S. Kite; P. Gasda; C.J. Tino; C. Weitz; L. Thompson; B.M. Tutolo; C.A. Mondro; W.H. Farrand; S. Gupta; J. Schieber; W.E. Dietrich; N. Mangold; et al. (Earth and Planetary Science Letters, 2025)

Acute heat stress and the extirpation of a threatened coral species from a remote, subtropical reef system - Ava M. Thompson; Anastasios Stathakopoulos; Karli J. Hollister; Amelia M. Lynch; Jordan C. Holder; Ilsa B. Kuffner (Coral Reefs, 2025)
The ecological significance of the reef-building elkhorn coral, Acropora palmata , is threatened by heat-stress-induced mortality. The intensity and duration of the ocean heatwave affecting Dry Tortugas National Park in the summer of 2023 was historically unprecedented in its early timing and maximum temperatures reached and resulted in 100% A. palmata mortality. To understand the lethality of this event, we examined temperature data measured by in situ data loggers and estimated from satellites (National Oceanic and Atmospheric Administration’s Coral Reef Watch) to investigate the timing of peak ocean temperatures and coral mortality. The in situ dataset revealed warmer water temperatures during the heatwave than those reported from the satellites, and the difference between the datasets was significantly pronounced during the summer. Our results support that, at least for this subtropical population, A. palmata may have an upper-threshold temperature that caused lethality faster than expected from the gradual accumulation of heat stress.

Publisher Correction: Investigation of blood–brain barrier penetration and pharmacokinetics of a new formulation of cyanide antidote dimethyl trisulfide - Lóránd Kiss; Fruzsina R. Walter; Gábor Katona; Ana Raquel Santa-Maria; Ashley C. Whiteman; Christian T. Rios; Kyler D. Kelley; Breanna Nelson; David E. Thompson; Ildikó Csóka; Piroska Szabó-Révész; Mária A. Deli; et al. (Toxicology and Environmental Health Sciences, 2025)

Investigation of blood–brain barrier penetration and pharmacokinetics of a new formulation of cyanide antidote dimethyl trisulfide - Lóránd Kiss; Fruzsina R. Walter; Gábor Katona; Ana Raquel Santa-Maria; Ashley C. Whiteman; Christian T. Rios; Kyler D. Kelley; Breanna Nelson; David E. Thompson; Ildikó Csóka; Piroska Szabó-Révész; Mária A. Deli; et al. (Toxicology and Environmental Health Sciences, 2025)
Objective During cyanide poisoning, the rescue of vital organs like the brain is urgent. However, due to the presence of the blood–brain barrier (BBB), the currently available cyanide antidotes cannot reach the brain. Dimethyl trisulfide (DMTS) is a potent cyanide antidote and has excellent BBB permeability. Nonetheless, its formulation and application are challenging due to its highly lipophilic profile. In this work, a novel DMTS formulation, called FF-DMTS, was investigated. Its effect on in vitro DMTS permeability through BBB models, cellular viability, and in vivo absorption were tested. Methods The particle size was measured in FF-DMTS formulation. The permeability of DMTS in this new formulation was tested in BBB-PAMPA and in primary triple co-culture models of BBB. The effect of FF-DMTS on cellular viability was determined. To test the membrane and barrier integrity transendothelial electrical resistance (TEER) and cell layer impedance measurements, immunofluorescent stainings and the fluorescein permeability technique were applied. The pharmacokinetics of DMTS were revealed in blood and brain tissue. Results The average size of micelles in FF-DMTS was 16 nm. The permeability of DMTS through BBB-PAMPA and cell culture model was 7.68 × 10 –6 and 23.81 × 10 –6 cm/s, respectively. The FF-DMTS disturbed the barrier integrity of brain endothelial cells without causing any alteration in cellular viability until 300 µg/ml DMTS concentration. After administration of 150 mg/kg DMTS to mice, its absorption into the blood was rapid (5 min) and the plasma concentration of DMTS reached 5.2 µg/ml. The DMTS was also detected in brain, where its peak concentration was 495 ng/g brain tissue after 10 min of intramuscular administration. Furthermore, even 2 h later, DMTS was detected in brain. Conclusions Here, we showed that the novel FF-DMTS formulation has good permeability through BBB and a remarkable pharmacokinetic profile. Therefore, further investigation of the efficacy of FF-DMTS for treating cyanide intoxication is important.

Characterisation of tyre wear particle transport from road runoff to sea in coastal environments - Florence N.F. Parker-Jurd; Geoffrey D. Abbott; Daniel C. Conley; Cijo M. Xavier; Florian Pohl; Richard C. Thompson (Marine Pollution Bulletin, 2025)

Citizen science reveals litter trends in the UK: Population density effects on coastal and inland regions - Imogen E. Napper; Bede F.R. Davies; Aquila Erskine; Richard C. Thompson; Rachel Yates; Heather Koldewey (Marine Pollution Bulletin, 2025)

Study of D s 1 ( 2460 ) + → D s + π + π - in B → D ‾ ( * ) D s + π + π - decays - R. Aaij; A.S.W. Abdelmotteleb; C.Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2025)

Withdrawn: Evaluation of a bioreactor for chorionic girdle organoid proliferation and function - R.E. Thompson; M.A. Meyers; J.L. Sones; C. Magee; F.K. Hollinshead (Journal of Equine Veterinary Science, 2025)

Registry versus claims-based index dates for studies of cancer diagnosis in administrative data - Sarah E. Soppe; Sharon Peacock Hinton; Jamie C. Halula; Jennifer L. Lund; Chris D. Baggett; Sandi L. Pruitt; Megan A. Mullins; Ellis C. Dillon; Matthew E. Barclay; Matthew Thompson; Nicholas Pettit; Georgios Lyratzopoulos; et al. (Cancer Causes & Control, 2025)

BioTIME 2.0: Expanding and Improving a Database of Biodiversity Time Series - Maria Dornelas; Laura H. Antão; Amanda E. Bates; Viviana Brambilla; Jonathan M. Chase; Cher F. Y. Chow; Ada Fontrodona‐Eslava; Anne E. Magurran; Inês S. Martins; Faye Moyes; Alban Sagouis; Samuel Adu‐Acheampong; et al. (Global Ecology and Biogeography, 2025)
Motivation Here, we make available a second version of the BioTIME database, which compiles records of abundance estimates for species in sample events of ecological assemblages through time. The updated version expands version 1.0 of the database by doubling the number of studies and includes substantial additional curation to the taxonomic accuracy of the records, as well as the metadata. Moreover, we now provide an R package (BioTIMEr) to facilitate use of the database. Main Types of Variables Included The database is composed of one main data table containing the abundance records and 11 metadata tables. The data are organised in a hierarchy of scales where 11,989,233 records are nested in 1,603,067 sample events, from 553,253 sampling locations, which are nested in 708 studies. A study is defined as a sampling methodology applied to an assemblage for a minimum of 2 years. Spatial Location and Grain Sampling locations in BioTIME are distributed across the planet, including marine, terrestrial and freshwater realms. Spatial grain size and extent vary across studies depending on sampling methodology. We recommend gridding of sampling locations into areas of consistent size. Time Period and Grain The earliest time series in BioTIME start in 1874, and the most recent records are from 2023. Temporal grain and duration vary across studies. We recommend doing sample‐level rarefaction to ensure consistent sampling effort through time before calculating any diversity metric. Major Taxa and Level of Measurement The database includes any eukaryotic taxa, with a combined total of 56,400 taxa. Software Format csv and. SQL.

Predicting the progression of MCI and Alzheimer’s disease on structural brain integrity and other features with machine learning - Marthe Mieling; Mushfa Yousuf; Nico Bunzeck; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; Susan Landau; Monica Rivera-Mindt; Leslie M. Shaw; Edward B. Lee; et al. (GeroScience, 2025)
Machine learning (ML) on structural MRI data shows high potential for classifying Alzheimer’s disease (AD) progression, but the specific contribution of brain regions, demographics, and proteinopathy remains unclear. Using Alzheimer’s Disease Neuroimaging Initiative (ADNI) data, we applied an extreme gradient-boosting algorithm and SHAP (SHapley Additive exPlanations) values to classify cognitively normal (CN) older adults, those with mild cognitive impairment (MCI) and AD dementia patients. Features included structural MRI, CSF status, demographics, and genetic data. Analyses comprised one cross-sectional multi-class classification (CN vs. MCI vs. AD dementia, n = 568) and two longitudinal binary-class classifications (CN-to-MCI converters vs. CN stable, n = 92; MCI-to-AD converters vs. MCI stable, n = 378). All classifications achieved 70–77% accuracy and 61–83% precision. Key features were CSF status, hippocampal volume, entorhinal thickness, and amygdala volume, with a clear dissociation: hippocampal properties contributed to the conversion to MCI, while the entorhinal cortex characterized the conversion to AD dementia. The findings highlight explainable, trajectory-specific insights into AD progression.

Large polluted river plumes threats sustainable mariculture in the Baia da Ilha Grande - A.F.O. Andrade; C. Lima; L. Bacha; M.A.P. Oliveira; L. Leomil; C.E. Rezende; J.C.F.A. Wasserman; P.M.S. Costa; S., R. Costa; E. Siegle; C. Thompson; F.L. Thompson; et al. (Regional Studies in Marine Science, 2025)

Modeling the impacts of sand placement strategies on barrier island evolution in a semi-enclosed bay system - Davina L. Passeri; Rangley C. Mickey; David M. Thompson; Michael Itzkin; Elizabeth Godsey; Matthew V. Bilskie; Alexander Seymour; Autumn Poisson; Jin Ikeda; Scott C. Hagen (Coastal Engineering, 2025)

Dissociation of intake and incentive sensitization during intermittent- and continuous-access heroin self-administration in rats - Elizabeth A. Rakowski; Christopher P. King; Brady M. Thompson; Gabriel Santos; Esther Holmes; Leah C. Solberg Woods; Oksana Polesskaya; Abraham A. Palmer; Paul J. Meyer (Psychopharmacology, 2025)
Rationale Opioid misuse is a prominent public health concern, although patterns of use may confer different vulnerability to relapse. Continuous-access ( ContA ) self-administration has traditionally been used in preclinical models to study drug-motivated behaviors and produces robust escalation of intake and tolerance development. Alternatively, studies using intermittent access ( IntA ), where self-administration occurs in discrete drug-available periods, suggest that overall intake may be dissociable from subsequent increases in motivation (i.e., incentive sensitization). However, IntA paradigms have focused primarily on psychostimulants like cocaine and methamphetamine and have not been as comprehensively studied with opioids. Objective We compared two paradigms of heroin self-administration, ContA and IntA, to assess their effect on heroin intake and motivation. Methods Male and female rats were trained to self-administer heroin, then were transitioned to either ContA or IntA paradigms. Following self-administration, rats were tested in progressive-ratio, behavioral economics threshold probe, and conditioned reinforcement tests to measure motivation-related behaviors. Results Both patterns of intake evoked similar heroin-directed motivation during progressive-ratio and conditioned reinforcement tests, despite lower overall intake throughout IntA for male rats. Females had similar responding between treatments in self-administration and progressive-ratio even though IntA rats had less time to earn infusions. During threshold probe, IntA-trained subjects showed more inelastic responding (lower α values), suggesting a greater degree of dependence-like behavior. Conclusions These results suggest the importance of dissociating heroin intake from incentive sensitization and emphasize the significance of sex differences as a modifier of heroin consumption and motivation.

Neuroinflammation in Severe COVID-19: The Dynamics of Inflammatory and Brain Injury Markers During Hospitalization - Carla Andretta Moreira Neves; Gilson P. Dorneles; Paula C. Teixeira; Paulo C. Santana Filho; Alessandra Peres; Carina Rodrigues Boeck; Liane N. Rotta; Claudia E. Thompson; Pedro R. T. Romão (Molecular Neurobiology, 2025)

Diverse microbial prey in the guts of gelatinous grazers revealed by microscopy - Terra C. Hiebert; Anne W. Thompson; Kelly R. Sutherland (Marine Biology, 2025)

Voxel-wise insights into early Alzheimer’s disease pathology progression: the association with APOE and memory decline - Maha Wybitul; Nicolas Langer; Christoph Hock; Anton Gietl; Valerie Treyer; Michael Weiner; Paul Aisen; Ronald-Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowski; Arthur W. Toga; et al. (GeroScience, 2025)
Longitudinal investigation of the Apolipoprotein E (APOE) genotype’s impact on Alzheimer’s disease (AD) biomarker progression, focusing on amyloid beta (Aβ) accumulation and gray matter (GM) atrophy, integrating cognitive decline and baseline levels. Longitudinal florbetapir-PET and T1-weighted MRI data from 100 cognitively normal (CN) and mild cognitive impaired (MCI) participants both with considerable global Aβ accumulation (“high Aβ accumulators”) were analyzed using a voxel-wise approach. Associations of APOE genotype and memory decline with Aβ accumulation and GM atrophy were examined separately for each neuroimaging modality, controlling for baseline Aβ levels and diagnosis. Alternatively, the effect of baseline diagnosis, while controlling for memory decline, was investigated. A multimodal analysis evaluated interactions between genotype, memory decline, and GM atrophy on Aβ accumulation. High Aβ accumulators displayed extensive Aβ pathology predominantly in the medial orbito-frontal cortex, cingulate cortex, and precuneus, along with GM atrophy in temporal, occipital, orbito-frontal, and parietal areas. ɛ4 carriers with memory decline exhibited greater Aβ accumulation and GM atrophy in selective regions compared to non-carriers with memory decline, while no genotype difference was observed in individuals without decline. No interaction effect was observed for MCI diagnosis. Regional associations between the two biomarkers were similarly dependent on genotype and memory decline. ɛ4 carriers exhibiting memory decline present an accelerated neurobiological pattern at predementia stages, supporting early ɛ4 carrier monitoring and interventions in this at-risk group. Importantly, memory decline might be more informative than MCI regarding AD pathology progression emphasizing the importance of repeated cognitive assessments.

Prey particle surface property mediates differential selection by the ubiquitous appendicularian Oikopleura dioica - Terra C. Hiebert; Anne E. Aasjord; Daniel M. Chourrout; Anne W. Thompson; Kelly R. Sutherland (Limnology and Oceanography, 2025)
Cell surface properties can strongly mediate microbial interactions with predators in soil and host‐pathogen systems. Yet, the role of microbial surface properties in avoiding or enhancing predation in the ocean is less well known. Appendicularians are globally abundant marine suspension feeders that capture marine microorganisms in a complex mucous filtration system. We used artificial microspheres to test whether the surface properties of prey particles influenced selection by the appendicularian, Oikopleura dioica . We used a range of microsphere sizes (0.5, 1, 2, and 3 μ m), concentrations (~ 10 3 –10 6 particles mL −1 ), and two charges (amine‐modified, more positive vs. carboxylate‐modified, more negative) to represent open‐ocean microbial communities. We found that appendicularians selected between the particles of different charge. More negatively charged particles were enriched in the gut by up to 3.8‐fold, while more positive particles were enriched in the mucous filters by up to 4.7‐fold, leading to different particle fates. These results expand understanding of the mechanisms by which filter‐feeders select between prey and reveal a mechanism by which marine bacteria could rapidly alter their susceptibility to predation, either through adaption or acclimation.

Temperature Drives Seagrass Recovery Across the Western North Atlantic - Fee O. H. Smulders; Justin E. Campbell; Andrew H. Altieri; Anna R. Armitage; Elisabeth S. Bakker; Savanna C. Barry; S. Tatiana Becker; Enrique Bethel; James G. Douglass; Hannah J. van Duijnhoven; Jimmy de Fouw; Thomas K. Frazer; et al. (Global Change Biology, 2025)
Climate‐driven shifts in herbivores, temperature, and nutrient runoff threaten coastal ecosystem resilience. However, ecological resilience, particularly for foundation species, remains poorly understood due to the scarcity of field experiments conducted across appropriate spatial and temporal scales that investigate multiple stressors. This study evaluates the resilience of a widespread tropical marine plant (turtlegrass) to disturbances across its geographic range and examines how environmental gradients in (a)biotic factors influence recovery. We assessed turtlegrass resilience by following recovery rates for a year after a simulated pulse disturbance (complete above‐ and belowground biomass removal). Contrary to studies in temperate areas, higher temperature generally enhanced seagrass recovery. While nutrients had minimal individual effects, they reduced aboveground recovery when combined with high levels of herbivore grazing (meso and megaherbivore). Belowground recovery was also affected by combined high levels of nutrients and grazing (megaherbivores only). Light availability had minimal effects. Our results suggest that the resilience of some tropical species, particularly in cooler subtropical waters, may initially benefit from warming. However, continuing shifts in nutrient supply and changes in grazing pressure may ultimately serve to compromise seagrass recovery.

Adaptive sampling with PIXL on the Mars Perseverance rover - Peter R. Lawson; Tanya V. Kizovski; Michael M. Tice; Benton C. Clark; Scott J. VanBommel; David R. Thompson; Lawrence A. Wade; Robert W. Denise; Christopher M. Heirwegh; W. Timothy Elam; Mariek E. Schmidt; Yang Liu; et al. (Icarus, 2025)

Evidence of eastern rockhopper penguin feeding on a key commercial arrow squid species - Hugo R. Guímaro; David R. Thompson; Kyle W. Morrison; Joana Fragão; Ricardo S. Matias; José C. Xavier (Polar Biology, 2025)
Cephalopods are crucial to the Southern Ocean ecosystem, connecting top predators with mid-trophic organisms, yet their ecology in the Pacific sector is not well understood. This research used stable isotope analysis to explore the habitat and trophic ecology of cephalopods found in the diet of eastern rockhopper penguins ( Eudyptes chrysocome filholi ) around Campbell Island, a New Zealand sub-Antarctic island. Eastern rockhopper penguins were used as biologic samplers, revealing some differences in cephalopod diversity and ecology between two breeding seasons—1986–87 and 2012–13—, and the squid Nototodarus sloanii , a commercially valuable species, was described for the first time in the 2012–13 season. Stable isotope values ( δ 13 C and δ 15 N) for the squid species Moroteuthopsis ingens were consistent between seasons, indicating ecological stability, whereas the octopod species Octopus campbelli showed changes, suggesting shifts in habitat and feeding. Warmer oceanic temperatures in 2012–13 may have facilitated the emergence of N. sloanii on the diet of the eastern rockhopper penguins. These findings highlight potential changes in cephalopod biodiversity in the Pacific sector of the Southern Ocean, emphasizing the need for further research on ecological dynamics of this region.

Analysis of Oncology and Radiation Therapy Representation on the National Board of Medical Examiners Official Practice Material for the United States National Standardized Medical Board Examinations - Mary T. Mahoney; Lauren C. Linkowski; Trudy C. Wu; Jie Jane Chen; Beth K. Neilsen; Petria S. Thompson; Michael D. Mix; Karna T. Sura; Malcolm D. Mattes (Journal of Cancer Education, 2025)
Radiation therapy (RT) is a critical component of multidisciplinary cancer care, but has inconsistent curricular exposure. We characterize the radiation oncology (RO) content on the standardized undergraduate medical examinations by comparing its context and prevalence with other domains in oncology. National Board of Medical Examiners (NBME) self-assessments and sample questions for the United States Medical Licensing Exam (USMLE) Steps 1–3 and NBME clinical science shelf examinations were accessed ( n = 3878). Questions were inductively analyzed for content pertaining to oncology and treatment modalities of RT, systemic therapy (ST), and surgical intervention (SI). Questions were coded using USMLE Physician Tasks/Competencies and thematic analysis. Descriptive statistics and analyses using the Kruskal–Wallis test are reported. A total of 337 questions (8.6%) within the USMLE and shelf exams included oncology content, with 101 questions (2.6%) referencing at least one cancer treatment modality ( n = 35 RT, 45 ST, 57 SI). Treatment questions were more common on USMLE Step 2 CK ( n = 35/101, 32%) compared to Step 1 ( n = 23/101, 23%) and Step 3 ( n = 8/101, 8%) ( p < 0.001). RT was significantly less likely to be the correct answer (2/35, 6%) compared to ST (4/45, 9%) and SI (18/57, 32%) ( p = 0.003). Therapeutic oncology questions are uncommon on the examination material, with an under-representation of radiation-related content, and contextual bias favoring surgical approaches. We advocate for greater RO involvement in the content creation of such examinations to help trainees better understand multidisciplinary cancer care.

Assessing a Continuing Education Course for Dental Hygienists to Improve HPV and HPV Vaccine Knowledge and Self-efficacy - Stacey B. Griner; Malinee Neelamegam; Nolan Kline; Jane C. Cotter; Charlene Dickinson; Alexandra N. Farris; Erika L. Thompson (Journal of Cancer Education, 2025)

EuPPollNet : A European Database of Plant‐Pollinator Networks - Jose B. Lanuza; Tiffany M. Knight; Nerea Montes‐Perez; Will Glenny; Paola Acuña; Matthias Albrecht; Maddi Artamendi; Isabelle Badenhausser; Joanne M. Bennett; Paolo Biella; Ricardo Bommarco; Andree Cappellari; et al. (Global Ecology and Biogeography, 2025)
Motivation Pollinators play a crucial role in maintaining Earth's terrestrial biodiversity. However, rapid human‐induced environmental changes are compromising the long‐term persistence of plant‐pollinator interactions. Unfortunately, we lack robust, generalisable data capturing how plant‐pollinator communities are structured across space and time. Here, we present the EuPPollNet (European Plant‐Pollinator Networks) database, a fully open European‐level database containing harmonised taxonomic data on plant‐pollinator interactions referenced in both space and time, along with other ecological variables of interest. In addition, we evaluate the taxonomic and sampling coverage of EuPPollNet, and summarise key structural properties in plant‐pollinator networks. We believe EuPPollNet will stimulate research to address data gaps in plant‐pollinator interactions and guide future efforts in conservation planning. Main Types of Variables Included EuPPollNet contains 1,162,109 interactions between plants and pollinators from 1864 distinct networks, which belong to 52 different studies distributed across 23 European countries. Information about sampling methodology, habitat type, biogeographic region and additional taxonomic rank information (i.e. order, family, genus and species) is also provided. Spatial Location and Grain The database contains 1214 different sampling locations from 13 different natural and anthropogenic habitats that fall in 7 different biogeographic regions. All records are geo‐referenced and presented in the World Geodetic System 1984 (WGS84). Time Period and Grain Species interaction data was collected between 2004 and 2021. Major Taxa and Level of Measurement The database contains interaction data at the species level for 94% of the records, including a total of 1411 plant and 2223 pollinator species. The database includes data on 6% of the European species of flowering plants, 34% of bees, 26% of butterflies and 33% of syrphid species at the European level. Software Format The database was built with R and is stored in ‘.rds’ and ‘.csv’ formats. Its construction is fully reproducible and can be accessed at: https://doi.org/10.5281/zenodo.14747448 .

Global Marine Flyways Identified for Long‐Distance Migrating Seabirds From Tracking Data - Joanne M. Morten; Ana P. B. Carneiro; Martin Beal; Anne‐Sophie Bonnet‐Lebrun; Maria P. Dias; Marie‐Morgane Rouyer; Autumn‐Lynn Harrison; Jacob González‐Solís; Victoria R. Jones; Virginia A. Garcia Alonso; Michelle Antolos; Javier A. Arata; et al. (Global Ecology and Biogeography, 2025)
Aim To identify the broad‐scale oceanic migration routes (‘marine flyways’) used by multiple pelagic, long‐distance migratory seabirds based on a global compilation of tracking data. Location Global. Time Period 1989–2023. Major Taxa Studied Seabirds (Families: Phaethontidae, Hydrobatidae, Diomedeidae, Procellariidae, Laridae and Stercorariidae). Methods We collated a comprehensive global tracking dataset that included the migratory routes of 48 pelagic and long‐distance migrating seabird species across the Atlantic, Indian, Pacific and Southern Oceans. We grouped individuals that followed similar routes, independent of species or timings of migration, using a dynamic time warping clustering approach. We visualised the routes of each cluster using a line density analysis and used knowledge of seabird spatial ecology to combine the clusters to identify the broad‐scale flyways followed by most pelagic migratory seabirds tracked to‐date at an ocean‐basin scale. Results Six marine flyways were identified across the world's oceans: the Atlantic Ocean Flyway, North Indian Ocean Flyway, East Indian Ocean Flyway, West Pacific Ocean Flyway, Pacific Ocean Flyway and Southern Ocean Flyway. Generally, the flyways were used bidirectionally, and individuals either followed sections of a flyway, a complete flyway, or their movements linked two or more flyways. Transhemispheric figure‐of‐eight routes in the Atlantic and Pacific oceans, and a circumnavigation flyway in the Southern Ocean correspond with major wind ‐ driven ocean currents. Main Conclusions The marine flyways identified demonstrate that pelagic seabirds have similar and repeatable migration routes across ocean‐basin scales. Our study highlights the need to account for connectivity in seabird conservation and provides a framework for international cooperation.

Dynamic proportional loss of functional connectivity revealed change of left superior frontal gyrus in subjective cognitive decline: an explanatory study based on Chinese and Western cohorts - Luyao Wang; Wenjing Hu; Fan Dong; Can Sheng; Jinglong Wu; Ying Han; Jiehui Jiang; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2025)

The alongshore tilt of mean dynamic topography and its implications for model validation and ocean monitoring - Christoph Renkl; Eric C. J. Oliver; Keith R. Thompson (Ocean Science, 2025)
Mean dynamic topography (MDT) plays an important role in the dynamics of shelf circulation. Coastal tide gauge observations in combination with the latest generation of geoid models are providing estimates of the alongshore tilt of MDT with unprecedented accuracy. Additionally, high-resolution ocean models are providing better representations of nearshore circulation and the associated tilt of MDT along their coastal boundaries. It has been shown that the newly available geodetic estimates can be used to validate model predictions of coastal MDT variability on global and basin scales. On smaller scales, however, there are significant variations in alongshore MDT that are of the same order of magnitude as the accuracy of the geoid models. In this study, we use a regional ocean model of the Gulf of Maine and Scotian Shelf (GoMSS) to demonstrate that the new observations of geodetically referenced coastal sea level can also provide valuable information for the validation of such high-resolution models. The predicted coastal MDT is in good agreement with coastal tide gauge observations referenced to the Canadian Gravimetric Geoid 2013 – Version A (CGG2013a), including a significant tilt of alongshore MDT along the coast of Nova Scotia. Using the validated GoMSS model and two idealized models, we show that this alongshore tilt of MDT can be interpreted in two complementary, and dynamically consistent, ways: in the coastal view, the tilt of MDT along the coast can provide a direct estimate of the average alongshore current. In the regional view, the tilt provides a measure of area-integrated nearshore circulation. This highlights the value of using geodetic MDT estimates for model validation and ocean monitoring.

Minimal Impacts of Tyre Particle Exposure on Estuarine Meiofaunal Community Structure, Primary Production, and Nutrient Cycling - Charlotte Woodhouse; Dannielle Senga Green; Andy Foggo; Paul J. Somerfield; Richard C. Thompson; Samantha L. Garrard (Journal of Marine Science and Engineering, 2025)
Tyre wear particles are a significant source of primary microplastics in the natural environment with the potential to accumulate in aquatic sediments, yet our understanding of the ecological impact of these particles is limited. Using mesocosms of estuarine sediment containing a model macrofauna community (Scrobicularia plana and Hediste diversicolor), meiofauna, and microphytobenthos, we investigated the impact of exposure to sedimentary tyre particles (0.2, 1, and 5% kg sediment(dw)−1) upon meiofauna community structure, primary production, secondary production, and nutrient fluxes. Under the conditions (13 °C) and timescale (31 days) investigated, exposure to sedimentary tyre particles did not lead to any significant differences in nutrients for primary productivity, with limited impact on meiofaunal secondary productivity. An increase in Tanaidacea was observed in 1% and 5% tyre particle treatments, putatively due to reduced macrofaunal predation. Previous studies have highlighted the ecotoxicity of tyre wear particles. The limited impacts on meiofauna may be due to our experimental particles being too large for meiofauna to ingest or the timescale of the experiment being too short to witness changes at the community scale. Impacts from tyre particle leachates were likely limited due to dilution in the partial recirculation system. Leachate dilution will occur naturally in marine systems and should be a consideration in the design of future studies.

Epilithic algal composition and the functioning of Anthropocene coral reefs - Sterling B. Tebbett; Michael J. Emslie; Michelle J. Jonker; Scott D. Ling; Morgan S. Pratchett; Alexandre C. Siqueira; Angus A. Thompson; Helen F. Yan; David R. Bellwood (Marine Pollution Bulletin, 2025)

“It just made sense to me!” A Qualitative Exploration of Individual Motivation for Time-Restricted Eating - Hilmi S. Rathomi; Nahal Mavaddat; Judith M. Katzenellenbogen; Sandra C. Thompson (Appetite, 2025)

Putting seedlings on the map: Trade‐offs in demographic rates between ontogenetic size classes in five tropical forests - Stephan Kambach; Helge Bruelheide; Liza S. Comita; Richard Condit; S. Joseph Wright; Salomón Aguilar; Chia‐Hao Chang‐Yang; Yu‐Yun Chen; Nancy C. Garwood; Stephen P. Hubbell; Pei‐Jen Luo; Margaret R. Metz; et al. (Ecology, 2025)
All species must partition resources among the processes that underly growth, survival, and reproduction. The resulting demographic trade‐offs constrain the range of viable life‐history strategies and are hypothesized to promote local coexistence. Tropical forests pose ideal systems to study demographic trade‐offs as they have a high diversity of coexisting tree species whose life‐history strategies tend to align along two orthogonal axes of variation: a growth–survival trade‐off that separates species with fast growth from species with high survival and a stature–recruitment trade‐off that separates species that achieve large stature from species with high recruitment. As these trade‐offs have typically been explored for trees ≥1 cm dbh, it is unclear how species' growth and survival during earliest seedling stages are related to the trade‐offs for trees ≥1 cm dbh. Here, we used principal components and correlation analyses to (1) determine the main demographic trade‐offs among seed‐to‐seedling transition rates and growth and survival rates from the seedling to overstory size classes of 1188 tree species from large‐scale forest dynamics plots in Panama, Puerto Rico, Ecuador, Taiwan, and Malaysia and (2) quantify the predictive power of maximum dbh, wood density, seed mass, and specific leaf area for species' position along these demographic trade‐off gradients. In four out of five forests, the growth–survival trade‐off was the most important demographic trade‐off and encompassed growth and survival of both seedlings and trees ≥1 cm dbh. The second most important trade‐off separated species with relatively fast growth and high survival at the seedling stage from species with relatively fast growth and high survival ≥1 cm dbh. The relationship between seed‐to‐seedling transition rates and these two trade‐off aces differed between sites. All four traits were significant predictors for species' position along the two trade‐off gradients, albeit with varying importance. We concluded that, after accounting for the species' position along the growth–survival trade‐off, tree species tend to trade off growth and survival at the seedling with later life stages. This ontogenetic trade‐off offers a mechanistic explanation for the stature–recruitment trade‐off that constitutes an additional ontogenetic dimension of life‐history variation in species‐rich ecosystems.

Intrinsic and environmental drivers of pairwise cohesion in wild Canis social groups - John F. Benson; David A. Keiter; Peter J. Mahoney; Benjamin L. Allen; Lee Allen; Francisco Álvares; Morgan L. Anderson; Shannon M. Barber‐Meyer; Adi Barocas; James C. Beasley; Linda Behrendorff; Jerrold L. Belant; et al. (Ecology, 2025)
Animals within social groups respond to costs and benefits of sociality by adjusting the proportion of time they spend in close proximity to other individuals in the group (cohesion). Variation in cohesion between individuals, in turn, shapes important group‐level processes such as subgroup formation and fission–fusion dynamics. Although critical to animal sociality, a comprehensive understanding of the factors influencing cohesion remains a gap in our knowledge of cooperative behavior in animals. We tracked 574 individuals from six species within the genus Canis in 15 countries on four continents with GPS telemetry to estimate the time that pairs of individuals within social groups spent in close proximity and test hypotheses regarding drivers of cohesion. Pairs of social canids ( Canis spp.) varied widely in the proportion of time they spent together (5%–100%) during seasonal monitoring periods relative to both intrinsic characteristics and environmental conditions. The majority of our data came from three species of wolves (gray wolves, eastern wolves, and red wolves) and coyotes. For these species, cohesion within social groups was greatest between breeding pairs and varied seasonally as the nature of cooperative activities changed relative to annual life history patterns. Across species, wolves were more cohesive than coyotes. For wolves, pairs were less cohesive in larger groups, and when suitable, small prey was present reflecting the constraints of food resources and intragroup competition on social associations. Pair cohesion in wolves declined with increased anthropogenic modification of the landscape and greater climatic variability, underscoring challenges for conserving social top predators in a changing world. We show that pairwise cohesion in social groups varies strongly both within and across Canis species, as individuals respond to changing ecological context defined by resources, competition, and anthropogenic disturbance. Our work highlights that cohesion is a highly plastic component of animal sociality that holds significant promise for elucidating ecological and evolutionary mechanisms underlying cooperative behavior.

Transcriptomic data support phylogenetic congruence and reveal genomic changes associated with the repeated evolution of annualism in aplocheiloid killifishes (Cyprinodontiformes) - Andrew W. Thompson; Amanda C. Black; Yu Huang; Qiong Shi; Andrew I. Furness; Ingo Braasch; Federico G. Hoffmann; Guillermo Ortí (Molecular Phylogenetics and Evolution, 2024)

Using geophysical subsurface data for the reconstruction of valley-scale spatio-temporal floodplain evolution: Implications for upland river restoration - Arved C. Schwendel; David J. Milan; Richard J.J. Pope; Richard Williams; Warren Thompson (Geomorphology, 2024)

Characterizing variability in geochemistry and mineralogy of western US dust sources - Abby L. Mangum; Gregory T. Carling; Barry R. Bickmore; Nicholas Webb; DeTiare L. Leifi; Janice Brahney; Diego P. Fernandez; Kevin A. Rey; Stephen T. Nelson; Landon Burgener; Joshua J. LeMonte; Alyssa N. Thompson; et al. (Aeolian Research, 2024)

Species identification of modern and archaeological shark and ray skeletal tissues using collagen peptide mass fingerprinting - Michael Buckley; Ellie-May Oldfield; Cristina Oliveira; Clara Boulanger; Andrew C. Kitchener; Nicole R. Fuller; Traci Ardren; Victor D. Thompson; Scott M. Fitzpatrick; Michelle J. LeFebvre (Frontiers in Marine Science, 2024)
Introduction Elasmobranchs, such as sharks and rays, are among the world’s most endangered vertebrates, with over 70% loss in abundance over the past 50 years due to human impacts. Zooarchaeological baselines of elasmobranch diversity, distribution, and exploitation hold great promise for contributing essential historical contexts in the assessment of contemporary patterns in their taxonomic diversity and vulnerability to human-caused extinction. Yet, the historical ecology of elasmobranchs receives relatively less archaeological attention compared to that of ray-finned fishes or marine mammals, largely due to issues of taxonomic resolution across zooarchaeological identifications. Methods We explore the use of Zooarchaeology by Mass Spectrometry (ZooMS) for species identification in this unstudied group, using an archaeological case study from the marine environments of the Florida Keys, a marine biodiversity hotspot that is home to an array of elasmobranch species and conservation efforts. By comparison with 39 modern reference species, we could distinguish 12 taxa within the zooarchaeological assemblage from the Clupper archaeological site (Upper Matecumbe Key) that included nine sharks, two rays and a sawfish. Results and discussion The results indicate that, through additional complexity of the collagen peptide mass fingerprint, obtained due to the presence of the cartilaginous type II collagen, ZooMS collagen peptide mass fingerprinting provides exceptionally high taxonomic resolution in this group, yielding species-level identifications in all cases where sufficient reference material was used. This case study also highlights the added value of ZooMS for taxa that are more difficult to distinguish in zooarchaeological analyses, such as vertebrae of the Atlantic sharpnose shark ( Rhizoprionodon terraenovae ) and the hammerhead sharks ( Sphyrna spp.) in the Florida Keys. Therefore, the application of collagen peptide mass fingerprinting to elasmobranchs offers great potential to improve our understanding of their archaeological past and historical ecology.

Distribution, abundance, and reproductive stages of salps, doliolids, and chaetognaths in different water masses of the shelf and open ocean of the Southwestern Atlantic Ocean between 31° and 38° S - Gustavo A. Thompson; Graciela N. Molinari; Martin D. Ehrlich; Maria C. Daponte (Journal of Marine Systems, 2024)

Resistance and resilience: Tidal freshwater marsh response and recovery to acute and chronic saltwater intrusion - Madeleine F. Thompson; Steve C. Pennings; Joseph P. Schubauer-Berigan; Ellen R. Herbert; Galen Costomiris; Christopher B. Craft (Estuarine, Coastal and Shelf Science, 2024)

Pseudoalteromonas simplex sp. nov. Isolated from the Skin of Bandtail Puffer Fish (Sphoeroides spengleri) - Hannah K. Mattsson; Mayanne A. M. de Freitas; Gustavo P. R. de Azevedo; Vinicius Salazar; Verônica V. Vieira; Diogo A. Tschoeke; Cristiane C. Thompson; Fabiano L. Thompson (Current Microbiology, 2024)

The biophysical dynamics of giant kelp, Macrocystis pyrifera : Seasonal patterns and dispersal mechanisms in the southeast Pacific - G. Thompson‐Saud; A. Grech; S. Choukroun; S. I. Vásquez; C. Salas; A. Ospina‐Alvarez (Journal of Biogeography, 2024)
Aim Dispersal and connectivity play important roles in shaping the population structure of giant kelp, Macrocystis pyrifera , across the western coast of South America. Its high potential dispersal capacity suggests the existence of metapopulations, where discrete habitat patches or groups of patches form subpopulations that interact at some level. However, the dispersal patterns of giant kelp in this region have not been quantified. This study assesses the dispersal and settlement of Macrocystis pyrifera in the southeast Pacific, specifically focusing on the impact of environmental variables and ocean currents within the Humboldt Current System. Location Southeast Pacific (coast of Chile and Peru). Time Period 1997–2008. Major Taxa Studied Macrocystis pyrifera (giant kelp). Methods Using a combination of hydrodynamic and individual‐based models, we analysed kelp fragment movements over 12 years, with a particular emphasis on the effects of the El Niño‐Southern Oscillation (ENSO) and seasonal changes. Results Our results highlight a key settlement area in the southern Chilean region. We found that shorter travel distances of kelp fragments increased the likelihood of reaching a suitable habitat, underscoring the importance of local environmental conditions. We delineated intricate northward dispersal paths for kelp fragments, which appear to be governed by the interplay of wind and ocean current dynamics. Seasonal variations, notably in autumn and winter, favour the likelihood of reaching a settlement area due to favourable winds. Furthermore, ENSO events appear to influence dispersal distances, with fragments travelling the longest distances during El Niño phases. Main Conclusion These findings are essential for informing kelp conservation strategies in the context of climate change, emphasizing the necessity of considering local and seasonal environmental factors alongside ENSO impacts.

Leveraging ecological indicators to improve short term forecasts of fish recruitment - Eric J. Ward; Mary E. Hunsicker; Kristin N. Marshall; Kiva L. Oken; Brice X. Semmens; John C. Field; Melissa A. Haltuch; Kelli F. Johnson; Ian G. Taylor; Andrew R. Thompson; Nick Tolimieri (Fish and Fisheries, 2024)
Forecasting the recruitment of fish populations with skill has been a challenge in fisheries for over a century. Previous large‐scale meta‐analyses have suggested linkages between environmental or ecosystem drivers and recruitment; however, applying this information in a management setting remains underutilized. Here, we use a well‐studied database of groundfish assessments from the West Coast of the USA to ask whether environmental variables or ecosystem indicators derived from long‐term monitoring datasets offer an improvement in our ability to skilfully forecast fish recruitment. A secondary question is which types of modelling approaches (ranging from linear models to non‐parametric methods) yield the best forecast skill. Third, we examine whether simultaneous forecasting of multiple species offers an advantage over generating species‐specific forecasts. We find that for approximately one third of the 29 assessed stocks, ecosystem indicators from juvenile surveys yields the highest out of sample predictive skill compared to other covariates (including environmental variables from Regional Ocean Modeling System output) or null models. Across modelling approaches, our results suggest that simpler linear modelling approaches do as well or better than more complicated approaches (reducing out of sample Root Mean Square Error by ~40% compared to null models), and that there appears to be little benefit to performing multispecies forecasts instead of single‐species forecasts. Our results provide a general framework for generating recruitment forecasts in other species and ecosystems, as well as a benchmark for future analyses to evaluate skill. The most promising applications are likely for species that are short lived, have relatively high recruitment variability, and moderate amounts of age or length data. Forecasts using our approach may be useful in identifying covariates or mechanisms to include in operational assessments but also provide qualitative advice to managers implementing ecosystem based fisheries management.

Complementary value of molecular, phenotypic, and functional aging biomarkers in dementia prediction - Andreas Engvig; Karl Trygve Kalleberg; Lars T. Westlye; Esten Høyland Leonardsen; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowski; Arthur W. Toga; Laurel Beckett; et al. (GeroScience, 2024)
DNA methylation age (MA), brain age (BA), and frailty index (FI) are putative aging biomarkers linked to dementia risk. We investigated their relationship and combined potential for prediction of cognitive impairment and future dementia risk using the ADNI database. Of several MA algorithms, DunedinPACE and GrimAge2, associated with memory, were combined in a composite MA alongside BA and a data-driven FI in predictive analyses. Pairwise correlations between age- and sex-adjusted measures for MA (aMA), aBA, and aFI were low. FI outperformed BA and MA in all diagnostic tasks. A model including age, sex, and aFI achieved an area under the curve (AUC) of 0.94 for differentiating cognitively normal controls (CN) from dementia patients in a held-out test set. When combined with clinical biomarkers (apolipoprotein E ε4 allele count, memory, executive function), a model including aBA and aFI predicted 5-year dementia risk among MCI patients with an out-of-sample AUC of 0.88. In the prognostic model, BA and FI offered complementary value (both β s 0.50). The tested MAs did not improve predictions. Results were consistent across FI algorithms, with data-driven health deficit selection yielding the best performance. FI had a stronger adverse effect on prognosis in males, while BA’s impact was greater in females. Our findings highlight the complementary value of BA and FI in dementia prediction. The results support a multidimensional view of dementia, including an intertwined relationship between the biomarkers, sex, and prognosis. The tested MA’s limited contribution suggests caution in their use for individual risk assessment of dementia.

Correction: Understanding the role of microbes in health and disease of farmed aquatic organisms - Cristiane C. Thompson; Wilson Wasielesky; Felipe Landuci; Michele S. Lima; Leonardo Bacha; Luciane M. Perazzolo; Cátia Lourenço-Marques; Florbela Soares; Pedro Pousão-Ferreira; Larry Hanson; Bruno Gomez-Gil; Mateus Thompson; et al. (Marine Life Science & Technology, 2024)

Hydrocarbon composition of oils spilt on the Brazilian coast in 2019 and 2022 - Antônia M. Corrêa; Felipe F. Campos; Marcus F. Tenório; Alice M.S. Rodrigues; Carlos D. Pérez; Fabiano Thompson; Andressa S. Batista; Pedro V. Gatts; Carlos E. de Rezende; Kátia Z. Leal; Marcelo C. Bernardes (Marine Pollution Bulletin, 2024)

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

Lateglacial Interstadial to mid-Holocene stratigraphy and palynology at Pepper Arden Bottoms, North Yorkshire, UK - James B. Innes; Mairead M. Rutherford; David R. Bridgland; Ben R. Gearey; Malcolm C. Lillie; Wishart A. Mitchell; Charlotte E. O'Brien; Richard T. Jones; Gareth J. Thompson (Proceedings of the Geologists' Association, 2024)

A framework and process for community-engaged, mixed-methods cancer needs assessments - Todd Burus; Jessica R. Thompson; Caree R. McAfee; Lovoria B. Williams; Jennifer Redmond Knight; Bin Huang; Sarojini Kanotra; Natalie P. Wilhite; Elaine Russell; Melinda Rogers; Connie L. Sorrell; Christine Stroebel; et al. (Cancer Causes & Control, 2024)
Purpose Community health needs assessments are required for most state and local public health agencies and non-profit hospitals. Typically based on community health improvement planning models, these assessments encompass overall community health and multiple diseases to inform program planning. National Cancer Institute (NCI)-designated Cancer Centers and community-based cancer-focused programs share the goal of reducing cancer burden in the catchment areas they serve. However, to date, no published models exist to guide cancer-specific needs assessments for a determined geographic area that can inform both public health and research initiatives. The purpose of this article is to outline a cancer needs assessment (CNA) framework and community-engaged, mixed-methods process, along with a case study of how we applied it in Kentucky. Methods We convened a steering committee of key organizational partners to provide input throughout the process. We developed a conceptual framework of multi-level determinants affecting cancer-related outcomes. We incorporated both quantitative and qualitative data gathered through a variety of means, including a novel application of group concept mapping to guide definition of priorities. Results The resulting CNA has helped guide strategic planning and priorities for Kentucky’s Cancer Action Plan, Markey Cancer Center, state agencies, and community-based organizations. Conclusion This framework and process can be used collaboratively by cancer center Community Outreach and Engagement offices, public health agencies, oncology programs, and community partners to plan impactful cancer control programs and research in their catchment areas. Universities can also use them to inform the planning of community engagement and health equity research efforts.

CYP2E1 in 1,4-dioxane metabolism and liver toxicity: insights from CYP2E1 knockout mice study - Yewei Wang; Georgia Charkoftaki; David J. Orlicky; Emily Davidson; Reza Aalizadeh; Ning Sun; Gary Ginsberg; David C. Thompson; Vasilis Vasiliou; Ying Chen (Archives of Toxicology, 2024)

Local molecular and connectomic contributions of tau-related neurodegeneration - Fardin Nabizadeh; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowski; Arthur W. Toga; Laurel Beckett; Robert C. Green; Andrew J. Saykin; John Morris; et al. (GeroScience, 2024)

Understanding the role of microbes in health and disease of farmed aquatic organisms - Cristiane C. Thompson; Wilson Wasielesky; Felipe Landuci; Michele S. Lima; Leonardo Bacha; Luciane M. Perazzolo; Cátia Lourenço-Marques; Florbela Soares; Pedro Pousão-Ferreira; Larry Hanson; Bruno Gomez-Gil; Mateus Thompson; et al. (Marine Life Science & Technology, 2024)

From riverbank to the sea: An initial assessment of plastic pollution along the Ciliwung River, Indonesia - Muhammad Reza Cordova; Max R. Kelly; Muhammad Hafizt; Singgih Prasetyo Adi Wibowo; Yaya Ihya Ulumuddin; Triyoni Purbonegoro; Deny Yogaswara; Muhammad Taufik Kaisupy; Riyana Subandi; Sofia Yuniar Sani; Richard C. Thompson; Susan Jobling (Marine Pollution Bulletin, 2024)

Age-related effects of neuromuscular fatigue and acute recovery responses on maximal and rapid torque measures of the leg extensors and flexors - Brennan J. Thompson; Eric C. Conchola; Kimberly A. Clevenger (European Journal of Applied Physiology, 2024)

An assessment of latrine front-end characteristics and associated surface E. coli indicated faecal contamination in rural Fiji - Sabita Adhikari; Shylett Anthony; Ponipate Baleinamau; Jeremaia Coriakula; Thompson Daurewa; Rachel Devi; Sikeli Gavidi; Pierre Horwitz; Erin C. Hunter; Aaron Jenkins; Stacy Jupiter; Maria Lalamacuata; et al. (Environmental Science and Pollution Research, 2024)
In Fiji, 90% of the population has access to basic sanitation; however, there are still persistent health risks from endemic faecal-oral diseases such as typhoid fever. There is a need to assess the contribution of existing sanitation facilities in the faecal pathogen transmission pathway. This study was conducted as part of a larger planetary health study across 29 rural communities within five river catchments. This specific research aimed to characterise latrine front-ends, both infrastructure and usage behaviour, and to assess the faecal contamination levels on various frequently contacted latrine surfaces in rural Fiji. A sanitation survey, along with observation and latrine swab sampling, was conducted in households over three phases: baseline ( n = 311) (Aug–Dec 2019), endline ( n = 262) (Jun–Sep 2022) and an in-depth front-end study ( n = 12) (Oct–Nov 2022). Of 311 households, almost all had pedestal-type latrines, predominately cistern-flush (83%), followed by pour-flush (13%), and then hole-type (pit) latrines (4%). Washable latrine floors had significantly higher E. coli densities (6.7 × 10 2 CFU/25 cm 2 ) compared to non-washable floors (1.3 × 10 2 CFU/25 cm 2 ) ( p = 0.05), despite washable floors indicating improved latrines. The in-depth front-end analysis found that moist latrine surfaces had significantly elevated E. coli densities (1.2 × 10 3 CFU/25 cm 2 ) compared to the dry ones (14.3 CFU/25 cm 2 ) ( p < 0.001), highlighting the importance of maintaining dry latrine surfaces. Latrine floors and mid-walls were the most frequently contaminated surfaces, emphasising the need to clean and disinfect these surfaces. Only 46% of the households reported always using soap for handwashing after defecation, exacerbating the risk of transmitting faecal pathogens. This study highlights that latrine cleanliness and hygiene are as crucial as latrine infrastructures for the effective disruption of faecal pathogens transmission during latrine use.

Letter to the editor of environmental pollution: In regard to Wan et al. (2024) “GenX caused liver injury and potential hepatocellular carcinoma of mice via drinking water even at environmental concentration” - Chad M. Thompson; Melissa M. Heintz; John M. Cullen; Laurie C. Haws (Environmental Pollution, 2024)

Exposure to Total Suspended Solids (TSS) Impacts Gill Structure and Function in Adult Zebrafish - Xena C. Montoya; W. Andrew Thompson; Courtney M. Smith; Jonathan M. Wilson; Mathilakath M. Vijayan (Bulletin of Environmental Contamination and Toxicology, 2024)

Complementary feeding practices of caregivers of infants with Down syndrome as compared to caregivers of typically developing infants - Kelsey L. Thompson; Emily C. Clarke; Heather Wasser; Michaela A. Schenkelberg; Seema Agrawal; Erik A. Willis (Appetite, 2024)

A global initiative for ecological and evolutionary hologenomics - Aoife Leonard; Javier Abalos; Titus Adhola; Windsor Aguirre; Ostaizka Aizpurua; Shahzad Ali; Franco Andreone; Fabien Aubret; Hefer D. Ávila-Palma; Lizbeth Fabiola Bautista Alcantara; Juan F. Beltrán; Rachel Berg; et al. (Trends in Ecology & Evolution, 2024)

Scaling of soil organic carbon in space and time in the Southern Coastal Plain, USA - Rajneesh Sharma; Matthew R. Levi; Matthew C. Ricker; Aaron Thompson; Elizabeth G. King; Kevin Robertson (Science of The Total Environment, 2024)

Downscaling the ocean response to the Madden–Julian Oscillation in the Northwest Atlantic and adjacent shelf seas - Christoph Renkl; Eric C. J. Oliver; Keith R. Thompson (Climate Dynamics, 2024)
Subseasonal-to-seasonal (S2S) prediction is a global effort to forecast the state of the atmosphere and ocean with lead times between two weeks and a season. This study explores the feasibility of S2S prediction of the ocean using a variety of tools including statistical analysis, a statistical-dynamical mixed layer model, and a regional, high-resolution ocean circulation model based on physical principles. Ocean predictability on S2S timescales is analyzed by compositing winter sea surface temperature (SST) anomalies in the North Atlantic with respect to the state of the Madden–Julian Oscillation (MJO). It is found that statistically significant, large-scale SST changes, particularly along the eastern seaboard of North America, can be related to the MJO. This signal is shown to be driven by anomalous air–sea heat fluxes caused by atmospheric perturbations in response to the MJO. The high-resolution model of the Gulf of Maine and Scotian Shelf is used to downscale the mean ocean response to the MJO. The model is able to capture the observed relationship between the MJO and SST in the northwest Atlantic. It is also shown that the anomalous atmospheric circulation in response to the MJO leads to anomalous upwelling on the Scotian Shelf. Overall, this study demonstrates that it is feasible, and of value, to use regional ocean models for S2S prediction.

The dispersant Corexit 9500 and (dispersed) oil are lethal to coral endosymbionts - Tooba Varasteh; Michele S. Lima; Tatiana A. Silva; Maria Luíza R. da Cruz; Reza Amir Ahmadi; Georgia C. Atella; Marcia Attias; Jean Swings; Wanderley de Souza; Fabiano L. Thompson; Cristiane C. Thompson (Marine Pollution Bulletin, 2024)

Oil and gas platforms degrade benthic invertebrate diversity and food web structure - Zelin Chen; Tom C. Cameron; Elena Couce; Clement Garcia; Natalie Hicks; Gareth E. Thomas; Murray S.A. Thompson; Corinne Whitby; Eoin J. O'Gorman (Science of The Total Environment, 2024)

Genomic and physiological characterization of Kitasatospora sp. nov., an actinobacterium with potential for biotechnological application isolated from Cerrado soil - I. C. Cunha-Ferreira; C. S. Vizzotto; M. A. M. Freitas; J. Peixoto; L. S. Carvalho; M. R. Tótola; F. L. Thompson; R. H. Krüger (Brazilian Journal of Microbiology, 2024)

Ocean surface radiation measurement best practices - Laura D. Riihimaki; Meghan F. Cronin; Raja Acharya; Nathan Anderson; John A. Augustine; Kelly A. Balmes; Patrick Berk; Roberto Bozzano; Anthony Bucholtz; Kenneth J. Connell; Christopher J. Cox; Alcide G. di Sarra; et al. (Frontiers in Marine Science, 2024)
Ocean surface radiation measurement best practices have been developed as a first step to support the interoperability of radiation measurements across multiple ocean platforms and between land and ocean networks. This document describes the consensus by a working group of radiation measurement experts from land, ocean, and aircraft communities. The scope was limited to broadband shortwave (solar) and longwave (terrestrial infrared) surface irradiance measurements for quantification of the surface radiation budget. Best practices for spectral measurements for biological purposes like photosynthetically active radiation and ocean color are only mentioned briefly to motivate future interactions between the physical surface flux and biological radiation measurement communities. Topics discussed in these best practices include instrument selection, handling of sensors and installation, data quality monitoring, data processing, and calibration. It is recognized that platform and resource limitations may prohibit incorporating all best practices into all measurements and that spatial coverage is also an important motivator for expanding current networks. Thus, one of the key recommendations is to perform interoperability experiments that can help quantify the uncertainty of different practices and lay the groundwork for a multi-tiered global network with a mix of high-accuracy reference stations and lower-cost platforms and practices that can fill in spatial gaps.

Plastic alternatives and substitutes in the packaging sector – A UK consumer perspective - Sohvi Nuojua; Sabine Pahl; Richard C. Thompson (Sustainable Production and Consumption, 2024)

Imaging spectroscopy investigations in wet carbon ecosystems: A review of the literature from 1995 to 2022 and future directions - Thomas C. Ingalls; Jiwei Li; Yvonne Sawall; Roberta E. Martin; David R. Thompson; Gregory P. Asner (Remote Sensing of Environment, 2024)

Effect of the age of garments used under real-life conditions on microfibre release from polyester and cotton clothing - Andreia N. Fernandes; Larissa Z. Lara; Francesca De Falco; Andrew Turner; Richard C. Thompson (Environmental Pollution, 2024)

Tracking data highlight the importance of human-induced mortality for large migratory birds at a flyway scale - Juan Serratosa; Steffen Oppel; Shay Rotics; Andrea Santangeli; Stuart H.M. Butchart; Luis S. Cano-Alonso; Jose Luis Tellería; Ryno Kemp; Aaron Nicholas; Aigars Kalvāns; Aitor Galarza; Aldina M.A. Franco; et al. (Biological Conservation, 2024)

Correction: Identifying opportunities for collective action around community nutrition programming through participatory systems science - Perla Chebli; Lan N. Đoàn; Rachel L. Thompson; Matthew Chin; Nasim Sabounchi; Victoria Foster; Terry T. K. Huang; Chau Trinh‑Shevrin; Simona C. Kwon; Stella S. Yi (Cancer Causes & Control, 2024)

Deep learning of estuary salinity dynamics is physically accurate at a fraction of hydrodynamic model computational cost - Galen Gorski; Salme Cook; Amelia Snyder; Alison P. Appling; Theodore Thompson; Jared D. Smith; John C. Warner; Simon N. Topp (Limnology and Oceanography, 2024)
Salinity dynamics in the Delaware Bay estuary are a critical water quality concern as elevated salinity can damage infrastructure and threaten drinking water supplies. Current state‐of‐the‐art modeling approaches use hydrodynamic models, which can produce accurate results but are limited by significant computational costs. We developed a machine learning (ML) model to predict the 250 mg L −1 Cl − isochlor, also known as the “salt front,” using daily river discharge, meteorological drivers, and tidal water level data. We use the ML model to predict the location of the salt front, measured in river miles (RM) along the Delaware River, during the period 2001–2020, and we compare predictions of the ML model to the hydrodynamic Coupled Ocean–Atmosphere‐Wave‐Sediment Transport (COAWST) model. The ML model predicts the location of the salt front with greater accuracy (root mean squared error [RMSE] = 2.52 RM) than the COAWST model does (RMSE = 5.36); however, the ML model struggles to predict extreme events. Furthermore, we use functional performance and expected gradients, tools from information theory and explainable artificial intelligence, to show that the ML model learns physically realistic relationships between the salt front location and drivers (particularly discharge and tidal water level). These results demonstrate how an ML modeling approach can provide predictive and functional accuracy at a significantly reduced computational cost compared to process‐based models. In addition, these results provide support for using ML models in operational forecasting, scenario testing, management decisions, hindcasting, and resulting opportunities to understand past behavior and develop hypotheses.

Increases in regional brain volume across two native South American male populations - Nikhil N. Chaudhari; Phoebe E. Imms; Nahian F. Chowdhury; Margaret Gatz; Benjamin C. Trumble; Wendy J. Mack; E. Meng Law; M. Linda Sutherland; James D. Sutherland; Christopher J. Rowan; L. Samuel Wann; Adel H. Allam; et al. (GeroScience, 2024)
Industrialized environments, despite benefits such as higher levels of formal education and lower rates of infections, can also have pernicious impacts upon brain atrophy. Partly for this reason, comparing age-related brain volume trajectories between industrialized and non-industrialized populations can help to suggest lifestyle correlates of brain health. The Tsimane, indigenous to the Bolivian Amazon, derive their subsistence from foraging and horticulture and are physically active. The Moseten, a mixed-ethnicity farming population, are physically active but less than the Tsimane. Within both populations ( N = 1024; age range = 46–83), we calculated regional brain volumes from computed tomography and compared their cross-sectional trends with age to those of UK Biobank (UKBB) participants ( N = 19,973; same age range). Surprisingly among Tsimane and Moseten (T/M) males, some parietal and occipital structures mediating visuospatial abilities exhibit small but significant increases in regional volume with age. UKBB males exhibit a steeper negative trend of regional volume with age in frontal and temporal structures compared to T/M males. However, T/M females exhibit significantly steeper rates of brain volume decrease with age compared to UKBB females, particularly for some cerebro-cortical structures (e.g., left subparietal cortex). Across the three populations, observed trends exhibit no interhemispheric asymmetry. In conclusion, the age-related rate of regional brain volume change may differ by lifestyle and sex. The lack of brain volume reduction with age is not known to exist in other human population, highlighting the putative role of lifestyle in constraining regional brain atrophy and promoting elements of non-industrialized lifestyle like higher physical activity.

Sex differences in interacting genetic and functional connectivity biomarkers in Alzheimer’s disease - Jordan N. Williamson; Shirley A. James; Sean P. Mullen; Bradley P. Sutton; Tracey Wszalek; Beni Mulyana; Peter Mukli; Andriy Yabluchanskiy; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2024)

Creek systems in restored coastal wetlands: Morphological evolution and design implications - C. Chirol; N. Pontee; S.L. Gallop; C.E.L. Thompson; H. Kassem; I.D. Haigh (Science of The Total Environment, 2024)

Nitrate exposure from drinking water and dietary sources among Iowa farmers using private wells - Timothy G. Skalaban; Darrin A. Thompson; Jessica M. Madrigal; Benjamin C. Blount; Maria Morel Espinosa; Dana W. Kolpin; Nicole C. Deziel; Rena R. Jones; Laura Beane Freeman; Jonathan N. Hofmann; Mary H. Ward (Science of The Total Environment, 2024)

Understanding vessel noise across a network of marine protected areas - Megan F McKenna; Timothy J Rowell; Tetyana Margolina; Simone Baumann-Pickering; Alba Solsona-Berga; Jeffrey D Adams; John Joseph; Ella B Kim; Annebelle CM Kok; Anke Kügler; Marc O Lammers; Karlina Merkens; et al. (Environmental Monitoring and Assessment, 2024)
Protected areas are typically managed as a network of sites exposed to varying anthropogenic conditions. Managing these networks benefits from monitoring of conditions across sites to help prioritize coordinated efforts. Monitoring marine vessel activity and related underwater radiated noise impacts across a network of protected areas, like the U.S. National Marine Sanctuary system, helps managers ensure the quality of habitats used by a wide range of marine species. Here, we use underwater acoustic detections of vessels to quantify different characteristics of vessel noise at 25 locations within eight marine sanctuaries including the Hawaiian Archipelago and the U.S. east and west coasts. Vessel noise metrics, including temporal presence and sound levels, were paired with Automatic Identification System (AIS) vessel tracking data to derive a suite of robust vessel noise indicators for use across the network of marine protected areas. Network-wide comparisons revealed a spectrum of vessel noise conditions that closely matched AIS vessel traffic composition. Shifts in vessel noise were correlated with the decrease in vessel activity early in the COVID-19 pandemic, and vessel speed reduction management initiatives. Improving our understanding of vessel noise conditions in these protected areas can help direct opportunities for reducing vessel noise, such as establishing and maintaining noise-free periods, enhancing port efficiency, engaging with regional and international vessel quieting initiatives, and leveraging co-benefits of management actions for reducing ocean noise.

Features of the highway road network that generate or retain tyre wear particles - Florence N. F. Parker-Jurd; Geoffrey D. Abbott; Bill Guthery; Gustav M. C. Parker-Jurd; Richard C. Thompson (Environmental Science and Pollution Research, 2024)

Utilising male stimulus to improve the reproductive efficiency of 8-month-old nulliparous ewes and adult parous ewes - César A. Rosales-Nieto; Andrew N. Thompson; Venancio Cuevas-Reyes; Luisa E.S. Hérnandez-Arteaga; Johan C. Greeff; Richard Ehrhardt; Almudena Veiga-Lopez; Graeme B. Martin (Theriogenology, 2024)

Correction: Effects of Intra-REV Pore Distribution Modeling in the Flow of Non-Newtonian Fluids in Porous Media - Allan B. G. Motta; Roney L. Thompson; Mateus P. Schwalbert; Luiz F. L. R. Silva; Jovani L. Favero; Rodrigo A. C. Dias; Raphael J. Leitão (Transport in Porous Media, 2024)

Transient dynamics mask the resilience of coral reefs - Karlo Hock; Alan Hastings; Christopher Doropoulos; Russell C. Babcock; Juan C. Ortiz; Angus Thompson; Peter J. Mumby (Theoretical Ecology, 2024)
Coral reefs are model systems for studies of ecological resilience, with communities generally exhibiting multiple stable states and more resilient regions trending towards a single, coral-dominated, regime. We expand the theory of ecological resilience beyond the concepts of distinct stable states to integrate emerging ideas from transient dynamics as long-term intermediate states with no pronounced trend towards equilibria. We show that low coral abundance, together with stochastic larval supply and disturbance, can trap otherwise resilient reefs in a persistent intermediate state whose long-term outcome is difficult to predict. Common metrics, such as the ecosystem slowing down before crossing tipping points and using historical coral cover trends, may become unreliable predictors of future behaviour. Helping reefs out of transient states requires agile management that allows for short-term, targeted interventions after which natural ecological feedbacks can take over.

Measures of Subjective Memory for People with Epilepsy: A Systematic Review of Measurement Properties - Kate Thompson; Ada H. Y. Lo; Hannah L. McGlashan; Tamara Ownsworth; Catherine Haslam; Alan Pegna; David C. Reutens (Neuropsychology Review, 2024)

Scaling of fast‐start performance and its thermal dependence in mummichog Fundulus heteroclitus - David C. Collar; Trevor J. Hobbs; Jessica S. Thompson (Journal of Fish Biology, 2024)
Fast‐start predator‐escape performance and its sensitivity to temperature (24, 30, and 36°C) were evaluated in mummichog Fundulus heteroclitus across a range of body sizes spanning YOY to adult (35–68 mm standard length). Mummichogs exhibit isometry of body dimensions and areas of the dorsal and anal fins but negative allometry of the caudal fin area. These scaling relationships are consistent with observed decreases in fast‐start angular velocities with increasing body size. Linear velocity, on the contrary, does not vary with size, and both large and small mummichogs are capable of traversing similar distances in a given amount of time. In addition, temperature influences fast‐start performance in similar ways over the size range, though the magnitude of the effect varies with size for some performance measures. In general, fast‐start performance increases with test temperature, but mummichogs acclimated to warmer temperatures exhibit lower performance at each test temperature. Altogether, our results suggest that mummichogs across the adult size range may suffer decreases in their predator‐escape performance as increasing sea temperatures combine with short‐term temperature fluctuations in the estuaries these fish occupy.

State of the California Current Ecosystem report in 2022: a tale of two La Niñas - Andrew R. Thompson; Rasmus Swalethorp; Michaela Alksne; Jarrod A. Santora; Elliott L. Hazen; Andrew Leising; Erin Satterthwaite; William J. Sydeman; Clarissa R. Anderson; Toby D. Auth; Simone Baumann-Pickering; Timothy Baumgardner; et al. (Frontiers in Marine Science, 2024)
2022 marked the third consecutive La Niña and extended the longest consecutive stretch of negative Oceanic Niño Index since 1998-2001. While physical and biological conditions in winter and spring largely adhered to prior La Niña conditions, summer and fall were very different. Similar to past La Niña events, in winter and spring coastal upwelling was either average or above average, temperature average or below average, salinity generally above average. In summer and fall, however, upwelling and temperature were generally average or slightly below average, salinity was close to average and chlorophyll a was close to average. Again, as during prior La Niña events, biomass of northern/southern copepods was above/below average off Oregon in winter, and body size of North Pacific krill in northern California was above average in winter. By contrast, later in the year the abundance of northern krill dropped off Oregon while southern copepods increased and body sizes of North Pacific krill fell in northern California. Off Oregon and Washington abundances of market squid and Pacific pompano (indicators of warm, non-typical La Niña conditions) were high. In the 20 th century, Northern anchovy recruitment tended to be high during cold conditions, but despite mostly warm conditions from 2015-2021 anchovy populations boomed and remained high in 2022. Resident seabird reproductive success, which tended in the past to increase during productive La Niña conditions was highly variable throughout the system as common murre and pelagic cormorant, experienced complete reproductive failure at Yaquina Head, Oregon while Brandt’s cormorant reproduction was average. At three sampling locations off central California, however, common murre reproduction was close to or above average while both pelagic and Brandt’s cormorant were above average. California sealion reproduction has been above average each year since 2016, and pup weight was also above average in 2022, likely in response not to La Niña or El Niño but continuous high abundance of anchovy. The highly variable and often unpredictable physical and biological conditions in 2022 highlight a growing recognition of disconnects between basin-scale indices and local conditions in the CCE. “July-December 2022 is the biggest outlier from individual “strong” La Niña (events) ever going back to the 50s.” – Nate Mantua

Excess feeding increases adipogenesis but lowers leptin transcript abundance in zebrafish larvae - William Andrew Thompson; Jithine Jayakumar Rajeswari; Alison C. Holloway; Mathilakath M. Vijayan (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2024)

Dark waters: Evaluating seagrass community response to optical water quality and freshwater discharges in a highly managed subtropical estuary - Paul Julian II; Mark Thompson; Eric C. Milbrandt (Regional Studies in Marine Science, 2024)

Temperature Thresholds for Leaf Damage from Two Extreme Freeze Events (2018 and 2021) Near the Northern Range Limit of Black Mangroves (Avicennia germinans) in Southeastern North America - Simen Kaalstad; Michael J. Osland; Donna J. Devlin; C. Edward Proffitt; Laura C. Feher; Anna R. Armitage; Richard H. Day; Kathleen M. Swanson; Gordon H. Anderson; Brigid Berger; Just Cebrian; Karen L. Cummins; et al. (Estuaries and Coasts, 2024)

Integrating Remote Sensing with Ground-based Observations to Quantify the Effects of an Extreme Freeze Event on Black Mangroves (Avicennia germinans) at the Landscape Scale - Melinda Martinez; Michael J. Osland; James B. Grace; Nicholas M. Enwright; Camille L. Stagg; Simen Kaalstad; Gordon H. Anderson; Anna R. Armitage; Just Cebrian; Karen L. Cummins; Richard H. Day; Donna J. Devlin; et al. (Ecosystems, 2024)

A critical re‐analysis of constraints on the timing and rate of Laurentide Ice Sheet recession in the northeastern United States - Christopher T. Halsted; Paul R. Bierman; Jeremy D. Shakun; P. Thompson Davis; Lee B. Corbett; Jason S. Drebber; John C. Ridge (Journal of Quaternary Science, 2024)
We review geochronological data relating to the timing and rate of Laurentide Ice Sheet recession in the northeastern United States and model ice margin movements in a Bayesian framework using compilations of previously published organic 14 C ( n = 133) and in situ cosmogenic 10 Be ( n = 95) ages. We compare the resulting method‐specific chronologies with glacial varve records that serve as independent constraints on the pace of ice recession to: (1) construct a synthesis of deglacial chronology throughout the region; and (2) assess the accuracy of each chronometer for constraining the timing of deglaciation. Near the Last Glacial Maximum terminal moraine zone, 10 Be and organic 14 C ages disagree by thousands of years and limit determination of the initial recession to a date range of 24–20 ka. We infer that 10 Be inherited from pre‐glacial exposure adds 2–6 kyr to many exposure ages near the terminal moraines, whereas macrofossil 14 C ages are typically 4–8 kyr too young due to a substantial lag between ice recession and sufficient organic material accumulation for dating in some basins. Age discrepancies between these chronometers decrease with distance from the terminal moraine, due to less 10 Be inherited from prior exposure and a reduced lag between ice recession and organic material deposition. 14 C and 10 Be ages generally agree at locations more than 200 km distal from the terminal moraines and suggest a mostly continuous history of ice recession throughout the region from 18 to 13 ka with a variable pace best documented by varves.

Catalyzing progress in the blue economy through joint marine microbiome research across the Atlantic - Alice C. Ortmann; Kelly D. Goodwin; Henk Bolhuis; René Groben; Thulani Makhalanyane; Jeff Bowman; Shawn Robinson; Fabiano Thompson (Frontiers in Marine Science, 2023)
International agreements recognize the importance of cooperative scientific research to conserve and promote sustainable development of a shared Atlantic Ocean. In 2022, the All-Atlantic Ocean Research and Innovation Alliance Declaration was signed. The All-Atlantic Declaration continues and extends relationships forged by the Galway Statement on Atlantic Ocean Cooperation and the Belém Statement on Atlantic Ocean Research and Innovation Cooperation. These efforts are consistent with programs, actions, and aims of the United Nations Decade of Ocean Science for Sustainable Development. In preparation for implementation of the All-Atlantic Declaration, members of the Marine Microbiome Working Group and the Marine Biotechnology Initiative for the Atlantic under the Galway and Belém Statements respectively, joined forces to call for cooperation across the Atlantic to increase marine microbiome and biotechnology research to promote ocean health and a sustainable bioeconomy. This article reviews the goals of the marine microbiome and biotechnology initiatives under the Galway and Belém Statements and outlines an approach to implement those goals under the All-Atlantic Declaration through a Blue Biotech and Marine Microbiome (BBAMM) collaboration.

RETRACTED: Collapse of scallop Nodipecten nodosus production in the tropical Southeast Brazil as a possible consequence of global warming and water pollution - Cristiane Thompson; Leonardo Bacha; Pedro Henrique C. Paz; Marcelo de Assis Passos Oliveira; Braulio Cherene Vaz Oliveira; Claudia Omachi; Caroline Chueke; Marcela de Lima Hilário; Michele Lima; Luciana Leomil; Thais Felix-Cordeiro; Thalya Lou Cordeiro da Cruz; et al. (Science of The Total Environment, 2023)

Simultaneous stream assessment of antibiotics, bacteria, antibiotic resistant bacteria, and antibiotic resistance genes in an agricultural region of the United States - Carrie E. Givens; Dana W. Kolpin; Laura E. Hubbard; Shannon M. Meppelink; David M. Cwiertny; Darrin A. Thompson; Rachael F. Lane; Michaelah C. Wilson (Science of The Total Environment, 2023)

Identifying opportunities for collective action around community nutrition programming through participatory systems science - Perla Chebli; Lan N. Đoàn; Rachel L. Thompson; Matthew Chin; Nasim Sabounchi; Victoria Foster; Terry T. K. Huang; Chau Trinh-Shevrin; Simona C. Kwon; Stella S. Yi (Cancer Causes & Control, 2023)

Review of Solar Energetic Particle Prediction Models - Kathryn Whitman; Ricky Egeland; Ian G. Richardson; Clayton Allison; Philip Quinn; Janet Barzilla; Irina Kitiashvili; Viacheslav Sadykov; Hazel M. Bain; Mark Dierckxsens; M. Leila Mays; Tilaye Tadesse; et al. (Advances in Space Research, 2023)

Distinct patterns of inheritance shape life‐history traits in steelhead trout - Anne K. Beulke; Alicia Abadía‐Cardoso; Devon E. Pearse; Laura C. Goetz; Neil F. Thompson; Eric C. Anderson; John Carlos Garza (Molecular Ecology, 2023)
Life‐history variation is the raw material of adaptation, and understanding its genetic and environmental underpinnings is key to designing effective conservation strategies. We used large‐scale genetic pedigree reconstruction of anadromous steelhead trout ( Oncorhynchus mykiss ) from the Russian River, CA, USA, to elucidate sex‐specific patterns of life‐history traits and their heritability. SNP data from adults returning from sea over a 14‐year period were used to identify 13,474 parent–offspring trios. These pedigrees were used to determine age structure, size distributions and family sizes for these fish, as well as to estimate the heritability of two key life‐history traits, spawn date and age at maturity (first reproduction). Spawn date was highly heritable ( h 2 = 0.73) and had a cross‐sex genetic correlation near unity. We provide the first estimate of heritability for age at maturity in ocean‐going fish from this species and found it to be highly heritable ( h 2 from 0.29 to 0.62, depending on sex and method), with a much lower genetic correlation across sexes. We also evaluated genotypes at a migration‐associated inversion polymorphism and found sex‐specific correlations with age at maturity. The significant heritability of these two key reproductive traits in these imperiled fish, and their patterns of inheritance in the two sexes, is consistent with predictions of both natural and sexually antagonistic selection (sexes experience opposing selection pressures). This emphasizes the importance of anthropogenic factors, including hatchery practices and ecosystem modifications, in shaping the fitness of this species, thus providing important guidance for management and conservation efforts.

Translocation of 14C-polystyrene nanoplastics into fish during a very-low concentration dietary exposure - Nathaniel J. Clark; Astrid C. Fischer; Lee Durndell; Tamara S. Galloway; Richard C. Thompson (Chemosphere, 2023)

They really do move in herds: evidence of group living in an aquatic turtle - Donald T. McKnight; Jaren C. Serano; Denise M. Thompson; Day B. Ligon (Animal Behaviour, 2023)

The distribution and characterisation of microplastics in air, surface water and sediment within a major river system - Imogen E. Napper; Anju Baroth; Aaron C. Barrett; Sunanda Bhola; Gawsia W. Chowdhury; Bede F.R. Davies; Emily M. Duncan; Sumit Kumar; Sarah E. Nelms; Md. Nazmul Hasan Niloy; Bushra Nishat; Taylor Maddalene; et al. (Science of The Total Environment, 2023)

Role of Shape and Kinematics in the Hydrodynamics of a Fish-like Oscillating Hydrofoil - Siddharth Gupta; Atul Sharma; Amit Agrawal; Mark C. Thompson; Kerry Hourigan (Journal of Marine Science and Engineering, 2023)
In the present two-dimensional numerical study, we investigate the roles of geometrical parameters of a hydrofoil (shape/curvature of the leading and trailing edges and thickness) and kinematic parameters (phase difference between heave and pitch (ϕ)) on the propulsive performance of different-shaped hydrofoils oscillating at maximum angles of attack up to αmax=30∘. The study was carried out at a fixed non-dimensional maximum heave to chord ratio h∘/C=0.75, Strouhal number St=0.25, and Reynolds number Re=5000. Our findings reveal that hydrofoil performance and stability improve with leading and trailing edge curvatures but decline as thickness increases. By analyzing the near-wake structure, we establish that even minimal flow separation increases power consumption while moderate flow separation enhances thrust. Over the range of different-shaped hydrofoils at different αmax and ϕ, maximum propulsion efficiency occurs for those parameters for which there is a small degree of flow separation but with no roll-up of a separating vortex. In comparison, maximum thrust generation occurs when there is a moderately strong flow separation but without induction of a significant amount of fluid around the trailing edge. These insights offer valuable knowledge for understanding fish propulsion efficiency and have applications in designing autonomous underwater vehicles (AUVs) and micro-air vehicles (MAVs).

Devaluation Effects in Food-Specific Response Inhibition Training: A Conceptual Replication - L. Tzavella; C.R. Pennington; K.S. Button; F. Abdullahi; E. Aboaba; Z. Abutayeh; N. Bushell; A. Caddle; S. Chi Chan; A. Denman; C. Gabe-Jones; M. Mushongah; et al. (Appetite, 2023)

Metrics matter: Multiple diversity metrics at different spatial scales are needed to understand species diversity in urban environments - Kathryn A. O'Shaughnessy; Antony M. Knights; Stephen J. Hawkins; Mick E. Hanley; Paul Lunt; Richard C. Thompson; Louise B. Firth (Science of The Total Environment, 2023)

Parent-reported Fruit and Vegetable Home Availability and Accessibility in an Online Obesity Prevention Program for Pre-adolescent Black Girls - C. Callender; S. Musaad; D. Thompson (Journal of the Academy of Nutrition and Dietetics, 2023)

Metagenomic and isotopic signatures of the Amazon River plume into the southern red snapper fish (Lutjanus purpureus) - Luciane de C. Nogueira; Nils E. Asp; Carlos E. Rezende; Rodrigo Petry C. Sousa; Breno Barros; Raphael Paixão; Pedro V. Gatts; Cristiane C. Thompson; Ronaldo B. Francini-Filho; Marcelo Vallinoto; Fabiano L. Thompson (Estuarine, Coastal and Shelf Science, 2023)

An assessment of the ecosystem services of marine zooplankton and the key threats to their provision - Zara L.R. Botterell; Penelope K. Lindeque; Richard C. Thompson; Nicola J. Beaumont (Ecosystem Services, 2023)

Multi-omics profiling reveals cellular pathways and functions regulated by ALDH1B1 in colon cancer cells - Yewei Wang; Zeljka Popovic; Georgia Charkoftaki; Rolando Garcia-Milian; TuKiet T. Lam; David C. Thompson; Ying Chen; Vasilis Vasiliou (Chemico-Biological Interactions, 2023)

Towards hyperlocal source identification of pollutants in cities by combining mobile measurements with atmospheric modeling - John C. Lin; Ben Fasoli; Logan Mitchell; Ryan Bares; Francesca Hopkins; Tammy M. Thompson; Ramón A. Alvarez (Atmospheric Environment, 2023)

Mountain lion predation in a multi-prey system on private lands in Texas - Amanda M. Veals Dutt; Catherine C. Dennison; Patricia Moody Harveson; Bert W. Geary; Ron W. Thompson; Dana Milani; Louis A. Harveson (Mammal Research, 2023)

Kinetic Modeling and Parameter Estimation of a Prebiotic Peptide Reaction Network - Hayley Boigenzahn; Leonardo D. González; Jaron C. Thompson; Victor M. Zavala; John Yin (Journal of Molecular Evolution, 2023)

Variation in hysterectomy prevalence and trends among U.S. States and Territories—Behavioral Risk Factor Surveillance System, 2012–2020 - Sameer V. Gopalani; Sabitha R. Dasari; Emily E. Adam; Trevor D. Thompson; Mary C. White; Mona Saraiya (Cancer Causes & Control, 2023)

Corrigendum to “Evaluating the performance of the ‘Seabin’ – A fixed point mechanical litter removal device for sheltered waters” [Mar. Pollut. Bull. 184 (2022) 114199] - Florence N.F. Parker-Jurd; Natalie S. Smith; Liam Gibson; Sohvi Nuojua; Richard C. Thompson (Marine Pollution Bulletin, 2023)

P16-25: In vitro assessment of triazole and newly developed tetrazole antifungals for potential interferences with corticosteroid biosynthesis and peripheral metabolism - M.-C. Jäger; V. González-Ruiz; J. Boccard; F.L. Joos; D.V. Winter; G.R. Thompson III; S. Rudaz; A. Odermatt (Toxicology Letters, 2023)

S12-01: Physiologically-Based Kinetic (PBK) Models and Applications In Read-Across - J. Madden; C. Thompson; S. Webb; P. Penson; C. Tan; A. Paini (Toxicology Letters, 2023)

Prenatal and postnatal exposure to polychlorinated biphenyls alter follicle numbers, gene expression, and a proliferation marker in the rat ovary - Kathy M. De La Torre; Yuna Lee; Adira Safar; Mary J. Laws; Daryl D. Meling; Lindsay M. Thompson; Madeline Streifer; Karen E. Weis; Lori T. Raetzman; Andrea C. Gore; Jodi A. Flaws (Reproductive Toxicology, 2023)

Effectiveness of Qualitative and Quantitative Instruments in Assessment and Evaluation of Community Based Nutrition Education Programs - O. Udenyi; C. Castor; L. Thompson; T. Fungwe; A. Graham (Journal of the Academy of Nutrition and Dietetics, 2023)

Effect of pelleting on the enzymatic digestibility of corn stover - Xueli Chen; Antonio C. Freitas dos Santos; Diana M. Ramirez Gutierrez; Peiyuan Song; John E. Aston; David N. Thompson; James H. Dooley; Michael R. Ladisch; Nathan S. Mosier (Bioresource Technology, 2023)

Transitions in modes of coastal adaptation: addressing blight, engagement and sustainability - Sally Brown; Emma L. Tompkins; Natalie Suckall; Jon French; Ivan D. Haigh; Eli Lazarus; Robert J. Nicholls; Edmund C. Penning-Rowsell; Charlie E. L. Thompson; Ian Townend; Sien van der Plank (Frontiers in Marine Science, 2023)
Coastal defences have long provided protection from erosion and flooding to cities, towns and villages. In many parts of the world, continued defence is being questioned due to both environmental, sustainability and economic considerations. This is exemplified in England and Wales, where strategic Shoreline Management Plans envisage realignment of many protected coasts, often with low population densities, over the coming decades. The policy transition from protection to realignment is often resisted by affected communities and can have high political costs. Whilst some preparations for such transitions have been made, the communities affected are often not fully aware of the implications of policy change, and this brings the potential for blight. In this paper, we investigate the challenges of implementing transitions in coastal policy within England and Wales. The analysis is based on data obtained from three workshops held in 2019 that were attended by council members, engineers, planners, scientists and other relevant professionals. Five conditions are found to promote contention: (i) policy actors with competing priorities and different decision making time frames (immediate to decadal to a century); (ii) divergence between regulations and ad hoc political decisions (e.g. in relation to the demand for new housing); (iii) limited or non-existent funding to support policy transition; (iv) community expectation that protection is forever; and (v) a disconnection between people and ongoing coastal change. Our research indicates that transitions can be better supported through: (1) integrated multi-scalar preparedness for coastal change; (2) an accessible evidence base and future vision to nurture political confidence in adaptation; and (3) defined, time-bound and accessible diverse funding streams to achieve transitions. Critically, these generic actions need to be embedded within the local political and planning system to facilitate transition to more sustainable coasts and their communities.

Compositional shifts of alpine plant communities across the high Andes - F. Cuesta; J. Carilla; L. D. LLambí; P. Muriel; M. V. Lencinas; R. I. Meneses; K. J. Feeley; H. Pauli; N. Aguirre; S. Beck; A. Bernardi; S. Cuello; et al. (Global Ecology and Biogeography, 2023)
Aim Climate change is transforming mountain summit plant communities worldwide, but we know little about such changes in the High Andes. Understanding large‐scale patterns of vegetation changes across the Andes, and the factors driving these changes, is fundamental to predicting the effects of global warming. We assessed trends in vegetation cover, species richness (SR) and community‐level thermal niches (CTN) and tested whether they are explained by summits' climatic conditions and soil temperature trends. Location High Andes. Time period Between 2011/2012 and 2017/2019. Major taxa studied Vascular plants. Methods Using permanent vegetation plots placed on 45 mountain summits and soil temperature loggers situated along a ~6800 km N‐S gradient, we measured species and their relative percentage cover and estimated CTN in two surveys (intervals between 5 and 8 years). We then estimated the annual rate of changes for the three variables and used generalized linear models to assess their relationship with annual precipitation, the minimum air temperatures of each summit and rates of change in the locally recorded soil temperatures. Results Over time, there was an average loss of vegetation cover (mean = −0.26%/yr), and a gain in SR across summits (mean = 0.38 species m 2 /yr), but most summits had significant increases in SR and vegetation cover. Changes in SR were positively related to minimum air temperature and soil temperature rate of change. Most plant communities experienced shifts in their composition by including greater abundances of species with broader thermal niches and higher optima. However, the measured changes in soil temperature did not explain the observed changes in CTN. Main conclusions High Andean vegetation is changing in cover and SR and is shifting towards species with wider thermal niche breadths. The weak relationship with soil temperature trends could have resulted from the short study period that only marginally captures changes in vegetation through time.

Glucose metabolism in posterior cingulate cortex has supplementary value to predict the progression of cognitively unimpaired to dementia due to Alzheimer’s disease: an exploratory study of 18F-FDG-PET - Qi Zhang; Chunqiu Fan; Luyao Wang; Taoran Li; Min Wang; Ying Han; Jiehui Jiang; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2023)

Overview of the search for signs of space weathering on the low-albedo asteroid (101955) Bennu - B.E. Clark; A. Sen; X.-D. Zou; D.N. DellaGiustina; S. Sugita; N. Sakatani; M. Thompson; D. Trang; E. Tatsumi; M.A. Barucci; M. Barker; H. Campins; et al. (Icarus, 2023)

Revisiting hydro-ecological impacts of climate change on a restored floodplain wetland via hydrological / hydraulic modelling and the UK Climate Projections 2018 scenarios - Julian R. Thompson; Hannah M. Clilverd; Jiaxuan Zheng; Honeyeh Iravani; Carl D. Sayer; Catherine M. Heppell; Jan C. Axmacher (Wetlands, 2023)
The hydro-ecological impacts of 40 UK Climate Projections 2018 scenarios on a restored lowland England river floodplain are assessed using a MIKE SHE / MIKE 11 model. Annual precipitation declines for 60% of scenarios (range: -26%–21%, with small, <5%, declines for the central probability level). Potential evapotranspiration increases for all probability levels except the most extreme, very unlikely, 10% level (range: -4%–43%, central probability 9%–20%) Mean, peak and low river discharges are reduced for all but the extreme 90% probability level. Reduced frequency of bankfull discharge dominates (at least halved for the central probability level). Floodplain inundation declines for over 97% of 320 scenario-events. Winter water table levels still intercept the surface, while mean and summer low levels are reduced. Declines in mean summer floodplain water table levels for the central probability level (0.22 m and 0.28 m for the 2050s and 2080s, respectively) are twice as large as those in the more dynamic riparian area. Declines reach 0.39 m for some 10% probability level scenarios. Simulated hydrological changes differ subtly from a previous assessment using earlier UK climate projections. A soil aeration stress index demonstrates that, under baseline conditions, prolonged high winter floodplain water tables drive long periods of low root-zone oxygen, in turn favouring vegetation communities adapted to waterlogged conditions. Climate change reduces aeration stress and the extent of appropriate conditions for these plant communities in favour of communities less tolerant of wet conditions.

Seagrass Abundance Predicts Surficial Soil Organic Carbon Stocks Across the Range of Thalassia testudinum in the Western North Atlantic - James W. Fourqurean; Justin E. Campbell; O. Kennedy Rhoades; Calvin J. Munson; Johannes R. Krause; Andrew H. Altieri; James G. Douglass; Kenneth L. Heck; Valerie J. Paul; Anna R. Armitage; Savanna C. Barry; Enrique Bethel; et al. (Estuaries and Coasts, 2023)

Correction to: Macroinvertebrate diversity and rarity in non-glacial Alpine streams - R. Alther; C. Thompson; B. Lods‑Crozet; C. T. Robinson (Aquatic Sciences, 2023)

Impact of the 2014–2016 marine heatwave on US and Canada West Coast fisheries: Surprises and lessons from key case studies - Christopher M. Free; Sean C. Anderson; Elizabeth A. Hellmers; Barbara A. Muhling; Michael O. Navarro; Kate Richerson; Lauren A. Rogers; William H. Satterthwaite; Andrew R. Thompson; Jenn M. Burt; Steven D. Gaines; Kristin N. Marshall; et al. (Fish and Fisheries, 2023)
Marine heatwaves are increasingly affecting marine ecosystems, with cascading impacts on coastal economies, communities, and food systems. Studies of heatwaves provide crucial insights into potential ecosystem shifts under future climate change and put fisheries social‐ecological systems through “stress tests” that expose both vulnerabilities and resilience. The 2014–16 Northeast Pacific heatwave was the strongest and longest marine heatwave on record and resulted in profound ecological changes that impacted fisheries, fisheries management, and human livelihoods. Here, we synthesize the impacts of the 2014–2016 marine heatwave on US and Canada West Coast fisheries and extract key lessons for preparing global fisheries science, management, and industries for the future. We set the stage with a brief review of the impacts of the heatwave on marine ecosystems and the first systematic analysis of the economic impacts of these changes on commercial and recreational fisheries. We then examine ten key case studies that provide instructive examples of the complex and surprising challenges that heatwaves pose to fisheries social‐ecological systems. These reveal important insights into improving the resilience of monitoring and management and increasing adaptive capacity to future stressors. Key recommendations include: (1) expanding monitoring to enhance mechanistic understanding, provide early warning signals, and improve predictions of impacts; (2) increasing the flexibility, adaptiveness, and inclusiveness of management where possible; (3) using simulation testing to help guide management decisions; and (4) enhancing the adaptive capacity of fishing communities by promoting engagement, flexibility, experimentation, and failsafes. These advancements are important as global fisheries prepare for a changing ocean.

Microbiome diversity from sponges biogeographically distributed between South America and Antarctica - Mayanne A.M. de Freitas; Isabel C. Cunha-Ferreira; Camille V. Leal; Julio C.C. Fernandez; Claudia Y. Omachi; Lucia S. Campos; Bruno P. Masi; Ricardo H. Krüger; Eduardo Hajdu; Cristiane C. Thompson; Fabiano L. Thompson (Science of The Total Environment, 2023)

Pre- and postnatal developmental exposure to the polychlorinated biphenyl mixture aroclor 1221 alters female rat pituitary gonadotropins and estrogen receptor alpha levels - Karen E. Weis; Lindsay M. Thompson; Madeline Streifer; Isabella Guardado; Jodi A. Flaws; Andrea C. Gore; Lori T. Raetzman (Reproductive Toxicology, 2023)

“The People's Summit”: A case for lived experience of food environments as a critical source of evidence to inform the follow-up to the 2021 UN Food Systems Summit - M. Spires; J. Battersby; N. Cohen; M. Daivadanam; K.M. Demmler; D. Mattioni; R. Pradeilles; C. Thompson; C. Turner; C. Venegas Hargous; S. Wertheim-Heck; W. Wills; et al. (Global Food Security, 2023)

Geographic and taxonomic variation in adaptive capacity among mountain-dwelling small mammals: Implications for conservation status and actions - Erik A. Beever; Jennifer L. Wilkening; Peter D. Billman; Lindsey L. Thurman; Kristina A. Ernest; David H. Wright; Alisha M. Gill; April C. Craighead; Nolan A. Helmstetter; Leona K. Svancara; Meghan J. Camp; Sabuj Bhattacharyya; et al. (Biological Conservation, 2023)

A Coupled Humanitarian and Biodiversity Crisis in Western Madagascar - Katharine E. T. Thompson; Cortni Borgerson; Patricia C. Wright; Jeanne Mathilde Randriamanetsy; Mamy Yves Andrianantenaina; Niaina Nirina Mahefa Andriamavosoloarisoa; Théofrico Alexander Razafindrahasy; Ryan S. Rothman; Claire Surkis; Richard J. Bankoff; Carter Daniels; Katheryn C. Twiss (International Journal of Primatology, 2023)

Phylogeography of the blacklegged tick ( Ixodes scapularis ) throughout the USA identifies candidate loci for differences in vectorial capacity - Julia C. Frederick; Alec T. Thompson; Prisha Sharma; Guha Dharmarajan; Isobel Ronai; Risa Pesapane; Ryan C. Smith; Kellee D. Sundstrom; Jean I. Tsao; Holly C. Tuten; Michael J. Yabsley; Travis C. Glenn (Molecular Ecology, 2023)
The blacklegged tick ( Ixodes scapularis ( Journal of the Academy of Natural Sciences of Philadelphia , 1821, 2 , 59)) is a vector of Borrelia burgdorferi sensu stricto ( s.s .) ( International Journal of Systematic Bacteriology , 1984, 34 , 496), the causative bacterial agent of Lyme disease, part of a slow‐moving epidemic of Lyme borreliosis spreading across the northern hemisphere. Well‐known geographical differences in the vectorial capacity of these ticks are associated with genetic variation. Despite the need for detailed genetic information in this disease system, previous phylogeographical studies of these ticks have been restricted to relatively few populations or few genetic loci. Here we present the most comprehensive phylogeographical study of genome‐wide markers in I. scapularis , conducted by using 3RAD (triple‐enzyme restriction‐site associated sequencing) and surveying 353 ticks from 33 counties throughout the species' range. We found limited genetic variation among populations from the Northeast and Upper Midwest, where Lyme disease is most common, and higher genetic variation among populations from the South. We identify five spatially associated genetic clusters of I. scapularis . In regions where Lyme disease is increasing in frequency, the I. scapularis populations genetically group with ticks from historically highly Lyme‐endemic regions. Finally, we identify 10 variable DNA sites that contribute the most to population differentiation. These variable sites cluster on one of the chromosome‐scale scaffolds for I. scapularis and are within identified genes. Our findings illuminate the need for additional research to identify loci causing variation in the vectorial capacity of I. scapularis and where additional tick sampling would be most valuable to further understand disease trends caused by pathogens transmitted by I. scapularis .

Climate warming has direct and indirect effects on microbes associated with carbon cycling in northern lakes - Johanna C. Winder; Lucas P. P. Braga; McKenzie A. Kuhn; Lauren M. Thompson; David Olefeldt; Andrew J. Tanentzap (Global Change Biology, 2023)
Northern lakes disproportionately influence the global carbon cycle, and may do so more in the future depending on how their microbial communities respond to climate warming. Microbial communities can change because of the direct effects of climate warming on their metabolism and the indirect effects of climate warming on groundwater connectivity from thawing of surrounding permafrost, especially at lower landscape positions. Here we used shotgun metagenomics to compare the taxonomic and functional gene composition of sediment microbes in 19 peatland lakes across a 1600‐km permafrost transect in boreal western Canada. We found microbes responded differently to the loss of regional permafrost cover than to increases in local groundwater connectivity. These results suggest that both the direct and indirect effects of climate warming, which were respectively associated with loss of permafrost and subsequent changes in groundwater connectivity interact to change microbial composition and function. Archaeal methanogens and genes involved in all major methanogenesis pathways were more abundant in warmer regions with less permafrost, but higher groundwater connectivity partly offset these effects. Bacterial community composition and methanotrophy genes did not vary with regional permafrost cover, and the latter changed similarly to methanogenesis with groundwater connectivity. Finally, we found an increase in sugar utilization genes in regions with less permafrost, which may further fuel methanogenesis. These results provide the microbial mechanism for observed increases in methane emissions associated with loss of permafrost cover in this region and suggest that future emissions will primarily be controlled by archaeal methanogens over methanotrophic bacteria as northern lakes warm. Our study more generally suggests that future predictions of aquatic carbon cycling will be improved by considering how climate warming exerts both direct effects associated with regional‐scale permafrost thaw and indirect effects associated with local hydrology.

Corrigendum to “Quantifying annual spatial consistency in chick-rearing seabirds to inform important site identification” [Biol. Conserv. 281 (2023) 109994] - Martin Beal; Paulo Catry; Richard A. Phillips; Steffen Oppel; John P.Y. Arnould; Maria I. Bogdanova; Mark Bolton; Ana P.B. Carneiro; Corey Clatterbuck; Melinda Conners; Francis Daunt; Karine Delord; et al. (Biological Conservation, 2023)

Equal use of Indigenous and scientific knowledge in species assessments: A case study from the Northwest Territories, Canada - Claire L. Singer; Mélanie R. Routh; Michele J. Grabke; Leon Andrew; Suzanne Carrière; Aimee Guile; Alestine Andre; Allison Thompson; Deborah Simmons; Kaytlin Cooper; Lynda Yonge; Moise Rabesca; et al. (Biological Conservation, 2023)

Quantifying annual spatial consistency in chick-rearing seabirds to inform important site identification - Martin Beal; Paulo Catry; Richard A. Phillips; Steffen Oppel; John P.Y. Arnould; Maria I. Bogdanova; Mark Bolton; Ana P.B. Carneiro; Corey Clatterbuck; Melinda Conners; Francis Daunt; Karine Delord; et al. (Biological Conservation, 2023)

The global EPTO database: Worldwide occurrences of aquatic insects - Afroditi Grigoropoulou; Suhaila Ab Hamid; Raúl Acosta; Emmanuel Olusegun Akindele; Salman A. Al‐Shami; Florian Altermatt; Giuseppe Amatulli; David G. Angeler; Francis O. Arimoro; Jukka Aroviita; Anna Astorga‐Roine; Rafael Costa Bastos; et al. (Global Ecology and Biogeography, 2023)
Motivation Aquatic insects comprise 64% of freshwater animal diversity and are widely used as bioindicators to assess water quality impairment and freshwater ecosystem health, as well as to test ecological hypotheses. Despite their importance, a comprehensive, global database of aquatic insect occurrences for mapping freshwater biodiversity in macroecological studies and applied freshwater research is missing. We aim to fill this gap and present the Global EPTO Database , which includes worldwide geo‐referenced aquatic insect occurrence records for four major taxa groups: Ephemeroptera, Plecoptera, Trichoptera and Odonata (EPTO). Main type of variables contained A total of 8,368,467 occurrence records globally, of which 8,319,689 (99%) are publicly available. The records are attributed to the corresponding drainage basin and sub‐catchment based on the Hydrography90m dataset and are accompanied by the elevation value, the freshwater ecoregion and the protection status of their location. Spatial location and grain The database covers the global extent, with 86% of the observation records having coordinates with at least four decimal digits (11.1 m precision at the equator) in the World Geodetic System 1984 (WGS84) coordinate reference system. Time period and grain Sampling years span from 1951 to 2021. Ninety‐nine percent of the records have information on the year of the observation, 95% on the year and month, while 94% have a complete date. In the case of seven sub‐datasets, exact dates can be retrieved upon communication with the data contributors. Major taxa and level of measurement Ephemeroptera, Plecoptera, Trichoptera and Odonata, standardized at the genus taxonomic level. We provide species names for 7,727,980 (93%) records without further taxonomic verification. Software format The entire tab‐separated value (.csv) database can be downloaded and visualized at https://glowabio.org/project/epto_database/ . Fifty individual datasets are also available at https://fred.igb‐berlin.de , while six datasets have restricted access. For the latter, we share metadata and the contact details of the authors.

Protectin DX as a therapeutic strategy against frailty in mice - Laís R. Perazza; Adam C. Gower; Holly M. Brown-Borg; Paola Divieti Pajevic; LaDora V. Thompson (GeroScience, 2023)
Frailty in aging is driven by the dysregulation of multiple biological pathways. Protectin DX (PDX) is a docosahexaenoic acid (DHA)-derived molecule that alleviates many chronic inflammatory disorders, but its potential effects on frailty remain unknown. Our goal is to identify age-related impairments in metabolic systems and to evaluate the therapeutic potential of PDX on frailty, physical performance, and health parameters. A set of 22-month-old C57BL/6 male and female mice were assigned to vehicle (Old) or PDX daily gavage treatment for 9 weeks, whereas 6-month-old (Adult) mice received only vehicle. Forelimb and hindlimb strength, endurance, voluntary wheel activity and walking speed determined physical performance and were combined with a frailty index score and body weight loss to determine frailty status. Our data shows that old vehicle-treated mice from both sexes had body weight loss paralleling visceromegaly, and Old females also had impaired insulin clearance as compared to the Adult group. Aging was associated with physical performance decline together with higher odds of frailty development. There was also age-driven mesangial expansion and glomerular hypertrophy as well as bone mineral density loss. All of the in vivo and in vitro impairments observed with aging co-occurred with upregulation of inflammatory pathways and Myc signaling as well as downregulation of genes related to adipogenesis and oxidative phosphorylation in liver. PDX attenuated the age-driven physical performance (strength, exhaustion, walking speed) decline, promoted robustness, prevented bone losses and partially reversed changes in hepatic expression of Myc targets and metabolic genes. In conclusion, our data provides evidence of the beneficial therapeutic effect of PDX against features of frailty in mice. Further studies are warranted to investigate the mechanisms of action and the potential for human translation.

Prevalence of neonicotinoid insecticides in paired private-well tap water and human urine samples in a region of intense agriculture overlying vulnerable aquifers in eastern Iowa - Darrin A. Thompson; Dana W. Kolpin; Michelle L. Hladik; Hans-Joachim Lehmler; Shannon M. Meppelink; Matthew C. Poch; John D. Vargo; Victor A. Soupene; Nafis Md Irfan; Morgan Robinson; Kurunthachalam Kannan; Laura E. Beane Freeman; et al. (Chemosphere, 2023)

Juxtaposition of intensive agriculture, vulnerable aquifers, and mixed chemical/microbial exposures in private-well tapwater in northeast Iowa - Paul M. Bradley; Dana W. Kolpin; Darrin A. Thompson; Kristin M. Romanok; Kelly L. Smalling; Sara E. Breitmeyer; Mary C. Cardon; David M. Cwiertny; Nicola Evans; R. William Field; Michael J. Focazio; Laura E. Beane Freeman; et al. (Science of The Total Environment, 2023)

Regional variability in peatland burning at mid-to high-latitudes during the Holocene - Thomas G. Sim; Graeme T. Swindles; Paul J. Morris; Andy J. Baird; Angela V. Gallego-Sala; Yuwan Wang; Maarten Blaauw; Philip Camill; Michelle Garneau; Mark Hardiman; Julie Loisel; Minna Vӓliranta; et al. (Quaternary Science Reviews, 2023)

Nonequilibrium spherulitic magnetite in the Ryugu samples - Elena Dobrică; Hope A. Ishii; John P. Bradley; Kenta Ohtaki; Adrian J. Brearley; Takaaki Noguchi; Toru Matsumoto; Akira Miyake; Yohei Igami; Mitsutaka Haruta; Hikaru Saito; Satoshi Hata; et al. (Geochimica et Cosmochimica Acta, 2023)

Treatment of acid mine drainage and chromium (VI) removal using synthesised chitosan composites blended with kenaf fibre and γ-Fe2O3 nanoparticles - C. N. Nkuna; E. R. Sadiku; G. Perry; B. Oboirien; M. K. Dludlu; C. Thompson (International Journal of Environmental Science and Technology, 2023)

Environmental variability and krill abundance in the central California current: Implications for ecosystem monitoring - Jeffrey G. Dorman; William J. Sydeman; Sarah Ann Thompson; Joseph D. Warren; Helen J. Killeen; Brian A. Hoover; John C. Field; Jarrod A. Santora (Frontiers in Marine Science, 2023)
Krill are a direct conduit between primary productivity and recreationally and commercially important higher trophic level species globally. Determining how krill abundance varies with temporal environmental variation is key to understanding their function in coastal-pelagic food webs, as well as applications in fisheries management. We used nine years (2012–19 and 2021) of late spring/early summer hydroacoustic-trawl survey data in the California Current Ecosystem (CCE), coupled with new target strength models of two krill species ( Euphausia pacifica and Thysanoessa spinifera ), to investigate how adult krill biomass varied during a decade of unusual ocean climate variability. We estimate a mean biomass of 1.75–2.0 million metric tons on the central and northern California continental shelf. Overall, relative krill biomass was ~30% lower during 2015 and 2016, corresponding to a major warming event, and ~30% higher in 2013 and 2018, years of exceptionally strong upwelling. Variation in biomass was related to the prior year’s environmental conditions derived from our seasonal Multivariate Ocean Climate Index (MOCI), and E. pacifica and T. spinifera showed similar covariation during the study period. Biomass co-varied at different spatial scales and across sampling devices, suggesting that multiple indicators of abundance (and dispersion) are available and should be applied in ecosystem monitoring and modeling of krill and krill-dependent predators in the California Current ecosystem.

The role of field-collected cues in the host recognition of twig girdlers (Oncideres rhodosticta) on honey mesquite (Prosopis glandulosa) - Ikju Park; David C. Thompson (Journal of Asia-Pacific Entomology, 2023)

Alteration of oral microbiome composition in children living with pesticide-exposed farm workers - Ian B. Stanaway; James C. Wallace; Sungwoo Hong; Carly S. Wilder; Foad H. Green; Jesse Tsai; Misty Knight; Tomomi Workman; Eric M. Vigoren; Marissa N. Smith; William C. Griffith; Beti Thompson; et al. (International Journal of Hygiene and Environmental Health, 2023)

Targeting de novo loss-of-function variants in constrained disease genes improves diagnostic rates in the 100,000 Genomes Project - Eleanor G. Seaby; N. Simon Thomas; Amy Webb; Helen Brittain; Ana Lisa Taylor Tavares; J. C. Ambrose; P Arumugam; R Bevers; M Bleda; F Boardman-Pretty; C. R. Boustred; H Brittain; et al. (Human Genetics, 2023)
Background Genome sequencing was first offered clinically in the UK through the 100,000 Genomes Project (100KGP). Analysis was restricted to predefined gene panels associated with the patient’s phenotype. However, panels rely on clearly characterised phenotypes and risk missing diagnoses outside of the panel(s) applied. We propose a complementary method to rapidly identify pathogenic variants, including those missed by 100KGP methods. Methods The Loss-of-function Observed/Expected Upper-bound Fraction (LOEUF) score quantifies gene constraint, with low scores correlated with haploinsufficiency. We applied DeNovoLOEUF, a filtering strategy to sequencing data from 13,949 rare disease trios in the 100KGP, by filtering for rare, de novo, loss-of-function variants in disease genes with a LOEUF score < 0.2. We compared our findings with the corresponding patient’s diagnostic reports. Results 324/332 (98%) of the variants identified using DeNovoLOEUF were diagnostic or partially diagnostic (whereby the variant was responsible for some of the phenotype). We identified 39 diagnoses that were “missed” by 100KGP standard analyses, which are now being returned to patients. Conclusion We have demonstrated a highly specific and rapid method with a 98% positive predictive value that has good concordance with standard analysis, low false-positive rate, and can identify additional diagnoses. Globally, as more patients are being offered genome sequencing, we anticipate that DeNovoLOEUF will rapidly identify new diagnoses and facilitate iterative analyses when new disease genes are discovered.

The impacts of a global pandemic on the efficacy and stability of contemporary wildlife conservation: South Africa as a case study - David A. Ehlers Smith; Yvette C. Ehlers Smith; Harriet T. Davies-Mostert; Lindy J. Thompson; Daniel M. Parker; Deon de Villiers; Dean Ricketts; Brent Coverdale; Peter J. Roberts; Christopher Kelly; Duncan N. Macfadyen; Nomthandazo S. Manqele; et al. (Ambio, 2023)
Conservationists speculated on potential benefits to wildlife of lockdown restrictions because of the COVID-19 pandemic but voiced concern that restrictions impeded nature conservation. We assessed the effects of lockdown restrictions on biodiversity conservation in South Africa, a biodiverse country with economic inequality and reliance on wildlife resources. We solicited expert opinion using the IUCN’s Threats Classification Scheme to structure a questionnaire and illustrated responses with individual case studies from government parastatal and non-governmental conservation organisations. The most highly reported threats were biological resource use, residential/commercial developments, invasive species, and human intrusions. The trends reported by 90 survey respondents were supported by case studies using environmental compliance data from parastatal conservation organisations. Lack of tourism revenue and funding were cited as hindrances to conservation. Mechanisms to prevent environmental degradation in the face of global emergencies must be implemented and ‘ring-fenced’ to ensure conservation is not a casualty during future global crises.

Controls on methylmercury concentrations in lakes and streams of peatland‐rich catchments along a 1700 km permafrost gradient - Lauren M. Thompson; McKenzie A. Kuhn; Johanna C. Winder; Lucas P. P. Braga; Ryan H. S. Hutchins; Andrew J. Tanentzap; Vincent L. St. Louis; David Olefeldt (Limnology and Oceanography, 2023)
Permafrost thaw may increase the production of neurotoxic methylmercury (MeHg) in northern peatlands, but the downstream delivery of MeHg is uncertain. We quantified total mercury (THg) and MeHg concentrations in lakes and streams along a 1700 km permafrost transect in boreal western Canada to determine the influence of regional permafrost extent compared to local lake and catchment characteristics. In lakes, we assessed sediment microbial communities and modeled potential rates of water column photodemethylation (PD). Regardless of permafrost conditions, peatlands were the primary sources of MeHg across the transect as MeHg concentrations in streams increased with aromatic dissolved organic carbon (DOC), iron, and lower pH. Higher DOC and greater catchment peatland extent were further associated with higher stream %MeHg (MeHg/THg). Peatland lakes were potential MeHg sinks, with lower MeHg concentrations than streams (mean ± 1SD: 0.19 ± 0.23 and 0.47 ± 0.77 ng MeHg L −1 , respectively), and larger stream catchments had lower %MeHg where PD may occur in abundant small lakes. Microbial communities in lake sediments showed that abundance of Hg reducing genes ( mer A) predominated over Hg methylating ( hgc A) and MeHg demethylating ( mer B) genes. The effects of permafrost extent on MeHg processes in lakes were secondary to the influence of local catchment characteristics, but lakes in regions with less permafrost had higher DOC concentrations, higher %MeHg, and lower potential rates of PD. Our study highlights a need to understand the impacts of climate change on MeHg source and sink processes, particularly as mediated through changes to peatland DOC, to improve projections of future MeHg concentrations in northern catchments.

Response of Pacific halibut (Hippoglossus stenolepis) to future climate scenarios in the Northeast Pacific Ocean - Patrick L. Thompson; Christopher N. Rooper; Jessica Nephin; Ashley E. Park; James R. Christian; Sarah C. Davies; Karen Hunter; Devin A. Lyons; M. Angelica Peña; Beatrice Proudfoot; Emily M. Rubidge; Amber M. Holdsworth (Fisheries Research, 2023)

Complex crop rotations improve organic nitrogen cycling - Lauren C. Breza; Maria Mooshammer; Timothy M. Bowles; Virginia L. Jin; Marty R. Schmer; Bennett Thompson; A. Stuart Grandy (Soil Biology and Biochemistry, 2023)

Polaris Gold: An Attractive, Yellow-fleshed Tablestock Cultivar with Chipping Potential - Thomas R. Stefaniak; Jeffrey Miller; Colin R. Jones; Michael Miller; Muyideen Yusuf; Megan A. Harder; John C. Larsen; Cari A. Schmitz Carley; Darrin Haagenson; Asunta Thompson; Thomas E. Michaels; Christian Thill; et al. (American Journal of Potato Research, 2023)

Uptake, distribution and elimination of palladium-doped polystyrene nanoplastics in rainbow trout (Oncorhynchus mykiss) following dietary exposure - Nathaniel J. Clark; Farhan R. Khan; Charlotte Crowther; Denise M. Mitrano; Richard C. Thompson (Science of The Total Environment, 2023)

Quartz-hosted inclusions and embayments reveal storage, fluxing, and ascent of the Mesa Falls Tuff, Yellowstone - Kenneth S. Befus; Anna C. Ruefer; Chelsea M. Allison; James O. Thompson (Earth and Planetary Science Letters, 2023)

Flooding triggers increased surface activity in a bottom‐dwelling turtle - Donald T. McKnight; Jaren C. Serano; Denise M. Thompson; Day B. Ligon (Ecology, 2023)

The Great Amazon Reef System: A fact - Thomás N. S. Banha; Osmar J. Luiz; Nils E. Asp; Hudson T. Pinheiro; Rafael A. Magris; Ralf T. S. Cordeiro; Michel M. Mahiques; Miguel Mies; Vinicius J. Giglio; Claudia Y. Omachi; Eduardo Siegle; Luciane C. Nogueira; et al. (Frontiers in Marine Science, 2022)

Relationships between physical activity, healthy eating and cortical thickness in children and young adults - Brendan C. Angelo; Alexis DeFendis; Anita Yau; Jasmin M. Alves; Paul M. Thompson; Anny H. Xiang; Kathleen A. Page; Shan Luo (Brain Imaging and Behavior, 2022)

Effects of Intra-REV Pore Distribution Modeling in the Flow of Non-Newtonian Fluids in Porous Media - Allan B. G. Motta; Roney L. Thompson; Mateus P. Schwalbert; Luiz F. L. R. Silva; Jovani L. Favero; Rodrigo A. C. Dias; Raphael J. Leitão (Transport in Porous Media, 2022)

Conceptualizing a probabilistic risk and loss assessment framework for wildfires - Negar Elhami-Khorasani; Hamed Ebrahimian; Lawrence Buja; Susan L. Cutter; Branko Kosovic; Neil Lareau; Brian J. Meacham; Eric Rowell; Ertugrul Taciroglu; Matthew P. Thompson; Adam C. Watts (Natural Hazards, 2022)

Vibrio fluminensis sp. nov. isolated from the skin of Southern Atlantic sharpnose-pufferfish (Canthigaster figueiredoi) - Gustavo P. R. de Azevedo; Hannah K. Mattsson; Luciane A. Chimetto Tonon; Tatiane Arruda; Vinicius Salazar; Vincent A. Bielinski; Fernanda Chagas; Diogo A. Tschoeke; Cristiane C. Thompson; Fabiano L. Thompson (Archives of Microbiology, 2022)

Recommendations for quantifying and reducing uncertainty in climate projections of species distributions - Stephanie Brodie; James A. Smith; Barbara A. Muhling; Lewis A. K. Barnett; Gemma Carroll; Paul Fiedler; Steven J. Bograd; Elliott L. Hazen; Michael G. Jacox; Kelly S. Andrews; Cheryl L. Barnes; Lisa G. Crozier; et al. (Global Change Biology, 2022)
Projecting the future distributions of commercially and ecologically important species has become a critical approach for ecosystem managers to strategically anticipate change, but large uncertainties in projections limit climate adaptation planning. Although distribution projections are primarily used to understand the scope of potential change—rather than accurately predict specific outcomes—it is nonetheless essential to understand where and why projections can give implausible results and to identify which processes contribute to uncertainty. Here, we use a series of simulated species distributions, an ensemble of 252 species distribution models, and an ensemble of three regional ocean climate projections, to isolate the influences of uncertainty from earth system model spread and from ecological modeling. The simulations encompass marine species with different functional traits and ecological preferences to more broadly address resource manager and fishery stakeholder needs, and provide a simulated true state with which to evaluate projections. We present our results relative to the degree of environmental extrapolation from historical conditions, which helps facilitate interpretation by ecological modelers working in diverse systems. We found uncertainty associated with species distribution models can exceed uncertainty generated from diverging earth system models (up to 70% of total uncertainty by 2100), and that this result was consistent across species traits. Species distribution model uncertainty increased through time and was primarily related to the degree to which models extrapolated into novel environmental conditions but moderated by how well models captured the underlying dynamics driving species distributions. The predictive power of simulated species distribution models remained relatively high in the first 30 years of projections, in alignment with the time period in which stakeholders make strategic decisions based on climate information. By understanding sources of uncertainty, and how they change at different forecast horizons, we provide recommendations for projecting species distribution models under global climate change.

State of the California Current Ecosystem in 2021: Winter is coming? - Andrew R. Thompson; Eric P. Bjorkstedt; Steven J. Bograd; Jennifer L. Fisher; Elliott L. Hazen; Andrew Leising; Jarrod A. Santora; Erin V. Satterthwaite; William J. Sydeman; Michaela Alksne; Toby D. Auth; Simone Baumann-Pickering; et al. (Frontiers in Marine Science, 2022)
In late 2020, models predicted that a strong La Niña would take place for the first time since 2013, and we assessed whether physical and biological indicators in 2021 were similar to past La Niñas in the California Current Ecosystem (CCE). The Pacific Decadal Oscillation and Oceanic Niño Index indeed remained negative throughout 2021; the North Pacific Gyre Oscillation Index, however, remained strongly negative. The seventh largest marine heatwave on record was unexpectedly present from April to the end of 2021; however, similar to past La Niñas, this mass of warm water mostly remained seaward of the continental shelf. As expected from past La Niñas, upwelling and chlorophyll were mostly high and sea surface temperature was low throughout the CCE; however, values were close to average south of Point Conception. Similar to past La Niñas, abundances of lipid-rich, northern copepods off Oregon increased. In northern California, unlike past La Niñas, the body size of North Pacific krill ( Euphausia pacifica ) was close to average. Predictably, overall krill abundance was above average in far northern California but, unexpectedly, below average south of Cape Mendocino. Off Oregon, similar to past La Niñas, larval abundances of three of six coastal species rose, while five of six southern/offshore taxa decreased in 2021. Off California, as expected based on 2020, Northern Anchovy ( Engraulis mordax ) were very abundant, while Pacific Sardine ( Sardinops sagax ) were low. Similar to past La Niñas, market squid ( Doryteuthis opalescens ) and young of the year (YOY) Pacific Hake ( Merluccius pacificus ), YOY sanddabs ( Citharichthys spp.), and YOY rockfishes ( Sebastes spp.) increased. Southern mesopelagic (e.g., Panama lightfish Vinciguerria lucetia , Mexican lampfish Triphoturus mexicanus ) larvae decreased as expected but were still well above average, while northern mesopelagic (e.g., northern lampfish Stenobrachius leucopsarus ) larvae increased but were still below average. In line with predictions, most monitored bird species had above-average reproduction in Oregon and California. California sea lion ( Zalophus californianus ) pup count, growth, and weight were high given the abundant Anchovy forage. The CCE entered an enduring La Niña in 2021, and assessing the responses of various ecosystem components helped articulate aspects of the system that are well understood and those that need further study.

Glucose metabolism patterns: A potential index to characterize brain ageing and predict high conversion risk into cognitive impairment - Jiehui Jiang; Can Sheng; Guanqun Chen; Chunhua Liu; Shichen Jin; Lanlan Li; Xueyan Jiang; Ying Han; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2022)

Risk of clear-cell adenocarcinoma of the vagina and cervix among US women with potential exposure to diethylstilbestrol in utero - Mary C. White; Hannah K. Weir; Ashwini V. Soman; Lucy A. Peipins; Trevor D. Thompson (Cancer Causes & Control, 2022)

Mismatches in scale between highly mobile marine megafauna and marine protected areas - Melinda G. Conners; Nicholas B. Sisson; Pierre D. Agamboue; Philip W. Atkinson; Alastair M. M. Baylis; Scott R. Benson; Barbara A. Block; Steven J. Bograd; Pablo Bordino; W. D. Bowen; Paul Brickle; Ignacio M. Bruno; et al. (Frontiers in Marine Science, 2022)
Marine protected areas (MPAs), particularly large MPAs, are increasing in number and size around the globe in part to facilitate the conservation of marine megafauna under the assumption that large-scale MPAs better align with vagile life histories; however, this alignment is not well established. Using a global tracking dataset from 36 species across five taxa, chosen to reflect the span of home range size in highly mobile marine megafauna, we show most MPAs are too small to encompass complete home ranges of most species. Based on size alone, 40% of existing MPAs could encompass the home ranges of the smallest ranged species, while only < 1% of existing MPAs could encompass those of the largest ranged species. Further, where home ranges and MPAs overlapped in real geographic space, MPAs encompassed < 5% of core areas used by all species. Despite most home ranges of mobile marine megafauna being much larger than existing MPAs, we demonstrate how benefits from MPAs are still likely to accrue by targeting seasonal aggregations and critical life history stages and through other management techniques.

Comprehensive analysis of epigenetic clocks reveals associations between disproportionate biological ageing and hippocampal volume - Lidija Milicic; Michael Vacher; Tenielle Porter; Vincent Doré; Samantha C. Burnham; Pierrick Bourgeat; Rosita Shishegar; James Doecke; Nicola J. Armstrong; Rick Tankard; Paul Maruff; Colin L. Masters; et al. (GeroScience, 2022)
The concept of age acceleration, the difference between biological age and chronological age, is of growing interest, particularly with respect to age-related disorders, such as Alzheimer’s Disease (AD). Whilst studies have reported associations with AD risk and related phenotypes, there remains a lack of consensus on these associations. Here we aimed to comprehensively investigate the relationship between five recognised measures of age acceleration, based on DNA methylation patterns (DNAm age), and cross-sectional and longitudinal cognition and AD-related neuroimaging phenotypes (volumetric MRI and Amyloid-β PET) in the Australian Imaging, Biomarkers and Lifestyle (AIBL) and the Alzheimer’s Disease Neuroimaging Initiative (ADNI). Significant associations were observed between age acceleration using the Hannum epigenetic clock and cross-sectional hippocampal volume in AIBL and replicated in ADNI. In AIBL, several other findings were observed cross-sectionally, including a significant association between hippocampal volume and the Hannum and Phenoage epigenetic clocks. Further, significant associations were also observed between hippocampal volume and the Zhang and Phenoage epigenetic clocks within Amyloid-β positive individuals. However, these were not validated within the ADNI cohort. No associations between age acceleration and other Alzheimer’s disease-related phenotypes, including measures of cognition or brain Amyloid-β burden, were observed, and there was no association with longitudinal change in any phenotype. This study presents a link between age acceleration, as determined using DNA methylation, and hippocampal volume that was statistically significant across two highly characterised cohorts. The results presented in this study contribute to a growing literature that supports the role of epigenetic modifications in ageing and AD-related phenotypes.

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Bridge to the future: Important lessons from 20 years of ecosystem observations made by the OzFlux network - Jason Beringer; Caitlin E. Moore; Jamie Cleverly; David I. Campbell; Helen Cleugh; Martin G. De Kauwe; Miko U. F. Kirschbaum; Anne Griebel; Sam Grover; Alfredo Huete; Lindsay B. Hutley; Johannes Laubach; et al. (Global Change Biology, 2022)
In 2020, the Australian and New Zealand flux research and monitoring network, OzFlux, celebrated its 20 th anniversary by reflecting on the lessons learned through two decades of ecosystem studies on global change biology. OzFlux is a network not only for ecosystem researchers, but also for those ‘next users’ of the knowledge, information and data that such networks provide. Here, we focus on eight lessons across topics of climate change and variability, disturbance and resilience, drought and heat stress and synergies with remote sensing and modelling. In distilling the key lessons learned, we also identify where further research is needed to fill knowledge gaps and improve the utility and relevance of the outputs from OzFlux. Extreme climate variability across Australia and New Zealand (droughts and flooding rains) provides a natural laboratory for a global understanding of ecosystems in this time of accelerating climate change. As evidence of worsening global fire risk emerges, the natural ability of these ecosystems to recover from disturbances, such as fire and cyclones, provides lessons on adaptation and resilience to disturbance. Drought and heatwaves are common occurrences across large parts of the region and can tip an ecosystem's carbon budget from a net CO 2 sink to a net CO 2 source. Despite such responses to stress, ecosystems at OzFlux sites show their resilience to climate variability by rapidly pivoting back to a strong carbon sink upon the return of favourable conditions. Located in under‐represented areas, OzFlux data have the potential for reducing uncertainties in global remote sensing products, and these data provide several opportunities to develop new theories and improve our ecosystem models. The accumulated impacts of these lessons over the last 20 years highlights the value of long‐term flux observations for natural and managed systems. A future vision for OzFlux includes ongoing and newly developed synergies with ecophysiologists, ecologists, geologists, remote sensors and modellers.

Data Quality Influences the Predicted Distribution and Habitat of Four Southern-Hemisphere Albatross Species - Kimberly T. Goetz; Fabrice Stephenson; Andrew Hoskins; Aidan D. Bindoff; Rachael A. Orben; Paul M. Sagar; Leigh G. Torres; Caitlin E. Kroeger; Lisa A. Sztukowski; Richard A. Phillips; Stephen C. Votier; Stuart Bearhop; et al. (Frontiers in Marine Science, 2022)
Few studies have assessed the influence of data quality on the predicted probability of occurrence and preferred habitat of marine predators. We compared results from four species distribution models (SDMs) for four southern-hemisphere albatross species, Buller’s ( Thalassarche bulleri ), Campbell ( T. impavida ), grey-headed ( T. chrysostoma ), and white-capped ( T. steadi ), based on datasets of differing quality, ranging from no location data to twice-daily locations of individual birds collected by geolocation devices. Two relative environmental suitability (RES) models were fit using minimum and maximum preferred and absolute values for each environmental variable based on (1) monthly 50% kernel density contours and background environmental data, and (2) primary literature or expert opinion. Additionally, two boosted regression tree (BRT) models were fit using (1) opportunistic sightings data, and (2) geolocation data from bird-borne electronic tags. Using model-specific threshold values, habitat was quantified for each species and model. Model variables included distance from land, bathymetry, sea surface temperature, and chlorophyll- a concentration. Results from both RES models and the BRT model fit with opportunistic sightings were compared to those from the BRT model fit using geolocation data to assess the influence of data quality on predicted occupancy and habitat. For all species, BRT models outperformed RES models. BRT models offer a predictive advantage over RES models by being able to identify relevant variables, incorporate environmental interactions, and provide spatially explicit estimates of model uncertainty. RES models resulted in larger, less refined areas of predicted habitat for all species. Our study highlights the importance of data quality in predicting the distribution and habitat of albatrosses and emphasises the need to consider the pros and cons associated with different levels of data quality when using SDMs to inform management decisions. Furthermore, we examine the overlap in preferred habitat predicted by each SDM with fishing effort. We discuss the influence of data quality on predicting the wide-scale distributions of pelagic seabirds and how these impacts could result in different protection measures.

Heat Stress and Kidney Function in Farmworkers in the US: A Scoping Review - Daniel J Smith; Lisa M Pius; Laura C Plantinga; Lisa M Thompson; Valerie Mac; Vicki S Hertzberg (Journal of Agromedicine, 2022)

In vitro larvae metamorphosis of a New Zealand native freshwater mussel (Bivalvia: Unionida: Hyriidae) Echyridella menziesii - Karen J. Thompson; Mark C. Fenwick; Susan J. Clearwater (Molluscan Research, 2022)

Is Neuroscience FAIR? A Call for Collaborative Standardisation of Neuroscience Data - Jean-Baptiste Poline; David N. Kennedy; Friedrich T. Sommer; Giorgio A. Ascoli; David C. Van Essen; Adam R. Ferguson; Jeffrey S. Grethe; Michael J. Hawrylycz; Paul M. Thompson; Russell A. Poldrack; Satrajit S. Ghosh; David B. Keator; et al. (Neuroinformatics, 2022)
In this perspective article, we consider the critical issue of data and other research object standardisation and, specifically, how international collaboration, and organizations such as the International Neuroinformatics Coordinating Facility (INCF) can encourage that emerging neuroscience data be Findable, Accessible, Interoperable, and Reusable (FAIR) . As neuroscientists engaged in the sharing and integration of multi-modal and multiscale data, we see the current insufficiency of standards as a major impediment in the Interoperability and Reusability of research results. We call for increased international collaborative standardisation of neuroscience data to foster integration and efficient reuse of research objects.

Dynamics and predicted distribution of an irrupting ‘sleeper’ population: fallow deer in Tasmania - Calum X. Cunningham; George L. W. Perry; David M. J. S. Bowman; David M. Forsyth; Michael M. Driessen; Matt Appleby; Barry W. Brook; Greg Hocking; Jessie C. Buettel; Ben J. French; Rowena Hamer; Sally L. Bryant; et al. (Biological Invasions, 2022)

The role of nutrients underlying interactions among root-nodule bacteria (Bradyrhizobium sp.), arbuscular mycorrhizal fungi (Funneliformis mosseae) and root-lesion nematodes (Pratylenchus thornei) in nitrogen fixation and growth of mung bean (Vigna radiata) - E. C. Gough; K. J. Owen; R. S. Zwart; J. P. Thompson (Plant and Soil, 2022)

14–3-3 protein regulation of excitation–contraction coupling - Walter C. Thompson; Paul H. Goldspink (Pflügers Archiv - European Journal of Physiology, 2022)
14–3-3 proteins (14–3-3 s) are a family of highly conserved proteins that regulate many cellular processes in eukaryotes by interacting with a diverse array of client proteins. The 14–3-3 proteins have been implicated in several disease states and previous reviews have condensed the literature with respect to their structure, function, and the regulation of different cellular processes. This review focuses on the growing body of literature exploring the important role 14–3-3 proteins appear to play in regulating the biochemical and biophysical events associated with excitation–contraction coupling (ECC) in muscle. It presents both a timely and unique analysis that seeks to unite studies emphasizing the identification and diversity of 14–3-3 protein function and client protein interactions, as modulators of muscle contraction. It also highlights ideas within these two well-established but intersecting fields that support further investigation with respect to the mechanistic actions of 14–3-3 proteins in the modulation of force generation in muscle.

Does crop insurance inhibit climate change technology adoption? - Sarah C. Sellars; Nathanael M. Thompson; Michael E. Wetzstein; Laura Bowling; Keith Cherkauer; Charlotte Lee; Jane Frankenberger; Ben Reinhart (Mitigation and Adaptation Strategies for Global Change, 2022)

Corrigendum: State of the California Current 2019–2020: Back to the Future With Marine Heatwaves? - Edward D. Weber; Toby D. Auth; Simone Baumann-Pickering; Timothy R. Baumgartner; Eric P. Bjorkstedt; Steven J. Bograd; Brian J. Burke; José L. Cadena-Ramírez; Elizabeth A. Daly; Martin de la Cruz; Heidi Dewar; John C. Field; et al. (Frontiers in Marine Science, 2022)

Beyond bulk: Density fractions explain heterogeneity in global soil carbon abundance and persistence - Katherine Heckman; Caitlin E. Hicks Pries; Corey R. Lawrence; Craig Rasmussen; Susan E. Crow; Alison M. Hoyt; Sophie F. von Fromm; Zheng Shi; Shane Stoner; Casey McGrath; Jeffrey Beem‐Miller; Asmeret Asefaw Berhe; et al. (Global Change Biology, 2022)
Understanding the controls on the amount and persistence of soil organic carbon (C) is essential for predicting its sensitivity to global change. The response may depend on whether C is unprotected, isolated within aggregates, or protected from decomposition by mineral associations. Here, we present a global synthesis of the relative influence of environmental factors on soil organic C partitioning among pools, abundance in each pool (mg C g −1 soil), and persistence (as approximated by radiocarbon abundance) in relatively unprotected particulate and protected mineral‐bound pools. We show that C within particulate and mineral‐associated pools consistently differed from one another in degree of persistence and relationship to environmental factors. Soil depth was the best predictor of C abundance and persistence, though it accounted for more variance in persistence. Persistence of all C pools decreased with increasing mean annual temperature (MAT) throughout the soil profile, whereas persistence increased with increasing wetness index (MAP/PET) in subsurface soils (30–176 cm). The relationship of C abundance (mg C g −1 soil) to climate varied among pools and with depth. Mineral‐associated C in surface soils (

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

Socio-environmental drivers of establishment of Lymantria dispar, a nonnative forest pest, in the United States - Rebecca Epanchin-Niell; Jieyi Lu; Alexandra Thompson; Patrick C. Tobin; David R. Gray; Andrew M. Liebhold (Biological Invasions, 2022)

Associations of alcohol use, HIV infection, and age with brain white matter microstructure - Mollie A. Monnig; Joseph M. Gullett; Eric C. Porges; Adam J. Woods; Peter M. Monti; Karen Tashima; Neda Jahanshad; Paul Thompson; Talia Nir; Ronald A. Cohen (Journal of NeuroVirology, 2021)

Detecting forest response to droughts with global observations of vegetation water content - Alexandra G. Konings; Sassan S. Saatchi; Christian Frankenberg; Michael Keller; Victor Leshyk; William R. L. Anderegg; Vincent Humphrey; Ashley M. Matheny; Anna Trugman; Lawren Sack; Elizabeth Agee; Mallory L. Barnes; et al. (Global Change Biology, 2021)
Droughts in a warming climate have become more common and more extreme, making understanding forest responses to water stress increasingly pressing. Analysis of water stress in trees has long focused on water potential in xylem and leaves, which influences stomatal closure and water flow through the soil‐plant‐atmosphere continuum. At the same time, changes of vegetation water content (VWC) are linked to a range of tree responses, including fluxes of water and carbon, mortality, flammability, and more. Unlike water potential, which requires demanding in situ measurements, VWC can be retrieved from remote sensing measurements, particularly at microwave frequencies using radar and radiometry. Here, we highlight key frontiers through which VWC has the potential to significantly increase our understanding of forest responses to water stress. To validate remote sensing observations of VWC at landscape scale and to better relate them to data assimilation model parameters, we introduce an ecosystem‐scale analog of the pressure–volume curve, the non‐linear relationship between average leaf or branch water potential and water content commonly used in plant hydraulics. The sources of variability in these ecosystem‐scale pressure‐volume curves and their relationship to forest response to water stress are discussed. We further show to what extent diel, seasonal, and decadal dynamics of VWC reflect variations in different processes relating the tree response to water stress. VWC can also be used for inferring belowground conditions—which are difficult to impossible to observe directly. Lastly, we discuss how a dedicated geostationary spaceborne observational system for VWC, when combined with existing datasets, can capture diel and seasonal water dynamics to advance the science and applications of global forest vulnerability to future droughts.

High-pressure crystal structure and equation of state of ferromagnesian jeffbenite: implications for stability in the transition zone and uppermost lower mantle - Fei Wang; Elizabeth C. Thompson; Dongzhou Zhang; Ercan E. Alp; Jiyong Zhao; Joseph R. Smyth; Steven D. Jacobsen (Contributions to Mineralogy and Petrology, 2021)

Untangling local and remote influences in two major petrel habitats in the oligotrophic Southern Ocean - Daniel C. Jones; Filipe R. Ceia; Eugene Murphy; Karine Delord; Robert W. Furness; Ariane Verdy; Matthew Mazloff; Richard A. Phillips; Paul M. Sagar; Jean‐Baptiste Sallée; Ben Schreiber; David R. Thompson; et al. (Global Change Biology, 2021)
Ocean circulation connects geographically distinct ecosystems across a wide range of spatial and temporal scales via exchanges of physical and biogeochemical properties. Remote oceanographic processes can be especially important for ecosystems in the Southern Ocean, where the Antarctic Circumpolar Current transports properties across ocean basins through both advection and mixing. Recent tracking studies have indicated the existence of two large‐scale, open ocean habitats in the Southern Ocean used by grey petrels ( Procellaria cinerea ) from two populations (i.e., Kerguelen and Antipodes islands) during their nonbreeding season for extended periods during austral summer (i.e., October to February). In this work, we use a novel combination of large‐scale oceanographic observations, surface drifter data, satellite‐derived primary productivity, numerical adjoint sensitivity experiments, and output from a biogeochemical state estimate to examine local and remote influences on these grey petrel habitats. Our aim is to understand the oceanographic features that control these isolated foraging areas and to evaluate their ecological value as oligotrophic open ocean habitats. We estimate the minimum local primary productivity required to support these populations to be much

The Toxicology Investigators Consortium 2020 Annual Report - Meghan B. Spyres; Kim Aldy; Lynn A Farrugia; A. Min Kang; Jennifer S. Love; Sharan L. Campleman; Shao Li; Alexandra Amaducci; Evan Schwarz; Paul M. Wax; Jeffery Brent; J. Acciani; et al. (Journal of Medical Toxicology, 2021)

A dry future for the Everglades favors invasive herpetofauna - Hunter J. Howell; Giacomo L. Delgado; Alyssa C. Wood; Leila M. Thompson; Eric A. Cline; Christopher A. Searcy (Biological Invasions, 2021)

Differential household vulnerability to climatic and non-climatic stressors in semi-arid areas of Mali, West Africa - Alcade C. Segnon; Edmond Totin; Robert B. Zougmoré; Jourdain C. Lokossou; Mary Thompson-Hall; Benjamin O. Ofori; Enoch G. Achigan-Dako; Christopher Gordon (Climate and Development, 2021)

Genetic analyses of gynecological disease identify genetic relationships between uterine fibroids and endometrial cancer, and a novel endometrial cancer genetic risk region at the WNT4 1p36.12 locus - Pik Fang Kho; Sally Mortlock; Frederic Amant; Daniela Annibali; Katie Ashton; John Attia; Paul L. Auer; Matthias W. Beckmann; Amanda Black; Louise Brinton; Daniel D. Buchanan; Stephen J. Chanock; et al. (Human Genetics, 2021)

State of the California Current 2019–2020: Back to the Future With Marine Heatwaves? - Edward D. Weber; Toby D. Auth; Simone Baumann-Pickering; Timothy R. Baumgartner; Eric P. Bjorkstedt; Steven J. Bograd; Brian J. Burke; José L. Cadena-Ramírez; Elizabeth A. Daly; Martin de la Cruz; Heidi Dewar; John C. Field; et al. (Frontiers in Marine Science, 2021)
The California Current System (CCS) has experienced large fluctuations in environmental conditions in recent years that have dramatically affected the biological community. Here we synthesize remotely sensed, hydrographic, and biological survey data from throughout the CCS in 2019–2020 to evaluate how recent changes in environmental conditions have affected community dynamics at multiple trophic levels. A marine heatwave formed in the north Pacific in 2019 and reached the second greatest area ever recorded by the end of summer 2020. However, high atmospheric pressure in early 2020 drove relatively strong Ekman-driven coastal upwelling in the northern portion of the CCS and warm temperature anomalies remained far offshore. Upwelling and cooler temperatures in the northern CCS created relatively productive conditions in which the biomass of lipid-rich copepod species increased, adult krill size increased, and several seabird species experienced positive reproductive success. Despite these conditions, the composition of the fish community in the northern CCS remained a mixture of both warm- and cool-water-associated species. In the southern CCS, ocean temperatures remained above average for the seventh consecutive year. Abundances of juvenile fish species associated with productive conditions were relatively low, and the ichthyoplankton community was dominated by a mixture of oceanic warm-water and cosmopolitan species. Seabird species associated with warm water also occurred at greater densities than cool-water species in the southern CCS. The population of northern anchovy, which has been resurgent since 2017, continued to provide an important forage base for piscivorous fishes, offshore colonies of seabirds, and marine mammals throughout the CCS. Coastal upwelling in the north, and a longer-term trend in warming in the south, appeared to be controlling the community to a much greater extent than the marine heatwave itself.

Arbuscular mycorrhizal fungi acted synergistically with Bradyrhizobium sp. to improve nodulation, nitrogen fixation, plant growth and seed yield of mung bean (Vigna radiata) but increased the population density of the root-lesion nematode Pratylenchus thornei - Elaine C. Gough; Kirsty J. Owen; Rebecca S. Zwart; John P. Thompson (Plant and Soil, 2021)

Genome sequence of Vibrio fluvialis 362.3 isolated from coral Mussismilia braziliensis reveals genes related to marine environment adaptation - Livia M. R. Vidal; Aline R. P. Gonçalves; Tainá M. Venas; Gizele D. Garcia; Diogo A. Tschoeke; Fabiano L. Thompson; Cristiane C. Thompson (Archives of Microbiology, 2021)

Host recognition by Rhinocyllus conicus of floral scents from invasive and threatened thistles - Ikju Park; David C. Thompson (Biological Invasions, 2021)

SNAPSHOT USA 2019: a coordinated national camera trap survey of the United States - Michael V. Cove; Roland Kays; Helen Bontrager; Claire Bresnan; Monica Lasky; Taylor Frerichs; Renee Klann; Thomas E. Lee; Seth C. Crockett; Anthony P. Crupi; Katherine C. B. Weiss; Helen Rowe; et al. (Ecology, 2021)
With the accelerating pace of global change, it is imperative that we obtain rapid inventories of the status and distribution of wildlife for ecological inferences and conservation planning. To address this challenge, we launched the SNAPSHOT USA project, a collaborative survey of terrestrial wildlife populations using camera traps across the United States. For our first annual survey, we compiled data across all 50 states during a 14‐week period (17 August–24 November of 2019). We sampled wildlife at 1,509 camera trap sites from 110 camera trap arrays covering 12 different ecoregions across four development zones. This effort resulted in 166,036 unique detections of 83 species of mammals and 17 species of birds. All images were processed through the Smithsonian’s eMammal camera trap data repository and included an expert review phase to ensure taxonomic accuracy of data, resulting in each picture being reviewed at least twice. The results represent a timely and standardized camera trap survey of the United States. All of the 2019 survey data are made available herein. We are currently repeating surveys in fall 2020, opening up the opportunity to other institutions and cooperators to expand coverage of all the urban–wild gradients and ecophysiographic regions of the country. Future data will be available as the database is updated at eMammal.si.edu/snapshot‐usa, as will future data paper submissions. These data will be useful for local and macroecological research including the examination of community assembly, effects of environmental and anthropogenic landscape variables, effects of fragmentation and extinction debt dynamics, as well as species‐specific population dynamics and conservation action plans. There are no copyright restrictions; please cite this paper when using the data for publication.

Coordinating Global Multi-Site Studies of Military-Relevant Traumatic Brain Injury: Opportunities, Challenges, and Harmonization Guidelines - David F Tate; Emily L Dennis; John T Adams; Maheen M Adamson; Heather G Belanger; Erin D Bigler; Heather C Bouchard; Alexandra L Clark; Lisa M Delano-Wood; Seth G Disner; Blessen C Eapen; Carol E Franz; et al. (Brain Imaging and Behavior, 2021)

Challenges and opportunities for neuroimaging in young patients with traumatic brain injury: a coordinated effort towards advancing discovery from the ENIGMA pediatric moderate/severe TBI group - Emily L Dennis; Karen Caeyenberghs; Robert F Asarnow; Talin Babikian; Brenda Bartnik-Olson; Erin D Bigler; Anthony Figaji; Christopher C Giza; Naomi J Goodrich-Hunsaker; Cooper B Hodges; Kristen R Hoskinson; Marsh Königs; et al. (Brain Imaging and Behavior, 2021)

The ENIGMA sports injury working group:– an international collaboration to further our understanding of sport-related brain injury - Inga K. Koerte; Carrie Esopenko; Sidney R. Hinds; Martha E. Shenton; Elena M. Bonke; Jeffrey J. Bazarian; Kevin C. Bickart; Erin D. Bigler; Sylvain Bouix; Thomas A. Buckley; Meeryo C. Choe; Paul S. Echlin; et al. (Brain Imaging and Behavior, 2021)
Sport-related brain injury is very common, and the potential long-term effects include a wide range of neurological and psychiatric symptoms, and potentially neurodegeneration. Around the globe, researchers are conducting neuroimaging studies on primarily homogenous samples of athletes. However, neuroimaging studies are expensive and time consuming, and thus current findings from studies of sport-related brain injury are often limited by small sample sizes. Further, current studies apply a variety of neuroimaging techniques and analysis tools which limit comparability among studies. The ENIGMA Sports Injury working group aims to provide a platform for data sharing and collaborative data analysis thereby leveraging existing data and expertise. By harmonizing data from a large number of studies from around the globe, we will work towards reproducibility of previously published findings and towards addressing important research questions with regard to diagnosis, prognosis, and efficacy of treatment for sport-related brain injury. Moreover, the ENIGMA Sports Injury working group is committed to providing recommendations for future prospective data acquisition to enhance data quality and scientific rigor.

Overview of PAX gene family: analysis of human tissue-specific variant expression and involvement in human disease - Brian Thompson; Emily A. Davidson; Wei Liu; Daniel W. Nebert; Elspeth A. Bruford; Hongyu Zhao; Emmanouil T. Dermitzakis; David C. Thompson; Vasilis Vasiliou (Human Genetics, 2021)

Muricauda brasiliensis sp. nov., isolated from a mat-forming cyanobacterial culture - Carla Simone Vizzotto; Julianna Peixoto; Stefan Joshua Green; Fabyano Alvares C. Lopes; Marcelo Henrique S. Ramada; Osmindo R. Pires Júnior; Otávio Henrique B. Pinto; Marcos Rogério Tótola; Fabiano Lopes Thompson; Ricardo Henrique Krüger (Brazilian Journal of Microbiology, 2021)

Approaches to land snail shell bead manufacture in the Early Holocene of Malawi - Jennifer M. Miller; Hannah M. Keller; Claire Heckel; Potiphar M. Kaliba; Jessica C. Thompson (Archaeological and Anthropological Sciences, 2021)
Shell disc beads are important archeological indicators of social communication and exchange networks. There has been substantial research on ostrich eggshell (OES) beads, but little is known about the manufacture or chronology of similar beads from land snail shells (LSS). LSS beads are associated with Holocene hunter-gatherers in Africa, though direct dates are limited to the Iron Age, and there are no images or descriptions of the manufacturing sequence. Here, we combine experimental and archeological data to resolve the chronology, operational chains, and material properties of LSS bead manufacture. We then recommend and apply a modified OES production sequence to three Later Stone Age assemblages from the Kasitu Valley of northern Malawi (Hora 1, Mazinga 1, and Kadawonda 1). At these sites, LSS shows an unexpectedly high proportion of Pathway 2 manufacture (disc shaping prior to perforation), in direct contrast with known OES bead manufacture. Application of red color occurred at all stages of manufacture, albeit inconsistently. Production of finished beads involved substantial removal of material from preforms to create the final product. Finally, we report the earliest evidence for LSS bead manufacture with two directly dated preforms (~ 9500 cal BP), showing that the origins of LSS beadmaking do precede the Iron Age.

Cephalopods habitat and trophic ecology: historical data using snares penguin as biological sampler - H. R. Guímaro; D. R. Thompson; V. H. Paiva; F. R. Ceia; D. M. Cunningham; P. J. Moors; J. C. Xavier (Polar Biology, 2021)

Territoriality and condition of chevron butterflyfish (Chaetodon trifascialis) with varying coral cover on the great barrier reef, Australia - Cassandra A. Thompson; Andrew S. Hoey; Stefano R. Montanari; Vanessa Messmer; Peter C. Doll; Morgan S. Pratchett (Environmental Biology of Fishes, 2021)

Vibrio tetraodonis sp. nov.: genomic insights on the secondary metabolites repertoire - Gustavo P. R. Azevedo; Hannah K. Mattsson; Grasiele R. Lopes; Livia Vidal; Mariana Campeão; Luciane A. Chimetto Tonon; Gizele D. Garcia; Diogo A. Tschoeke; Bruno S. Silva; Koko Otsuki; Bruno Gomez-Gil; Jean Swings; et al. (Archives of Microbiology, 2021)

A global analysis of complexity–biodiversity relationships on marine artificial structures - Elisabeth M. A. Strain; Peter D. Steinberg; Maria Vozzo; Emma L. Johnston; Marco Abbiati; Moises A. Aguilera; Laura Airoldi; J. David Aguirre; Gail Ashton; Maritina Bernardi; Paul Brooks; Benny K. K. Chan; et al. (Global Ecology and Biogeography, 2021)
Aim Topographic complexity is widely accepted as a key driver of biodiversity, but at the patch‐scale, complexity–biodiversity relationships may vary spatially and temporally according to the environmental stressors complexity mitigates, and the species richness and identity of potential colonists. Using a manipulative experiment, we assessed spatial variation in patch‐scale effects of complexity on intertidal biodiversity. Location 27 sites within 14 estuaries/bays distributed globally. Time period 2015–2017. Major taxa studied Functional groups of algae, sessile and mobile invertebrates. Methods Concrete tiles of differing complexity (flat; 2.5‐cm or 5‐cm complex) were affixed at low–high intertidal elevation on coastal defence structures, and the richness and abundance of the colonizing taxa were quantified after 12 months. Results The patch‐scale effects of complexity varied spatially and among functional groups. Complexity had neutral to positive effects on total, invertebrate and algal taxa richness, and invertebrate abundances. However, effects on the abundance of algae ranged from positive to negative, depending on location and functional group. The tidal elevation at which tiles were placed accounted for some variation. The total and invertebrate richness were greater at low or mid than at high intertidal elevations. Latitude was also an important source of spatial variation, with the effects of complexity on total richness and mobile mollusc abundance greatest at lower latitudes, whilst the cover of sessile invertebrates and sessile molluscs responded most strongly to complexity at higher latitudes. Conclusions After 12 months, patch‐scale relationships between biodiversity and habitat complexity were not universally positive. Instead, the relationship varied among functional groups and according to local abiotic and biotic conditions. This result challenges the assumption that effects of complexity on biodiversity are universally positive. The variable effect of complexity has ramifications for community and applied ecology, including eco‐engineering and restoration that seek to bolster biodiversity through the addition of complexity.

Assessment of Nitrogen Fixation by Mungbean Genotypes in Different Soil Textures Using 15N Natural Abundance Method - Andre A. Diatta; Wade E. Thomason; Ozzie Abaye; Thomas L. Thompson; Martin L. Battaglia; Larry J. Vaughan; Mamadou Lo; Jose F. D. C. L. Filho (Journal of Soil Science and Plant Nutrition, 2020)

A new genomic taxonomy system for the Synechococcus collective - Vinícius W. Salazar; Diogo A. Tschoeke; Jean Swings; Carlos A. Cosenza; Marta Mattoso; Cristiane C. Thompson; Fabiano L. Thompson (Environmental Microbiology, 2020)
Summary Cyanobacteria of the genus Synechococcus are major contributors to global primary productivity and are found in a wide range of aquatic ecosystems. This Synechococcus collective (SC) is metabolically diverse, with some lineages thriving in polar and nutrient‐rich locations and others in tropical or riverine waters. Although many studies have discussed the ecology and evolution of the SC, there is a paucity of knowledge on its taxonomic structure. Thus, we present a new taxonomic classification framework for the SC based on recent advances in microbial genomic taxonomy. Phylogenomic analyses of 1085 cyanobacterial genomes demonstrate that organisms classified as Synechococcus are polyphyletic at the order rank. The SC is classified into 15 genera, which are placed into five distinct orders within the phylum Cyanobacteria: (i) Synechococcales ( Cyanobium , Inmanicoccus , Lacustricoccus gen. Nov., Parasynechococcus , Pseudosynechococcus , Regnicoccus , Synechospongium gen. nov., Synechococcus and Vulcanococcus ); (ii) Cyanobacteriales ( Limnothrix ); (iii) Leptococcales ( Brevicoccus and Leptococcus ); (iv) Thermosynechococcales ( Stenotopis and Thermosynechococcus ) and (v) Neosynechococcales ( Neosynechococcus ). The newly proposed classification is consistent with habitat distribution patterns (seawater, freshwater, brackish and thermal environments) and reflects the ecological and evolutionary relationships of the SC.

NEOTROPICAL CARNIVORES: a data set on carnivore distribution in the Neotropics - Mariana Nagy‐Reis; Júlia Emi de Faria Oshima; Claudia Zukeran Kanda; Francesca Belem Lopes Palmeira; Fabiano Rodrigues de Melo; Ronaldo Gonçalves Morato; Lilian Bonjorne; Marcelo Magioli; Caroline Leuchtenberger; Fabio Rohe; Frederico Gemesio Lemos; Felipe Martello; et al. (Ecology, 2020)
Mammalian carnivores are considered a key group in maintaining ecological health and can indicate potential ecological integrity in landscapes where they occur. Carnivores also hold high conservation value and their habitat requirements can guide management and conservation plans. The order Carnivora has 84 species from 8 families in the Neotropical region: Canidae; Felidae; Mephitidae; Mustelidae; Otariidae; Phocidae; Procyonidae; and Ursidae. Herein, we include published and unpublished data on native terrestrial Neotropical carnivores (Canidae; Felidae; Mephitidae; Mustelidae; Procyonidae; and Ursidae). NEOTROPICAL CARNIVORES is a publicly available data set that includes 99,605 data entries from 35,511 unique georeferenced coordinates. Detection/non‐detection and quantitative data were obtained from 1818 to 2018 by researchers, governmental agencies, non‐governmental organizations, and private consultants. Data were collected using several methods including camera trapping, museum collections, roadkill, line transect, and opportunistic records. Literature (peer‐reviewed and grey literature) from Portuguese, Spanish and English were incorporated in this compilation. Most of the data set consists of detection data entries (n = 79,343; 79.7%) but also includes non‐detection data (n = 20,262; 20.3%). Of those, 43.3% also include count data (n = 43,151). The information available in NEOTROPICAL CARNIVORES will contribute to macroecological, ecological, and conservation questions in multiple spatio‐temporal perspectives. As carnivores play key roles in trophic interactions, a better understanding of their distribution and habitat requirements are essential to establish conservation management plans and safeguard the future ecological health of Neotropical ecosystems. Our data paper, combined with other large‐scale data sets, has great potential to clarify species distribution and related ecological processes within the Neotropics. There are no copyright restrictions and no restriction for using data from this data paper, as long as the data paper is cited as the source of the information used. We also request that users inform us of how they intend to use the data.

NEOTROPICAL ALIEN MAMMALS: a data set of occurrence and abundance of alien mammals in the Neotropics - Clarissa Alves da Rosa; Bruno R. Ribeiro; Vanesa Bejarano; Fernando Henrique Puertas; Adriana Bocchiglieri; Adriana Loeser dos Santos Barbosa; Adriano Garcia Chiarello; Adriano Pereira Paglia; Adriele Aparecida Pereira; Adryelle Francisca de Souza Moreira; Agnis Cristiane de Souza; Aiesca Pellegrin; et al. (Ecology, 2020)
Biological invasion is one of the main threats to native biodiversity. For a species to become invasive, it must be voluntarily or involuntarily introduced by humans into a nonnative habitat. Mammals were among first taxa to be introduced worldwide for game, meat, and labor, yet the number of species introduced in the Neotropics remains unknown. In this data set, we make available occurrence and abundance data on mammal species that (1) transposed a geographical barrier and (2) were voluntarily or involuntarily introduced by humans into the Neotropics. Our data set is composed of 73,738 historical and current georeferenced records on alien mammal species of which around 96% correspond to occurrence data on 77 species belonging to eight orders and 26 families. Data cover 26 continental countries in the Neotropics, ranging from Mexico and its frontier regions (southern Florida and coastal‐central Florida in the southeast United States) to Argentina, Paraguay, Chile, and Uruguay, and the 13 countries of Caribbean islands. Our data set also includes neotropical species (e.g., Callithrix sp., Myocastor coypus , Nasua nasua) considered alien in particular areas of Neotropics. The most numerous species in terms of records are from Bos sp. ( n = 37,782), Sus scrofa ( n = 6,730), and Canis familiaris ( n = 10,084); 17 species were represented by only one record (e.g., S yncerus caffer, Cervus timorensis, Cervus unicolor, Canis latrans ). Primates have the highest number of species in the data set ( n = 20 species), partly because of uncertainties regarding taxonomic identification of the genera Callithrix, which includes the species Callithrix aurita, Callithrix flaviceps, Callithrix geoffroyi, Callithrix jacchus, Callithrix kuhlii, Callithrix penicillata , and their hybrids. This unique data set will be a valuable source of information on invasion risk assessments, biodiversity redistribution and conservation‐related research. There are no copyright restrictions. Please cite this data paper when using the data in publications. We also request that researchers and teachers inform us on how they are using the data.

Temporal pattern of offspring release and degree of parental investment in two viviparous asterinid sea stars with an overview of matrotrophy and offspring size variation in echinoderms that care for their offspring - M. S. R. Khan; C. M. Whittington; M. B. Thompson; M. Byrne (Invertebrate Reproduction & Development, 2020)

The Toxicology Investigators Consortium Case Registry—the 2019 Annual Report - Meghan B. Spyres; Lynn A. Farrugia; A. Min Kang; Kim Aldy; Diane P. Calello; Sharan L. Campleman; Shao Li; Gillian A Beauchamp; Timothy Wiegand; Paul M. Wax; Jeffery Brent; P. A. Akpunonu; et al. (Journal of Medical Toxicology, 2020)

Rapid screening of marine bacterial symbionts using MALDI-TOF MS - Livia M. R. Vidal; Tainá M. Venas; Aline R. P. Gonçalves; Hannah K. Mattsson; Raphael V. P. Silva; Maria S. Nóbrega; Gustavo P. R. Azevedo; Gizele D. Garcia; Diogo A. Tschoeke; Verônica V. Vieira; Fabiano L. Thompson; Cristiane C. Thompson (Archives of Microbiology, 2020)

Callitrichid responses to dead and dying infants: the effects of paternal bonding and cause of death - Cynthia L. Thompson; Rebecca Hrit; Leonardo C. O. Melo; Christopher J. Vinyard; Kimberly N. Bottenberg; Maria A. B. de Oliveira (Primates, 2020)

Learning to be an interdisciplinary researcher: incorporating training about dispositional and epistemological differences into graduate student environmental science teams - David C. Gosselin; Kate Thompson; Deana Pennington; Shirley Vincent (Journal of Environmental Studies and Sciences, 2020)

Use of Environmental DNA to Detect Grass Carp Spawning Events - Cari-Ann Hayer; Michael F. Bayless; Amy George; Nathan Thompson; Catherine A. Richter; Duane C. Chapman (Fishes, 2020)
The timing and location of spawning events are important data for managers seeking to control invasive grass carp populations. Ichthyoplankton tows for grass carp eggs and larvae can be used to detect spawning events; however, these samples can be highly debris-laden, and are expensive and laborious to process. An alternative method, environmental DNA (eDNA) technology, has proven effective in determining the presence of aquatic species. The objectives of this project were to assess the use of eDNA collections and quantitative eDNA analysis to assess the potential spawning of grass carp in five reservoir tributaries, and to compare those results to the more traditional method of ichthyoplankton tows. Grass carp eDNA was detected in 56% of sampling occasions and was detected in all five rivers. Concentrations of grass carp eDNA were orders of magnitude higher in June, corresponding to elevated discharge and egg presence. Grass carp environmental DNA flux (copies/h) was lower when no eggs were present and was higher when velocities and discharge increased and eggs were present. There was a positive relationship between grass carp eDNA flux and egg flux. Our results support the further development of eDNA analysis as a method to detect the spawning events of grass carp or other rheophilic spawners.

A Brief Observation of Endangered Coquerel’s Sifaka (Propithecus coquereli) Feeding on Red Mangrove (Rhizophora mucronata) Vegetation in a Mangrove Environment, Northwest Madagascar - C. Chell; M. E. Corral; I. Grant; C. J. Laskai; H. Gough; S. D. Rakotomalala; S. J. Ward; C. Thompson (International Journal of Primatology, 2020)

Effects of body size on estimation of mammalian area requirements - Michael J. Noonan; Christen H. Fleming; Marlee A. Tucker; Roland Kays; Autumn‐Lynn Harrison; Margaret C. Crofoot; Briana Abrahms; Susan C. Alberts; Abdullahi H. Ali; Jeanne Altmann; Pamela Castro Antunes; Nina Attias; et al. (Conservation Biology, 2020)
Accurately quantifying species’ area requirements is a prerequisite for effective area‐based conservation. This typically involves collecting tracking data on species of interest and then conducting home‐range analyses. Problematically, autocorrelation in tracking data can result in space needs being severely underestimated. Based on the previous work, we hypothesized the magnitude of underestimation varies with body mass, a relationship that could have serious conservation implications. To evaluate this hypothesis for terrestrial mammals, we estimated home‐range areas with global positioning system (GPS) locations from 757 individuals across 61 globally distributed mammalian species with body masses ranging from 0.4 to 4000 kg. We then applied block cross‐validation to quantify bias in empirical home‐range estimates. Area requirements of mammals 1, meaning the scaling of the relationship changed substantially at the upper end of the mass spectrum.

Uncertainty assessment in river flow projections for Ethiopia’s Upper Awash Basin using multiple GCMs and hydrological models - Wilson C. H. Chan; Julian R. Thompson; Richard G. Taylor; Alistair E. Nay; Tenalem Ayenew; Alan M. MacDonald; Martin C. Todd (Hydrological Sciences Journal, 2020)

Differential responses of heather and red grouse to long-term spatio-temporal variation in sheep grazing - Sonja C. Ludwig; Nicholas J. Aebischer; Michael Richardson; Staffan Roos; Des B. A. Thompson; Jeremy D. Wilson; David Baines (Biodiversity and Conservation, 2020)

Caveolin and lipid domains–close companions in managing cellular pathways - Jody V. Vykoukal; Johannes F. Fahrmann; Timothy C. Thompson (Cancer and Metastasis Reviews, 2020)

Tyre wear particles: an abundant yet widely unreported microplastic? - Lydia J. Knight; Florence N. F. Parker-Jurd; Maya Al-Sid-Cheikh; Richard C. Thompson (Environmental Science and Pollution Research, 2020)

Weather underground: Subsurface hydrologic processes mediate tree vulnerability to extreme climatic drought - Blair C. McLaughlin; Rachel Blakey; Andrew P. Weitz; Xue Feng; Brittni J. Brown; David D. Ackerly; Todd E. Dawson; Sally E. Thompson (Global Change Biology, 2020)
Drought extent and severity have increased and are predicted to continue to increase in many parts of the world. Understanding tree vulnerability to drought at both individual and species levels is key to ongoing forest management and preparation for future transitions in community composition. The influence of subsurface hydrologic processes is particularly important in water‐limited ecosystems, and is an under‐studied aspect of tree drought vulnerability. With California's 2013–2016 extraordinary drought as a natural experiment, we studied four co‐occurring woodland tree species, blue oak ( Quercus douglasii ), valley oak ( Quercus lobata ), gray pine ( Pinus sabiniana ), and California juniper ( Juniperus californica ), examining drought vulnerability as a function of climate, lithology and hydrology using regional aerial dieback surveys and site‐scale field surveys. We found that in addition to climatic drought severity (i.e., rainfall), subsurface processes explained variation in drought vulnerability within and across species at both scales. Regionally for blue oak, severity of dieback was related to the bedrock lithology, with higher mortality on igneous and metamorphic substrates, and to regional reductions in groundwater. At the site scale, access to deep subsurface water, evidenced by stem water stable isotope composition, was related to canopy condition across all species. Along hillslope gradients, channel locations supported similar environments in terms of water stress across a wide climatic gradient, indicating that subsurface hydrology mediates species’ experience of drought, and that areas associated with persistent access to subsurface hydrologic resources may provide important refugia at species’ xeric range edges. Despite this persistent overall influence of the subsurface environment, individual species showed markedly different response patterns. We argue that hydrologic niche segregation can be a useful lens through which to interpret these differences in vulnerability to climatic drought and climate change.

Design catalogue for eco-engineering of coastal artificial structures: a multifunctional approach for stakeholders and end-users - Kathryn A. O’Shaughnessy; Stephen J. Hawkins; Ally J. Evans; Mick E. Hanley; Paul Lunt; Richard C. Thompson; Robert A. Francis; Simon P. G. Hoggart; Pippa J. Moore; Gregorio Iglesias; David Simmonds; James Ducker; et al. (Urban Ecosystems, 2020)
Coastal urbanisation, energy extraction, food production, shipping and transportation have led to the global proliferation of artificial structures within the coastal and marine environments (sensu “ocean sprawl”), with subsequent loss of natural habitats and biodiversity. To mitigate and compensate impacts of ocean sprawl, the practice of eco-engineering of artificial structures has been developed over the past decade. Eco-engineering aims to create sustainable ecosystems that integrate human society with the natural environment for the benefit of both. The science of eco-engineering has grown markedly, yet synthesis of research into a user-friendly and practitioner-focused format is lacking. Feedback from stakeholders has repeatedly stated that a “photo user guide” or “manual” covering the range of eco-engineering options available for artificial structures would be beneficial. However, a detailed and structured “user guide” for eco-engineering in coastal and marine environments is not yet possible; therefore we present an accessible review and catalogue of trialled eco-engineering options and a summary of guidance for a range of different structures tailored for stakeholders and end-users as the first step towards a structured manual. This work can thus serve as a potential template for future eco-engineering guides. Here we provide suggestions for potential eco-engineering designs to enhance biodiversity and ecosystem functioning and services of coastal artificial structures with the following structures covered: (1) rock revetment, breakwaters and groynes composed of armour stones or concrete units; (2) vertical and sloping seawalls; (3) over-water structures (i.e., piers) and associated support structures; and (4) tidal river walls.

Emergence of an evolutionary innovation: Gene expression differences associated with the transition between oviparity and viviparity - Charles S. P. Foster; Michael B. Thompson; James U. Van Dyke; Matthew C. Brandley; Camilla M. Whittington (Molecular Ecology, 2020)
Our understanding of the evolution of complex biological traits is greatly advanced by examining taxa with intermediate phenotypes. The transition from oviparity (egg‐laying) to viviparity (live‐bearing) has occurred independently in many animal lineages, but there are few phenotypic intermediates. The lizard Saiphos equalis exhibits bimodal reproduction, with some viviparous populations, and other oviparous populations with long egg‐retention, a rare trait where most of embryonic development occurs inside the mother prior to late ovipositioning. We posit that oviparous S. equalis represent an intermediate form between “true” oviparity and viviparity. We used transcriptomics to compare uterine gene expression in these two phenotypes, and provide a molecular model for the genetic control and evolution of reproductive mode. Many genes are differentially expressed throughout the reproductive cycle of both phenotypes, which have clearly different gene expression profiles overall. The differentially expressed genes within oviparous and viviparous individuals have broadly similar biological functions putatively important for sustaining embryos, including uterine remodelling, respiratory gas and water exchange, and immune regulation. These functional similarities indicate either that long egg‐retention is an exaptation for viviparity, or might reflect parallel evolution of similar gravidity‐related changes in gene expression in long egg‐retention oviparity. In contrast, gene expression changes across the reproductive cycle of long egg‐retaining oviparous S. equalis are dramatically different from those of “true” oviparous skinks (such as Lampropholis guichenoti ), supporting our assertion that oviparous S. equalis exhibit an intermediate phenotype between “true” oviparity and viviparity.

Extreme temperature events will drive coral decline in the Coral Triangle - Lisa C. McManus; Vítor V. Vasconcelos; Simon A. Levin; Diane M. Thompson; Joan A. Kleypas; Frederic S. Castruccio; Enrique N. Curchitser; James R. Watson (Global Change Biology, 2020)
In light of rapid environmental change, quantifying the contribution of regional‐ and local‐scale drivers of coral persistence is necessary to characterize fully the resilience of coral reef systems. To assess multiscale responses to thermal perturbation of corals in the Coral Triangle (CT), we developed a spatially explicit metacommunity model with coral–algal competition, including seasonal larval dispersal and external spatiotemporal forcing. We tested coral sensitivity in 2,083 reefs across the CT region and surrounding areas under potential future temperature regimes, with and without interannual climate variability, exploring a range of 0.5–2.0°C overall increase in temperature in the system by 2054. We found that among future projections, reef survival probability and mean percent coral cover over time were largely determined by the presence or absence of interannual sea surface temperature (SST) extremes as well as absolute temperature increase. Overall, reefs that experienced SST time series that were filtered to remove interannual variability had approximately double the chance of survival than reefs subjected to unfiltered SST. By the end of the forecast period, the inclusion of thermal anomalies was equivalent to an increase of at least 0.5°C in SST projections without anomalies. Change in percent coral cover varied widely across the region within temperature scenarios, with some reefs experiencing local extinction while others remaining relatively unchanged. Sink strength and current thermal stress threshold were found to be significant drivers of these patterns, highlighting the importance of processes that underlie larval connectivity and bleaching sensitivity in coral networks.

Ketamine induces immediate and delayed alterations of OCD-like behavior - Summer L. Thompson; Amanda C. Welch; Julia Iourinets; Stephanie C. Dulawa (Psychopharmacology, 2020)

mGluR5 Allosteric Modulation Promotes Neurorecovery in a 6-OHDA-Toxicant Model of Parkinson’s Disease - Kyle Farmer; Khaled S. Abd-Elrahman; Alexa Derksen; Elyn M. Rowe; Ashley M. Thompson; Christopher A. Rudyk; Natalie A. Prowse; Zachary Dwyer; Samantha C. Bureau; Teresa Fortin; Stephen S.G. Ferguson; Shawn Hayley (Molecular Neurobiology, 2020)

Insights on the genetic repertoire of the coral Mussismilia braziliensis endosymbiont Symbiodinium - Arthur W. Silva Lima; Luciana Leomil; Louisi Oliveira; Tooba Varasteh; Janelle R. Thompson; Mónica Medina; Cristiane C. Thompson; Fabiano L. Thompson (Symbiosis, 2020)

Fast‐start escape performance across temperature and salinity gradients in mummichog Fundulus heteroclitus - David C. Collar; Jessica S. Thompson; Tyler C. Ralston; Trevor J. Hobbs (Journal of Fish Biology, 2020)
Fast‐start predator‐escape performance of mummichogs Fundulus heteroclitus was tested across field‐informed variation in temperature (24, 30 and 36°C) and salinity (2, 12 and 32 ppt). Performance was similar across temperatures and salinities when fish were allowed to acclimate to these conditions. However, when mummichogs experienced acute temperature changes, performance exhibited thermal dependence in two contrasting ways. Fast‐start turning rates and linear speeds varied directly with the temperature at which the manoeuvre was executed, but these aspects of performance varied inversely with acclimation temperature, with cool‐acclimated fish exhibiting faster starts across test temperatures. Temperature effects were consistent across salinities. These results suggest that while mummichogs increase performance with acute temperature increases, long‐term rises in sea temperature may cause these fish to become more susceptible to predation during abrupt cooling events, such as when storm events flood shallow water estuaries with cool rainwater.

Enterovibrio baiacu sp. nov. - Gustavo P. R. Azevedo; Hannah K. Mattsson; Luciana R. Appolinario; Gabriela Calegario; Luciana Leomil; Juline M. Walter; Mariana Campeão; Luciane A. Chimetto Tonon; Ana Paula B. Moreira; Livia Vidal; Verônica V. Vieira; Koko Otsuki; et al. (Current Microbiology, 2020)

TRY plant trait database – enhanced coverage and open access - Jens Kattge; Gerhard Bönisch; Sandra Díaz; Sandra Lavorel; Iain Colin Prentice; Paul Leadley; Susanne Tautenhahn; Gijsbert D. A. Werner; Tuomas Aakala; Mehdi Abedi; Alicia T. R. Acosta; George C. Adamidis; et al. (Global Change Biology, 2020)
Plant traits—the morphological, anatomical, physiological, biochemical and phenological characteristics of plants—determine how plants respond to environmental factors, affect other trophic levels, and influence ecosystem properties and their benefits and detriments to people. Plant trait data thus represent the basis for a vast area of research spanning from evolutionary biology, community and functional ecology, to biodiversity conservation, ecosystem and landscape management, restoration, biogeography and earth system modelling. Since its foundation in 2007, the TRY database of plant traits has grown continuously. It now provides unprecedented data coverage under an open access data policy and is the main plant trait database used by the research community worldwide. Increasingly, the TRY database also supports new frontiers of trait‐based plant research, including the identification of data gaps and the subsequent mobilization or measurement of new data. To support this development, in this article we evaluate the extent of the trait data compiled in TRY and analyse emerging patterns of data coverage and representativeness. Best species coverage is achieved for categorical traits—almost complete coverage for ‘plant growth form’. However, most traits relevant for ecology and vegetation modelling are characterized by continuous intraspecific variation and trait–environmental relationships. These traits have to be measured on individual plants in their respective environment. Despite unprecedented data coverage, we observe a humbling lack of completeness and representativeness of these continuous traits in many aspects. We, therefore, conclude that reducing data gaps and biases in the TRY database remains a key challenge and requires a coordinated approach to data mobilization and trait measurements. This can only be achieved in collaboration with other initiatives.

Temporal population variability in local forest communities has mixed effects on tree species richness across a latitudinal gradient - Tak Fung; Ryan A. Chisholm; Kristina Anderson‐Teixeira; Norm Bourg; Warren Y. Brockelman; Sarayudh Bunyavejchewin; Chia‐Hao Chang‐Yang; Rutuja Chitra‐Tarak; George Chuyong; Richard Condit; Handanakere S. Dattaraja; Stuart J. Davies; et al. (Ecology Letters, 2020)
Among the local processes that determine species diversity in ecological communities, fluctuation‐dependent mechanisms that are mediated by temporal variability in the abundances of species populations have received significant attention. Higher temporal variability in the abundances of species populations can increase the strength of temporal niche partitioning but can also increase the risk of species extinctions, such that the net effect on species coexistence is not clear. We quantified this temporal population variability for tree species in 21 large forest plots and found much greater variability for higher latitude plots with fewer tree species. A fitted mechanistic model showed that among the forest plots, the net effect of temporal population variability on tree species coexistence was usually negative, but sometimes positive or negligible. Therefore, our results suggest that temporal variability in the abundances of species populations has no clear negative or positive contribution to the latitudinal gradient in tree species richness.

Nitrogen provisioned and recycled by cover crops in monoculture and mixture across two organic farms - Ashley A. Holmes; Ashley A. Thompson; Sarah T. Lovell; Maria B. Villamil; Anthony C. Yannarell; Jeffrey O. Dawson; Sam E. Wortman (Nutrient Cycling in Agroecosystems, 2019)

Vortioxetine reverses medial prefrontal cortex-mediated cognitive deficits in male rats induced by castration as a model of androgen deprivation therapy for prostate cancer - Alexandra M. Sharp; Suphada Lertphinyowong; Samantha S. Yee; Denisse Paredes; Jonathan Gelfond; Teresa L. Johnson-Pais; Robin J. Leach; Michael Liss; April L. Risinger; Anna C. Sullivan; Ian M. Thompson; David A. Morilak (Psychopharmacology, 2019)

Geochemical characteristics of magnetite in Longqiao skarn iron deposit in the Middle-Lower Yangtze Metallogenic Belt, Eastern China - Yinan Liu; Yu Fan; Taofa Zhou; Xin Xiao; Noel C White; Jay Thompson; Haolan Hong; Lejun Zhang (Mineralium Deposita, 2019)

Access Matting Reduces Mixedgrass Prairie Soil and Vegetation Responses to Industrial Disturbance - F. Najafi; K. A. Thompson; C. N. Carlyle; S. A. Quideau; E. W. Bork (Environmental Management, 2019)

A resting state fMRI analysis pipeline for pooling inference across diverse cohorts: an ENIGMA rs-fMRI protocol - Bhim M. Adhikari; Neda Jahanshad; Dinesh Shukla; Jessica Turner; Dominik Grotegerd; Udo Dannlowski; Harald Kugel; Jennifer Engelen; Bruno Dietsche; Axel Krug; Tilo Kircher; Els Fieremans; et al. (Brain Imaging and Behavior, 2019)

Genomics detects population structure within and between ocean basins in a circumpolar seabird: The white‐chinned petrel - Kalinka Rexer‐Huber; Andrew J. Veale; Paulo Catry; Yves Cherel; Ludovic Dutoit; Yasmin Foster; John C. McEwan; Graham C. Parker; Richard A. Phillips; Peter G. Ryan; Andrew J. Stanworth; Tracey van Stijn; et al. (Molecular Ecology, 2019)
The Southern Ocean represents a continuous stretch of circumpolar marine habitat, but the potential physical and ecological drivers of evolutionary genetic differentiation across this vast ecosystem remain unclear. We tested for genetic structure across the full circumpolar range of the white‐chinned petrel ( Procellaria aequinoctialis ) to unravel the potential drivers of population differentiation and test alternative population differentiation hypotheses. Following range‐wide comprehensive sampling, we applied genomic (genotyping‐by‐sequencing or GBS; 60,709 loci) and standard mitochondrial‐marker approaches (cytochrome b and first domain of control region) to quantify genetic diversity within and among island populations, test for isolation by distance, and quantify the number of genetic clusters using neutral and outlier (non‐neutral) loci. Our results supported the multi‐region hypothesis, with a range of analyses showing clear three‐region genetic population structure, split by ocean basin, within two evolutionary units. The most significant differentiation between these regions confirmed previous work distinguishing New Zealand and nominate subspecies. Although there was little evidence of structure within the island groups of the Indian or Atlantic oceans, a small set of highly‐discriminatory outlier loci could assign petrels to ocean basin and potentially to island group, though the latter needs further verification. Genomic data hold the key to revealing substantial regional genetic structure within wide‐ranging circumpolar species previously assumed to be panmictic.

Identification of a novel species of Eimeria Schneider, 1875 from the woylie, Bettongia penicillata Gray (Diprotodontia: Potoroidae) and the genetic characterisation of three Eimeria spp. from other potoroid marsupials - Amy S. Northover; Sarah Keatley; Aileen D. Elliot; Russell P. Hobbs; Rongchang Yang; Alan J. Lymbery; Stephanie S. Godfrey; Adrian F. Wayne; R. C. Andrew Thompson (Systematic Parasitology, 2019)

Toward the Integrated Marine Debris Observing System - Nikolai Maximenko; Paolo Corradi; Kara Lavender Law; Erik Van Sebille; Shungudzemwoyo P. Garaba; Richard Stephen Lampitt; Francois Galgani; Victor Martinez-Vicente; Lonneke Goddijn-Murphy; Joana Mira Veiga; Richard C. Thompson; Christophe Maes; et al. (Frontiers in Marine Science, 2019)

SMART Cables for Observing the Global Ocean: Science and Implementation - Bruce M. Howe; Brian K. Arbic; Jérome Aucan; Christopher R. Barnes; Nigel Bayliff; Nathan Becker; Rhett Butler; Laurie Doyle; Shane Elipot; Gregory C. Johnson; Felix Landerer; Stephen Lentz; et al. (Frontiers in Marine Science, 2019)

Uses for humanised mouse models in precision medicine for neurodegenerative disease - Remya R. Nair; Silvia Corrochano; Samanta Gasco; Charlotte Tibbit; David Thompson; Cheryl Maduro; Zeinab Ali; Pietro Fratta; Abraham Acevedo Arozena; Thomas J. Cunningham; Elizabeth M. C. Fisher (Mammalian Genome, 2019)
Neurodegenerative disease encompasses a wide range of disorders afflicting the central and peripheral nervous systems and is a major unmet biomedical need of our time. There are very limited treatments, and no cures, for most of these diseases, including Alzheimer’s Disease, Parkinson's Disease, Huntington Disease, and Motor Neuron Diseases. Mouse and other animal models provide hope by analysing them to understand pathogenic mechanisms, to identify drug targets, and to develop gene therapies and stem cell therapies. However, despite many decades of research, virtually no new treatments have reached the clinic. Increasingly, it is apparent that human heterogeneity within clinically defined neurodegenerative disorders, and between patients with the same genetic mutations, significantly impacts disease presentation and, potentially, therapeutic efficacy. Therefore, stratifying patients according to genetics, lifestyle, disease presentation, ethnicity, and other parameters may hold the key to bringing effective therapies from the bench to the clinic. Here, we discuss genetic and cellular humanised mouse models, and how they help in defining the genetic and environmental parameters associated with neurodegenerative disease, and so help in developing effective precision medicine strategies for future healthcare.

Emotional real-world scenes impact visual search - Robert C. A. Bendall; Aisha Mohamed; Catherine Thompson (Cognitive Processing, 2019)

Constraining Southern Ocean Air-Sea-Ice Fluxes Through Enhanced Observations - Sebastiaan Swart; Sarah T. Gille; Bruno Delille; Simon Josey; Matthew Mazloff; Louise Newman; Andrew F. Thompson; Jim Thomson; Brian Ward; Marcel D. du Plessis; Elizabeth C. Kent; James Girton; et al. (Frontiers in Marine Science, 2019)

Exploration of Shared Genetic Architecture Between Subcortical Brain Volumes and Anorexia Nervosa - E. Walton; D. Hibar; Z. Yilmaz; N. Jahanshad; J. Cheung; V.-L. Batury; J. Seitz; C. M. Bulik; P. M. Thompson; Stefan Ehrlich (Molecular Neurobiology, 2019)

Macroinvertebrate diversity and rarity in non-glacial Alpine streams - R. Alther; C. Thompson; B. Lods-Crozet; C. T. Robinson (Aquatic Sciences, 2019)

Spatial resilience of the Great Barrier Reef under cumulative disturbance impacts - Camille Mellin; Samuel Matthews; Kenneth R.N. Anthony; Stuart C. Brown; M. Julian Caley; Kerryn A. Johns; Kate Osborne; Marjetta Puotinen; Angus Thompson; Nicholas H. Wolff; Damien A. Fordham; M. Aaron MacNeil (Global Change Biology, 2019)
In the face of increasing cumulative effects from human and natural disturbances, sustaining coral reefs will require a deeper understanding of the drivers of coral resilience in space and time. Here we develop a high‐resolution, spatially explicit model of coral dynamics on Australia's Great Barrier Reef (GBR). Our model accounts for biological, ecological and environmental processes, as well as spatial variation in water quality and the cumulative effects of coral diseases, bleaching, outbreaks of crown‐of‐thorns starfish ( Acanthaster cf. solaris ), and tropical cyclones. Our projections reconstruct coral cover trajectories between 1996 and 2017 over a total reef area of 14,780 km 2 , predicting a mean annual coral loss of −0.67%/year mostly due to the impact of cyclones, followed by starfish outbreaks and coral bleaching. Coral growth rate was the highest for outer shelf coral communities characterized by digitate and tabulate Acropora spp. and exposed to low seasonal variations in salinity and sea surface temperature, and the lowest for inner‐shelf communities exposed to reduced water quality. We show that coral resilience (defined as the net effect of resistance and recovery following disturbance) was negatively related to the frequency of river plume conditions, and to reef accessibility to a lesser extent. Surprisingly, reef resilience was substantially lower within no‐take marine protected areas, however this difference was mostly driven by the effect of water quality. Our model provides a new validated, spatially explicit platform for identifying the reefs that face the greatest risk of biodiversity loss, and those that have the highest chances to persist under increasing disturbance regimes.

NEOTROPICAL XENARTHRANS: a data set of occurrence of xenarthran species in the Neotropics - Paloma Marques Santos; Adriana Bocchiglieri; Adriano Garcia Chiarello; Adriano Pereira Paglia; Adryelle Moreira; Agnis Cristiane de Souza; Agustin Manuel Abba; Agustin Paviolo; Ailin Gatica; Akyllan Zoppi Medeiro; Alan Nilo Costa; Alberto Gonzalez Gallina; et al. (Ecology, 2019)
Xenarthrans—anteaters, sloths, and armadillos—have essential functions for ecosystem maintenance, such as insect control and nutrient cycling, playing key roles as ecosystem engineers. Because of habitat loss and fragmentation, hunting pressure, and conflicts with domestic dogs, these species have been threatened locally, regionally, or even across their full distribution ranges. The Neotropics harbor 21 species of armadillos, 10 anteaters, and 6 sloths. Our data set includes the families Chlamyphoridae (13), Dasypodidae (7), Myrmecophagidae (3), Bradypodidae (4), and Megalonychidae (2). We have no occurrence data on Dasypus pilosus (Dasypodidae). Regarding Cyclopedidae, until recently, only one species was recognized, but new genetic studies have revealed that the group is represented by seven species. In this data paper, we compiled a total of 42,528 records of 31 species, represented by occurrence and quantitative data, totaling 24,847 unique georeferenced records. The geographic range is from the southern United States, Mexico, and Caribbean countries at the northern portion of the Neotropics, to the austral distribution in Argentina, Paraguay, Chile, and Uruguay. Regarding anteaters, Myrmecophaga tridactyla has the most records ( n = 5,941), and Cyclopes sp. have the fewest ( n = 240). The armadillo species with the most data is Dasypus novemcinctus ( n = 11,588), and the fewest data are recorded for Calyptophractus retusus ( n = 33). With regard to sloth species, Bradypus variegatus has the most records ( n = 962), and Bradypus pygmaeus has the fewest ( n = 12). Our main objective with Neotropical Xenarthrans is to make occurrence and quantitative data available to facilitate more ecological research, particularly if we integrate the xenarthran data with other data sets of Neotropical Series that will become available very soon (i.e., Neotropical Carnivores, Neotropical Invasive Mammals, and Neotropical Hunters and Dogs). Therefore, studies on trophic cascades, hunting pressure, habitat loss, fragmentation effects, species invasion, and climate change effects will be possible with the Neotropical Xenarthrans data set. Please cite this data paper when using its data in publications. We also request that researchers and teachers inform us of how they are using these data.

Optimal investment to enable evolutionary rescue - Jaime Ashander; Lisa C. Thompson; James N. Sanchirico; Marissa L. Baskett (Theoretical Ecology, 2019)

Frequency content of environmental variability and extinction risk of age-structured populations: Chinook salmon (Oncorhynchus tschawytscha) as an example - D. Patrick Kilduff; Louis W. Botsford; Lisa C. Thompson (Theoretical Ecology, 2019)

Cotton (Gossypium hirsutum L.) mutants with reduced levels of palmitic acid (C16:0) in seed lipids - Corey N. Thompson; Bralie R. Hendon; Deepika Mishra; Jacob M. Rieff; Cindy C. Lowery; Kimberly C. Lambert; Travis W. Witt; Steven J. Oswalt; Efrem Bechere; C. Wayne Smith; Roy G. Cantrell; Brendan R. Kelly; et al. (Euphytica, 2019)

Metagenomic Analysis of the Whole Gut Microbiota in Brazilian Termitidae Termites Cornitermes cumulans, Cyrilliotermes strictinasus, Syntermes dirus, Nasutitermes jaraguae, Nasutitermes aquilinus, Grigiotermes bequaerti, and Orthognathotermes mirim - Maria B. Grieco; Fabyano A. C. Lopes; Louisi S. Oliveira; Diogo A. Tschoeke; Claudia C. Popov; Cristiane C. Thompson; Luna C. Gonçalves; Reginaldo Constantino; Orlando B. Martins; Ricardo H. Kruger; Wanderley de Souza; Fabiano L. Thompson (Current Microbiology, 2019)

Halomonas coralii sp. nov. Isolated from Mussismilia braziliensis - Livia M. R. Vidal; Aline Gonçalves; Tainá M. Venas; Mariana E. Campeão; Gabriela Calegario; Juline M. Walter; Bruno S. Silva; Gizele D. Garcia; Diogo A. Tschoeke; Jean Swings; Fabiano L. Thompson; Cristiane C. Thompson (Current Microbiology, 2019)

Cancer-associated mucins: role in immune modulation and metastasis - Rakesh Bhatia; Shailendra K. Gautam; Andrew Cannon; Christopher Thompson; Bradley R. Hall; Abhijit Aithal; Kasturi Banerjee; Maneesh Jain; Joyce C. Solheim; Sushil Kumar; Surinder K. Batra (Cancer and Metastasis Reviews, 2019)

Sorghum 3-Deoxyanthocyanidin Flavonoids Confer Resistance against Corn Leaf Aphid - Rupesh R. Kariyat; Iffa Gaffoor; Sampurna Sattar; Cullen W. Dixon; Nadia Frock; Juliet Moen; Consuelo M. De Moraes; Mark C. Mescher; Gary A. Thompson; Surinder Chopra (Journal of Chemical Ecology, 2019)

Imaging Spectroscopy for the Detection, Assessment and Monitoring of Natural and Anthropogenic Hazards - C. Ong; V. Carrère; S. Chabrillat; R. Clark; T. Hoefen; R. Kokaly; R. Marion; C. R. Souza Filho; G. Swayze; D. R. Thompson (Surveys in Geophysics, 2019)

Exposure to antibiotics in the first 24 months of life and neurocognitive outcomes at 11 years of age - R. F. Slykerman; C. Coomarasamy; K. Wickens; J. M. D. Thompson; T. V. Stanley; C. Barthow; J. Kang; J. Crane; E. A. Mitchell (Psychopharmacology, 2019)

Gut microbiome and brain functional connectivity in infants-a preliminary study focusing on the amygdala - Wei Gao; Andrew P. Salzwedel; Alexander L. Carlson; Kai Xia; M. Andrea Azcarate-Peril; Martin A. Styner; Amanda L. Thompson; Xiujuan Geng; Barbara D. Goldman; John H. Gilmore; Rebecca C. Knickmeyer (Psychopharmacology, 2019)

Airway Exposure to Modified Multi-walled Carbon Nanotubes Perturbs Cardiovascular Adenosinergic Signaling in Mice - Leslie C. Thompson; Nicole L. Sheehan; Dianne M. Walters; Robert M. Lust; Jared M. Brown; Christopher J. Wingard (Cardiovascular Toxicology, 2019)

Subcortical shape and neuropsychological function among U.S. service members with mild traumatic brain injury - David F. Tate; Benjamin S. C. Wade; Carmen S. Velez; Ann Marie Drennon; Jacob D. Bolzenius; Douglas B. Cooper; Jan E. Kennedy; Matthew W. Reid; Amy O. Bowles; Paul M. Thompson; Boris A. Gutman; Jeffrey D. Lewis; et al. (Brain Imaging and Behavior, 2019)

Can gypsy moth stand the heat? A reciprocal transplant experiment with an invasive forest pest across its southern range margin - Trevor M. Faske; Lily M. Thompson; Nana Banahene; Andi Levorse; Melisa Quiroga Herrera; Kayla Sherman; Sarah E. Timko; Banruo Yang; David R. Gray; Dylan Parry; Patrick C. Tobin; Andrew J. Eckert; et al. (Biological Invasions, 2019)

Molecular identification of Botryosphaeria dothidea as a fungal associate of the gall midge Asphondylia prosopidis on mesquite in the United States - Ikju Park; Soum Sanogo; Stephen F. Hanson; David C. Thompson (BioControl, 2019)

A catchment‐scale perspective of plastic pollution - Fredric M. Windsor; Isabelle Durance; Alice A. Horton; Richard C. Thompson; Charles R. Tyler; Steve J. Ormerod (Global Change Biology, 2019)
Plastic pollution is distributed across the globe, but compared with marine environments, there is only rudimentary understanding of the distribution and effects of plastics in other ecosystems. Here, we review the transport and effects of plastics across terrestrial, freshwater and marine environments. We focus on hydrological catchments as well‐defined landscape units that provide an integrating scale at which plastic pollution can be investigated and managed. Diverse processes are responsible for the observed ubiquity of plastic pollution, but sources, fluxes and sinks in river catchments are poorly quantified. Early indications are that rivers are hotspots of plastic pollution, supporting some of the highest recorded concentrations. River systems are also likely pivotal conduits for plastic transport among the terrestrial, floodplain, riparian, benthic and transitional ecosystems with which they connect. Although ecological effects of micro‐ and nanoplastics might arise through a variety of physical and chemical mechanisms, consensus and understanding of their nature, severity and scale are restricted. Furthermore, while individual‐level effects are often graphically represented in public media, knowledge of the extent and severity of the impacts of plastic at population, community and ecosystem levels is limited. Given the potential social, ecological and economic consequences, we call for more comprehensive investigations of plastic pollution in ecosystems to guide effective management action and risk assessment. This is reliant on (a) expanding research to quantify sources, sinks, fluxes and fates of plastics in catchments and transitional waters both independently as a major transport routes to marine ecosystems, (b) improving environmentally relevant dose–response relationships for different organisms and effect pathways, (c) scaling up from studies on individual organisms to populations and ecosystems, where individual effects are shown to cause harm and; (d) improving biomonitoring through developing ecologically relevant metrics based on contemporary plastic research.

Risk and dynamics of unprecedented hot months in South East China - Vikki Thompson; Nick J. Dunstone; Adam A. Scaife; Doug M. Smith; Steven C. Hardiman; Hong-Li Ren; Bo Lu; Stephen E. Belcher (Climate Dynamics, 2019)

International consensus criteria for diagnosing and staging hand–arm vibration syndrome - C. J. M. Poole; M. Bovenzi; T. Nilsson; I. J. Lawson; R. House; A. Thompson; S. Youakim (International Archives of Occupational and Environmental Health, 2019)

Drivers of species richness and abundance of marine macrophytes on shallow tropical reefs of north‐western Australia - Ylva S. Olsen; Lydiane Mattio; Andrea Zavala Perez; Russ C. Babcock; Damian Thompson; Michael D.E. Haywood; John Keesing; Gary A. Kendrick (Journal of Biogeography, 2019)
Aim Marine macrophytes are important components of tropical reefs that are influenced by environmental conditions and biotic interactions. Here, we aimed to identify the factors that shape macrophyte communities on shallow reefs in a region with limited anthropogenic impacts, but that is influenced by periodic disturbances from cyclones and marine heatwaves. Location Pilbara coast, Western Australia. Methods Macrophyte species richness and biomass were assessed at 75 shallow reefs along 300 km of shoreline in November 2013 and May 2014. The influence of 28 predictor variables including seascape descriptors, physico‐chemical variables, and herbivore abundances were evaluated using distance based linear models (Dist LM ), redundancy analyses (db RDA ), and full‐subsets multiple regressions. Results We identified 188 macrophyte species; 60% were Rhodophyta, whereas Phaeophyceae made up 67% of the biomass. Macrophyte assemblages did not show any broad‐scale patterns but a number of key drivers were identified, including sea surface temperature, salinity, and sediment uniformity. Two of the main predictors of macrophyte abundance and species richness were rugosity and coral cover rather than herbivory, unlike what has been demonstrated for many reefs globally. Availability of space therefore appears to be a major factor on these reefs and it is possible that macrophytes benefit from periodic disturbances as they can free up space through physical removal of organisms. Main conclusions Macrophyte assemblages along the Pilbara coast show no distinct large‐scale patterns; instead, local biotic and environmental drivers such as rugosity appear to be structuring assemblages. We propose that natural disturbance plays a key role on these shallow reefs by increasing substrate availability. Data on the long‐term community structure of macroalgae, in particular how communities respond to heatwaves and cyclones, would improve our ability to manage these reefs and predict potential “phase shifts” which can have severe ecological and economic consequences.

How the Comprehensive Cancer Control National Partnership shapes the public health workforce - Margaret M. Farrell; Kelsy M. Gibson; Angela Marler; Leslie Given; Aubrey Van Kirk Villalobos; Candace Deaton Maynard; Frank S. Bright; Ginny Thompson Kirklin; Truemenda C. Green; Melanie Ruhe; Julia Thorsness; Stephanie Weiss (Cancer Causes & Control, 2018)

Human Neural Stem Cell Extracellular Vesicles Improve Tissue and Functional Recovery in the Murine Thromboembolic Stroke Model - Robin L. Webb; Erin E. Kaiser; Shelley L. Scoville; Tyler A. Thompson; Sumbul Fatima; Chirayukumar Pandya; Karishma Sriram; Raymond L. Swetenburg; Kumar Vaibhav; Ali S. Arbab; Babak Baban; Krishnan M. Dhandapani; et al. (Translational Stroke Research, 2018)

Eastern rockhopper penguins Eudyptes filholi as biological samplers of juvenile and sub-adult cephalopods around Campbell Island, New Zealand - J. C. Xavier; Y. Cherel; F. R. Ceia; J. P. Queirós; B. Guimarães; R. Rosa; D. M. Cunningham; P. J. Moors; D. R. Thompson (Polar Biology, 2018)

Correction to: Down from the treetops: red langur (Presbytis rubicunda) terrestrial behavior - Susan M. Cheyne; Supiansyah; Adul; Claire J. Neale; Carolyn Thompson; Cara H. Wilcox; Yvette C. Ehlers Smith; David A. Ehlers Smith (Primates, 2018)

Down from the treetops: red langur (Presbytis rubicunda) terrestrial behavior - Susan M. Cheyne; Supiansyah; Adul; Claire J. Neale; Carolyn Thompson; Cara H. Wilcox; Yvette C. Ehlers Smith; David A. Ehlers Smith (Primates, 2018)

Marine Biotechnology in Brazil: Recent Developments and Its Potential for Innovation - Fabiano Thompson; Ricardo Krüger; Cristiane C. Thompson; Roberto G. S. Berlinck; Ricardo Coutinho; Melissa F. Landell; Mauro Pavão; Paulo A. S. Mourão; Ana Salles; Naiane Negri; Fabyano A. C. Lopes; Vitor Freire; et al. (Frontiers in Marine Science, 2018)

Description of Alteromonas abrolhosensis sp. nov., isolated from sea water of Abrolhos Bank, Brazil - Maria S. Nóbrega; Bruno S. Silva; Luciana Leomil; Diogo Antonio Tschoeke; Mariana E. Campeão; Gizele D. Garcia; Graciela A. Dias; Verônica V. Vieira; Cristiane C. Thompson; Fabiano L. Thompson (Antonie van Leeuwenhoek, 2018)

Front Cover - James A. Lutz; Tucker J. Furniss; Daniel J. Johnson; Stuart J. Davies; David Allen; Alfonso Alonso; Kristina J. Anderson‐Teixeira; Ana Andrade; Jennifer Baltzer; Kendall M. L. Becker; Erika M. Blomdahl; Norman A. Bourg; et al. (Global Ecology and Biogeography, 2018)

Global importance of large‐diameter trees - James A. Lutz; Tucker J. Furniss; Daniel J. Johnson; Stuart J. Davies; David Allen; Alfonso Alonso; Kristina J. Anderson‐Teixeira; Ana Andrade; Jennifer Baltzer; Kendall M. L. Becker; Erika M. Blomdahl; Norman A. Bourg; et al. (Global Ecology and Biogeography, 2018)
Aim To examine the contribution of large‐diameter trees to biomass, stand structure, and species richness across forest biomes. Location Global. Time period Early 21st century. Major taxa studied Woody plants. Methods We examined the contribution of large trees to forest density, richness and biomass using a global network of 48 large (from 2 to 60 ha) forest plots representing 5,601,473 stems across 9,298 species and 210 plant families. This contribution was assessed using three metrics: the largest 1% of trees ≥ 1 cm diameter at breast height (DBH), all trees ≥ 60 cm DBH, and those rank‐ordered largest trees that cumulatively comprise 50% of forest biomass. Results Averaged across these 48 forest plots, the largest 1% of trees ≥ 1 cm DBH comprised 50% of aboveground live biomass, with hectare‐scale standard deviation of 26%. Trees ≥ 60 cm DBH comprised 41% of aboveground live tree biomass. The size of the largest trees correlated with total forest biomass ( r 2 = .62, p r 2 = .45, p r 2 = .33, p r 2 = .17, p = .002). The concentration of biomass in the largest 1% of trees declined with increasing absolute latitude ( r 2 = .46, p r 2 = .31, p r 2 = .26, p Main conclusions Because large‐diameter trees constitute roughly half of the mature forest biomass worldwide, their dynamics and sensitivities to environmental change represent potentially large controls on global forest carbon cycling. We recommend managing forests for conservation of existing large‐diameter trees or those that can soon reach large diameters as a simple way to conserve and potentially enhance ecosystem services.

Jaguar movement database: a GPS‐based movement dataset of an apex predator in the Neotropics - Ronaldo G. Morato; Jeffrey J. Thompson; Agustin Paviolo; Jesus A. de La Torre; Fernando Lima; Roy T. McBride; Rogerio C. Paula; Laury Cullen; Leandro Silveira; Daniel L. Z. Kantek; Emiliano E. Ramalho; Louise Maranhão; et al. (Ecology, 2018)
The field of movement ecology has rapidly grown during the last decade, with important advancements in tracking devices and analytical tools that have provided unprecedented insights into where, when, and why species move across a landscape. Although there has been an increasing emphasis on making animal movement data publicly available, there has also been a conspicuous dearth in the availability of such data on large carnivores. Globally, large predators are of conservation concern. However, due to their secretive behavior and low densities, obtaining movement data on apex predators is expensive and logistically challenging. Consequently, the relatively small sample sizes typical of large carnivore movement studies may limit insights into the ecology and behavior of these elusive predators. The aim of this initiative is to make available to the conservation‐scientific community a dataset of 134,690 locations of jaguars ( Panthera onca ) collected from 117 individuals (54 males and 63 females) tracked by GPS technology. Individual jaguars were monitored in five different range countries representing a large portion of the species’ distribution. This dataset may be used to answer a variety of ecological questions including but not limited to: improved models of connectivity from local to continental scales; the use of natural or human‐modified landscapes by jaguars; movement behavior of jaguars in regions not represented in this dataset; intraspecific interactions; and predator‐prey interactions. In making our dataset publicly available, we hope to motivate other research groups to do the same in the near future. Specifically, we aim to help inform a better understanding of jaguar movement ecology with applications towards effective decision making and maximizing long‐term conservation efforts for this ecologically important species. There are no costs, copyright, or proprietary restrictions associated with this data set. When using this data set, please cite this article to recognize the effort involved in gathering and collating the data and the willingness of the authors to make it publicly available.

Rapid isolation of culturable microalgae from a tropical shallow lake system - Giovana O. Fistarol; Paulo I. Hargreaves; Juline M. Walter; Tatiana V. Viana; Piter D. F. Gomes; Caio Brito Lourenço; Carlos E. Rezende; Gustavo Gregoracci; Cintia Rua; Cristiane C. Thompson; Fabiano L. Thompson; Paulo S. Salomon (Journal of Applied Phycology, 2018)

Perspectives on the Great Amazon Reef: Extension, Biodiversity, and Threats - Ronaldo B. Francini-Filho; Nils E. Asp; Eduardo Siegle; John Hocevar; Kenneth Lowyck; Nilo D'Avila; Agnaldo A. Vasconcelos; Ricardo Baitelo; Carlos E. Rezende; Claudia Y. Omachi; Cristiane C. Thompson; Fabiano L. Thompson (Frontiers in Marine Science, 2018)

Ecological risk, demography and technological complexity in the Late Pleistocene of northern Malawi: implications for geographical patterning in the Middle Stone Age - Jessica C. Thompson; Alexander Mackay; Sheila Nightingale; David Wright; Jeong‐Heon Choi; Menno Welling; Hari Blackmore; Elizabeth Gomani‐Chindebvu (Journal of Quaternary Science, 2018)
The Late Pleistocene Middle Stone Age (MSA) record of Africa provides early examples of standardised stone tool production and complex manufacturing sequences, superficially implying a long‐term trend towards greater complexity in MSA technology at a continental scale. However, at this scale, spatial and temporal expressions of technological complexity are uneven. New lithic and chronometric data from the East–Central African record add further regional perspective to these patterns. Stone artefact assemblages from Karonga, northern, Malawi (92–22 ka), persistently lack the complexity demonstrated elsewhere in Africa at the same times, despite similar lithic raw materials. These new data provide an essential avenue for exploring hypotheses about the roles of environmental risk and demography in shaping the expression of MSA technology across the continent, not just at a local scale. When set within this framework, the simplicity of the Karonga MSA is best explained by its position in an environment that was persistently low in relative extrinsic subsistence risk. These results reinforce that motivations to invest in complex tools were variable through space and time, and that this variation, more than factors relating to behavioural capacity, may explain the patchy evidence for lithic complexity in the later MSA.

Genomic Attributes of Novel Symbiont Pseudovibrio brasiliensis sp. nov. Isolated From the Sponge Arenosclera brasiliensis - Adriana M. Fróes; Thamyres C. Freitas; Livia Vidal; Luciana R. Appolinario; Luciana Leomil; Tainá Venas; Mariana E. Campeão; Carlos J. F. Silva; Ana Paula B. Moreira; Roberto G. S. Berlinck; Fabiano L. Thompson; Cristiane C. Thompson (Frontiers in Marine Science, 2018)

Non-communicable chronic diseases and timely breast cancer screening among women of the Eastern Caribbean Health Outcomes Research Network (ECHORN) Cohort Study - K. H. Wang; T. A. Thompson; D. Galusha; H. Friedman; C. M. Nazario; M. Nunez; R. G. Maharaj; O. P. Adams; M. Nunez-Smith (Cancer Causes & Control, 2018)

Geographic variation in Sundew ( Drosera ) leaf colour: plant–plant interactions counteract expected effects of abiotic factors - Jonathan Millett; George W. Foot; Julia C. Thompson; Brita M. Svensson (Journal of Biogeography, 2018)
Aim To identify geographic patterns in leaf colour of roundleaved sundew ( Drosera rotundifolia ) growing on ombrotrophic (rain fed) bogs across Europe and establish the controls over these patterns. Location North‐west Europe. Taxon Angiosperms, Drosera rotundifolia . Methods We measured leaf colour of D. rotundifolia plants growing on 24 ombrotrophic bogs across north‐west Europe covering 26.4 degrees of longitude and 21.1 degrees of latitude. We measured the height and cover of co‐occurring vascular plant vegetation and the amount of incident light intercepted by the vegetation canopy. We determined the role of abiotic variables in controlling the patterns found. In a separate experimental study, we manipulated plant–plant interactions with D. rotundifolia by removing aboveground vascular plant vegetation and monitoring leaf colour over a single summer. Results Drosera rotundifolia leaf colour varied between bogs. Leaves were redder in northern latitudes and eastern longitudes, and in sites/plots with lower canopy influence, lower nutrient deposition, and a more continental climate. Canopy influence was greater on sites in southern latitudes, eastern longitudes, and with higher nutrient deposition, longer growing seasons and a more maritime climate. Nutrient deposition was higher at more southerly latitudes, eastern sites had a more continental climate, and southern and western sites had warmer and longer growing seasons. In the in situ experiment, leaves became more red when canopy light transmission was increased by removing vegetation, but not when shade net was subsequently added to reduce light transmission. Main Conclusion Geographic variation in Drosera rotundifolia leaf colour is strongly affected by its light environment, mediated by plant–plant interactions, but leaf colour is also affected by other abiotic factors. The relative importance of biotic and abiotic factors in determining geographic patterns in traits, and also species responses to environmental change, might depend on the growth form and competitive ability of a species.

Secondary resistance to tolvaptan in two patients with SIAD due to small cell lung cancer - A. Garrahy; A. M. Hannon; H. M. Zia-Ul-Hussnain; D. J. Williams; C. J. Thompson (European Journal of Clinical Pharmacology, 2018)

Simulation of the hydrological impacts of climate change on a restored floodplain - Julian R. Thompson; Honeyeh Iravani; Hannah M. Clilverd; Carl D. Sayer; Catherine M. Heppell; Jan C. Axmacher (Hydrological Sciences Journal, 2017)

Application of low‐frequency sonophoresis and reduction of antibiotics in the aquatic systems - C Cobo Labarca; J Radinger; V Schöning; R Ariav; R Jung; K D Thompson; W Kloas; K Knopf (Journal of Fish Diseases, 2017)
A major concern in aquaculture is the use of chemical therapeutics, such as antibiotics, because of their impact on the environment as well as on the fish product. As a potential tool for reducing antibiotic use, we tested the application of low‐frequency ultrasound as a method for enhancing antibiotic uptake. Rainbow trout juveniles ( Oncorhynchus mykiss) were exposed to two different concentrations of oxytetracycline ( OTC ), flumequine ( FLU ) and florfenicol ( FLO ), administered by bath after the application of ultrasound. After exposure, concentrations of these substances were measured in the liver and blood of treated fish. Results showed that the ultrasound treatment can significantly increase the uptake for all three antibiotics. The uptake of OTC for example, in fish exposed to an OTC concentration of 20 mg L −1 after prior treatment with ultrasound, was similar to the OTC concentrations in their liver and blood to fish exposed to 100 mg L −1 without sonication. For FLU and FLO , the use of ultrasound caused significant differences of uptake in the liver at high antibiotic concentrations. This suggests that the use of ultrasound as a technique to deliver antibiotics to fish can ultimately reduce the amount of antibiotics discharged into the aquatic environment.

Outbreak of Cleidodiscus in juvenile black crappies ( Pomoxis nigromaculatus ) and bath treatment with praziquantel - C Bader; J Jesudoss Chelladurai; K Thompson; D Starling; M T Brewer (Journal of Fish Diseases, 2017)

Integrative Taxonomy of Amazon Reefs' Arenosclera spp.: A New Clade in the Haplosclerida (Demospongiae) - Camille V. Leal; Fernando C. Moraes; Adriana M. Fróes; Ana C. Soares; Louisi S. de Oliveira; Ana Paula B. Moreira; Fabiano L. Thompson; Eduardo Hajdu (Frontiers in Marine Science, 2017)

Human subcortical brain asymmetries in 15,847 people worldwide reveal effects of age and sex - Tulio Guadalupe; Samuel R. Mathias; Theo G. M. vanErp; Christopher D. Whelan; Marcel P. Zwiers; Yoshinari Abe; Lucija Abramovic; Ingrid Agartz; Ole A. Andreassen; Alejandro Arias-Vásquez; Benjamin S. Aribisala; Nicola J. Armstrong; et al. (Brain Imaging and Behavior, 2017)

Arbuscular mycorrhizas are present on Spitsbergen - K. K. Newsham; P. B. Eidesen; M. L. Davey; J. Axelsen; E. Courtecuisse; C. Flintrop; A. G. Johansson; M. Kiepert; S.E. Larsen; K. E. Lorberau; M. Maurset; J. McQuilkin; et al. (Mycorrhiza, 2017)

Facing a wicked problem with optimism: issues and priorities for coral conservation in Hong Kong - N. N. Duprey; S. E. McIlroy; T. P. T. Ng; P. D. Thompson; T. Kim; J. C. Y. Wong; C. W. M. Wong; S. M. Husa; S. M. H. Li; G. A. Williams; D. M. Baker (Biodiversity and Conservation, 2017)

Natriuretic peptide activation of extracellular regulated kinase 1/2 (ERK1/2) pathway by particulate guanylyl cyclases in GH3 somatolactotropes - Kim C. Jonas; Timothy Melrose; Iain R. Thompson; Gary F. Baxter; Victoria J. Lipscomb; Stijn J. Niessen; Charlotte Lawson; Craig A. McArdle; Mark S. Roberson; Imelda M. McGonnell; Caroline P. Wheeler-Jones; Robert C. Fowkes (Cell and Tissue Research, 2017)

High occurrence of jellyfish predation by black‐browed and Campbell albatross identified by DNA metabarcoding - Julie C. McInnes; Rachael Alderman; Mary‐Anne Lea; Ben Raymond; Bruce E. Deagle; Richard A. Phillips; Andrew Stanworth; David R. Thompson; Paulo Catry; Henri Weimerskirch; Cristián G. Suazo; Michaël Gras; et al. (Molecular Ecology, 2017)
Gelatinous zooplankton are a large component of the animal biomass in all marine environments, but are considered to be uncommon in the diet of most marine top predators. However, the diets of key predator groups like seabirds have conventionally been assessed from stomach content analyses, which cannot detect most gelatinous prey. As marine top predators are used to identify changes in the overall species composition of marine ecosystems, such biases in dietary assessment may impact our detection of important ecosystem regime shifts. We investigated albatross diet using DNA metabarcoding of scats to assess the prevalence of gelatinous zooplankton consumption by two albatross species, one of which is used as an indicator species for ecosystem monitoring. Black‐browed and Campbell albatross scats were collected from eight breeding colonies covering the circumpolar range of these birds over two consecutive breeding seasons. Fish was the main dietary item at most sites; however, cnidarian DNA , primarily from scyphozoan jellyfish, was present in 42% of samples overall and up to 80% of samples at some sites. Jellyfish was detected during all breeding stages and consumed by adults and chicks. Trawl fishery catches of jellyfish near the Falkland Islands indicate a similar frequency of jellyfish occurrence in albatross diets in years of high and low jellyfish availability, suggesting jellyfish consumption may be selective rather than opportunistic. Warmer oceans and overfishing of finfish are predicted to favour jellyfish population increases, and we demonstrate here that dietary DNA metabarcoding enables measurements of the contribution of gelatinous zooplankton to the diet of marine predators.

Distribution and abundance of cetaceans in a wind energy development area offshore of Massachusetts and Rhode Island - Kelsey M. Stone; Sarah M. Leiter; Robert D. Kenney; Brooke C. Wikgren; Jessica L. Thompson; Jessica K. D. Taylor; Scott D. Kraus (Journal of Coastal Conservation, 2017)

Hydrologic refugia, plants, and climate change - Blair C. McLaughlin; David D. Ackerly; P. Zion Klos; Jennifer Natali; Todd E. Dawson; Sally E. Thompson (Global Change Biology, 2017)
Climate, physical landscapes, and biota interact to generate heterogeneous hydrologic conditions in space and over time, which are reflected in spatial patterns of species distributions. As these species distributions respond to rapid climate change, microrefugia may support local species persistence in the face of deteriorating climatic suitability. Recent focus on temperature as a determinant of microrefugia insufficiently accounts for the importance of hydrologic processes and changing water availability with changing climate. Where water scarcity is a major limitation now or under future climates, hydrologic microrefugia are likely to prove essential for species persistence, particularly for sessile species and plants. Zones of high relative water availability – mesic microenvironments – are generated by a wide array of hydrologic processes, and may be loosely coupled to climatic processes and therefore buffered from climate change. Here, we review the mechanisms that generate mesic microenvironments and their likely robustness in the face of climate change. We argue that mesic microenvironments will act as species‐specific refugia only if the nature and space/time variability in water availability are compatible with the ecological requirements of a target species. We illustrate this argument with case studies drawn from California oak woodland ecosystems. We posit that identification of hydrologic refugia could form a cornerstone of climate‐cognizant conservation strategies, but that this would require improved understanding of climate change effects on key hydrologic processes, including frequently cryptic processes such as groundwater flow.

The Asia-Pacific’s role in the emerging solar geoengineering debate - Masahiro Sugiyama; Shinichiro Asayama; Atsushi Ishii; Takanobu Kosugi; John C. Moore; Jolene Lin; Penehuro F. Lefale; Wil Burns; Masatomo Fujiwara; Arunabha Ghosh; Joshua Horton; Atsushi Kurosawa; et al. (Climatic Change, 2017)

Erratum to: Older age at the completion of linear growth is associated with an increased risk of adult glioma - Rebecca B. Little; L. Burt Nabors; Jeffrey J. Olson; Zachary J. Thompson; Carrie M. Rozmeski; Renato V. LaRocca; Peter A. Forsyth; Reid C. Thompson; Robert A. Oster; Sajeel A. Chowdhary; Kathleen M. Egan (Cancer Causes & Control, 2017)

Older age at the completion of linear growth is associated with an increased risk of adult glioma - Rebecca B. Little; L. Burt Nabors; Jeffrey J. Olson; Zachary J. Thompson; Carrie M. Rozmeski; Renato V. LaRocca; Peter A. Forsyth; Reid C. Thompson; Robert A. Oster; Sajeel A. Chowdhary; Kathleen M. Egan (Cancer Causes & Control, 2017)

Tracking reveals limited interactions between Campbell Albatross and fisheries during the breeding season - Lisa A. Sztukowski; Mariëlle L. van Toor; Henri Weimerskirch; David R. Thompson; Leigh G. Torres; Paul M. Sagar; Peter A. Cotton; Stephen C. Votier (Journal of Ornithology, 2017)

Increased appendicularian zooplankton alter carbon cycling under warmer more acidified ocean conditions - Monika Winder; Jean‐Marie Bouquet; J. Rafael Bermúdez; Stella A. Berger; Thomas Hansen; Jay Brandes; Andrey F. Sazhin; Jens C. Nejstgaard; Ulf Båmstedt; Hans H. Jakobsen; Jörg Dutz; Marc E. Frischer; et al. (Limnology and Oceanography, 2017)
Anthropogenic atmospheric loading of CO 2 raises concerns about combined effects of increasing ocean temperature and acidification, on biological processes. In particular, the response of appendicularian zooplankton to climate change may have significant ecosystem implications as they can alter biogeochemical cycling compared to classical copepod dominated food webs. However, the response of appendicularians to multiple climate drivers and effect on carbon cycling are still not well understood. Here, we investigated how gelatinous zooplankton (appendicularians) affect carbon cycling of marine food webs under conditions predicted by future climate scenarios. Appendicularians performed well in warmer conditions and benefited from low pH levels, which in turn altered the direction of carbon flow. Increased appendicularians removed particles from the water column that might otherwise nourish copepods by increasing carbon transport to depth from continuous discarding of filtration houses and fecal pellets. This helps to remove CO 2 from the atmosphere, and may also have fisheries implications.

Microanatomical diversification of the zona pellucida in aplochelioid killifishes - A. W. Thompson; A. I. Furness; C. Stone; C. M. Rade; G. Ortí (Journal of Fish Biology, 2017)
This study investigates zona pellucida ( ZP ) ultrastructure in fertilized eggs of annual killifishes (suborder Aplocheiloidei), a group of highly specialized fishes that are able to survive desiccation for several weeks to months before they hatch. Little is known about ZP or chorionic ultrastructure sustaining these life‐history modes, so scanning electron microscopy ( SEM ) was used to describe this trait in a large number of aplocheiloids with a focus on the family Rivulidae and the genus Hypsolebias. New images of ZP ultrastructure for 52 aplocheiloid species are provided, more than doubling the number characterized thus far. The evolution of chorionic structure within this group is studied using these new data. Characters were coded into a morphological matrix and optimized onto a consensus phylogeny to assess phylogenetic signal and reconstruct ancestral character states. Although ZP characters seem highly homoplastic and exhibit a large amount of structural convergence among lineages, aplocheiloid killifishes have evolved a number of unique structures associated with the chorion. Some annual species seem to have lost long filaments because eggs are deposited in the soil instead of being adhered to aquatic plants.

Puffins reveal contrasting relationships between forage fish and ocean climate in the North Pacific - William J. Sydeman; John F. Piatt; Sarah Ann Thompson; Marisol García‐Reyes; Scott A. Hatch; Mayumi L. Arimitsu; Leslie Slater; Jeffrey C. Williams; Nora A. Rojek; Stephani G. Zador; Heather M. Renner (Fisheries Oceanography, 2017)
Long‐term studies of predator food habits (i.e., ‘predator‐based sampling’) are useful for identifying patterns of spatial and temporal variability of forage nekton in marine ecosystems. We investigated temporal changes in forage fish availability and relationships to ocean climate by analyzing diet composition of three puffin species (horned puffin Fratercula corniculata , tufted puffin Fratercula cirrhata , and rhinoceros auklet Cerorhinca monocerata ) from five sites in the North Pacific from 1978–2012. Dominant forage species included squids and hexagrammids in the western Aleutians, gadids and Pacific sand lance ( Ammodytes personatus ) in the eastern Aleutians and western Gulf of Alaska (GoA), and sand lance and capelin ( Mallotus villosus ) in the northern and eastern GoA. Interannual fluctuations in forage availability dominated variability in the western Aleutians, whereas lower‐frequency shifts in forage fish availability dominated elsewhere. We produced regional multivariate indicators of sand lance, capelin, and age‐0 gadid availability by combining data across species and sites using Principal Component Analysis, and related these indices to environmental factors including sea level pressure ( SPL ), winds, and sea surface temperature ( SST ). There was coherence in the availability of sand lance and capelin across the study area. Sand lance availability increased linearly with environmental conditions leading to warmer ocean temperatures, whereas capelin availability increased in a non‐linear manner when environmental changes led to lower ocean temperatures. Long‐term studies of puffin diet composition appear to be a promising tool for understanding the availability of these difficult‐to‐survey forage nekton in remote regions of the North Pacific.

Surface sensing and stress-signalling in Ulva and fouling diatoms – potential targets for antifouling: a review - Stephanie E. M. Thompson; Juliet C. Coates (Biofouling, 2017)

DNA Sequencing as a Tool to Monitor Marine Ecological Status - Kelly D. Goodwin; Luke R. Thompson; Bernardo Duarte; Tim Kahlke; Andrew R. Thompson; João C. Marques; Isabel Caçador (Frontiers in Marine Science, 2017)

White-chinned petrel population estimate, Disappointment Island (Auckland Islands) - Kalinka Rexer-Huber; Graham C. Parker; Paul M. Sagar; David R. Thompson (Polar Biology, 2017)

Genetic characterization of canine parvovirus type 2 subtypes in Maputo, Mozambique - J. Figueiredo; C. Miranda; R. Souto; E. Silva; J. Fafetine; G. Thompson (Archives of Microbiology, 2017)

Wildfire effects on physiological properties in conifers of central Idaho forests, USA - Matthew T. C. Thompson; Akihiro Koyama; Kathleen L. Kavanagh (Trees, 2017)

Spatial Pair-Copula Modeling of Grade in Ore Bodies: A Case Study - G. Nishani Musafer; M. Helen Thompson; E. Kozan; R. C. Wolff (Natural Resources Research, 2017)

A metamorphic mineral source for tungsten in the turbidite-hosted orogenic gold deposits of the Otago Schist, New Zealand - Ben J. Cave; Iain K. Pitcairn; Dave Craw; Ross R. Large; Jay M. Thompson; Sean C. Johnson (Mineralium Deposita, 2017)

Modeling abundance, growth, and health of the solitary coral Scolymia wellsi (Mussidae) in turbid SW Atlantic coral reefs - Ericka O. C. Coni; Camilo M. Ferreira; Pedro M. Meirelles; Rafael Menezes; Erika F. C. Santana; Ana Paula B. Moreira; Gilberto M. Amado-Filho; Beatrice P. Ferreira; Guilherme H. Pereira-Filho; Fabiano L. Thompson; Rodrigo L. Moura; Ronaldo B. Francini-Filho (Marine Biology, 2017)

Acrolein Inhalation Alters Myocardial Synchrony and Performance at and Below Exposure Concentrations that Cause Ventilatory Responses - Leslie C. Thompson; Allen D. Ledbetter; Najwa Haykal-Coates; Wayne E. Cascio; Mehdi S. Hazari; Aimen K. Farraj (Cardiovascular Toxicology, 2017)

Effects of life‐history requirements on the distribution of a threatened reptile - Denise M. Thompson; Day B. Ligon; Jason C. Patton; Monica Papeş (Conservation Biology, 2017)
Survival and reproduction are the two primary life‐history traits essential for species’ persistence; however, the environmental conditions that support each of these traits may not be the same. Despite this, reproductive requirements are seldom considered when estimating species’ potential distributions. We sought to examine potentially limiting environmental factors influencing the distribution of an oviparous reptile of conservation concern with respect to the species’ survival and reproduction and to assess the implications of the species’ predicted climatic constraints on current conservation practices. We used ecological niche modeling to predict the probability of environmental suitability for the alligator snapping turtle (Macrochelys temminckii). We built an annual climate model to examine survival and a nesting climate model to examine reproduction. We combined incubation temperature requirements, products of modeled soil temperature data, and our estimated distributions to determine whether embryonic development constrained the northern distribution of the species. Low annual precipitation constrained the western distribution of alligator snapping turtles, whereas the northern distribution was constrained by thermal requirements during embryonic development. Only a portion of the geographic range predicted to have a high probability of suitability for alligator snapping turtle survival was estimated to be capable of supporting successful embryonic development. Historic occurrence records suggest adult alligator snapping turtles can survive in regions with colder climes than those associated with consistent and successful production of offspring. Estimated egg‐incubation requirements indicated that current reintroductions at the northern edge of the species’ range are within reproductively viable environmental conditions. Our results highlight the importance of considering survival and reproduction when estimating species’ ecological niches, implicating conservation plans, and benefits of incorporating physiological data when evaluating species’ distributions.

Demography and ecology of southern right whales Eubalaena australis wintering at sub-Antarctic Campbell Island, New Zealand - Leigh G. Torres; Will Rayment; Carlos Olavarría; David R. Thompson; Brittany Graham; C. Scott Baker; Nathalie Patenaude; Sarah Jane Bury; Laura Boren; Graham Parker; Emma L. Carroll (Polar Biology, 2017)

Louis M. Herman 1930–2016 - Adam A. Pack; Elia Y. K. Herman; C. Scott Baker; Gordon B. Bauer; Phillip J. Clapham; Richard C. Connor; Alison S. Craig; Paul H. Forestell; Adam S. Frankel; Giuseppe Notarbartolo di Sciara; Matthias Hoffmann‐Kuhnt; Eduardo Mercado; et al. (Marine Mammal Science, 2017)

Proposal of fifteen new species of Parasynechococcus based on genomic, physiological and ecological features - F. H. Coutinho; B. E. Dutilh; C. C. Thompson; F. L. Thompson (Archives of Microbiology, 2016)

Microplastics in Seawater: Recommendations from the Marine Strategy Framework Directive Implementation Process - Jesus Gago; Francois Galgani; Thomas Maes; Richard C. Thompson (Frontiers in Marine Science, 2016)

Field Evaluation of Potato Genotypes for Resistance to Powdery Scab on Tubers and Root Gall Formation Caused by Spongospora subterranea - Francisco G. Bittara; Asunta L. Thompson; Neil C. Gudmestad; Gary A. Secor (American Journal of Potato Research, 2016)

Sheep grazing in the North Atlantic region: A long-term perspective on environmental sustainability - Louise C. Ross; Gunnar Austrheim; Leif-Jarle Asheim; Gunnar Bjarnason; Jon Feilberg; Anna Maria Fosaa; Alison J. Hester; Øystein Holand; Ingibjörg S. Jónsdóttir; Lis E. Mortensen; Atle Mysterud; Erla Olsen; et al. (Ambio, 2016)

Metaproteomics reveals metabolic transitions between healthy and diseased stony coral Mussismilia braziliensis - Gizele D. Garcia; Eidy de O. Santos; Gabriele V. Sousa; Russolina B. Zingali; Cristiane C. Thompson; Fabiano L. Thompson (Molecular Ecology, 2016)
Infectious diseases such as white plague syndrome ( WPS ) and black band disease ( BBD ) have caused massive coral loss worldwide. We performed a metaproteomic study on the Abrolhos coral Mussismilia braziliensis to define the types of proteins expressed in healthy corals compared to WPS ‐ and BBD ‐affected corals. A total of 6363 MS / MS spectra were identified as 361 different proteins. Healthy corals had a set of proteins that may be considered markers of holobiont homoeostasis, including tubulin, histone, Rab family, ribosomal, peridinin–chlorophyll a‐binding protein, F0F1‐type ATP synthase, alpha‐ iG protein, calmodulin and ADP ‐ribosylation factor. Cnidaria proteins found in healthy M. braziliensis were associated with Cnidaria – Symbiodinium endosymbiosis and included chaperones (hsp70, hsp90 and calreticulin), structural and membrane modelling proteins (actin) and proteins with functions related to intracellular vesicular traffic (Rab7 and ADP ‐ribosylation factor 1) and signal transduction (14‐3‐3 protein and calmodulin). WPS resulted in a clear shift in the predominance of proteins, from those related to aerobic nitrogen‐fixing bacteria (i.e. Rhizobiales, Sphingomonadales and Actinomycetales ) in healthy corals to those produced by facultative/anaerobic sulphate‐reducing bacteria (i.e. Enterobacteriales , Alteromonadales , Clostridiales and Bacteroidetes ) in WPS corals. BBD corals developed a diverse community dominated by cyanobacteria and sulphur cycle bacteria. Hsp60, hsp90 and adenosylhomocysteinase proteins were produced mainly by cyanobacteria in BBD corals, which is consistent with elevated oxidative stress in hydrogen sulphide‐ and cyanotoxin‐rich environments. This study demonstrates the usefulness of metaproteomics for gaining better comprehension of coral metabolic status in health and disease, especially in reef systems such as the Abrolhos that are suffering from the increase in global and local threatening events.

Genetic distinctiveness of the damselfly Coenagrion puella in North Africa: an overlooked and endangered taxon - Sónia Ferreira; Jean-Pierre Boudot; Mohamed El Haissoufi; Paulo Célio Alves; David J. Thompson; José Carlos Brito; Phillip C. Watts (Conservation Genetics, 2016)

Minimal residual disease in breast cancer: an overview of circulating and disseminated tumour cells - A. Tachtsidis; L. M. McInnes; N. Jacobsen; E. W. Thompson; C. M. Saunders (Clinical & Experimental Metastasis, 2016)

Material type and roughness influence structure of inter‐tidal communities on coastal defenses - Eva Cacabelos; Gustavo M. Martins; Richard Thompson; Afonso C. L. Prestes; José Manuel N. Azevedo; Ana I. Neto (Marine Ecology, 2016)
On a global scale, urbanization has resulted in substantial proportions of coasts being replaced by artificial structures such as marinas, breakwaters and seawalls. There is broad consensus that coastal defense structures are poor surrogates of the natural habitats that they replace. Here we investigated the effects of the type and roughness of materials used for the construction of artificial structures on the surrounding biota by comparing abundances and distribution of key inter‐tidal taxa between natural shores and coastal defenses. Lower abundances of gastropods and barnacles were found on artificial coastal defense structures (regardless of the material type). At small spatial scales, abundances of key taxa increased with increasing roughness. Our results suggest that the choice of materials used for the construction of coastal defense structures has little effect on community structure per se , but that enhanced roughness could make coastal defenses better surrogates of natural habitats by supporting assemblages that are more similar to those found on natural shores.

The association between habitual physical activity and cigarette cravings, and influence of smokers’ characteristics in disadvantaged smokers not ready to quit - M. Haasova; F. C. Warren; T. Thompson; M. Ussher; A. H. Taylor (Psychopharmacology, 2016)

Detecting grizzly bear use of ungulate carcasses using global positioning system telemetry and activity data - Michael R. Ebinger; Mark A. Haroldson; Frank T. van Manen; Cecily M. Costello; Daniel D. Bjornlie; Daniel J. Thompson; Kerry A. Gunther; Jennifer K. Fortin; Justin E. Teisberg; Shannon R. Pils; P. J. White; Steven L. Cain; et al. (Oecologia, 2016)

Erratum to: Description of Endozoicomonas arenosclerae sp. nov. using a genomic taxonomy approach - Luciana R. Appolinario; Diogo A. Tschoeke; Cintia P. J. Rua; Tainá Venas; Mariana E. Campeão; Gilda R. S. Amaral; Luciana Leomil; Louisi de Oliveira; Verônica Viana Vieira; Koko Otsuki; Jean Swings; Fabiano L. Thompson; et al. (Antonie van Leeuwenhoek, 2016)

Quantitative immunoenzymatic detection of viral encephalopathy and retinopathy virus (betanodavirus) in sea bass Dicentrarchus labrax - N Nuñez‐Ortiz; V Stocchi; A Toffan; F Pascoli; N Sood; F Buonocore; S Picchietti; C Papeschi; A R Taddei; K D Thompson; G Scapigliati (Journal of Fish Diseases, 2016)
Viral encephalopathy and retinopathy disease caused by betanodavirus, genus of the family Nodaviridae, affects marine, wild and farmed species including sea bass, one of the most important farmed species in Europe. This work describes a reliable and sensitive indirect ELISA assay to detect betanodavirus in biological samples using a polyclonal antiserum (pAb 283) against the 283/I09 virus strain, the most common red‐spotted grouper nervous necrosis virus ( RGNNV ) genotype in the Mediterranean area, and a capture‐based ELISA using a monoclonal antibody (mAb 4C3) specific to a common epitope present on the capsid protein. Using adsorbed, purified VER v preparation, the detection limit of indirect ELISA was 2 μg mL −1 (3 × 10 5 TCID 50 per mL), whereas for capture‐based ELISA, the sensitivity for the antigen in solution was 17 μg mL −1 (35 × 10 5 TCID 50 per mL). The capture‐based ELISA was employed to detect VER v in brain homogenates of in vivo infected sea bass and resulted positive in 22 of 32 samples, some of these with a high viral load estimates (about 1.1 × 10 8 TCID 50 per mL). The ELISA system we propose may be helpful in investigations where coupling of viral content in fish tissues with the presence of circulating VER v‐specific IgM is required, or for use in samples where PCR is difficult to perform.

The effects of increasing dietary levels of amino acid-supplemented soy protein concentrate and constant dietary supplementation of phosphorus on growth, composition and immune responses of juvenile Atlantic salmon (Salmo salar L.) - C. Metochis; V. O. Crampton; K. Ruohonen; J. G. Bell; A. Adams; K. D. Thompson (Fish Physiology and Biochemistry, 2016)

Highly heritable resistance to root-lesion nematode (Pratylenchus thornei) in Australian chickpea germplasm observed using an optimised glasshouse method and multi-environment trial analysis - M. S. Rodda; K. B. Hobson; C. R. Forknall; R. P. Daniel; J. P. Fanning; D. D. Pounsett; S. Simpfendorfer; K. J. Moore; K. J. Owen; J. G. Sheedy; J. P. Thompson; G. J. Hollaway; et al. (Australasian Plant Pathology, 2016)

The canalized parental roles of a Eudyptes penguin constrain provisioning and growth of chicks during nutritional stress - Kyle W. Morrison; Neil C. Morrison; Raymond M. Buchheit; Rob Dunn; Phil F. Battley; David R. Thompson (Behavioral Ecology and Sociobiology, 2016)

Insights from genome of Clostridium butyricum INCQS635 reveal mechanisms to convert complex sugars for biofuel production - Thiago Bruce; Fernanda Gomes Leite; Milene Miranda; Cristiane C. Thompson; Nei Pereira; Mariana Faber; Fabiano L. Thompson (Archives of Microbiology, 2016)

Description of Endozoicomonas arenosclerae sp. nov. using a genomic taxonomy approach - Luciana R. Appolinario; Diogo A. Tschoeke; Cintia P. J. Rua; Tainá Venas; Mariana E. Campeão; Gilda R. S. Amaral; Luciana Leomil; Louisi de Oliveira; Verônica Viana Vieira; Koko Otsuki; Jean Swings; Fabiano L. Thompson; et al. (Antonie van Leeuwenhoek, 2016)

The ecological impacts of marine debris: unraveling the demonstrated evidence from what is perceived - Chelsea M. Rochman; Mark Anthony Browne; A. J. Underwood; Jan A. van Franeker; Richard C. Thompson; Linda A. Amaral‐Zettler (Ecology, 2016)
Anthropogenic debris contaminates marine habitats globally, leading to several perceived ecological impacts. Here, we critically and systematically review the literature regarding impacts of debris from several scientific fields to understand the weight of evidence regarding the ecological impacts of marine debris. We quantified perceived and demonstrated impacts across several levels of biological organization that make up the ecosystem and found 366 perceived threats of debris across all levels. Two hundred and ninety‐six of these perceived threats were tested, 83% of which were demonstrated. The majority (82%) of demonstrated impacts were due to plastic, relative to other materials (e.g., metals, glass) and largely (89%) at suborganismal levels (e.g., molecular, cellular, tissue). The remaining impacts, demonstrated at higher levels of organization (i.e., death to individual organisms, changes in assemblages), were largely due to plastic marine debris (>1 mm; e.g., rope, straws, and fragments). Thus, we show evidence of ecological impacts from marine debris, but conclude that the quantity and quality of research requires improvement to allow the risk of ecological impacts of marine debris to be determined with precision. Still, our systematic review suggests that sufficient evidence exists for decision makers to begin to mitigate problematic plastic debris now, to avoid risk of irreversible harm.

Clinically effective OCD treatment prevents 5-HT1B receptor-induced repetitive behavior and striatal activation - Emily V. Ho; Summer L. Thompson; William R. Katzka; Mitra F. Sharifi; James A. Knowles; Stephanie C. Dulawa (Psychopharmacology, 2016)

Predictability of the Madden–Julian Oscillation index: seasonality and dependence on MJO phase - Eric C. J. Oliver; Keith R. Thompson (Climate Dynamics, 2016)

Plant biodiversity effects in reducing fluvial erosion are limited to low species richness - Daniel C. Allen; Bradley J. Cardinale; Theresa Wynn‐Thompson (Ecology, 2016)
It has been proposed that plant biodiversity may increase the erosion resistance of soils, yet direct evidence for any such relationship is lacking. We conducted a mesocosm experiment with eight species of riparian herbaceous plants, and found evidence that plant biodiversity significantly reduced fluvial erosion rates, with the eight‐species polyculture decreasing erosion by 23% relative to monocultures. Species richness effects were largest at low levels of species richness, with little increase between four and eight species. Our results suggest that plant biodiversity reduced erosion rates indirectly through positive effects on root length and number of root tips, and that interactions between legumes and non‐legumes were particularly important in producing biodiversity effects. Presumably, legumes increased root production of non‐legumes by increasing soil nitrogen availability due to their ability to fix atmospheric nitrogen. Our data suggest that a restoration project using species from different functional groups might provide the best insurance to maintain long‐term erosion resistance.

Sensitivity to Tuber Necrosis Caused by Potato Mop-Top Virus in Advanced Potato (Solanum tuberosum L.) Breeding Selections - O. Domfeh; A. L. Thompson; N. C. Gudmestad (American Journal of Potato Research, 2015)

Defining multiple, distinct, and shared spatiotemporal patterns of DNA replication and endoreduplication from 3D image analysis of developing maize (Zea mays L.) root tip nuclei - Hank W. Bass; Gregg G. Hoffman; Tae-Jin Lee; Emily E. Wear; Stacey R. Joseph; George C. Allen; Linda Hanley-Bowdoin; William F. Thompson (Plant Molecular Biology, 2015)

Diversity enhances carbon storage in tropical forests - L. Poorter; M. T. van der Sande; J. Thompson; E. J. M. M. Arets; A. Alarcón; J. Álvarez‐Sánchez; N. Ascarrunz; P. Balvanera; G. Barajas‐Guzmán; A. Boit; F. Bongers; F. A. Carvalho; et al. (Global Ecology and Biogeography, 2015)
Aim Tropical forests store 25% of global carbon and harbour 96% of the world's tree species, but it is not clear whether this high biodiversity matters for carbon storage. Few studies have teased apart the relative importance of forest attributes and environmental drivers for ecosystem functioning, and no such study exists for the tropics. Location Neotropics. Methods We relate aboveground biomass ( AGB ) to forest attributes (diversity and structure) and environmental drivers (annual rainfall and soil fertility) using data from 144,000 trees, 2050 forest plots and 59 forest sites. The sites span the complete latitudinal and climatic gradients in the lowland Neotropics, with rainfall ranging from 750 to 4350 mm year −1 . Relationships were analysed within forest sites at scales of 0.1 and 1 ha and across forest sites along large‐scale environmental gradients. We used a structural equation model to test the hypothesis that species richness, forest structural attributes and environmental drivers have independent, positive effects on AGB . Results Across sites, AGB was most strongly driven by rainfall, followed by average tree stem diameter and rarefied species richness, which all had positive effects on AGB . Our indicator of soil fertility (cation exchange capacity) had a negligible effect on AGB , perhaps because we used a global soil database. Taxonomic forest attributes (i.e. species richness, rarefied richness and Shannon diversity) had the strongest relationships with AGB at small spatial scales, where an additional species can still make a difference in terms of niche complementarity, while structural forest attributes (i.e. tree density and tree size) had strong relationships with AGB at all spatial scales. Main conclusions Biodiversity has an independent, positive effect on AGB and ecosystem functioning, not only in relatively simple temperate systems but also in structurally complex hyperdiverse tropical forests. Biodiversity conservation should therefore be a key component of the UN Reducing Emissions from Deforestation and Degradation strateg y.

Microbial and sponge loops modify fish production in phase‐shifting coral reefs - Cynthia B. Silveira; Arthur W. Silva‐Lima; Ronaldo B. Francini‐Filho; Jomar S.M. Marques; Marcelo G. Almeida; Cristiane C. Thompson; Carlos E. Rezende; Rodolfo Paranhos; Rodrigo L. Moura; Paulo S. Salomon; Fabiano L. Thompson (Environmental Microbiology, 2015)
Summary Shifts from coral to algae dominance of corals reefs have been correlated to fish biomass loss and increased microbial metabolism. Here we investigated reef benthic and planktonic primary production, benthic dissolved organic carbon ( DOC ) release and bacterial growth efficiency in the A brolhos B ank, S outh A tlantic. Benthic DOC release rates are higher while water column bacterial growth efficiency is lower at impacted reefs. A trophic model based on the benthic and planktonic primary production was able to predict the observed relative fish biomass in healthy reefs. In contrast, in impacted reefs, the observed omnivorous fish biomass is higher, while that of the herbivorous/coralivorous fish is lower than predicted by the primary production‐based model. Incorporating recycling of benthic‐derived carbon in the model through microbial and sponge loops explains the difference and predicts the relative fish biomass in both reef types. Increased benthic carbon release rates and bacterial carbon metabolism, but decreased bacterial growth efficiency could lead to carbon losses through respiration and account for the uncoupling of benthic and fish production in phase‐shifting reefs. Carbon recycling by microbial and sponge loops seems to promote an increase of small‐bodied fish productivity in phase‐shifting coral reefs.

Medical Advocacy and Supportive Environments for African-Americans Following Abnormal Mammograms - Yamile Molina; Bridgette H. Hempstead; Jacci Thompson-Dodd; Shauna Rae Weatherby; Claire Dunbar; Sarah D. Hohl; Rachel C. Malen; Rachel M. Ceballos (Journal of Cancer Education, 2015)

Field Evaluation of Transgenic Switchgrass Plants Overexpressing PvMYB4 for Reduced Biomass Recalcitrance - Holly L. Baxter; Charleson R. Poovaiah; Kelsey L. Yee; Mitra Mazarei; Miguel Rodriguez; Olivia A. Thompson; Hui Shen; Geoffrey B. Turner; Stephen R. Decker; Robert W. Sykes; Fang Chen; Mark F. Davis; et al. (BioEnergy Research, 2015)

A missense variant in CST3 exerts a recessive effect on susceptibility to age-related macular degeneration resembling its association with Alzheimer’s disease - Joe M. Butler; Umar Sharif; Manir Ali; Martin McKibbin; Joseph P. Thompson; Richard Gale; Yit C. Yang; Chris Inglehearn; Luminita Paraoan (Human Genetics, 2015)

Human ALDH1B1 Polymorphisms may Affect the Metabolism of Acetaldehyde and All-trans retinaldehyde—In Vitro Studies and Computational Modeling - Brian C. Jackson; Philip Reigan; Bettina Miller; David C. Thompson; Vasilis Vasiliou (Pharmaceutical Research, 2015)

Finding diagnostic phenotypic features of Photobacterium in the genome sequences - Gilda Rose S. Amaral; Mariana E. Campeão; Jean Swings; Fabiano L. Thompson; Cristiane C. Thompson (Antonie van Leeuwenhoek, 2015)

Microbial taxonomy in the post-genomic era: Rebuilding from scratch? - Cristiane C. Thompson; Gilda R. Amaral; Mariana Campeão; Robert A. Edwards; Martin F. Polz; Bas E. Dutilh; David W. Ussery; Tomoo Sawabe; Jean Swings; Fabiano L. Thompson (Archives of Microbiology, 2015)

Reforestation with native mixed‐species plantings in a temperate continental climate effectively sequesters and stabilizes carbon within decades - Shaun C. Cunningham; Timothy R. Cavagnaro; Ralph Mac Nally; Keryn I. Paul; Patrick J. Baker; Jason Beringer; James R. Thomson; Ross M. Thompson (Global Change Biology, 2015)
Reforestation has large potential for mitigating climate change through carbon sequestration. Native mixed‐species plantings have a higher potential to reverse biodiversity loss than do plantations of production species, but there are few data on their capacity to store carbon. A chronosequence (5–45 years) of 36 native mixed‐species plantings, paired with adjacent pastures, was measured to investigate changes to stocks among C pools following reforestation of agricultural land in the medium rainfall zone (400–800 mm yr −1 ) of temperate Australia. These mixed‐species plantings accumulated 3.09 ± 0.85 t C ha −1 yr −1 in aboveground biomass and 0.18 ± 0.05 t C ha −1 yr −1 in plant litter, reaching amounts comparable to those measured in remnant woodlands by 20 years and 36 years after reforestation respectively. Soil C was slower to increase, with increases seen only after 45 years, at which time stocks had not reached the amounts found in remnant woodlands. The amount of trees (tree density and basal area) was positively associated with the accumulation of carbon in aboveground biomass and litter. In contrast, changes to soil C were most strongly related to the productivity of the location (a forest productivity index and soil N content in the adjacent pasture). At 30 years, native mixed‐species plantings had increased the stability of soil C stocks, with higher amounts of recalcitrant C and higher C : N ratios than their adjacent pastures. Reforestation with native mixed‐species plantings did not significantly change the availability of macronutrients (N, K, Ca, Mg, P, and S) or micronutrients (Fe, B, Mn, Zn, and Cu), content of plant toxins (Al, Si), acidity, or salinity (Na, electrical conductivity) in the soil. In this medium rainfall area, native mixed‐species plantings provided comparable rates of C sequestration to local production species, with the probable additional benefit of providing better quality habitat for native biota. These results demonstrate that reforestation using native mixed‐species plantings is an effective alternative for carbon sequestration to standard monocultures of production species in medium rainfall areas of temperate continental climates, where they can effectively store C, convert C into stable pools and provide greater benefits for biodiversity.

Transcriptional Regulatory Events Initiated by Ascl1 and Neurog2 During Neuronal Differentiation of P19 Embryonic Carcinoma Cells - Holly S. Huang; Tanya M. Redmond; Ginger M. Kubish; Shweta Gupta; Robert C. Thompson; David L. Turner; Michael D. Uhler (Journal of Molecular Neuroscience, 2015)

Rare germline copy number deletions of likely functional importance are implicated in endometrial cancer predisposition - Gemma L. Moir-Meyer; John F. Pearson; Felicity Lose; Rodney J. Scott; Mark McEvoy; John Attia; Elizabeth G. Holliday; Paul D. Pharoah; Alison M. Dunning; Deborah J. Thompson; Douglas F. Easton; Amanda B. Spurdle; et al. (Human Genetics, 2015)

Cereal cultivars can be ranked consistently for resistance to root-lesion nematodes (Pratylenchus thornei & P. neglectus) using diverse procedures - J. G. Sheedy; A. C. McKay; J. Lewis; V. A. Vanstone; S. Fletcher; A. Kelly; J. P. Thompson (Australasian Plant Pathology, 2015)

Microbial community diversity and physical–chemical features of the Southwestern Atlantic Ocean - Nelson Alves Junior; Pedro Milet Meirelles; Eidy de Oliveira Santos; Bas Dutilh; Genivaldo G. Z. Silva; Rodolfo Paranhos; Anderson S. Cabral; Carlos Rezende; Tetsuya Iida; Rodrigo L. de Moura; Ricardo Henrique Kruger; Renato C. Pereira; et al. (Archives of Microbiology, 2015)

Candidate locus analysis of the TERT–CLPTM1L cancer risk region on chromosome 5p15 identifies multiple independent variants associated with endometrial cancer risk - Luis G. Carvajal-Carmona; Tracy A. O’Mara; Jodie N. Painter; Felicity A. Lose; Joe Dennis; Kyriaki Michailidou; Jonathan P. Tyrer; Shahana Ahmed; Kaltin Ferguson; Catherine S. Healey; Karen Pooley; Jonathan Beesley; et al. (Human Genetics, 2015)

Using extended pedigrees to identify novel autism spectrum disorder (ASD) candidate genes - Marc Woodbury-Smith; Andrew D. Paterson; Bhooma Thiruvahindrapduram; Anath C. Lionel; Christian R. Marshall; Daniele Merico; Bridget A. Fernandez; Eric Duku; James S. Sutcliffe; Irene O’Conner; Christina Chrysler; Ann Thompson; et al. (Human Genetics, 2015)

Influence of nocturnal and daytime sleep on initial orthostatic hypotension - N. C. S. Lewis; H. Jones; P. N. Ainslie; A. Thompson; K. Marrin; G. Atkinson (European Journal of Applied Physiology, 2015)

Juvenile and adult hardhead Mylopharodon conocephalus oxygen consumption rates: effects of temperature and swimming velocity - Nann A. Fangue; Dennis E. Cocherell; Felipe La Luz; Joseph J. Cech; Lisa C. Thompson (Environmental Biology of Fishes, 2015)

CTFS ‐Forest GEO : a worldwide network monitoring forests in an era of global change - Kristina J. Anderson‐Teixeira; Stuart J. Davies; Amy C. Bennett; Erika B. Gonzalez‐Akre; Helene C. Muller‐Landau; S. Joseph Wright; Kamariah Abu Salim; Angélica M. Almeyda Zambrano; Alfonso Alonso; Jennifer L. Baltzer; Yves Basset; Norman A. Bourg; et al. (Global Change Biology, 2015)
Global change is impacting forests worldwide, threatening biodiversity and ecosystem services including climate regulation. Understanding how forests respond is critical to forest conservation and climate protection. This review describes an international network of 59 long‐term forest dynamics research sites ( CTFS ‐Forest GEO ) useful for characterizing forest responses to global change. Within very large plots (median size 25 ha), all stems ≥1 cm diameter are identified to species, mapped, and regularly recensused according to standardized protocols. CTFS ‐Forest GEO spans 25°S–61°N latitude, is generally representative of the range of bioclimatic, edaphic, and topographic conditions experienced by forests worldwide, and is the only forest monitoring network that applies a standardized protocol to each of the world's major forest biomes. Supplementary standardized measurements at subsets of the sites provide additional information on plants, animals, and ecosystem and environmental variables. CTFS ‐Forest GEO sites are experiencing multifaceted anthropogenic global change pressures including warming (average 0.61 °C), changes in precipitation (up to ±30% change), atmospheric deposition of nitrogen and sulfur compounds (up to 3.8 g N m −2 yr −1 and 3.1 g S m −2 yr −1 ), and forest fragmentation in the surrounding landscape (up to 88% reduced tree cover within 5 km). The broad suite of measurements made at CTFS ‐Forest GEO sites makes it possible to investigate the complex ways in which global change is impacting forest dynamics. Ongoing research across the CTFS ‐Forest GEO network is yielding insights into how and why the forests are changing, and continued monitoring will provide vital contributions to understanding worldwide forest diversity and dynamics in an era of global change.

Carbon storage in old‐growth forests of the Mid‐Atlantic: toward better understanding the eastern forest carbon sink - Jennifer C. McGarvey; Jonathan R. Thompson; Howard E. Epstein; Herman H. Shugart (Ecology, 2015)
Few old‐growth stands remain in the matrix of secondary forests that dominates the eastern North American landscape. These remnant stands offer insight on the potential carbon (C) storage capacity of now‐recovering secondary forests. We surveyed the remaining old‐growth forests on sites characteristic of the general Mid‐Atlantic United States and estimated the size of multiple components of forest C storage. Within and between old‐growth stands, variability in C density is high and related to overstory tree species composition. The sites contain 219 ± 46 Mg C/ha (mean ± SD), including live and dead aboveground biomass, leaf litter, and the soil O horizon, with over 20% stored in downed wood and snags. Stands dominated by tulip poplar ( Liriodendron tulipifera ) store the most live biomass, while the mixed oak ( Quercus spp.) stands overall store more dead wood. Total C density is 30% higher (154 Mg C/ha), and dead wood C density is 1800% higher (46 Mg C/ha) in the old‐growth forests than in the surrounding younger forests (120 and 5 Mg C/ha, respectively). The high density of dead wood in old growth relative to secondary forests reflects a stark difference in historical land use and, possibly, the legacy of the local disturbance (e.g., disease) history. Our results demonstrate the potential for dead wood to maintain the sink capacity of secondary forests for many decades to come.

Emergent stability in a large, free‐flowing watershed - Jonathan W. Moore; Michael P. Beakes; Holly K. Nesbitt; Justin D. Yeakel; David A. Patterson; Lisa A. Thompson; Corey C. Phillis; Douglas C. Braun; Corinna Favaro; David Scott; Charmaine Carr-Harris; William I. Atlas (Ecology, 2015)
While it is widely recognized that financial stock portfolios can be stabilized through diverse investments, it is also possible that certain habitats can function as natural portfolios that stabilize ecosystem processes. Here we propose and examine the hypothesis that free‐flowing river networks act as such portfolios and confer stability through their integration of upstream geological, hydrological, and biological diversity. We compiled a spatially (142 sites) and temporally (1980–present) extensive data set on fisheries, water flows, and temperatures, from sites within one of the largest watersheds in the world that remains without dams on its mainstem, the Fraser River, British Columbia, Canada. We found that larger catchments had more stable fisheries catches, water flows, and water temperatures than smaller catchments. These data provide evidence that free‐flowing river networks function as hierarchically nested portfolios with stability as an emergent property. Thus, free‐flowing river networks can represent a natural system for buffering variation and extreme events.

New insight into the spawning behavior of lake trout, Salvelinus namaycush, from a recovering population in the Laurentian Great Lakes - T. R. Binder; H. T. Thompson; A. M. Muir; S. C. Riley; J. E. Marsden; C. R. Bronte; C. C. Krueger (Environmental Biology of Fishes, 2015)

Nanosecond pulsed electric fields modulate the expression of Fas/CD95 death receptor pathway regulators in U937 and Jurkat Cells - Larry E. Estlack; Caleb C. Roth; Gary L. Thompson; William A. Lambert; Bennett L. Ibey (Apoptosis, 2014)

Oenococcus alcoholitolerans sp. nov., a lactic acid bacteria isolated from cachaça and ethanol fermentation processes - Fernanda Badotti; Ana Paula B. Moreira; Luciane A. Chimetto Tonon; Brígida T. Luckwu de Lucena; Fátima de Cássia O. Gomes; Ricardo Kruger; Cristiane C. Thompson; Marcos Antonio de Morais; Carlos A. Rosa; Fabiano L. Thompson (Antonie van Leeuwenhoek, 2014)

Phenotypic variation in shell form in the intertidal acorn barnacle Chthamalus montagui: distribution, response to predators and life history trade-offs - Jefferson Murua; Michael T. Burrows; Roger N. Hughes; Stephen J. Hawkins; Richard C. Thompson; Stuart R. Jenkins (Marine Biology, 2014)

Vibrio madracius sp. nov. Isolated from Madracis decactis (Scleractinia) in St Peter & St Paul Archipelago, Mid-Atlantic Ridge, Brazil - Ana Paula B. Moreira; Gwen Duytschaever; Luciane A. Chimetto Tonon; Graciela M. Dias; Milene Mesquita; Margo Cnockaert; Ronaldo B. Francini-Filho; Paul De Vos; Cristiane C. Thompson; Fabiano L. Thompson (Current Microbiology, 2014)

Is obesity associated with colorectal cancer screening for African American and Latino individuals in the context of patient navigation? - Errol J. Philip; Rachel C. Shelton; Hayley S. Thompson; Elizaveta Efuni; Steven Itzkowitz; Lina Jandorf (Cancer Causes & Control, 2014)

Floral Scent Contributes to Interaction Specificity in Coevolving Plants and Their Insect Pollinators - Magne Friberg; Christopher Schwind; Lindsey C. Roark; Robert A. Raguso; John N. Thompson (Journal of Chemical Ecology, 2014)

Molecular assessment of heterotrophy and prey digestion in zooxanthellate cnidarians - M. C. Leal; J. C. Nejstgaard; R. Calado; M. E. Thompson; M. E. Frischer (Molecular Ecology, 2014)
Zooxanthellate cnidarians are trophically complex, relying on both autotrophy and heterotrophy. Although several aspects of heterotrophy have been studied in these organisms, information linking prey capture with digestion is still missing. We used prey‐specific PCR ‐based tools to assess feeding and prey digestion of two zooxanthellate cnidarians – the tropical sea anemone A iptasia sp. and the scleractinian coral O culina arbuscula . Prey DNA disappeared rapidly for the initial 1–3 days, whereas complete digestion of prey DNA required up to 10 days in O . arbuscula and 5 or 6 days in A iptasia sp. depending on prey species. These digestion times are considerably longer than previously reported from microscopy‐based examination of zooxanthellate cnidarians and prey DNA breakdown in other marine invertebrates, but similar to prey DNA breakdown reported from terrestrial invertebrates such as heteroptera and spiders. Deprivation of external prey induced increased digestion rates during the first days after feeding in O. arbuscula , but after 6 days of digestion, there were no differences in the remaining prey levels in fed and unfed corals. This study indicates that prey digestion by symbiotic corals may be slower than previously reported and varies with the type of prey, the cnidarian species and its feeding history. These observations have important implications for bioenergetic and trophodynamic studies on zooxanthellate cnidarians.

Coral feeding on microalgae assessed with molecular trophic markers - Miguel C. Leal; Christine Ferrier‐Pagès; Ricardo Calado; Megan E. Thompson; Marc E. Frischer; Jens C. Nejstgaard (Molecular Ecology, 2014)
Herbivory in corals, especially for symbiotic species, remains controversial. To investigate the capacity of scleractinian and soft corals to capture microalgae, we conducted controlled laboratory experiments offering five algal species: the cryptophyte R hodomonas marina , the haptophytes Isochrysis galbana and P haeocystis globosa , and the diatoms C onticribra weissflogii and T halassiosira pseudonana . Coral species included the symbiotic soft corals H eteroxenia fuscescens and S inularia flexibilis , the asymbiotic scleractinian coral T ubastrea coccinea , and the symbiotic scleractinian corals S tylophora pistillata, P avona cactus and O culina arbuscula . Herbivory was assessed by end‐point PCR amplification of algae‐specific 18 S r RNA gene fragments purified from coral tissue genomic DNA extracts. The ability to capture microalgae varied with coral and algal species and could not be explained by prey size or taxonomy. Herbivory was not detected in S . flexibilis and S . pistillata . P . globosa was the only algal prey that was never captured by any coral. Although predation defence mechanisms have been shown for P haeocystis spp. against many potential predators, this study is the first to suggest this for corals. This study provides new insights into herbivory in symbiotic corals and suggests that corals may be selective herbivorous feeders.

Stakeholders’ Responses to the Use of Innovative Water Trading Systems in East Anglia, England - D. M. Lumbroso; C. Twigger-Ross; J. Raffensperger; J. J. Harou; M. Silcock; A. J. K. Thompson (Water Resources Management, 2014)

Use of leaf litter breakdown and macroinvertebrates to evaluate gradient of recovery in an acid mine impacted stream remediated with an active alkaline doser - Kelly S. Johnson; Peter C. Thompson; Lori Gromen; Jen Bowman (Environmental Monitoring and Assessment, 2014)

Resurrection of Mesoplodon hotaula Deraniyagala 1963: A new species of beaked whale in the tropical Indo‐Pacific - Merel L. Dalebout; C. Scott Baker; Debbie Steel; Kirsten Thompson; Kelly M. Robertson; Susan J. Chivers; William F. Perrin; Manori Goonatilake; R. Charles Anderson; James G. Mead; Charles W. Potter; Lisa Thompson; et al. (Marine Mammal Science, 2014)
We present genetic and morphological evidence supporting the recognition of a previously synonymized species of Mesoplodon beaked whale in the tropical Indo‐Pacific, Mesoplodon hotaula . Although the new species is closely‐related to the rare ginkgo‐toothed beaked whale M. ginkgodens, we show that these two lineages can be differentiated by maternally (mitochondrial DNA ), biparentally (autosomal), and paternally (Y chromosome) inherited DNA sequences, as well as by morphological features. The reciprocal monophyly of the mt DNA genealogies and the largely parapatric distribution of these lineages is consistent with reproductive isolation. The new lineage is currently known from at least seven specimens: Sri Lanka (1), Gilbert Islands, Republic of Kiribati (1+), Palmyra Atoll, Northern Line Islands, U.S.A. (3), Maldives (1), and Seychelles (1). The type specimen (Sri Lanka) was described as a new species, M. hotaula , in 1963, but later synonymized with M. ginkgodens . This discovery brings the total number of Mesoplodon species to 15, making it, by far, the most speciose yet least known genus of cetaceans.

The ENIGMA Consortium: large-scale collaborative analyses of neuroimaging and genetic data - Paul M. Thompson; Jason L. Stein; Sarah E. Medland; Derrek P. Hibar; Alejandro Arias Vasquez; Miguel E. Renteria; Roberto Toro; Neda Jahanshad; Gunter Schumann; Barbara Franke; Margaret J. Wright; Nicholas G. Martin; et al. (Brain Imaging and Behavior, 2014)

Genetic analysis of quantitative phenotypes in AD and MCI: imaging, cognition and biomarkers - Li Shen; Paul M. Thompson; Steven G. Potkin; Lars Bertram; Lindsay A. Farrer; Tatiana M. Foroud; Robert C. Green; Xiaolan Hu; Matthew J. Huentelman; Sungeun Kim; John S. K. Kauwe; Qingqin Li; et al. (Brain Imaging and Behavior, 2014)

Remote Antarctic feeding ground important for east Australian humpback whales - Rochelle Constantine; Debbie Steel; Judy Allen; Megan Anderson; Olive Andrews; C. Scott Baker; Peta Beeman; Daniel Burns; Jean-Benoît Charrassin; Simon Childerhouse; Michael Double; Paul Ensor; et al. (Marine Biology, 2014)

Prototype decision support system based on the VegSyst simulation model to calculate crop N and water requirements for tomato under plastic cover - M. Gallardo; R. B. Thompson; C. Giménez; F. M. Padilla; C. O. Stöckle (Irrigation Science, 2014)

Genome-wide association study of subtype-specific epithelial ovarian cancer risk alleles using pooled DNA - Madalene A. Earp; Linda E. Kelemen; Anthony M. Magliocco; Kenneth D. Swenerton; Georgia Chenevix-Trench; Yi Lu; Alexander Hein; Arif B. Ekici; Matthias W. Beckmann; Peter A. Fasching; Diether Lambrechts; Evelyn Despierre; et al. (Human Genetics, 2014)

Viral over-expression of D1 dopamine receptors in the prefrontal cortex increase high-risk behaviors in adults: Comparison with adolescents - Kai C. Sonntag; Heather C. Brenhouse; Nadja Freund; Britta S. Thompson; Matthew Puhl; Susan L. Andersen (Psychopharmacology, 2014)

Kinetics of short-term carbon mineralization in roots of biofuel crops in soils - F. A. Rivas; M. A. Tabatabai; D. C. Olk; M. L. Thompson (Biology and Fertility of Soils, 2014)

Multiple-Point Simulation with an Existing Reservoir Model as Training Image - L. Y. Hu; Y. Liu; C. Scheepens; A. W. Shultz; R. D. Thompson (Mathematical Geosciences, 2014)

Homologous and heterologous desensitization of guanylyl cyclase-B signaling in GH3 somatolactotropes - Iain R. Thompson; Samantha M. Mirczuk; Lorna Smith; Andrew J. Lessey; Bigboy Simbi; Andrew Sunters; Gary F. Baxter; Victoria J. Lipscomb; Imelda M. McGonnell; Caroline P. Wheeler-Jones; Abir Mukherjee; Mark S. Roberson; et al. (Cell and Tissue Research, 2014)

Improving the science-policy dialogue to meet the challenges of biodiversity conservation: having conversations rather than talking at one-another - Juliette C. Young; Kerry A. Waylen; Simo Sarkki; Steve Albon; Ian Bainbridge; Estelle Balian; James Davidson; David Edwards; Roddy Fairley; Ceri Margerison; Davy McCracken; Roger Owen; et al. (Biodiversity and Conservation, 2014)

Bergmann's rule is maintained during a rapid range expansion in a damselfly - Christopher Hassall; Simon Keat; David J. Thompson; Phillip C. Watts (Global Change Biology, 2014)
Climate‐induced range shifts result in the movement of a sample of genotypes from source populations to new regions. The phenotypic consequences of those shifts depend upon the sample characteristics of the dispersive genotypes, which may act to either constrain or promote phenotypic divergence, and the degree to which plasticity influences the genotype–environment interaction. We sampled populations of the damselfly Erythromma viridulum from northern Europe to quantify the phenotypic (latitude–body size relationship based on seven morphological traits) and genetic (variation at microsatellite loci) patterns that occur during a range expansion itself. We find a weak spatial genetic structure that is indicative of high gene flow during a rapid range expansion. Despite the potentially homogenizing effect of high gene flow, however, there is extensive phenotypic variation among samples along the invasion route that manifests as a strong, positive correlation between latitude and body size consistent with Bergmann's rule. This positive correlation cannot be explained by variation in the length of larval development (voltinism). While the adaptive significance of latitudinal variation in body size remains obscure, geographical patterns in body size in odonates are apparently underpinned by phenotypic plasticity and this permits a response to one or more environmental correlates of latitude during a range expansion.

Macrochannels and their significance for flood-risk minimisation: examples from southeast Queensland and New South Wales, Australia - J. Croke; I. Reinfelds; C. Thompson; E. Roper (Stochastic Environmental Research and Risk Assessment, 2014)

Circadian pathway genes in relation to glioma risk and outcome - Melissa H. Madden; Gabriella M. Anic; Reid C. Thompson; L. Burton Nabors; Jeffrey J. Olson; James E. Browning; Alvaro N. Monteiro; Kathleen M. Egan (Cancer Causes & Control, 2014)

Riding the storm: the response of Plantago lanceolata to simulated tidal flooding - Mick E. Hanley; P. Y. S. Yip; S. Hoggart; D. T. Bilton; S. D. Rundle; R. C. Thompson (Journal of Coastal Conservation, 2013)

Effects of temperature on hardhead minnow (Mylopharodon conocephalus) blood-oxygen equilibria - Robert C. Kaufman; Robert Coalter; Nancy L. Nordman; Dennis Cocherell; Joseph J. Cech; Lisa C. Thompson; Nann A. Fangue (Environmental Biology of Fishes, 2013)

Validity of Darwin’s naturalization hypothesis relates to the stages of invasion - S. Pellock; A. Thompson; K. He; C. Mecklin; Jie Yang (Community Ecology, 2013)

Toenail iron, genetic determinants of iron status, and the risk of glioma - Gabriella M. Anic; Melissa H. Madden; Reid C. Thompson; L. Burton Nabors; Jeffrey J. Olson; Renato V. LaRocca; James E. Browning; John D. Brockman; Peter A. Forsyth; Kathleen M. Egan (Cancer Causes & Control, 2013)

Fossil evidence for seasonal calving and migration of extinct blue antelope ( Hippotragus leucophaeus ) in southern Africa - J. Tyler Faith; Jessica C. Thompson (Journal of Biogeography, 2013)
Aim Palaeoecological data are crucial to understanding the historical extinction of the blue antelope ( Hippotragus leucophaeus ). This study examined late Quaternary fossil evidence bearing on the blue antelope's calving and migratory habits. Location Cape Floristic Region ( CFR ), South Africa. Methods Blue antelope mortality patterns were reconstructed from dental remains from fossil assemblages spanning the last c . 200,000 years and located in the CFR 's winter and year‐round rainfall zones. Two demographic measures were examined: (1) the frequencies of juveniles relative to adults; and (2) the frequencies of neonates relative to older juveniles. Geographical trends were examined across a longitudinal gradient of decreasing winter rainfall and increasing summer rainfall. Results There was a significant longitudinal trend in the blue antelope mortality data, with juveniles and neonates declining in frequency from west to east. This suggests that calving occurred primarily in the winter rainfall zone, probably during the winter months when seasonal rains promoted the growth of C 3 grasses. The summer drought and lack of adequate forage forced blue antelope to migrate east, in time with summer rainfall and the increased availability of C 4 grasses. The migration route probably depended in part on reduced sea levels during glacial phases of the Pleistocene. Main conclusions Blue antelope were probably migratory. Rising sea levels at the onset of the Holocene disrupted their migration routes, limited access to west‐coast calving grounds, and fragmented populations. Such disruption would have devastated the blue antelope population and contributed to its vulnerability to extinction. Blue antelope survived previous marine transgressions, however, suggesting that other factors played a role in its demise. Agricultural expansion early in the colonial era may have further disrupted migration routes and played an important role in its extinction.

Effects of neuromuscular fatigue on the electromechanical delay of the leg extensors and flexors in young and old men - E. C. Conchola; B. J. Thompson; D. B. Smith (European Journal of Applied Physiology, 2013)

Initial census, woody seedling, seed rain, and stand structure data for the SCBI SIGEO Large Forest Dynamics Plot - Norman A. Bourg; William J. McShea; Jonathan R. Thompson; Jennifer C. McGarvey; Xiaoli Shen (Ecology, 2013)
We present data from the first five years (2008–2012) of the establishment of the 25.6‐ha Smithsonian Conservation Biology Institute (SCBI) Large Forest Dynamics Plot, comprising the initial woody stem census, woody seedling plot surveys, seed rain, and dendrochronological data. The plot is in mature secondary mixed deciduous forest 5 km south of Front Royal, Virginia, USA. The initial plot census enumerated 38 932 free‐standing living stems and 29 991 living individuals ≥1 cm dbh comprising 62 species, 38 genera, and 26 families, along with an additional 1248 dead/missing standing stems, for a total of 40 180 stems. Dominant canopy trees include tulip poplar ( Liriodendron tulipifera ), hickories ( Carya spp.), oaks ( Quercus spp.), white ash ( Fraxinus americana ), and black gum ( Nyssa sylvatica ). Prominent understory components include spicebush ( Lindera benzoin ), pawpaw ( Asimina triloba ), American hornbeam ( Carpinus caroliniana ), witchhazel ( Hamamelis virginiana ), and eastern redbud ( Cercis canadensis ). Few species predominate numerically on the plot; seven species have >1000 individuals (71.3% of the total). Mean stand density was 1179 living individuals/ha, while mean basal area was 34.1 m 2 /ha. Of the total plot area, 4 ha have had white‐tailed deer ( Odocoileus virginianus ) exclusion since 1990. Woody seedling surveys from 2010–2012 in 354 1‐m 2 plots measured 19 415 seedlings of 47 species, from new germinants up to 1 cm dbh. Community‐wide seed rain data from 200 0.5‐m 2 litterfall traps yielded a total of 9197 records from 37 species. Long‐term seed data collected from 1986–2011 for Quercus and Carya within the exclosure and two replicate sites are also presented, documenting considerable annual variation in mast production. Dendrochronological data from 492 tree cores suggested the major canopy trees established circa 1900, but scattered trees of several species existed earlier. Large‐scale forest dynamics plots employing standardized methodology have a long, rich history in the tropics. Similar plots in the temperate zone have been largely lacking, however. The SCBI plot represents one of the first of its kind in the Smithsonian Global Earth Observatory's recently established network of such plots, complementing its well‐known network of tropical forest plots and enabling comparative studies on forest ecology and climate change at the global scale.

“Panta Rhei—Everything Flows”: Change in hydrology and society—The IAHS Scientific Decade 2013–2022 - A. Montanari; G. Young; H.H.G. Savenije; D. Hughes; T. Wagener; L.L. Ren; D. Koutsoyiannis; C. Cudennec; E. Toth; S. Grimaldi; G. Blöschl; M. Sivapalan; et al. (Hydrological Sciences Journal, 2013)

Effects of ocean acidification, temperature and nutrient regimes on the appendicularian Oikopleura dioica: a mesocosm study - Christofer Troedsson; Jean-Marie Bouquet; Carla M. Lobon; Aliona Novac; Jens C. Nejstgaard; Sam Dupont; Suncica Bosak; Hans H. Jakobsen; Nadezda Romanova; Lene M. Pankoke; Alejandro Isla; Jörg Dutz; et al. (Marine Biology, 2013)

Testing Decision Rules for Categorizing Species’ Extinction Risk to Help Develop Quantitative Listing Criteria for the U.S. Endangered Species Act - TRACEY J. REGAN; BARBARA L. TAYLOR; GRANT G. THOMPSON; JEAN FITTS COCHRANE; KATHERINE RALLS; MICHAEL C. RUNGE; RICHARD MERRICK (Conservation Biology, 2013)
Lack of guidance for interpreting the definitions of endangered and threatened in the U.S. Endangered Species Act (ESA) has resulted in case‐by‐case decision making leaving the process vulnerable to being considered arbitrary or capricious. Adopting quantitative decision rules would remedy this but requires the agency to specify the relative urgency concerning extinction events over time, cutoff risk values corresponding to different levels of protection, and the importance given to different types of listing errors. We tested the performance of 3 sets of decision rules that use alternative functions for weighting the relative urgency of future extinction events: a threshold rule set, which uses a decision rule of x % probability of extinction over y years; a concave rule set, where the relative importance of future extinction events declines exponentially over time; and a shoulder rule set that uses a sigmoid shape function, where relative importance declines slowly at first and then more rapidly. We obtained decision cutoffs by interviewing several biologists and then emulated the listing process with simulations that covered a range of extinction risks typical of ESA listing decisions. We evaluated performance of the decision rules under different data quantities and qualities on the basis of the relative importance of misclassification errors. Although there was little difference between the performance of alternative decision rules for correct listings, the distribution of misclassifications differed depending on the function used. Misclassifications for the threshold and concave listing criteria resulted in more overprotection errors, particularly as uncertainty increased, whereas errors for the shoulder listing criteria were more symmetrical. We developed and tested the framework for quantitative decision rules for listing species under the U.S. ESA. If policy values can be agreed on, use of this framework would improve the implementation of the ESA by increasing transparency and consistency. Evaluando Reglas de Decisión para Categorizar el Riesgo de Extinción de Especies con el Fin de Desarrollar de Criterios Cuantitativos de Alistamiento en el Acta de Especies en Peligro de los EE. UU.

VegSyst, a simulation model of daily crop growth, nitrogen uptake and evapotranspiration for pepper crops for use in an on-farm decision support system - C. Giménez; M. Gallardo; C. Martínez-Gaitán; C. O. Stöckle; R. B. Thompson; M. R. Granados (Irrigation Science, 2013)

Anthropometric factors in relation to risk of glioma - Rebecca B. Little; Melissa H. Madden; Reid C. Thompson; Jeffrey J. Olson; Renato V. LaRocca; Edward Pan; James E. Browning; Kathleen M. Egan; L. Burton Nabors (Cancer Causes & Control, 2013)

Cigarette smoking and risk of ovarian cancer: a pooled analysis of 21 case–control studies - Mette T. Faber; Susanne K. Kjær; Christian Dehlendorff; Jenny Chang-Claude; Klaus K. Andersen; Estrid Høgdall; Penelope M. Webb; Susan J. Jordan; Mary Anne Rossing; Jennifer A. Doherty; Galina Lurie; Pamela J. Thompson; et al. (Cancer Causes & Control, 2013)

The 2011–2016 Transdisciplinary Research on Energetics and Cancer (TREC) Initiative: Rationale and Design - Ruth E. Patterson; Graham A. Colditz; Frank B. Hu; Kathryn H. Schmitz; Rexford S. Ahima; Ross C. Brownson; Kenneth R. Carson; Jorge E. Chavarro; Lewis A. Chodosh; Sarah Gehlert; Jeff Gill; Karen Glanz; et al. (Cancer Causes & Control, 2013)

Quantification of Field Resistance to Verticillium dahliae in Eight Russet-Skinned Potato Cultivars Using Real-Time PCR - J. S. Pasche; A. L. Thompson; Neil C. Gudmestad (American Journal of Potato Research, 2013)

Different responses of selected hormones to three types of exercise in young men - Keith A. Stokes; Kate L. Gilbert; George M. Hall; Robert C. Andrews; Dylan Thompson (European Journal of Applied Physiology, 2013)

Survival of captured and relocated adult spring-run Chinook salmon Oncorhynchus tshawytscha in a Sacramento River tributary after cessation of migration - Christopher M. Mosser; Lisa C. Thompson; Joshua S. Strange (Environmental Biology of Fishes, 2013)

Fire in the Air: Biomass Burning Impacts in a Changing Climate - Melita Keywood; Maria Kanakidou; Andreas Stohl; Frank Dentener; Giacomo Grassi; C. P. Meyer; Kjetil Torseth; David Edwards; Anne M. Thompson; Ulrike Lohmann; John Burrows (Critical Reviews in Environmental Science and Technology, 2013)

Extreme surface and near-bottom currents in the northwest Atlantic - Eric C. J. Oliver; Jinyu Sheng; Keith R. Thompson; Jorge R. Urrego Blanco (Natural Hazards, 2012)

Carbon Accumulation Patterns During Post-Fire Succession in Cajander Larch (Larix cajanderi) Forests of Siberia - Heather D. Alexander; Michelle C. Mack; Scott Goetz; Michael M. Loranty; Pieter S. A. Beck; Kamala Earl; Sergey Zimov; Sergey Davydov; Catharine C. Thompson (Ecosystems, 2012)

Erratum to: An exploratory analysis of common genetic variants in the vitamin D pathway including genome-wide associated variants in relation to glioma risk and outcome - Gabriella M. Anic; Reid C. Thompson; L. Burton Nabors; Jeffrey J. Olson; James E. Browning; Melissa H. Madden; F. Reed Murtagh; Peter A. Forsyth; Kathleen M. Egan (Cancer Causes & Control, 2012)

Insight in glioma susceptibility through an analysis of 6p22.3, 12p13.33-12.1, 17q22-23.2 and 18q23 SNP genotypes in familial and non-familial glioma - Yanhong Liu; Beatrice S. Melin; Preetha Rajaraman; Zhaoming Wang; Martha Linet; Sanjay Shete; Christopher I. Amos; Ching C. Lau; Michael E. Scheurer; Spiridon Tsavachidis; Georgina N. Armstrong; Richard S. Houlston; et al. (Human Genetics, 2012)

An exploratory analysis of common genetic variants in the vitamin D pathway including genome-wide associated variants in relation to glioma risk and outcome - Gabriella M. Anic; Reid C. Thompson; L. Burton Nabors; Jeffrey J. Olson; James E. Browning; Melissa H. Madden; F. Reed Murtagh; Peter A. Forsyth; Kathleen M. Egan (Cancer Causes & Control, 2012)

Reproductive allocation in female house wrens is not influenced by experimentally altered male attractiveness - Susan C. Grana; Scott K. Sakaluk; Rachel M. Bowden; Melissa A. Doellman; Laura A. Vogel; Charles F. Thompson (Behavioral Ecology and Sociobiology, 2012)

Cerebrovascular risk factors and brain microstructural abnormalities on diffusion tensor images in HIV-infected individuals - Beau K. Nakamoto; Neda Jahanshad; Aaron McMurtray; Kalpana J. Kallianpur; Dominic C. Chow; Victor G. Valcour; Robert H. Paul; Liron Marotz; Paul M. Thompson; Cecilia M. Shikuma (Journal of NeuroVirology, 2012)

Improving Knowledge and Screening for Colorectal Cancer Among Hispanics: Overcoming Barriers Through a PROMOTORA-Led Home-Based Educational Intervention - Ernesto A. Moralez; Satya P. Rao; Jennifer C. Livaudais; Beti Thompson (Journal of Cancer Education, 2012)

Ground Support Terminology and Classification: An Update - A. G. Thompson; E. Villaescusa; C. R. Windsor (Geotechnical and Geological Engineering, 2012)

The influences of climatic variation and vegetation on stream biota: lessons from the B ig D ry in southeastern A ustralia - James R. Thomson; Nick R. Bond; Shaun C. Cunningham; Leon Metzeling; Paul Reich; Ross M. Thompson; Ralph Mac Nally (Global Change Biology, 2012)
Aquatic biodiversity faces increasing threats from climate change, escalating exploitation of water and land use intensification. Loss of vegetation in catchments (= watersheds) has been identified as a substantial problem for many river basins, and there is an urgent need to better understand how climate change may interact with changes in catchment vegetation to influence the ecological condition of freshwater ecosystems. We used 20 years of biological monitoring data from V ictoria, southeastern A ustralia, to explore the influences of catchment vegetation and climate on stream macroinvertebrate assemblages. Southeastern A ustralia experienced a severe drought from 1997 to 2009, with reductions of stream flows >50% in some areas. The prolonged drying substantially altered macroinvertebrate assemblages, with reduced prevalence of many flow‐dependent taxa and increased prevalence of taxa that are tolerant of low‐flow conditions and poor water quality. Stream condition, as assessed by several commonly used macroinvertebrate indices, was consistently better in reaches with extensive native tree cover in upstream catchments. Prolonged drought apparently caused similar absolute declines in macroinvertebrate condition indices regardless of vegetation cover, but streams with intact catchment and riparian vegetation started in better condition and remained so throughout the drought. The largest positive effects of catchment tree cover on both water quality and macroinvertebrate assemblages occurred above a threshold of ca. 60% areal tree cover in upstream catchments and in higher rainfall areas. Riparian tree cover also had positive effects on macroinvertebrate assemblages, especially in warmer catchments. Our results suggest that the benefits of extensive tree cover via improved water quality and in‐channel habitat persist during drought and show the potential for vegetation management to reduce negative impacts of climatic extremes for aquatic ecosystems.

A novel approach of homozygous haplotype sharing identifies candidate genes in autism spectrum disorder - Jillian P. Casey; Tiago Magalhaes; Judith M. Conroy; Regina Regan; Naisha Shah; Richard Anney; Denis C. Shields; Brett S. Abrahams; Joana Almeida; Elena Bacchelli; Anthony J. Bailey; Gillian Baird; et al. (Human Genetics, 2012)

Stakeholder Participation in Management of Invasive Vertebrates - ADRIANA E. S. FORD‐THOMPSON; CAROLYN SNELL; GLEN SAUNDERS; PIRAN C. L. WHITE (Conservation Biology, 2012)
Stakeholders are increasingly involved in species conservation. We sought to understand what features of a participatory conservation program are associated with its ecological and social outcomes. We conducted a case study of the management of invasive vertebrates in Australia. Invasive vertebrates are a substantial threat to Australia's native species, and stakeholder participation in their management is often necessary for their control. First, we identified potential influences on the ecological and social outcomes of species conservation programs from the literature. We used this information to devise an interview questionnaire, which we administered to managers of 34 participatory invasive‐vertebrate programs. Effects of invasive species were related to program initiator (agency or citizen), reasons for use of a participatory approach, and stakeholder composition. Program initiator was also related to the participation methods used, level of governance (i.e., governed by an agency or citizens), changes in stakeholder interactions, and changes in abundance of invasive species. Ecological and social outcomes were related to changes in abundance of invasive species and stakeholder satisfaction. We identified relations between changes in the number of participants, stakeholder satisfaction, and occurrence of conflict. Potential ways to achieve ecological and social goals include provision of governmental support (e.g., funding) to stakeholders and minimization of gaps in representation of stakeholder groups or individuals to, for example, increase conflict mitigation. Our findings provide guidance for increasing the probability of achieving ecological and social objectives in management of invasive vertebrates and may be applicable to other participatory conservation programs.

Temporal turnover in the composition of tropical tree communities: functional determinism and phylogenetic stochasticity - Nathan G. Swenson; James C. Stegen; Stuart J. Davies; David L. Erickson; Jimena Forero-Montaña; Allen H. Hurlbert; W. John Kress; Jill Thompson; María Uriarte; S. Joseph Wright; Jess K. Zimmerman (Ecology, 2012)
The degree to which turnover in biological communities is structured by deterministic or stochastic factors and the identities of influential deterministic factors are fundamental, yet unresolved, questions in ecology. Answers to these questions are particularly important for projecting the fate of forests with diverse disturbance histories worldwide. To uncover the processes governing turnover we use species‐level molecular phylogenies and functional trait data sets for two long‐term tropical forest plots with contrasting disturbance histories: one forest is older‐growth, and one was recently disturbed. Having both phylogenetic and functional information further allows us to parse out the deterministic influences of different ecological filters. With the use of null models we find that compositional turnover was random with respect to phylogeny on average, but highly nonrandom with respect to measured functional traits. Furthermore, as predicted by a deterministic assembly process, the older‐growth and disturbed forests were characterized by less than and greater than expected functional turnover, respectively. These results suggest that the abiotic environment, which changes due to succession in the disturbed forest, strongly governs the temporal dynamics of disturbed and undisturbed tropical forests. Predicting future changes in the composition of disturbed and undisturbed forests may therefore be tractable when using a functional‐trait‐based approach.

A lateral-displacement flume for fish behavior and stranding studies during simulated pulsed flows - Sarah A. Cocherell; Stephanie N. Chun; Dennis E. Cocherell; Lisa C. Thompson; A. Peter Klimley; Joseph J. Cech (Environmental Biology of Fishes, 2012)

Factors that influence mammography use and breast cancer detection among Mexican-American and African-American women - Rachel Zenuk Garcia; Scott C. Carvajal; Anna V. Wilkinson; Patricia A. Thompson; Jesse N. Nodora; Ian K. Komenaka; Abenaa Brewster; Giovanna I. Cruz; Betsy C. Wertheim; Melissa L. Bondy; María Elena Martínez (Cancer Causes & Control, 2012)

Higher incidence of clear cell adenocarcinoma of the cervix and vagina among women born between 1947 and 1971 in the United States - Emily K. Smith; Mary C. White; Hannah K. Weir; Lucy A. Peipins; Trevor D. Thompson (Cancer Causes & Control, 2012)

Studies on the effect of temperature and pH on the inactivation of fish viral and bacterial pathogens - P F Dixon; D A Smail; M Algoët; T S Hastings; A Bayley; H Byrne; M Dodge; A Garden; C Joiner; E Roberts; D Verner‐Jeffreys; F Thompson (Journal of Fish Diseases, 2012)
Disposal of fish by‐products in the European Community must comply with Regulation (EC) No 1069/2009 which categorizes animal by‐products according to risk, and specifies methods of disposal of by‐products according to that risk. There is provision under the regulation for composting or ensiling to be used for by‐products from aquatic animals. Biosecurity considerations require knowledge of the parameters of time and temperature, or time and pH, required to inactivate any fish pathogens that may be present. To provide those data, we undertook laboratory studies on the inactivation of a number of fish pathogenic viruses and bacteria at 60 °C, pH 4.0 and pH 12.0 as a preliminary to conducting subsequent trials with the most resistant viruses and bacteria in fish tissues. The most resistant bacterium to 60 °C, pH 4.0 as well as pH 12.0 was Lactococcus garvieae . Its concentration was reduced to the level of sensitivity of the test after 24–48 h exposure to 60 °C, but it survived for at least 7 days at pH 4.0 and 14 days at pH 12.0. The most resistant virus to 60 °C was infectious pancreatic necrosis virus, and to pH 12.0 was infectious salmon anaemia virus. The majority of the viruses tested survived exposure to pH 4.0 for up to 28 days. The results suggest that the process of acid ensiling alone is not an effective method for the inactivation of many viral and bacterial pathogens, and fish by‐products would need further treatment by a method approved under the regulation following ensiling, whereas alkaline or heat treatment are likely to provide an increased degree of biosecurity for on‐farm processing of mortalities.

Modelling water-level options for ecosystem services and assessment of climate change: Loktak Lake, northeast India - C. R. Singh; J. R. Thompson; D. G. Kingston; J. R. French (Hydrological Sciences Journal, 2011)

Hydropower-related pulsed-flow impacts on stream fishes: a brief review, conceptual model, knowledge gaps, and research needs - Paciencia S. Young; Joseph J. Cech; Lisa C. Thompson (Reviews in Fish Biology and Fisheries, 2011)

Heat exposure does not alter eccentric exercise-induced increases in mitochondrial calcium and respiratory dysfunction - Ben Rattray; C. Caillaud; P. A. Ruell; M. W. Thompson (European Journal of Applied Physiology, 2011)

QTL and gene expression analyses identify genes affecting carcass weight and marbling on BTA14 in Hanwoo (Korean Cattle) - Seung Hwan Lee; J. H. J. van der Werf; Nam Kuk Kim; Sang Hong Lee; C. Gondro; Eung Woo Park; Sung Jong Oh; J. P. Gibson; J. M. Thompson (Mammalian Genome, 2011)

TRY – a global database of plant traits - J. KATTGE; S. DÍAZ; S. LAVOREL; I. C. PRENTICE; P. LEADLEY; G. BÖNISCH; E. GARNIER; M. WESTOBY; P. B. REICH; I. J. WRIGHT; J. H. C. CORNELISSEN; C. VIOLLE; et al. (Global Change Biology, 2011)
Plant traits – the morphological, anatomical, physiological, biochemical and phenological characteristics of plants and their organs – determine how primary producers respond to environmental factors, affect other trophic levels, influence ecosystem processes and services and provide a link from species richness to ecosystem functional diversity. Trait data thus represent the raw material for a wide range of research from evolutionary biology, community and functional ecology to biogeography. Here we present the global database initiative named TRY, which has united a wide range of the plant trait research community worldwide and gained an unprecedented buy‐in of trait data: so far 93 trait databases have been contributed. The data repository currently contains almost three million trait entries for 69 000 out of the world's 300 000 plant species, with a focus on 52 groups of traits characterizing the vegetative and regeneration stages of the plant life cycle, including growth, dispersal, establishment and persistence. A first data analysis shows that most plant traits are approximately log‐normally distributed, with widely differing ranges of variation across traits. Most trait variation is between species (interspecific), but significant intraspecific variation is also documented, up to 40% of the overall variation. Plant functional types (PFTs), as commonly used in vegetation models, capture a substantial fraction of the observed variation – but for several traits most variation occurs within PFTs, up to 75% of the overall variation. In the context of vegetation models these traits would better be represented by state variables rather than fixed parameter values. The improved availability of plant trait data in the unified global database is expected to support a paradigm shift from species to trait‐based ecology, offer new opportunities for synthetic plant trait research and enable a more realistic and empirically grounded representation of terrestrial vegetation in Earth system models.

Field estimates of reproductive success in a model insect: behavioural surrogates are poor predictors of fitness - David J. Thompson; Christopher Hassall; Chris D. Lowe; Phillip C. Watts (Ecology Letters, 2011)
Ecology Letters (2011) 14 : 905–913 Abstract Understanding, and therefore measuring, factors that determine fitness is a central problem in evolutionary biology. We studied a natural population of Coenagrion puella (Odonata: Zygoptera) over two entire breeding seasons, with over a thousand individuals uniquely marked and genotyped, and all mating events at the rendezvous site recorded. Using a parentage analysis, fitness of individuals in the first generation was quantified as the numbers of offspring that survived to maturity. Although mating behaviour can be predicted by environmental and demographical variables, the numbers of mature offspring produced (fitness) cannot, and crucially, are poorly correlated with behavioural observations of mating. While fitness of both sexes was positively related to mating behaviour and to female’s ectoparasite burden, these behavioural observations explained little more variance in offspring production than environmental and demographical variables. Thus, we demonstrate that behavioural measures of reproductive success are not necessarily reliable estimates of fitness in natural populations.

Pollen-based continental climate reconstructions at 6 and 21 ka: a global synthesis - P. J. Bartlein; S. P. Harrison; S. Brewer; S. Connor; B. A. S. Davis; K. Gajewski; J. Guiot; T. I. Harrison-Prentice; A. Henderson; O. Peyron; I. C. Prentice; M. Scholze; et al. (Climate Dynamics, 2011)

Training Experiences of Lay and Professional Patient Navigators for Colorectal Cancer Screening - Rachel C. Shelton; Hayley S. Thompson; Lina Jandorf; Alejandro Varela; Bridget Oliveri; Cristina Villagra; Heiddis B. Valdimarsdottir; William H. Redd (Journal of Cancer Education, 2011)

Using microsatellite diversity in wild Anegada iguanas (Cyclura pinguis) to establish relatedness in a captive breeding group of this critically endangered species - Adele A. Mitchell; Jennie Lau; Leona G. Chemnick; Elizabeth A. Thompson; Allison C. Alberts; Oliver A. Ryder; Glenn P. Gerber (Conservation Genetics, 2011)

Genes in the insulin and insulin-like growth factor pathway and odds of metachronous colorectal neoplasia - Elizabeth C. LeRoy; Jason H. Moore; Chengcheng Hu; María Elena Martínez; Peter Lance; David Duggan; Patricia A. Thompson (Human Genetics, 2011)

Assessment of flipper tag site healing in gray seal pups using thermography - W. Paterson; P. P. Pomeroy; C. E. Sparling; S. Moss; D. Thompson; J. I. Currie; D. J. McCafferty (Marine Mammal Science, 2011)
Infrared thermography was used to monitor the healing process at flipper tag sites in gray seal ( Halichoerus grypus ) pups. We tested the hypothesis that tagging would result in a rise in surface temperature associated with tag site healing processes compared with adjacent untagged areas of the flipper. Prior to tagging thermal images were recorded of the dorsal side of hind flippers of pups tagged in early lactation ( n = 20) and at weaning ( n = 19) on the Isle of May, Scotland (56°11′N, 02°33′W) from October to December 2008. Pups tagged in early lactation were sampled again at late lactation, at weaning and then every 3 d for an average of 29 d post‐tagging while pups tagged at weaning were sampled every 3 d for an average of 17 d post‐tagging. Tag sites were also scored for signs of infection or swelling at each sampling. Results showed that (1) small temperature increases associated with wound healing processes around the tag site returned to pre‐tagging levels before animals leave the island and (2) there was little evidence of tagging‐related infections or tag loss irrespective of age at tagging.

Longitudinal movement of fish in response to a single-day flow pulse - Lisa C. Thompson; Sarah A. Cocherell; Stephanie N. Chun; Joseph J. Cech; A. Peter Klimley (Environmental Biology of Fishes, 2011)

Phenological changes in intertidal con‐specific gastropods in response to climate warming - PIPPA J. MOORE; RICHARD C. THOMPSON; STEPHEN J. HAWKINS (Global Change Biology, 2011)
There is substantial evidence from terrestrial and freshwater systems of species responding to climate change through changes in their phenology. In the marine environment, however, there is less evidence. Using historic (1946–1949) and contemporary (2003–2007) data, collected from rocky shores of south‐west Britain, we investigated the affect of recent climate warming on the reproductive phenology of two con‐specific intertidal limpet grazers, with cool/boreal and warm/lusitanian centres of distribution. Reproductive development in the southern limpet, Patella depressa , has advanced, on average, 10.2 days per decade since the 1940s, with a longer reproductive season and more of the population reproductively active. The peak in the proportion of the population in advanced stages of gonad development was positively correlated with sea surface temperature (SST) in late spring/early summer, which has increased between the 1940s and 2000s. The advance in peak reproductive development of this species is double the average observed for terrestrial and freshwater systems and indicates, along with other studies, that marine species may be responding faster to climate warming. In contrast, the northern limpet, Patella vulgata , has experienced a delay in the timing of its reproductive development (on average 3.3 days per decade), as well as an increase in reproductive failure years and a reduction in the proportion of the population reaching advanced gonad stages. These results are the first to demonstrate a delay in the reproductive development of a cool‐temperate, winter spawner, towards cooler more favourable environmental conditions in response to climate warming. Such a delay in spawning will potentially lead to trophic miss‐matches, resulting in a rapid nonlinear decline of this species.

Erratum to: Measurement and estimation of plastic greenhouse reference evapotranspiration in a Mediterranean climate - M. D. Fernández; S. Bonachela; F. Orgaz; R. B. Thompson; J. C. López; M. R. Granados; M. Gallardo; E. Fereres (Irrigation Science, 2011)

Displacement, velocity preference, and substrate use of three native California stream fishes in simulated pulsed flows - Stephanie N. Chun; Sarah A. Cocherell; Dennis E. Cocherell; Javier B. Miranda; Gardner J. Jones; Justin Graham; A. Peter Klimley; Lisa C. Thompson; Joseph J. Cech (Environmental Biology of Fishes, 2011)

Rainbow trout Oncorhynchus mykiss energetic responsesto pulsed flows in the American River, California, assessed by electromyogram telemetry - Sarah A. Cocherell; Dennis E. Cocherell; Gardner J. Jones; Javier B. Miranda; Lisa C. Thompson; Joseph J. Cech; A. Peter Klimley (Environmental Biology of Fishes, 2011)

Effects of Central Airway Shunting on the Mechanical Impedance of the Mouse Lung - Benjamin L. Schwartz; Ron C. Anafi; Minara Aliyeva; John A. Thompson-Figueroa; Gilman B. Allen; Lennart K. A. Lundblad; Jason H. T. Bates (Annals of Biomedical Engineering, 2011)

Multi-component Polymeric System for Tumour Cell-Specific Gene Delivery Using a Universal Bungarotoxin Linker - Ralph A. Willemsen; Michal Pechar; Robert C. Carlisle; Erik Schooten; Robert Pola; Amber J. Thompson; Leonard W. Seymour; Karel Ulbrich (Pharmaceutical Research, 2010)

Patterns of spatial genetic structure and diversity at the onset of a rapid range expansion: colonisation of the UK by the small red-eyed damselfly Erythromma viridulum - Phillip C. Watts; Simon Keat; David J. Thompson (Biological Invasions, 2010)

Genomic analysis of oceanic cyanobacterial myoviruses compared with T4‐like myoviruses from diverse hosts and environments - Matthew B. Sullivan; Katherine H. Huang; Julio C. Ignacio‐Espinoza; Aaron M. Berlin; Libusha Kelly; Peter R. Weigele; Alicia S. DeFrancesco; Suzanne E. Kern; Luke R. Thompson; Sarah Young; Chandri Yandava; Ross Fu; et al. (Environmental Microbiology, 2010)
Summary T4‐like myoviruses are ubiquitous, and their genes are among the most abundant documented in ocean systems. Here we compare 26 T4‐like genomes, including 10 from non‐cyanobacterial myoviruses, and 16 from marine cyanobacterial myoviruses (cyanophages) isolated on diverse Prochlorococcus or Synechococcus hosts. A core genome of 38 virion construction and DNA replication genes was observed in all 26 genomes, with 32 and 25 additional genes shared among the non‐cyanophage and cyanophage subsets, respectively. These hierarchical cores are highly syntenic across the genomes, and sampled to saturation. The 25 cyanophage core genes include six previously described genes with putative functions ( psbA , mazG , phoH , hsp20 , hli03 , cobS ), a hypothetical protein with a potential phytanoyl‐CoA dioxygenase domain, two virion structural genes, and 16 hypothetical genes. Beyond previously described cyanophage‐encoded photosynthesis and phosphate stress genes, we observed core genes that may play a role in nitrogen metabolism during infection through modulation of 2‐oxoglutarate. Patterns among non‐core genes that may drive niche diversification revealed that phosphorus‐related gene content reflects source waters rather than host strain used for isolation, and that carbon metabolism genes appear associated with putative mobile elements. As well, phages isolated on Synechococcus had higher genome‐wide %G+C and often contained different gene subsets (e.g. petE , zwf , gnd , prnA , cpeT ) than those isolated on Prochlorococcus . However, no clear diagnostic genes emerged to distinguish these phage groups, suggesting blurred boundaries possibly due to cross‐infection. Finally, genome‐wide comparisons of both diverse and closely related, co‐isolated genomes provide a locus‐to‐locus variability metric that will prove valuable for interpreting metagenomic data sets.

A preliminary study on the properties and fouling-release performance of siloxane–polyurethane coatings prepared from poly(dimethylsiloxane) (PDMS) macromers - Stacy Sommer; Abdullah Ekin; Dean C. Webster; Shane J. Stafslien; Justin Daniels; Lyndsi J. VanderWal; Stephanie E.M. Thompson; Maureen E. Callow; James A. Callow (Biofouling, 2010)

The reliability of the IL-6, sIL-6R and sgp130 response to a preloaded time trial - I. Walshe; P. Robson-Ansley; A. St Clair Gibson; C. Lawrence; K. G. Thompson; L. Ansley (European Journal of Applied Physiology, 2010)

Distribution and movement of domestic rainbow trout, Oncorhynchus mykiss, during pulsed flows in the South Fork American River, California - Sarah A. Cocherell; Gardner J. Jones; Javier B. Miranda; Dennis E. Cocherell; Joseph J. Cech; Lisa C. Thompson; A. Peter Klimley (Environmental Biology of Fishes, 2010)

Erratum to: Measurement and estimation of plastic greenhouse reference evapotranspiration in a Mediterranean climate - M. D. Fernández; S. Bonachela; F. Orgaz; R. B. Thompson; J. C. López; M. R. Granados; M. Gallardo; E. Fereres (Irrigation Science, 2010)

Measurement and estimation of plastic greenhouse reference evapotranspiration in a Mediterranean climate - M. D. Fernández; S. Bonachela; F. Orgaz; R. Thompson; J. C. López; M. R. Granados; M. Gallardo; E. Fereres (Irrigation Science, 2010)

A polymorphism near IGF1 is associated with body composition and muscle function in women from the Health, Aging, and Body Composition Study - Matthew C. Kostek; Joseph M. Devaney; Heather Gordish-Dressman; Tamara B. Harris; Paul D. Thompson; Priscilla M. Clarkson; Theodore J. Angelopoulos; Paul M. Gordon; Niall M. Moyna; Linda S. Pescatello; Paul S. Visich; Robert F. Zoeller; et al. (European Journal of Applied Physiology, 2010)

Interleukin-22 genetic polymorphisms and risk of colon cancer - Cheryl L. Thompson; Sarah J. Plummer; Thomas C. Tucker; Graham Casey; Li Li (Cancer Causes & Control, 2010)

Phylogeny and character evolution in the Indo-Pacific genus Ctenogobiops (Gobiiformes: Gobiidae) - Christine E. Thacker; Andrew R. Thompson; Thomas C. Adam; Jen-Ping Chen (Ichthyological Research, 2010)

Influence of habitat dynamics on the distribution and abundance of the federally threatened Santa Ana Sucker, Catostomus santaanae, in the Santa Ana River - Andrew Richard Thompson; Jonathan N. Baskin; Camm C. Swift; Thomas R. Haglund; Randall J. Nagel (Environmental Biology of Fishes, 2010)

Nitrogen deposition causes widespread loss of species richness in British habitats - LINDSAY C. MASKELL; SIMON M. SMART; JAMES M. BULLOCK; KEN THOMPSON; CARLY J. STEVENS (Global Change Biology, 2010)
We use national scale data to test the hypothesis that nitrogen (N) deposition is strongly negatively correlated with plant species richness in a wide range of ecosystem types. Vegetation plots from a national ecological surveillance programme were drawn from heathland, acid, calcareous and mesotrophic grassland habitats. Mean species number and mean plant traits were calculated for each plot and related to atmospheric N deposition. There was a significant reduction in species richness with N deposition in acid grassland and heathland even after fitting covarying factors. In acid grassland and heathland, evidence from trait changes suggested that acidification rather than increased fertility was responsible for species loss. In contrast, calcareous grassland showed evidence of eutrophication in response to increasing N deposition. Loss of species richness from chronic N deposition is apparent in infertile grasslands and heathland. Mechanisms associated with loss of species richness differ between habitats so mitigation of N deposition should be targeted to habitat type.

Phytophthora capsici on vegetable hosts in South Africa: distribution, host range and genetic diversity - Julia C. Meitz; Celeste C. Linde; Alistair Thompson; Shaun Langenhoven; Adéle McLeod (Australasian Plant Pathology, 2010)

Abundance, population structure and claw morphology of the semi-terrestrial crab Pachygrapsus marmoratus (Fabricius, 1787) on shores of differing wave exposure - Ana Catarina Ferreira Silva; Sónia Brazão; Steve J. Hawkins; Richard C. Thompson; Diana M. Boaventura (Marine Biology, 2009)

Habitat preference and dispersal of the Duke of Burgundy butterfly (Hamearis lucina) on an abandoned chalk quarry in Bedfordshire, UK - Edgar C. Turner; Hanna M. V. Granroth; Henry R. Johnson; Colin B. H. Lucas; Alex M. Thompson; Hannah Froy; Richard N. German; Ross Holdgate (Journal of Insect Conservation, 2009)

A model study on oceanic processes during the Indian Ocean Dipole termination - B. Thompson; C. Gnanaseelan; A. Parekh; P. S. Salvekar (Meteorology and Atmospheric Physics, 2009)

Above‐ground forest biomass is not consistently related to wood density in tropical forests - James C. Stegen; Nathan G. Swenson; Renato Valencia; Brian J. Enquist; Jill Thompson (Global Ecology and Biogeography, 2009)
Aim It is increasingly accepted that the mean wood density of trees within a forest is tightly coupled to above‐ground forest biomass. It is unknown, however, if a positive relationship between forest biomass and mean community wood density is a general phenomenon across forests. Understanding spatial variation in biomass as a function of wood density both within and among forests is important for predicting changes in stored carbon in response to global change, and here we evaluated the generality of a positive biomass–wood density relationship within and among six tropical forests. Location Costa Rica, Panama, Puerto Rico and Ecuador. Methods Individual stem data, including diameter at breast height and spatial position, for six forest dynamics plots were merged with an extensive wood density database. Individual stem biomass values were calculated from these data using published statistical models. Total above ground biomass, total basal area and mean community wood density were also quantified across a range of subcommunity plot sizes within each forest. Results Among forests, biomass did not vary with mean community wood density. The relationship between subcommunity biomass and mean wood density within a forest varied from negative to null to positive depending on the size of subcommunities and forest identity. The direction of correlation was determined by the associated total basal area–mean wood density correlation, the slope of which increased strongly with whole forest mean wood density. Main conclusions There is no general relationship between forest biomass and wood density, and in some forests, stored carbon is highest where wood density is lowest. Our results suggest that declining wood density, due to global change, will result in decreased or increased stored carbon in forests with high or low mean wood density, respectively.

Reproductive timing and patterns of development for the damselfly Coenagrion puella in the field - Chris D. Lowe; Ian F. Harvey; Phillip C. Watts; David J. Thompson (Ecology, 2009)
By a combination of detailed behavioral observations and molecular genetic approaches we have assessed development time, timing of first maturity, and the extent of genetic structure through the flying season in a wild population of the damselfly Coenagrion puella in England. This work provides the first estimate of development time (egg to mature adult) in the field based on individual damselflies. Development time was significantly longer for females than males. In contrast to reported laboratory studies, there was no difference in development times between different female color morphs. Development time ranged between 347 and 396 days and was negatively correlated with egg‐laying date. As a result eggs laid early in one season reach adult maturity relatively late in the next; concurrently individuals developing from eggs laid late mature relatively early. We speculate that this pattern of development is a direct physiological response to seasonal environmental variation and results in reproductive synchrony within a population. Size, specifically hind wing length, declined with development time in males, but not in females. In one of the two years of the study there was evidence for weak clustering of related individuals during the reproductive season. This appeared to be the result of developmental synchronization within families: variance in timing of maturation was smaller in full‐sib families than in half‐sib families or randomly assigned unrelated groups.

Exercise-induced shear stress is associated with changes in plasma von Willebrand factor in older humans - Joaquin U. Gonzales; John R. Thistlethwaite; Benjamin C. Thompson; Barry W. Scheuermann (European Journal of Applied Physiology, 2009)

Guidelines for the treatment of marine mammals in field research - N. J. Gales; W. D. Bowen; D. W. Johnston; K. M. Kovacs; C. L. Littnan; W. F. Perrin; J. E. Reynolds; P. M. Thompson (Marine Mammal Science, 2009)

Predicting impacts of climate‐induced range expansion: an experimental framework and a test involving key grazers on temperate rocky shores - LOUISE B. FIRTH; TASMAN P. CROWE; PIPPA MOORE; RICHARD C. THOMPSON; STEPHEN J. HAWKINS (Global Change Biology, 2009)
Climate change has strong potential to modify the structure and functioning of ecosystems, but experimental field studies into its effects are rare. On rocky shores, grazing limpets strongly affect ecosystem structure and their distribution in NW Europe is changing in response to climate change. Three limpet species co‐occur in SW Britain ( Patella vulgata, Patella ulyssiponensis and Patella depressa ) on open rock and in pools. Shores in Ireland are similar, but currently lack P. depressa . It is anticipated that P. depressa will expand its range into Ireland as the climate warms, but we currently lack an empirical basis to predict the consequences of this change. Recent studies show that increasing abundance of P. depressa on British shores has been accompanied by a decline of P. vulgata suggesting interspecific competition. In this study, a new experimental framework was used to examine the potential for P. depressa to affect P. vulgata on Irish shores. P. vulgata was experimentally transplanted into enclosures on open rock and in pools in both Ireland and Britain. In pools, treatments also included transplanted P. ulyssiponensis to mimic natural assemblages. Growth and mortality of P. vulgata were measured over 6 months with no differences between Ireland and Britain. In Britain, P. vulgata caged in pools with transplanted P. depressa and P. ulyssiponensis showed reduced growth, compared with when caged in pools with P. ulyssiponensis alone. There was no effect of P. depressa on the growth rate of P. vulgata on open rock. Results indicate that if the range of P. depressa extends into Ireland, it would reduce the growth of P. vulgata where it co‐occurs with P. ulyssiponensis in pools. The framework used here provides a field‐based approach that could be used to examine the impacts of climate‐induced range expansions on the structure and functioning of other ecosystems.

ATP release from the human ureter on distension and P2X3 receptor expression on suburothelial sensory nerves - R. C. Calvert; C. S. Thompson; G. Burnstock (Purinergic Signalling, 2008)

Solid Phase Synthesis and Circular Dichroism Analysis of (i → i + 4) Cyclic Lactam Analogues of Kisspeptin - Michelle A. Camerino; David C. M. Kong; David K. Chalmers; Philip E. Thompson (International Journal of Peptide Research and Therapeutics, 2008)

Comparison of marker-based pairwise relatedness estimators on a pedigreed plant population - Marco C. A. M. Bink; Amy D. Anderson; W. Eric van de Weg; Elizabeth A. Thompson (Theoretical and Applied Genetics, 2008)

Association of Interleukin-1 gene polymorphisms with central obesity and metabolic syndrome in a coronary heart disease population - Kim W. Carter; Joseph Hung; Brenda L. Powell; Steven Wiltshire; Brendan T. X. Foo; Yuen C. Leow; Brendan M. McQuillan; Michelle Jennens; Pamela A. McCaskie; Peter L. Thompson; John P. Beilby; Lyle J. Palmer (Human Genetics, 2008)

Review Of The Sugar End Disorder In Potato (Solanum tuberosum, L.) - Asunta L. Thompson; Stephen L. Love; Joseph R. Sowokinos; Michael K. Thornton; Clinton C. Shock (American Journal of Potato Research, 2008)

Mortalities caused by off-road vehicles (ORVs) to a key member of sandy beach assemblages, the surf clam Donax deltoides - Thomas A. Schlacher; Luke M. C. Thompson; Simon J. Walker (Hydrobiologia, 2008)

A Comparison of Female Mating Strategies in Pan troglodytes and Pongo spp. - R. M. Stumpf; M. Emery Thompson; C. D. Knott (International Journal of Primatology, 2008)

Phenotype of exogenous microparticle-containing pigment cells of the human Peyer’s patch in inflamed and normal ileum - V. Thoree; J. Skepper; H Deere; L. C. Pele; R. P. H. Thompson; J. J. Powell (Inflammation Research, 2008)

Effects of recovery time on phosphocreatine kinetics during repeated bouts of heavy-intensity exercise - S. C. Forbes; G. H. Raymer; J. M. Kowalchuk; R. T. Thompson; G. D. Marsh (European Journal of Applied Physiology, 2008)

Antioxidant Properties of Cultivars and Selections from the Colorado Potato Breeding Program - C. Stushnoff; D. Holm; M. D. Thompson; W. Jiang; H. J. Thompson; N. I. Joyce; P. Wilson (American Journal of Potato Research, 2008)

A cross‐taxa phenological dataset from Mohonk Lake, NY and its relationship to climate - Benjamin I. Cook; Edward R. Cook; Paul C. Huth; John E. Thompson; Anna Forster; Daniel Smiley (International Journal of Climatology, 2008)
We present a detailed analysis of a rare cross‐taxa native species phenology dataset (plant flowering, insect first sighting, and amphibian first sighting) from Mohonk Lake, NY. This dataset is highly unusual in North America for its longevity of record, consistency of methodology and location, diversity of species available, and availability of local daily meteorological data. For each phenology series, we examined the flowering and first sighting Julian calendar dates for the existence of temporal trends. Only one of the five animal species (katydid) showed any evidence for a significant trend in first sighting. In contrast, the plant species showed a rich mixture of temporal trends in flowering that could be divided into four classes: woody plant–no trend, woody plant–negative trend, herbaceous plant–negative trend, and herbaceous plant–positive trend. Many of the trends were found to be statistically significant and robust to the method of trend estimation. The data within each of the four plant classes were also pooled as anomalies to provide more complete temporal coverage for tests of trend robustness. The results were strongly consistent with the trends of the individual species within each class and highly significant statistically. We next correlated the flowering and first sighting dates against growing degree‐day (GDD) summations for each day of the year to measure the sensitivity of each species to this common form of climatic forcing on phenology. All species showed a significant sensitivity to GDD summations, with peak correlations falling on or near the varying median flowering or first sighting dates. These results were robust whether the GDD analyses were conducted over the complete set of observations for each species (beginning on or after 1928) or over a latter period with a more serially complete set of cross‐taxa observations (1970–2002). The GDD correlations indicate significant climate sensitivity in all species, but the different magnitudes of correlation and timing of maximum correlation imply that plant and animal responses to climate changes in the future will not be homogeneous for the tested species at Mohonk Lake. Copyright © 2007 Royal Meteorological Society

Soil microbial and faunal responses to herbicide tolerant maize and herbicide in two soils - B. S. Griffiths; S. Caul; J. Thompson; C. A. Hackett; J. Cortet; C. Pernin; P. H. Krogh (Plant and Soil, 2008)

Physical damage to coastal dunes and ecological impacts caused by vehicle tracks associated with beach camping on sandy shores: a case study from Fraser Island, Australia - Luke M. C. Thompson; Thomas A. Schlacher (Journal of Coastal Conservation, 2008)

Senescence rates are determined by ranking on the fast–slow life‐history continuum - Owen R. Jones; Jean‐Michel Gaillard; Shripad Tuljapurkar; Jussi S. Alho; Kenneth B. Armitage; Peter H. Becker; Pierre Bize; Jon Brommer; Anne Charmantier; Marie Charpentier; Tim Clutton‐Brock; F. Stephen Dobson; et al. (Ecology Letters, 2008)
Comparative analyses of survival senescence by using life tables have identified generalizations including the observation that mammals senesce faster than similar‐sized birds. These generalizations have been challenged because of limitations of life‐table approaches and the growing appreciation that senescence is more than an increasing probability of death. Without using life tables, we examine senescence rates in annual individual fitness using 20 individual‐based data sets of terrestrial vertebrates with contrasting life histories and body size. We find that senescence is widespread in the wild and equally likely to occur in survival and reproduction. Additionally, mammals senesce faster than birds because they have a faster life history for a given body size. By allowing us to disentangle the effects of two major fitness components our methods allow an assessment of the robustness of the prevalent life‐table approach. Focusing on one aspect of life history – survival or recruitment – can provide reliable information on overall senescence.

Strong genetic divergence indicates that congeneric damselflies Coenagrion puella and C. pulchellum (Odonata: Zygoptera: Coenagrionidae) do not hybridise - Chris D. Lowe; Ian F. Harvey; David J. Thompson; Phillip C. Watts (Hydrobiologia, 2008)

Dakota Diamond: An Exceptionally High Yielding, Cold Chipping Potato Cultivar with Long-Term Storage Potential - A. L. Thompson; B. L. Farnsworth; N. C. Gudmestad; G. A. Secor; D. A. Preston; J. R. Sowokinos; M. Glynn; H. Hatterman-Valenti (American Journal of Potato Research, 2008)

Impairment of movement-associated brain deactivation in multiple sclerosis: further evidence for a functional pathology of interhemispheric neuronal inhibition - S. C. Manson; C. Wegner; M. Filippi; F. Barkhof; C. Beckmann; O. Ciccarelli; N. De Stefano; Christian Enzinger; F. Fazekas; F. Agosta; A. Gass; J. Hirsch; et al. (Experimental Brain Research, 2008)

Diverse historical processes shape deep phylogeographical divergence in the pollinating seed parasite Greya politella - KATHERINE A. RICH; JOHN N. THOMPSON; CATHERINE C. FERNANDEZ (Molecular Ecology, 2008)
Understanding the historical framework in which species interactions have diversified across landscapes may help to partition the effects of vicariance and geographically variable selection in shaping the geographical mosaic of coevolving species. We used phylogeographical analyses of the pollinating seed parasite Greya politella (Lepidoptera: Prodoxidae) to define the historical processes that may have structured interactions of this species with its host plants across major biogeographical breaks in western North America. Using 648 bp of cytochrome oxidase I and amplified fragment length polymorphisims, we identified deep genetic breaks among some populations consistent with some definitions of cryptic species. A combination of phylogenetic and population genetic approaches indicates that different historical processes may have structured G. politella genetic diversity in four regions: northern Pacific Northwest, southern Oregon, southern Sierra Nevada, and the remainder of California. The northern Pacific Northwest had high genetic diversity likely due to glacial refugia and subsequent spatial expansion, concordant with some other taxa. Populations in southern Oregon possessed unique, closely related haplotypes with restricted gene flow, possibly indicating a long‐standing set of populations in this endemic‐rich region. Analyses of California populations showed evidence of restricted gene flow and spatial expansion with many closely related haplotypes that occupy a broad geographical range. Southern Sierra Nevada populations were genetically distinct and highly diverse, possibly due to a localized glacial refugium. Together, these results suggest that vicariance and population expansion, possibly in combination with geographically variable selection, have shaped the diversification of G. politella and its interactions with its host plants.

North Indian Ocean warming and sea level rise in an OGCM - Bijoy Thompson; C. Gnanaseelan; Anant Parekh; P. S. Salvekar (Journal of Earth System Science, 2008)

Influence of Nitrogen Addition and Plant Root Parameters on Phytoremediation of Pyrene-contaminated Soil - Oriana A. Thompson; Duane C. Wolf; John D. Mattice; Gregory J. Thoma (Water, Air, & Soil Pollution, 2008)

Prior heavy knee extension exercise does not affect $$\dot{V}\hbox{O}_{2}$$ kinetics during subsequent heavy cycling exercise - John R. Thistlethwaite; Benjamin C. Thompson; Joaquin U. Gonzales; Barry W. Scheuermann (European Journal of Applied Physiology, 2008)

Density and population estimate of gibbons (Hylobates albibarbis) in the Sabangau catchment, Central Kalimantan, Indonesia - Susan M. Cheyne; Claire J. H. Thompson; Abigail C. Phillips; Robyn M. C. Hill; Suwido H. Limin (Primates, 2008)

An inhibitor of methionine aminopeptidase type-2, PPI-2458, ameliorates the pathophysiological disease processes of rheumatoid arthritis - D. D. Lazarus; E. G. Doyle; S. G. Bernier; A. B. Rogers; M. T. Labenski; J. D. Wakefield; R. M. Karp; E. J. Clark; J. Lorusso; J. G. Hoyt; C. D. Thompson; G. Hannig; et al. (Inflammation Research, 2008)

Dakota crisp: A new high-yielding, cold-chipping potato cultivar with tablestock potential - Asunta L. Thompson; Bryce L. Farnsworth; Gary A. Secor; Neil C. Gudmestad; Duane Preston; Joseph R. Sowokinos; Marty Glynn; Harlene Hatterman-Valenti (American Journal of Potato Research, 2007)

Temperature effects on low-light vision in juvenile rockfish (Genus Sebastes) and consequences for habitat utilization - C. R. L. Reilly; S. H. Thompson (Journal of Comparative Physiology A, 2007)

Poster abstracts - J. Ferrie; M. Shipley; F. Cappuccio; E. Brunner; M. Miller; M. Kumari; M. Marmot; A. Coenen; J. L. Castillo; F. Araya; G. Bustamante; L. Montecino; et al. (Sleep and Biological Rhythms, 2007)

Does size matter for dispersal distance? - David G. Jenkins; Camille R. Brescacin; Craig V. Duxbury; Jennifer A. Elliott; Jennafer A. Evans; Katherine R. Grablow; Melissa Hillegass; Boyd N. Lyon; Genevieve A. Metzger; Michelle L. Olandese; Diana Pepe; Greg A. Silvers; et al. (Global Ecology and Biogeography, 2007)
Aim The aim of this study is to answer the questions: (1) do small organisms disperse farther than large, or vice versa; and (2) does the observed pattern differ for passive and active dispersers? These questions are central to several themes in biogeography (including microbial biogeography), macroecology, metacommunity ecology and conservation biology. Location The meta‐analysis was conducted using published data collected worldwide. Methods We collected and analysed 795 data values in the peer‐reviewed literature for direct observations of both maximal dispersal distance and mass of the dispersing organisms (e.g. seeds, not trees). Analysed taxa ranged in size from bacteria to whales. We applied macroecology analyses based on null models (using Monte Carlo randomizations) to test patterns relative to specific hypotheses. Results Collected dispersal distance and mass data spanned 9 and 21 orders of magnitude, respectively. Active dispersers dispersed significantly farther ( P P Conclusions Size is important to maximal dispersal distance for active dispersers, but not for passive dispersers. Claims that microbes disperse widely cannot be tested by current data based on direct observations of dispersal: indirect approaches will need to be applied. Distance–mass relationships should contribute to a resolution of neutral and niche‐based metacommunity theories by helping scale expectations for dispersal limitation. Also, distance–mass relationships should inform analyses of latitudinal species richness and conservation biology topics such as fragmentation, umbrella species and taxonomic homogenization.

Historical changes in the phenology of British Odonata are related to climate - CHRISTOPHER HASSALL; DAVID J. THOMPSON; GRAHAM C. FRENCH; IAN F. HARVEY (Global Change Biology, 2007)
Responses of biota to climate change take a number of forms including distributional shifts, behavioural changes and life history changes. This study examined an extensive set of biological records to investigate changes in the timing of life history transitions (specifically emergence) in British Odonata between 1960 and 2004. The results show that there has been a significant, consistent advance in phenology in the taxon as a whole over the period of warming that is mediated by life history traits. British odonates significantly advanced the leading edge (first quartile date) of the flight period by a mean of 1.51 ±0.060 (SEM, n =17) days per decade or 3.08±1.16 (SEM, n =17) days per degree rise in temperature when phylogeny is controlled for. This study represents the first review of changes in odonate phenology in relation to climate change. The results suggest that the damped temperature oscillations experienced by aquatic organisms compared with terrestrial organisms are sufficient to evoke phenological responses similar to those of purely terrestrial taxa.

How useful is DNA extracted from the legs of archived insects for microsatellite-based population genetic analyses? - Phillip C. Watts; David J. Thompson; Katherine A. Allen; Stephen J. Kemp (Journal of Insect Conservation, 2007)

Hydrologic and edaphic characteristics of three mountain wetlands in southeastern Kentucky, USA - Yvonne Thompson; Brian C. Sandefur; Jarrod O. Miller; A. D. Karathanasis (Wetlands, 2007)

Peripheral blood mononuclear cell proliferative responses to soluble and particulate heat shock protein 65 in health and inflammatory bowel disease - L. C. Pele; S. J. Thompson; B. Kirkham; R. P. H. Thompson; J. J. Powell (Inflammation Research, 2007)

Resistance to phytophthora erythroseptica and pythium ultimum in a potato clone derived from s. berthaultii and s. etuberosum - Asunta L. Thompson; Raymond J. Taylor; Julie S. Pasche; Richard G. Novy; Neil C. Gudmestad (American Journal of Potato Research, 2007)

Historical changes in the phenology of British Odonata are related to climate - CHRISTOPHER HASSALL; DAVID J. THOMPSON; GRAHAM C. FRENCH; IAN F. HARVEY (Global Change Biology, 2007)

Compatible genetic and ecological estimates of dispersal rates in insect ( Coenagrion mercuriale : Odonata: Zygoptera) populations: analysis of ‘neighbourhood size’ using a more precise estimator - PHILLIP C. WATTS; FRANÇOIS ROUSSET; ILIK J. SACCHERI; RAPHAËL LEBLOIS; STEPHEN J. KEMP; DAVID J. THOMPSON (Molecular Ecology, 2007)
Genetic and demographic estimates of dispersal are often thought to be inconsistent. In this study, we use the damselfly Coenagrion mercuriale (Odonata: Zygoptera) as a model to evaluate directly the relationship between estimates of dispersal rate measured during capture–mark–recapture fieldwork with those made from the spatial pattern of genetic markers in linear and two‐dimensional habitats. We estimate the ‘neighbourhood size’ ( Nb ) — the product of the mean axial dispersal rate between parent and offspring and the population density — by a previously described technique, here called the regression method. Because C. mercuriale is less philopatric than species investigated previously by the regression method we evaluate a refined estimator that may be more applicable for relatively mobile species. Results from simulations and empirical data sets reveal that the new estimator performs better under most situations, except when dispersal is very localized relative to population density. Analysis of the C. mercuriale data extends previous results which demonstrated that demographic and genetic estimates of Nb by the regression method are equivalent to within a factor of two at local scales where genetic estimates are less affected by habitat heterogeneity, stochastic processes and/or differential selective regimes. The corollary is that with a little insight into a species’ ecology the pattern of spatial genetic structure provides quantitative information on dispersal rates and/or population densities that has real value for conservation management.

Molecular quantification of differential ingestion and particle trapping rates by the appendicularian Oikopleura dioica as a function of prey size and shape - Christofer Troedsson; Marc E. Frischer; Jens C. Nejstgaard; Eric M. Thompson (Limnology and Oceanography, 2007)
To investigate whether particles are ingested or merely trapped in the house of the appendicularian Oikopleura dioica, we developed a real‐time quantitative polymerase chain reaction (qPCR) assay and applied it in a controlled study where O. dioica was fed three types of algae at different concentrations. At particle concentrations ranging from 100 to 10,000 cells mL −1 , highest ingestion efficiencies (75‐96%) were observed with the smallest algal species ( Isochrysis sp.) compared to the larger cryptophyte Rhinomonas sp. (2‐87%) and a similar sized but spiny diatom, Chaetoceros calcitrans (4‐65%). When prey were mixed, the presence of C. calcitrans inhibited ingestion of Rhinomonas sp. but not the smaller Isochrysis sp., suggesting that C. calcitrans clogged the inlet filter and mechanically hindered ingestion of larger algae. O. dioica is adapted to feed on smaller particles at low (nonbloom) concentrations and may thus be subjected to bottom‐up regulation by larger spiny or colonial prey that typically dominate late‐stage phytoplankton blooms.

Evidence for reproductive isolation between two colour morphs of cavity nesting honey bees (Apis) in south India - B. P. Oldroyd; M. S. Reddy; N. C. Chapman; G. J. Thompson; M. Beekman (Insectes Sociaux, 2006)

Hurricanes 2004: An overview of their characteristics and coastal change - Asbury H. Sallenger; Hilary F. Stockdon; Laura Fauver; Mark Hansen; David Thompson; C. Wayne Wright; Jeff Lillycrop (Estuaries and Coasts, 2006)

A study on the variability of atmospheric and oceanic processes over the Arabian Sea during contrasting monsoons - J. S. Chowdary; C. Gnanaseelan; S. K. Sinha; B. Thompson (Meteorology and Atmospheric Physics, 2006)

Creatine supplementation does not enhance submaximal aerobic training adaptations in healthy young men and women - T. F. Reardon; P. A. Ruell; M. A. Fiatarone Singh; C. H. Thompson; K. B. Rooney (European Journal of Applied Physiology, 2006)

Empirical indices of spatial and executive processes in visuo-spatial working memory - J. M. Thompson; C. J. Hamilton; J. M. Gray; J. G. Quinn; P. Mackin; I. N. Ferrier; A. H. Young (Cognitive Processing, 2006)

Dakota Jewel: An attractive, new, bright red-skinned, fresh market potato cultivar with improved storage characteristics - A. L. Thompson; B. L. Farnsworth; G. A. Secor; N. C. Gudmestad; D. A. Preston; H. Hatterman-Valenti (American Journal of Potato Research, 2006)

Isolation and identification of Shewanella alga and its pathogenic effects on post‐larvae of abalone Haliotis diversicolor supertexta - J Cai; H Chen; K D Thompson; C Li (Journal of Fish Diseases, 2006)

Diet of Pacific sleeper shark, a potential Steller sea lion predator, in the north‐east Pacific Ocean - M. F. Sigler; L. B. Hulbert; C. R. Lunsford; N. H. Thompson; K. Burek; G. O’Corry‐Crowe; A. C. Hirons (Journal of Fish Biology, 2006)
Pacific sleeper sharks Somniosus pacificus were captured near Steller sea lion Eumetopias jubatus rookeries during the period when Steller sea lion pups are most vulnerable to Pacific sleeper shark predation (first water entrance and weaning). Analysis of stomach contents revealed that teleosts were the dominant prey in August and cephalopods were the dominant prey in May ( n = 198). Marine mammals were found in 15% of stomachs regardless of season, but no Steller sea lion tissues were detected. Molecular genetic analysis identified grey whale Eschrichtius robustus and harbour seal Phoca vitulina remains in some Pacific sleeper shark stomachs. Most mammals were cetacean and at least 70% of the cetaceans were probably scavenged. Although Pacific sleeper shark and Steller sea lion ranges overlapped, so predation could potentially occur, the diet study suggested that predation on Steller sea lions is unlikely, at least when pups first enter the water or during weaning. Harbour seals were infrequent prey and may have been consumed alive. Pacific sleeper sharks consume fast‐swimming prey like Pacific salmon Oncorhynchus sp., most likely live animals rather than scavenged animals. Pacific sleeper sharks appeared to be opportunistic consumers of the available prey and carrion, feeding both on the bottom and in the water column, and their diet shifted to teleosts and cetacean carrion as the fish grew larger.

Net Carbon Exchange Across the Arctic Tundra-Boreal Forest Transition in Alaska 1981–2000 - C. C. Thompson; A. D. McGuire; J. S. Clein; F. S. Chapin; J. Beringer (Mitigation and Adaptation Strategies for Global Change, 2006)

Dakota rose: A bright red tablestock potato cultivar that retains its skin color in storage - A. L. Thompson; G. A. Secor; J. H. Lorenzen; B. L. Farnsworth; R. G. Novy; N. C. Gudmestad; E. T. Holm; D. A. Preston (American Journal of Potato Research, 2006)

Use of stem diameter variations to detect plant water stress in tomato - M. Gallardo; R. B. Thompson; L. C. Valdez; M. D. Fernández (Irrigation Science, 2006)

Water relations of the burrowing sandhill frog, Arenophryne rotunda (Myobatrachidae) - V. A. Cartledge; P. C. Withers; G. G. Thompson; K. A. McMaster (Journal of Comparative Physiology B, 2006)

Dispersal and genetic structure in the American marten, Martes americana - T. BROQUET; C. A. JOHNSON; E. PETIT; I. THOMPSON; F. BUREL; J. M. FRYXELL (Molecular Ecology, 2006)
Natal dispersal in a vagile carnivore, the American marten ( Martes americana ), was studied by comparing radio‐tracking data and microsatellite genetic structure in two populations occupying contrasting habitats. The genetic differentiation determined among groups of individuals using F ST indices appeared to be weak in both landscapes, and showed no increase with geographical distance. Genetic structure investigated using pairwise genetic distances between individuals conversely showed a pattern of isolation by distance (IBD), but only in the population occurring in a homogeneous high‐quality habitat, therefore showing the advantage of individual‐based analyses in detecting within‐population processes and local landscape effects. The telemetry study of juveniles revealed a leptokurtic distribution of dispersal distances in both populations, and estimates of the mean squared parent–offspring axial distance (σ2) inferred both from the genetic pattern of IBD and from the radio‐tracking survey showed that most juveniles make little contribution to gene flow.

Testing metabolic ecology theory for allometric scaling of tree size, growth and mortality in tropical forests - Helene C. Muller‐Landau; Richard S. Condit; Jerome Chave; Sean C. Thomas; Stephanie A. Bohlman; Sarayudh Bunyavejchewin; Stuart Davies; Robin Foster; Savitri Gunatilleke; Nimal Gunatilleke; Kyle E. Harms; Terese Hart; et al. (Ecology Letters, 2006)
The theory of metabolic ecology predicts specific relationships among tree stem diameter, biomass, height, growth and mortality. As demographic rates are important to estimates of carbon fluxes in forests, this theory might offer important insights into the global carbon budget, and deserves careful assessment. We assembled data from 10 old‐growth tropical forests encompassing censuses of 367 ha and > 1.7 million trees to test the theory's predictions. We also developed a set of alternative predictions that retained some assumptions of metabolic ecology while also considering how availability of a key limiting resource, light, changes with tree size. Our results show that there are no universal scaling relationships of growth or mortality with size among trees in tropical forests. Observed patterns were consistent with our alternative model in the one site where we had the data necessary to evaluate it, and were inconsistent with the predictions of metabolic ecology in all forests.

Comparing tropical forest tree size distributions with the predictions of metabolic ecology and equilibrium models - Helene C. Muller‐Landau; Richard S. Condit; Kyle E. Harms; Christian O. Marks; Sean C. Thomas; Sarayudh Bunyavejchewin; George Chuyong; Leonardo Co; Stuart Davies; Robin Foster; Savitri Gunatilleke; Nimal Gunatilleke; et al. (Ecology Letters, 2006)
Tropical forests vary substantially in the densities of trees of different sizes and thus in above‐ground biomass and carbon stores. However, these tree size distributions show fundamental similarities suggestive of underlying general principles. The theory of metabolic ecology predicts that tree abundances will scale as the −2 power of diameter. Demographic equilibrium theory explains tree abundances in terms of the scaling of growth and mortality. We use demographic equilibrium theory to derive analytic predictions for tree size distributions corresponding to different growth and mortality functions. We test both sets of predictions using data from 14 large‐scale tropical forest plots encompassing censuses of 473 ha and > 2 million trees. The data are uniformly inconsistent with the predictions of metabolic ecology. In most forests, size distributions are much closer to the predictions of demographic equilibrium, and thus, intersite variation in size distributions is explained partly by intersite variation in growth and mortality.

Use of laser capture microdissection to detect integrated HIV-1 DNA in macrophages and astrocytes from autopsy brain tissues - Melissa J Churchill; Paul R Gorry; Daniel Cowley; Luxshimi Lal; Secondo Sonza; Damian FJ Purcell; Katherine A Thompson; Dana Gabuzda; Justin C McArthur; Carlos A Pardo; Steven L Wesselingh (Journal of NeuroVirology, 2006)

Diversity in the sunflower: Puccinia helianthi pathosystem in Australia - B. C. Sendall; G. A. Kong; K. C. Goulter; E. A. B. Aitken; S. M. Thompson; J. H. M. Mitchell; J. K. Kochman; W. Lawson; T. Shatte; T. J. Gulya (Australasian Plant Pathology, 2006)

Infectious pancreatic necrosis virus in Atlantic salmon, Salmo salar L., post‐smolts in the Shetland Isles, Scotland: virus identification, histopathology, immunohistochemistry and genetic comparison with Scottish mainland isolates - D A Smail; N Bain; D W Bruno; J A King; F Thompson; D J Pendrey; S Morrice; C O Cunningham (Journal of Fish Diseases, 2006)
During mid‐June 1999 peak mortalities of 11% of the total stock per week were seen at a sea cage site of Atlantic salmon, Salmo salar L., post‐smolts in the Shetland Isles, Scotland. Virus was isolated on chinook salmon embryo (CHSE) cells in a standard diagnostic test and infectious pancreatic necrosis virus (IPNV) identified by enzyme‐linked immunosorbent assay. IPNV was confirmed as serogroup A by a cell immunofluorescent antibody test using the cross‐reactive monoclonal antibody AS‐1. Four weeks after the main outbreak, virus titres in surviving moribund fish were assayed at >10 10 TCID 50 g −1 kidney. Histopathology of moribund fish was characterized by pancreatic acinar cell necrosis and a marked catarrhal enteritis of the intestinal mucosa. In the liver, necrosis, leucocytic infiltration and a generalized cell vacuolation were noted. IPNV‐specific immunostaining was demonstrated in pancreas, liver, heart, gill and kidney tissue. The nucleotide sequence of the coding region of segment A was determined from the Shetland isolate. A 1180 bp fragment of the VP2 gene of this isolate was compared with a 1979 reference isolate from mainland Scottish Atlantic salmon, La/79 and another more recent mainland isolate, 432/00. Both A2 isolates were derived from carrier fish without signs of IPN and serotyped by a plaque neutralization test. The Shetland isolate shows a different nucleotide and amino acid sequence compared with the two isolates from carrier fish. These latter isolates showed identical amino acid sequences in the fragment examined, despite the 21 years separating the isolations. Sequence comparisons with other A2 (Sp) isolates on the database confirm all three Scottish isolates are A2 (Sp).

Case Study Part 2: Probabilistic Modelling of Long-term Effects of Pesticides on Individual Breeding Success in Birds and Mammals - W. ROELOFS; D.R. CROCKER; R.F. SHORE; D.R.J. MOORE; G.C. SMITH; H.R. AKCAKAYA; R.S. BENNETT; P.F. CHAPMAN; M. CLOOK; M. CRANE; I.C. DEWHURST; P.J. EDWARDS; et al. (Ecotoxicology, 2005)

Case Study Part 1: How to Calculate Appropriate Deterministic Long-Term Toxicity to Exposure Ratios (TERs) for Birds and Mammals - R.F. SHORE; D.R. CROCKER; H.R. AKCAKAYA; R.S. BENNETT; P.F. CHAPMAN; M. CLOOK; M. CRANE; I.C. DEWHURST; P.J. EDWARDS; A. FAIRBROTHER; S. FERSON; D. FISCHER; et al. (Ecotoxicology, 2005)

Dakota Pearl: An attractive, bright white-skinned, cold-chipping cultivar with tablestock potential - A. L. Thompson; R. G. Novy; B. L. Farnsworth; G. A. Secor; N. C. Gudmestad; J. R. Sowokinos; E. T. Holm; J. H. Lorenzen; D. Preston (American Journal of Potato Research, 2005)

Identifying brain regions for integrative sensorimotor processing with ankle movements - O. Ciccarelli; A. T. Toosy; J. F. Marsden; C. M. Wheeler-Kingshott; C. Sahyoun; P. M. Matthews; D. H. Miller; A. J. Thompson (Experimental Brain Research, 2005)

Chromosomally located gene fusions constructed in Acinetobacter sp. ADP1 for the detection of salicylate - Wei E. Huang; Hui Wang; Hongjun Zheng; Linfeng Huang; Andrew C. Singer; Ian Thompson; Andrew S. Whiteley (Environmental Microbiology, 2005)
Summary Acinetobacter sp. ADP1 is a common soil‐associated bacterium with high natural competency, allowing it to efficiently integrate foreign DNA fragments into its chromosome. This property was exploited to engineer salicylate‐inducible luxCDABE and green fluorescent protein (GFP) variants of Acinetobacter sp. ADP1. Specifically, Acinetobacter sp. ADPWH _lux displayed the higher sensitivity when comparing the two variants (minimum detection c . 0.5–1 µM salicylate) and a faster turnover of the lux marker gene, making it suitable for whole‐cell luminescence assays of salicylate concentration. In contrast, the longer maturation and turnover times of the GFP protein make the Acinetobacter sp. ADPWH _gfp variant more suited to applications involving whole‐cell imaging of the presence of salicylate. The sensitivity of the luxCDABE variant was demonstrated by assaying salicylate production in naphthalene‐degrading cultures. Assays using ADPWH _lux specifically mapped the kinetics of salicylate production from naphthalene and were similar to that observed by high‐performance liquid chromatography (HPLC) data. However, ADPWH _lux exhibited the higher sensitivity, when compared with HPLC, for detecting salicylate production during the first 24 h of naphthalene metabolism. These data demonstrate that the engineered Acinetobacter variants have significant potential for salicylate detection strategies in laboratory and field studies, especially in scenarios where genetic stability of the construct is required for in situ monitoring.

A Comparison of Soil Microbial Community Structure, Protozoa and Nematodes in Field Plots of Conventional and Genetically Modified Maize Expressing the Bacillus thuringiens is CryIAb Toxin - B.S. Griffiths; S. Caul; J. Thompson; A.N.E. Birch; C. Scrimgeour; M.N. Andersen; J. Cortet; A. Messéan; C. Sausse; B. Lacroix; P.H. Krogh (Plant and Soil, 2005)

Burrow morphology, biometry, age and growth of piddocks (Mollusca: Bivalvia: Pholadidae) on the south coast of England - Eunice H. Pinn; C. A. Richardson; R. C. Thompson; S. J. Hawkins (Marine Biology, 2005)

The effects of eticlopride on Morris water task performance in male and female rats neonatally treated with quinpirole - Russell W. Brown; Kimberly N. Thompson; Ivy A. Click; Razaria A. C. Best; Stephanie K. Thacker; Marla K. Perna (Psychopharmacology, 2005)

Bioaugmentation for bioremediation: the challenge of strain selection - Ian P. Thompson; Christopher J. Van Der Gast; Lena Ciric; Andrew C. Singer (Environmental Microbiology, 2005)
Summary Despite its long‐term use in bioremediation, bioaugmentation of contaminated sites with microbial cells continues to be a source of controversy within environmental microbiology. This largely results from its notoriously unreliable performance record. In this article, we argue that the unpredictable nature of the approach comes from the initial strain selection step. Up until now, this has been dictated by the search for catabolically competent microorganisms, with little or no consideration given to other essential features that are required to be functionally active and persistent in target habitats. We describe how technical advances in molecular biology and analytical chemistry, now enable assessments of the functional diversity and spatial distribution of microbial communities to be made in situ . These advances now enable microbial populations, targeted for exploitation, to be differentiated to the cell level, an advance that is bound to improve microbial selection and exploitation. We argue that this information‐based approach is already proving to be more effective than the traditional ‘black‐box’ approach of strain selection. The future perspectives and opportunities for improving selection of effective microbial strains for bioaugmentation are also discussed.

Movement of male Heterozius rotundifrons (Crustacea: Decapoda: Brachyura) depends upon local sex ratio - B. A. Hazlett; C. E. Bach; G. A. Thompson; C. L. McLay (New Zealand Journal of Marine and Freshwater Research, 2005)
Heterozius rotundifrons is a New Zealand endemic crab that lives in the intertidal zone and is found under rocks during low tides. We investigated the role of the local sex ratio (= under rock) in affecting movement patterns of this crab. In the laboratory, male crabs moved more when the sex ratio was male biased. Field surveys suggested that there is an upper limit to the number of males found under rocks, even as the number of females increases. Field manipulations demonstrated that when the sex ratio under a rock is female biased there is no effect on female movement but when the ratio is male biased, males move away more frequently and move further. This increased movement by males is probably related to avoidance of male‐male competition for females.

Oligogenic combinations associated with breast cancer risk in women under 53years of age - Christopher E. Aston; David A. Ralph; Dominique P. Lalo; Sharmila Manjeshwar; Bobby A. Gramling; Daniele C. DeFreese; Amy D. West; Dannielle E. Branam; Linda F. Thompson; Melissa A. Craft; Debra S. Mitchell; Craig D. Shimasaki; et al. (Human Genetics, 2005)

Evidence for an extreme climatic event on Achill Island, Co. Mayo, Ireland around 5200–5100 cal. yr BP - C. Caseldine; G. Thompson; C. Langdon; D. Hendon (Journal of Quaternary Science, 2005)
A range of detailed palaeoenvironmental analyses carried out on a series of three peat profiles from Achill Island, Co. Mayo, western Ireland, reveal evidence for an extreme climatic event, probably a storm or series of storms, around 5200–5100 cal. yr BP that caused the deposition of an extensive layer of silt across blanket peat. This event followed a period of relatively dry climate during which Neolithic communities expanded in the region. There was a subsequent period of continuing dry conditions allowing extensive colonisation of the peat by Pinus before a shift to wetter conditions characteristic of the later Holocene. The extreme climatic event is possibly linked to human abandonment of the area comparable to that observed from the work on the internationally significant Céide Fields in the same region. Copyright © 2005 John Wiley & Sons, Ltd.

The nature of spatial transitions in the Arctic - H. E. Epstein; J. Beringer; W. A. Gould; A. H. Lloyd; C. D. Thompson; F. S. Chapin; G. J. Michaelson; C. L. Ping; T. S. Rupp; D. A. Walker (Journal of Biogeography, 2004)
Aim Describe the spatial and temporal properties of transitions in the Arctic and develop a conceptual understanding of the nature of these spatial transitions in the face of directional environmental change. Location Arctic tundra ecosystems of the North Slope of Alaska and the tundra‐forest region of the Seward Peninsula, Alaska Methods We synthesize information from numerous studies on tundra and treeline ecosystems in an effort to document the spatial changes that occur across four arctic transitions. These transitions are: (i) the transition between High‐Arctic and Low‐Arctic systems, (ii) the transition between moist non‐acidic tundra (MNT) and moist acidic tundra (MAT, also referred to as tussock tundra), (iii) the transition between tussock tundra and shrub tundra, (iv) the transition between tundra and forested systems. By documenting the nature of these spatial transitions, in terms of their environmental controls and vegetation patterns, we develop a conceptual model of temporal dynamics of arctic ecotones in response to environmental change. Results Our observations suggest that each transition is sensitive to a unique combination of controlling factors. The transition between High and Low Arctic is sensitive primarily to climate, whereas the MNT/MAT transition is also controlled by soil parent material, permafrost and hydrology. The tussock/shrub tundra transition appears to be responsive to several factors, including climate, topography and hydrology. Finally, the tundra/forest boundary responds primarily to climate and to climatically associated changes in permafrost. There were also important differences in the demography and distribution of the dominant plant species across the four vegetation transitions. The shrubs that characterize the tussock/shrub transition can achieve dominance potentially within a decade, whereas spruce trees often require several decades to centuries to achieve dominance within tundra, and Sphagnum moss colonization of non‐acidic sites at the MNT/MAT boundary may require centuries to millennia of soil development. Main conclusions We suggest that vegetation will respond most rapidly to climatic change when (i) the vegetation transition correlates more strongly with climate than with other environmental variables, (ii) dominant species exhibit gradual changes in abundance across spatial transitions, and/or (iii) the dominant species have demographic properties that allow rapid increases in abundance following climatic shifts. All three of these properties characterize the transition between tussock tundra and low shrub tundra. It is therefore not surprising that of the four transitions studied this is the one that appears to be responding most rapidly to climatic warming.

Darwin's cross‐promotion hypothesis and the evolution of stylar polymorphism - Adeline C. Cesaro; John D. Thompson (Ecology Letters, 2004)
There is growing appreciation that the ecological factors which impact on rates of pollen transfer can contribute significantly to reproductive trait evolution in plants. In heterostylous species, several studies support Darwin's claim that the reciprocal positions of stigmas and anthers enhance inter‐morph mating in comparison to intra‐morph mating and thus the maintenance of the polymorphism. In this study, we evaluate the relative importance of intra‐morph and inter‐morph pollen transfers in Narcissus assoanus , a species with dimorphic variation in style length but non‐reciprocity of anther positions. This stigma‐height dimorphism represents a transitional stage in theoretical models of the evolution of distyly. Seed set variation on recipient plants with donor plants of a single morph in experimental arrays in a natural population illustrate that inter‐morph cross‐pollination is more efficient that intra‐morph cross‐pollination as a result of high rates of pollen transfer from long‐styled to short‐styled plants. The observed rates of pollen transfer satisfy the theoretical conditions for the establishment of a stigma‐height dimorphism in an ancestral monomorphic long‐styled population in pollen‐limited situations. These results provide experimental evidence for the Darwinian hypothesis that enhanced inter‐morph cross‐pollination facilitates not only the maintenance of heterostyly but also the establishment of transitional forms implicated in the evolution of this polymorphism.

Molecular and ecological evidence for small‐scale isolation by distance in an endangered damselfly, Coenagrion mercuriale - P. C. WATTS; J. R. ROUQUETTE; I. J. SACCHERI; S. J. KEMP; D. J. THOMPSON (Molecular Ecology, 2004)
Coenagrion mercuriale (Charpentier) (Odonata: Zygoptera) is one of Europe's most threatened damselflies and is listed in the European Habitats directive. We combined an intensive mark‐release‐recapture (MRR) study with a microsatellite‐based genetic analysis for C. mercuriale from the Itchen Valley, UK, as part of an effort to understand the dispersal characteristics of this protected species. MRR data indicate that adult damselflies are highly sedentary, with only a low frequency of interpatch movement that is predominantly to neighbouring sites. This restricted dispersal leads to significant genetic differentiation throughout most of the Itchen Valley, except between areas of continuous habitat, and isolation by distance (IBD), even though the core populations are separated by less than 10 km. An urban area separating some sites had a strong effect on the spatial genetic structure. Average pairwise relatedness between individual damselflies is positive at short distances, reflecting fine‐scale genetic clustering and IBD both within‐ and between‐habitat patches. Damselflies from a fragmented habitat have higher average kinship than those from a large continuous population, probably because of poorer dispersal and localized breeding in the former. Although indirect estimates of gene flow must be interpreted with caution, it is encouraging that our results indicate that the spatial pattern of genetic variation matches closely with that expected from direct observations of movement. These data are further discussed with respect to possible barriers to dispersal within the study site and the ecology and conservation of C. mercuriale . To our knowledge, this is the first report of fine‐scale genetic structuring in any zygopteran species.

Land‐use influences on New Zealand stream communities: Effects on species composition, functional organisation, and food‐web structure - R. M. Thompson; C. R. Townsend (New Zealand Journal of Marine and Freshwater Research, 2004)
We used standardised techniques to assemble 18 food‐webs in streams subject to four land uses; exotic pasture, native tussock, native forest, and pine plantation. There were clear differences in the algal productivity and standing crops of organic matter between the forested (native and pine) and grassland (tussock and pasture), but not within each grouping. Algal productivity was more than twice as high in the grassland sites, whereas the converse was true for organic matter standing crop. These differences in energy resources were correlated with differences in community composition and food‐web structure. Although all streams had a generalist core of species, certain species of algae and invertebrates were predictably associated with either forested or grassland sites. Food‐web structure in the forested and grassland sites was also distinct. Grassland food‐webs were complex, highly internally connected, and typified by a “triangular” shape. Forested food‐webs in contrast were less highly connected, tended to have fewer trophic levels, and were “squarer” in shape. These results provide some support for the concept that energy supply may be an important contributing factor influencing stream community structure. In terms of riparian management, the results emphasise the importance of protecting representative vegetation around streams to protect stream communities.

Landscape Modeling of In Situ Soil Respiration in a Forested Watershed of Southeastern Kentucky, USA - Amanda C. Abnee; James A. Thompson; Randall K. Kolka (Environmental Management, 2004)

Landscape Influences on Potential Soil Respiration Rates in a Forested Watershed of Southeastern Kentucky - Amanda C. Abnee; James A. Thompson; Randall K. Kolka; Elisa M. D’Angelo; Mark S. Coyne (Environmental Management, 2004)

Physical disturbance of an upland grassland influences the impact of elevated UV‐B radiation on metabolic profiles of below‐ground micro‐organisms - L. M. Avery; P. C. Thorpe; K. Thompson; N. D. Paul; J. P. Grime; H. M. West (Global Change Biology, 2004)
This investigation determined the response of soil microbial communities to enhanced UV‐B radiation and disturbance in upland grassland. A factorial field experiment encompassing two levels of UV‐B supplementation (simulating ambient and a 30% increase in stratospheric ozone) and two levels of disturbance (disturbed and undisturbed) was established at Buxton Climate Change Impacts Laboratory, Derbyshire, UK, and maintained for 7 years prior to sampling. Enhanced UV‐B increased microbial utilization of carbohydrates, carboxylic acids, polymers and aromatic compounds present in Biolog® GN plates when inoculated with soils taken from disturbed plots, but did not affect carbon utilization of soil microbial communities associated with undisturbed plots (UV‐B×Disturbance interaction, P UV‐B treatment did not affect numbers of bacteria or fungi. Direct microscopic counts showed fewer bacteria in soil originating from disturbed plots than from undisturbed plots (Disturbance, P P UV‐B treatment did not affect total plant biomass within undisturbed plots or the biomass of individual groupings of grasses, forbs and mosses. Per cent root length colonized by arbuscular mycorrhizal fungi (AMF) was not affected by enhanced UV‐B radiation in the undisturbed plots. Neither AMF nor plant biomass was measured in disturbed plots. The key findings of this study show that UV‐B‐mediated alterations in carbon utilization occurred in soil microbial communities subjected to disturbance, but such changes were not observed in communities sampled from undisturbed grassland. Differences in the catabolic potential of microbial communities from disturbed grassland subjected to enhanced UV‐B are probably related to plant‐mediated changes in resource availability or quality.

Intra-specific variability in the temporal organisation of foraging activity in the limpet Patella vulgata - G. Santini; R. C. Thompson; C. Tendi; S. J. Hawkins; R. G. Hartnoll; G. Chelazzi (Marine Biology, 2004)

Prolonged vitamin C supplementation and recovery from eccentric exercise - D. Thompson; J. Hill; T. Hurst; J. R. Powell; C. Williams; D. M. Bailey (European Journal of Applied Physiology, 2004)

Identification and characterization of a novel mouse prion gene allele - Sarah E. Lloyd; Simon R. Thompson; Jonathan A. Beck; Jacqueline M. Linehan; Jonathan D. F. Wadsworth; Sebastian Brandner; John Collinge; Elizabeth M. C. Fisher (Mammalian Genome, 2004)

An improved enrichment procedure to develop multiple repeat classes of cotton microsatellite markers - Siva P. Kumpatla; Marilyn K. Manley; Erin C. Horne; Manju Gupta; Steven A. Thompson (Plant Molecular Biology Reporter, 2004)

Improved high-throughput sunflower and cotton genomic DNA extraction and PCR fidelity - Erin C. Horne; Siva P. Kumpatla; Koni A. Patterson; Manju Gupta; Steven A. Thompson (Plant Molecular Biology Reporter, 2004)

Emissions of N2O and CH4 during the Composting of Liquid Swine Manure - A. G. Thompson; C. Wagner-Riddle; R. Fleming (Environmental Monitoring and Assessment, 2004)

The effect of food supply on feeding strategy in sessile female gastropods Crepidula fecunda - O. R. Chaparro; C. J. Segura; J. M. Navarro; R. J. Thompson (Marine Biology, 2004)

A panel of microsatellite loci for the Southern Damselfly, Coenagrion mercuriale (Odonata: Coenagrionidae) - P.C. Watts; J.H. Wu; C. Westgarth; D.J. Thompson; S.J. Kemp (Conservation Genetics, 2004)

Denitrification in a constructed wetland receiving agricultural runoff - Amy C. Poe; Michael F. Piehler; Suzanne P. Thompson; Hans W. Paerl (Wetlands, 2003)

Ecological Forecasting and the Urbanization of Stream Ecosystems: Challenges for Economists, Hydrologists, Geomorphologists, and Ecologists - Christer Nilsson; James E. Pizzuto; Glenn E. Moglen; Margaret A. Palmer; Emily H. Stanley; Nancy E. Bockstael; Lisa C. Thompson (Ecosystems, 2003)

Effects of Land Cover on Stream Ecosystems: Roles of Empirical Models and Scaling Issues - David L. Strayer; R. Edward Beighley; Lisa C. Thompson; Shane Brooks; Christer Nilsson; Gilles Pinay; Robert J. Naiman (Ecosystems, 2003)

Analysis of Trans-Silencing Interactions Using Transcriptional Silencers of Varying Strength and Targets With and Without Flanking Nuclear Matrix Attachment Regions - Robert Ascenzi; Bekir Ülker; Joselyn J. Todd; Dolores A. Sowinski; Carolyn R. Schimeneck; George C. Allen; Arthur K. Weissinger; William F. Thompson (Transgenic Research, 2003)

Mid-Holocene climates of the Americas: a dynamical response to changed seasonality - S. P. Harrison; J. E. Kutzbach; Z. Liu; P. J. Bartlein; B. Otto-Bliesner; D. Muhs; I. C. Prentice; R. S. Thompson (Climate Dynamics, 2003)

Bacterial recovery from ancient glacial ice - Brent C. Christner; Ellen Mosley‐Thompson; Lonnie G. Thompson; John N. Reeve (Environmental Microbiology, 2003)
Summary Ice that forms the bottom 18 m of a 308 m ice core drilled from the Guliya ice cap on the Qinghan‐Tibetan plateau in Western China is over 750 000 years old and is the oldest glacial ice known to date. Fourteen bacterial isolates have been recovered from samples of this ice from ∼296 m below the surface (mbs). Based on 16S rDNA sequences, these are members of the α‐ and β‐proteobacterial, actinobacterial and low‐G + C Gram‐positive bacterial lineages. 16S rDNA molecules have also been amplified directly, cloned and sequenced from the ice‐core melt water. These originated from Pseudomonas and Acinetobacter γ‐proteobacterial species. These results demonstrate that bacteria can be recovered from water ice that has frozen for time periods relevant to biological survival through terrestrial ice ages or during interplanetary transport.

Characterization of Crystalline Drug Nanoparticles Using Atomic Force Microscopy and Complementary Techniques - Huaiqiu Galen Shi; Leon Farber; James N. Michaels; Allison Dickey; Karen C. Thompson; Suhas D. Shelukar; Patricia N. Hurter; Scott D. Reynolds; Michael J. Kaufman (Pharmaceutical Research, 2003)

Characterisation of the expression of a novel constitutive maize promoter in transgenic wheat and maize - S. Rasco-Gaunt; D. Liu; C. Li; A. Doherty; K. Hagemann; A. Riley; T. Thompson; C. Brunkan; M. Mitchell; K. Lowe; E. Krebbers; P. Lazzeri; et al. (Plant Cell Reports, 2003)

Elevation of Transgene Expression Level by Flanking Matrix Attachment Regions (MAR) is Promoter Dependent: A Study of the Interactions of Six Promoters with the RB7 3′ MAR - S. Luke Mankin; George C. Allen; Thomas Phelan; Steven Spiker; William F. Thompson (Transgenic Research, 2003)

Decreased Neurotropism of nef Long Terminal Repeat ( nef /LTR)-Deleted Simian Immunodeficiency Virus - Katherine A Thompson; Stephen J Kent; Michelle E Gahan; Damian FJ Purcell; Catriona A McLean; Scott Preiss; C Jane Dale; Steven L Wesselingh (Journal of NeuroVirology, 2003)

The Stable Carbon Isotope Ratio of Biogenic Emissions of Isoprene and the Potential Use of Stable Isotope Ratio Measurements to Study Photochemical Processing of Isoprene in the Atmosphere - J. Rudolph; R. S. Anderson; K. V. Czapiewski; E. Czuba; D. Ernst; T. Gillespie; L. Huang; C. Rigby; A. E. Thompson (Journal of Atmospheric Chemistry, 2003)

Statistical hypothesis testing formulations for U.S. environmental regulatory standards for ozone - Mary Lou Thompson; Lawrence H. Cox; Paul D. Sampson; David C. Caccia (Environmental and Ecological Statistics, 2002)

Legitimizing Fluvial Ecosystems as Users of Water: An Overview - ROBERT J. NAIMAN; STUART E. BUNN; CHRISTER NILSSON; GEOFF E. PETTS; GILLES PINAY; LISA C. THOMPSON (Environmental Management, 2002)

Cancer prevention behaviors and socioeconomic status among Hispanics and non-Hispanic Whites in a rural population in the United States - Beti Thompson; Gloria D. Coronado; Cam C. Solomon; Dale F. McClerran; Marian L. Neuhouser; Ziding Feng (Cancer Causes & Control, 2002)

High-throughput transgene copy number estimation by competitive PCR - Anton S. Callaway; Rita Abranches; Jeffery Scroggs; George C. Allen; William F. Thompson (Plant Molecular Biology Reporter, 2002)

Comparison of the Toxicity of Chromium III and Chromium VI to Cyanobacteria - S. L. Thompson; F. C. R. Manning; S. M. McColl (Bulletin of Environmental Contamination and Toxicology, 2002)

Impacts of Climate Changes on Elk Population Dynamics in Rocky Mountain National Park, Colorado, U.S.A. - Guiming Wang; N. Thompson Hobbs; Francis J. Singer; Dennis S. Ojima; Bruce C. Lubow (Climatic Change, 2002)

The paleolimnological analysis of sediments from high mountain lake Nižné Terianske pleso in the High Tatras (Slovakia) - F. Šporka; E. Štefková; P. Bitušík; A.R. Thompson; A. Agustí-Panareda; P.G. Appleby; J.A. Grytnes; C. Kamenik; I. Krno; A. Lami; N. Rose; N.E. Shilland (Journal of Paleolimnology, 2002)

Resistance gene homologues in melon are linked to genetic loci conferring disease and pest resistance - Y. Brotman; L. Silberstein; I. Kovalski; C. Perin; C. Dogimont; M. Pitrat; J. Klingler; G. Thompson; R. Perl-Treves (Theoretical and Applied Genetics, 2002)

Induction of persistent changes in the organisation of the human motor cortex - Darrin R. McKay; Michael C. Ridding; Philip D. Thompson; Timothy S. Miles (Experimental Brain Research, 2002)

Development and mapping of SSR markers for maize - Natalya Sharopova; Michael D. McMullen; Linda Schultz; Steve Schroeder; Hector Sanchez-Villeda; Jack Gardiner; Dean Bergstrom; Katherine Houchins; Susan Melia-Hancock; Theresa Musket; Ngozi Duru; Mary Polacco; et al. (Plant Molecular Biology, 2002)

Substrate‐regulated cyanide hydratase ( chy ) gene expression in Fusarium solani : the potential of a transcription‐based assay for monitoring the biotransformation of cyanide complexes - M. Barclay; J. C. Day; I. P. Thompson; C. J. Knowles; M. J. Bailey (Environmental Microbiology, 2002)
Summary The fungus Fusarium solani detoxifies cyanide through induction of the cyanide hydratase gene activity ( chy ) in the presence of either KCN or the metal‐complexed cyanides, K 2 Ni(CN) 4 or K 4 Fe(CN) 6 , at pH 7.0 and 4.0 respectively. Sequence analysis of the chy gene identified primers for reverse transcriptase–polymerase chain reaction (RT–PCR)‐directed analysis of mRNA transcripts, which demonstrated that activity correlated to the substrate‐specific induction of gene expression. chy transcription was initiated 30–60 min after exposure of F. solani cultures to cyanide complexes. Maximum expression was detected within 4.5 h, after which chy mRNA synthesis declined below the limits of detection within 26 h. A lag period of ≈ 2 h, following initial transcription, was recorded before cyanide complexes were converted to formamide. mRNA transcripts of chy were not detected in the absence of cyanide or cyanide complexes. The presence of introns within the gene resulted in a difference in size of 100 bp for DNA compared with mRNA of the corresponding 5 ′ region. This size difference facilitated PCR detection of gene and transcript respectively. Comparisons of the predicted amino acid sequence of the F. solani chy gene and those of Gloeocerospora sorghi , Fusarium lateritium and Leptosphaeria maculans demonstrate that cyanide hydratase genes are highly conserved and of a similar evolutionary origin. These data predict that the functional assay described here to monitor the induction of chy gene expression and, potentially, cyanide degradation would be applicable to a variety of polluted environments.

Identification of Mutator insertional mutants of starch-branching enzyme 1 (sbe1) in Zea mays L. - Susan L. Blauth; Kyung-Nam Kim; Jeffery Klucinec; Jack C. Shannon; Donald Thompson; Mark Guiltinan (Plant Molecular Biology, 2002)

Quantifying the 5-HT 1A agonist action of buspirone in man - Bridge M.; Marvin G.; Thompson C.; Sharma A.; Jones D.; Kendall M. (Psychopharmacology, 2001)

Population biology and secondary production of the suspension feeding polychaete Chaetopterus cf. variopedatus : Implications for benthic‐pelagic coupling in lower Chesapeake Bay - Michelle L. Thompson; Linda C. Schaffner (Limnology and Oceanography, 2001)
Benthic suspension feeders are functionally important components of many shallow estuarine and coastal ecosystems. Their relative importance in material and energy cycling depends on physical and biological factors, of which population dynamics of individual species are a key feature. We studied the demographics and secondary production of a population of the tubicolous, suspension feeding polychaete, Chaetopterus cf. variopedatus , of southern Chesapeake Bay, Virginia, to better understand its functional role in an estuarine ecosystem. Average worm densities in the study region ranged from 30 to >1000 individuals m −2 and were greatest after the summer recruitment period. Recruitment success varied threefold between 1994 and 1995. A two‐cohort model (juveniles and adults) with seasonality best described the data. High secondary production (18 g C m −2 yr −1 in 1994, 34 g C m −2 yr −1 in 1995) was mainly due to rapid growth and maturation of new recruits during summer and tube production. An interannual difference in production was associated with the interannual difference in recruitment success. General temporal trends of primary production and worm production were similar, and the worm population required 35%–100% of the estimated annual net water column community production per m 2 for this region of the estuary. Chaetopterus cf. variopedatus is an important component of the lower bay ecosystem and should be considered when modeling carbon, nutrient, and energy flow. Our results further demonstrate that temporal variations in population dynamics lead to significant temporal variability in the relative importance of benthic suspension feeder effects for ecosystem function.

Movement and stock structure of narrow‐barred Spanish mackerel as indicated by parasites - R. J. G. Lester; C. Thompson; H. Moss; S. C. Barker (Journal of Fish Biology, 2001)
Data from permanent parasites (juvenile trypanorhynchs and anisakids) indicated that Spanish mackerel Scomberomorus commerson from four sites on the west coast of Australia, Abrolhos. Shark Bay, Exmouth and Onslow, intermingled and were probably all drawn from the same stock. Fish from Broome, Kupang (Indonesia), Groote Eylandt‐Torres Strait and the east coast of Australia had distinct faunas of permanent parasites and probably each belonged to a different stock. There was evidence of movement of fish between Broome and the west coast. Abundances of temporary parasites (gill copepods and monogeneans) suggested that males and females on the west coast migrated separately because in several cases the parasite fauna of one sex was more similar to that offish in an adjacent area than to the opposite sex in the same area.

Isolation of bacteria and 16S rDNAs from Lake Vostok accretion ice - Brent C. Christner; Ellen Mosley‐Thompson; Lonnie G. Thompson; John N. Reeve (Environmental Microbiology, 2001)
Lake Vostok, the largest subglacial lake in Antarctica, is separated from the surface by ≈ 4 km of glacial ice. It has been isolated from direct surface input for at least 420 000 years, and the possibility of a novel environment and ecosystem therefore exists. Lake Vostok water has not been sampled, but an ice core has been recovered that extends into the ice accreted below glacial ice by freezing of Lake Vostok water. Here, we report the recovery of bacterial isolates belonging to the Brachybacteria , Methylobacterium , Paenibacillus and Sphingomonas lineages from a sample of melt water from this accretion ice that originated 3593 m below the surface. We have also amplified small‐subunit ribosomal RNA‐encoding DNA molecules (16S rDNAs) directly from this melt water that originated from α‐ and β‐proteobacteria, low‐ and high‐G+C Gram‐positive bacteria and a member of the Cytophaga / Flavobacterium / Bacteroides lineage.

Modeling Global Climate–Vegetation Interactions in a Doubled CO2 World - Jon C. Bergengren; Starley L. Thompson; David Pollard; Robert M. DeConto (Climatic Change, 2001)

The production of a lymphokine (macrophage activating factor) by rainbow trout, Oncorhynchus mykiss (Walbaum), leucocytes stimulated with the extracellular products of Mycobacterium sp. - S‐C Chen; K D Thompson; A Adams; R H Richards (Journal of Fish Diseases, 2001)
The production of macrophage activation factor (MAF) by rainbow trout, Oncorhynchus mykiss (Walbaum) , head kidney leucocytes was examined after culturing in vitro with extracellular products (ECP) collected from Mycobacterium sp. Cultures of leucocytes were prepared from naive fish, or fish previously vaccinated with either the ECP or with formalin killed whole cell preparations (WC) of the bacterium. The cells were then incubated with the ECP in vitro and the ability of their supernatants to activate macrophages assessed. Macrophages from control fish were incubated with the supernatants, and their ability to reduce nitroblue tetrazolium (NBT) measured as an indicator of macrophage activation. Incubation of head kidney macrophages from naive fish directly with 1, 10 or 100 μg mL –1 of ECP for 48 h significantly enhanced macrophage activation compared with control macrophages. Vaccination of fish with either ECP or WC had no significant effect on the respiratory burst of control macrophages 4 weeks post‐vaccination. By the eighth week, however, absorbance levels of respiratory burst reflecting both the primary (cells from vaccinated fish cultured in vitro with PBS) and the secondary (cells cultured in vitro with ECP) MAF responses of fish vaccinated with ECP and WC, had peaked and these were significantly different from the non‐vaccinated controls. This activity had fallen to levels similar to control fish by week 12 for fish vaccinated with WC.

Phloem-specific expression of the pumpkin fruit trypsin inhibitor - Joanne M. Dannenhoffer; Renee C. Suhr; Gary A. Thompson (Planta, 2001)

A Piscirickettsia salmonis ‐like organism in grouper, Epinephelus melanostigma , in Taiwan - S‐C Chen; P‐C Wang; M‐C Tung; K D Thompson; A Adams (Journal of Fish Diseases, 2000)

Variation of pollen limitation in the early flowering Mediterranean geophyte Narcissus assoanus (Amaryllidaceae) - A. M. Baker; S. C. H. Barrett; J. D. Thompson (Oecologia, 2000)

Dietary 4-HPR suppresses the development of bone metastasis in vivo in a mouse model of prostate cancer progression - Mohammad R. Shaker; Guang Yang; Terry L. Timme; Sang H. Park; Dov Kadmon; Chengzhen Ren; Xiaorong Ji; Hon-Man Lee; Inder Sehgal; Mario Anzano; Michael B. Sporn; Timothy C. Thompson (Clinical & Experimental Metastasis, 2000)

Incidence of hybridization between Atlantic salmon, Salmo salar L., and brown trout, Salmo trutta L., in Ireland - M. A. Matthews; W. R. Poole; C. E. Thompson; J. McKillen; A. Ferguson; K. Hindar; K. F. Wheelan (Fisheries Management and Ecology, 2000)
The substantial growth of the farmed salmon industry in Europe since the 1970s has highlighted concerns regarding the genetic impact of escaped farmed salmon on wild salmonid stocks. High incidences of salmon × trout hybrids have been recorded in rivers situated near intensive salmon farming in Norway and Scotland, which may be indicative of a breakdown in reproductive isolation between salmon, Salmo salar L., and brown trout, Salmo trutta L. In the present study, salmonid fry and 0+ parr were collected from rivers in western Ireland. Allozyme and minisatellite DNA analysis were carried out on fry to determine the frequency of F1 hybrids from 10 rivers located within 38 km of salmon farms and three rivers at least 80 km from salmon farms. A total of 49 hybrids were recorded from 4135 salmonid fry (frequency = 1.2%). Mitochondrial DNA analysis showed that all hybrids arose from Atlantic salmon female × brown trout male crosses. Hybrid parr were recorded from one of the low‐risk rivers (1.0%), but were present in seven out of the 10 catchments located within 38 km of salmon farms, with frequencies ranging from 0.7% to 3.1%. The results of the present survey, which represents the first extensive record of the levels of salmon‐trout hybridization in Ireland, are discussed in relation to the continued growth of salmon farming in this country.

Evidence for covalent linkage between xyloglucan and acidic pectins in suspension-cultured rose cells - James E. Thompson; Stephen C. Fry (Planta, 2000)

Use of matrix attachment regions (MARs) to minimize transgene silencing - George C. Allen; Steven Spiker; William F. Thompson (Plant Molecular Biology, 2000)

Effects of the nicotinic antagonist mecamylamine on inspection time - J. C. Thompson; C. Stough; D. Ames; C. Ritchie; P. J. Nathan (Psychopharmacology, 2000)

Abscisic acid biosynthesis in tomato: regulation of zeaxanthin epoxidase and 9-cis-epoxycarotenoid dioxygenase mRNAs by light/dark cycles, water stress and abscisic acid - Andrew J. Thompson; Alison C. Jackson; Rachel A. Parker; David R. Morpeth; Alan Burbidge; Ian B. Taylor (Plant Molecular Biology, 2000)

Amplifying dolphin mitochondrial DNA from faecal plumes - Kim M. Parsons; John F. Dallas; Diane E. Claridge; John W. Durban; Kenneth C. Balcomb Iii; Paul M. Thompson; Les R. Noble (Molecular Ecology, 1999)

Laboratory comparison of soil redox conditions between red soils and brown soils in Minnesota, USA - Daniel B. Wheeler; James A. Thompson; Jay C. Bell (Wetlands, 1999)

Laboratory Kinetic Studies of the Reactions of Cl Atoms with Species of Biogenic Origin: δ3-Carene, Isoprene, Methacrolein and Methyl Vinyl Ketone - Carlos E. Canosa-Mas; Hilary R. Hutton-Squire; Martin D. King; David J. Stewart; Katherine C. Thompson; Richard P. Wayne (Journal of Atmospheric Chemistry, 1999)

Contributory presentations/posters - N. Manoj; V. R. Srinivas; A. Surolia; M. Vijayan; K. Suguna; R. Ravishankar; K. Suguna; A. Surolia; M. Vijayan; R. Schwarzenbacher; K. Zeth; Diederichs; et al. (Journal of Biosciences, 1999)

Biodegradation and Ecotoxicity of HFCs and HCFCs - A. G. Berends; C. G. de Rooij; S. Shin-ya; R. S. Thompson (Archives of Environmental Contamination and Toxicology, 1999)

Metastasis-related Genes in Prostate Cancer: The Role of Caveolin-1 - Timothy C. Thompson (Cancer and Metastasis Reviews, 1998)

Ovarian steroids and serotonin neural function - C. L. Bethea; M. Pecins-Thompson; W. E. Schutzer; C. Gundlah; Z. N. Lu (Molecular Neurobiology, 1998)

The influence of epilithic microbial films on the settlement of Semibalanus balanoides cyprids – a comparison between laboratory and field experiments - R. C. Thompson; T. A. Norton; S. J. Hawkins (Hydrobiologia, 1998)

Characterising food‐webs in two New Zealand streams - N. G. Jaarsma; S. M. de Boer; C. R. Townsend; R. M. Thompson; E. D. Edwards (New Zealand Journal of Marine and Freshwater Research, 1998)
The food‐web communities of two stony tributaries of the Taieri River in New Zealand were documented. We placed heavy emphasis on algal and macroinvertebrate taxonomy, identifying most taxa to species or morpho‐species level. Food‐web attributes were derived from symmetrical matrices using an Excel macro. The values of the food‐web attributes are generally consistent with generalities that have previously been reported in food‐web studies, although some hypothesisied relationships between connectance and food‐web size did not hold. The patterns detected were robust to the inclusion or exclusion of species that were identified in gut contents but not in field samples. The attributes strongly reflected the trophic status of the streams. Dempsters Creek was classified as autotrophic (based on high primary production and a high ratio of production to respiration) and displayed a larger food‐web size and longer food‐chains than those seen in Healy Creek, which was classified as hetero‐trophic (lower primary production and production to respiration ratio). The importance of dynamic environmental attributes such as production and disturbance in structuring food‐webs is emphasised in this study.

Differential regulation of a homologous peptidergic neuron in grasshoppers: evolution of a neural circuit - C. T. Lundquist; R. A. Baines; K. S. J. Thompson; J. P. Bacon (Journal of Comparative Physiology A, 1998)

Acquisition of oral phencyclidine (PCP) self-administration in rhesus monkeys: effects of dose and an alternative non-drug reinforcer - U. C. Campbell; Sherry S. Thompson; Marilyn E. Carroll (Psychopharmacology, 1998)

Perspective: National Forest Mismanagement? - Michael C. Thompson (Journal of Forestry, 1998)

Preface - Ronny C. Woodruff; James N. Thompson (Genetica, 1998)

Rotifers in relation to littoral ecotone structure in Lake Rotomanuka, North Island, New Zealand - Ian C. Duggan; John D. Green; Keith Thompson; Russell J. Shiel (Hydrobiologia, 1998)

Population frequencies of alternative male phenotypes in tree lizards: geographic variation and common-garden rearing studies - Diana K. Hews; Christopher W. Thompson; Ignacio T. Moore; Michael C. Moore (Behavioral Ecology and Sociobiology, 1997)

Risk factors for bronchiolitis: Presentation of an on-going prospective clinical study - M. E. M Thompson; J. K. Nelson; C. McMaster, M. C. Stewart, M. D. Shie (Inflammation Research, 1997)

Guanosine 5′-diphosphate 3′-diphosphate (ppGpp) and clavulanic acid production in Streptomyces clavuligerus - C. Jones; A. Thompson; R. England (World Journal of Microbiology and Biotechnology, 1997)

Spontaneous but not experimental metastatic activities differentiate primary tumor-derived vs metastasis-derived mouse prostate cancer cell lines - Simon J. Hall; Timothy C. Thompson (Clinical & Experimental Metastasis, 1997)

s of papers presented at the 81st annual meeting of The Potato Association of America Charlottetown, P.E.I., Canada August 3 – 7, 1997 - S. T. Ali-Khan; C. Hetner; L. Ladislav; V. Currie; Walter J. Arsenault; A. Naseer Aziz; Janet E. A. Seabrook; George C. C. Tai; J. B. Bamberg; Alfonso H. del Rio; Max Martin; J. B. Bamberg; et al. (American Journal of Potato Research, 1997)

A comparison of the antigenicity of the extracellular products and whole‐cell sonicates from Mycobacterium spp. in rabbits, mice and fish by immunoblotting and enzyme‐linked immunosorbent assay - S.‐C. Chen; A. Adams; K.D. Thompson; R.H. Richards (Journal of Fish Diseases, 1997)
The antigenicity of extracellular products (ECPs) derived from Mycobacterium spp. isolated from snakehead, Channa striata (Bloch), and Siamese fighting fish, Betta splendens (Regan), were examined by immunoblotting and enzyme‐linked immunosorbent assay (ELISA) using sera collected from immunized rabbits, mice and fish (rainbow trout). All three species responded to a 65‐kDa protein present in both the ECPs and whole cell sonicates (WCSs) from a variety of Mycobacterium spp. Cross‐reactivity of anti‐ M. tuberculosis and anti‐human heat‐shock protein monoclonal antibodies (MAbs), and the presence of fibronectin binding proteins secreted into ECPs of mycobacteria were also examined. The MAbs against human 60‐kDa heat‐shock protein cross‐ reacted with the band at 65 kDa in the ECPs of TB1 (isolated from snakehead fish) and the type strain M. marinum, while the anti‐ M. tuberculosis MAb F29–47 elicited a strong reaction with a band at 21 kDa with most of the ECPs from mycobacterial strains examined. The major fibronectin‐binding proteins were located between 21 and 25 kDa. The 65‐kDa protein from ECPs of Mycobacterium spp. proved strongly immunogenic to rabbits, mice and fish. Rabbit antiserum against the 65‐kDa protein from strain TB267 reacted with many non‐ Mycobacterium WCSs, and therefore, the 65‐kDa protein from Mycobacterium spp. is believed to be a common protein found in many fish bacterial pathogens.

Proton efflux in human skeletal muscle during recovery from exercise - G. J. Kemp; C. H. Thompson; D. J. Taylor; G. K. Radda (European Journal of Applied Physiology, 1997)

Distribution and abundance of choanoflagellates (Acanthoecidae) in the coastal cold ocean of Newfoundland, Canada - C. H. McKenzie; D. Deibel; R. J. Thompson; B. A. MacDonald; R. W. Penney (Marine Biology, 1997)

Tetracycline-dependent activation of an upstream promoter reveals transcriptional interference between tandem genes within T-DNA in tomato - Andrew J. Thompson; Sarah C. Myatt (Plant Molecular Biology, 1997)

Estimating long-term annual precipitation in a mountainous region from a diagnostic model - C. S. Thompson; M. R. Sinclair; W. R. Gray (International Journal of Climatology, 1997)

Introduction of a plant intron into the luciferase gene ofPhotinus pyralis - S. Luke Mankin; George C. Allen; William F. Thompson (Plant Molecular Biology Reporter, 1997)

Multiple repetitive DNA sequences in the paracentromeric regions of Arabidopsis thaliana L. - A. Brandes; H. Thompson; C. Dean; J. S. Heslop-Harrison (Chromosome Research, 1997)

Juvenile Survival in a Population of Neotropical Migrant Birds. Supervivencia de Juveniles en una Poblacion de Aves Migratorias Neotropicales - Angela D. Anders; Donald C. Dearborn; John Faaborg; Frank R. Thompson Iii (Conservation Biology, 1997)

Food-deprivation increases cocaine-induced conditioned place preference and locomotor activity in rats - S. Michael Bell; Robert B. Stewart; Scott C. Thompson; R. A. Meisch (Psychopharmacology, 1997)

Purine modulation of dizocilpine effects on spontaneous alternation - C. M. Fraser; A. Fisher; M. J. Cooke; I. D. Thompson; T. W. Stone (Psychopharmacology, 1997)

Ten Guidelines for Ecosystem Researchers: Lessons from Missouri - David R. Larsen; Stephen R. Shifley; Frank R. Thompson III; Brian L. Brookshire; Daniel C. Dey; Eric W. Kurzejeski; Kristine England (Journal of Forestry, 1997)

Abstracts of presentations on plant protection issues at the fifth international Mango Symposium Abstracts of presentations on plant protection issues at the Xth international congress of Virology - J. E. Peña; M. Wysoki; Gajendra Singh; Nancy Boscán de M.; Freddy J. Godoy; A. Obligado; C. J. Rossetto; I. J. A. Ribeiro; P. B. Gallo; N. B. Soares; J. C. Sabino; A. L. M. Martins; et al. (Phytoparasitica, 1997)

Inhibition of Various Cholinesterases with the Enantiomers of Malaoxon - O. P. Rodriguez; G. W. Muth; C. E. Berkman; K. Kim; C. M. Thompson (Bulletin of Environmental Contamination and Toxicology, 1997)

Methylosulfonomonas methylovora gen. nov., sp. nov., and Marinosulfonomonas methylotropha gen. nov., sp. nov.: novel methylotrophs able to grow on methanesulfonic acid - Andrew J. Holmes; D. P. Kelly; Simon C. Baker; A. S. Thompson; Paolo De Marco; Elizabeth M. Kenna; J. Colin Murrell (Archives of Microbiology, 1997)

Mutation detection in FGFR2 craniosynostosis syndromes - G. E. Hollway; Graeme K. Suthers; Eric A. Haan; Elizabeth Thompson; David J. David; Jozef Gecz; John C. Mulley (Human Genetics, 1997)

Organochlorine pesticide contamination in neotropical migrant passerines - R. G. Harper; J. A. Frick; A. P. Capparella; B. Borup; M. Nowak; D. Biesinger; C. F. Thompson (Archives of Environmental Contamination and Toxicology, 1996)

Design and placement of a multi-species riparian buffer strip system - R. C. Schultz; J. P. Collettil; T. M. Isenhart; W. W. Simpkins; C. W. Mize; M. L. Thompson (Agroforestry Systems, 1995)

Goldrush: A new high quality russet-skinned potato cultivar - Robert H. Johansen; Bryce Farnsworth; Gary A. Secor; Neil C. Gudmestad; Asunta Thompson-Johns; Edna T. Holm (American Journal of Potato Research, 1994)

Genetic interrelationships of proteolyticClostridium botulinum types A, B, and F and other members of theClostridium botulinum complex as revealed by small-subunit rRNA gene sequences - R. A. Hutson; D. E. Thompson; P. A. Lawson; R. P. Schocken-Itturino; E. C. Bttger; M. D. Collins (Antonie van Leeuwenhoek, 1994)

Performance of biological erosion control in New Zealand soft rock hill terrain - R. C. Thompson; P. G. Luckman (Agroforestry Systems, 1993)

Changes in activity of avian serum esterases following exposure to organophosphorus insecticides - H. M. Thompson; C. H. Walker; A. R. Hardy (Archives of Environmental Contamination and Toxicology, 1991)

Inhibition of avian esterases by organophosphorus insecticides: Problems of reactivation and storage - H. M. Thompson; C. H. Walker; A. R. Hardy (Archives of Environmental Contamination and Toxicology, 1991)

Host specificity and biology of the weevilNeohydronomus affinis [Coleoptera: Curculionidae] a biological control agent ofPistia stratiotes - C. R. Thompson; D. H. Habeck (BioControl, 1989)

Applications of neutron activation analysis to the study of age-related neurological diseases - W. D. Ehmann; W. R. Markesbery; E. J. Kasarskis; D. E. Vance; S. S. Khare; J. D. Hord; C. M. Thompson (Biological Trace Element Research, 1987)

Pentachlorophenol alters the molecular organization of membranes in mammalian cells - C. L. Duxbury; J. E. Thompson (Archives of Environmental Contamination and Toxicology, 1987)

Biological trace-element measurements using synchrotron radiation - Robert D. Giauque; Joseph M. Jaklevic; Albert C. Thompson (Biological Trace Element Research, 1987)

Temperatures lethal for citrus blackfly parasites,Encarsia opulenta andE. Smithi [Hym.: Aphelinidae] - C. R. Thompson (BioControl, 1985)

Identification of the G-genome donor to Triticum timopheevii by DNA:DNA hybridizations - J. Nath; James P. Thompson; S. C. Gulati (Biochemical Genetics, 1985)

Song of the humpback whale ? Population comparisons - H. E. Winn; T. J. Thompson; W. C. Cummings; J. Hain; J. Hudnall; H. Hays; W. W. Steiner (Behavioral Ecology and Sociobiology, 1981)

Perturbation of lipid membranes by organic pollutants - E. D. Packham; J. E. Thompson; C. I. Mayfield; W. E. Inniss; J. Kruuv (Archives of Environmental Contamination and Toxicology, 1981)

Plot harvester for potatoes - R. W. Chase; N. R. Thompson; R. L. Ledebuhr; C. M. Hansen; R. B. Kitchen (American Journal of Potato Research, 1978)

Dislodgeable residues of ethion in Florida citrus and relationships to weather variables - H. N. Nigg; J. C. Allen; R. F. Brooks; G. J. Edwards; N. P. Thompson; Roy W. King; A. H. Blagg (Archives of Environmental Contamination and Toxicology, 1977)

s 60th annual meeting The Potato Association of America - R. Kunkel; N. M. Holstad; R. E. Thornton; J. C. Bishop; Herman Timm; V. C. Shekhar; W. M. Iritani; Thornton Robert; Gary Hyde; Malamud Oscar; Robert B. O’Keefe; Mccown Brent; et al. (American Journal of Potato Research, 1976)

Determination of glycoalkaloids in potatoes (S. Tuberosum) with a bisolvent extraction method - S. L. Wang; C. L. Bedford; N. R. Thompson (American Journal of Potato Research, 1972)

Protein in potato flakes: Evaluation by the meadow vole (Microtus pennsylvanicus) - Bertha J. Rios Iriarte; N. R. Thompson; C. L. Bedford (American Journal of Potato Research, 1972)

Processing characteristics of Solanum tuberosum—S. stoloniferum hybrids - L. R. Pope; C. L. Bedford; N. R. Thompson (American Journal of Potato Research, 1971)

s of papers presented at the Forty-Third annual meeting of The Potato Association of America - R. H. Bagnall; D. A. Young; Barrel R. Bienz; G. D. Brill; J. C. Campbell; G. R. Blake; Paul N. Carpenter; George O. Estes; Harold W. Gausman; Harold W. Gausman; Hawkins Arthur; Henning P. Hansen; et al. (American Journal of Potato Research, 1959)

s of papers presented at the Forty-First annual meeting - Jay L. Haddock; Ray D. Jackson; W. O. Harrington; R. L. Olson; W. J. Weston; Mary L. Belote; W. J. Hooker; A. P. Benson; R. W. Hougas; S. J. Poloquin; R. W. Ross; G. V. C. Houghland; et al. (American Journal of Potato Research, 1958)

The Osseo variety - F. A. Krantz; C. J. Eide; C. H. Griffith; B. C. Beresford; O. C. Turnquist; M. J. Thompson; A. G. Tolaas (American Journal of Potato Research, 1954)

Spectrophotometric comparison of internal black spot and melanin - C. H. VanMiddelem; W. C. Jacob; H. C. Thompson (American Journal of Potato Research, 1953)

Varietal susceptibility of potatoes to internal black spot - P. H. Massey; H. C. Thompson; Ora Smith (American Journal of Potato Research, 1952)

Sectional notes - B. A. Brown; Frank W. Hussey; E. L. Nedwick; Ralph W. Donaldson; H. C. Thompson; C. L. Fitch; H. L. Bailey; J. G. Milward (American Journal of Potato Research, 1935)

Cultivation experements with potatoes on Long Island - H. C. Thompson; P. H. Wessels (American Journal of Potato Research, 1931)

Potato notes - C. W. Tice; J. T. Rosa; A. E. Wilkinson; E. A. Stokdyk; E. L. Newdick; Verdal T. Maxwell; C. F. Clark; W. Stuart; Charles A. Thompson; J. Gilbert Borton; Ellwood Douglass; Orley G. Bowen; et al. (American Journal of Potato Research, 1924)